Correction to: Sequence dynamics and plastome evolution: decoding the complete chloroplast genome of Oenothera drummondii and comparative analysis within Oenothera (Onagraceae) - Chang An; Wenbo Xu; Yixin Yao; Min Li; Yanxiang Lin; S. V. G. N. Priyadarshani; Aya Elderini; Yan Cheng; Site Luo; Yuan Qin; Ping Zheng (Functional & Integrative Genomics, 2026)

Sequence dynamics and plastome evolution: decoding the complete chloroplast genome of Oenothera drummondii and comparative analysis within Oenothera (Onagraceae) - Chang An; Wenbo Xu; Yixin Yao; Min Li; Yanxiang Lin; S. V. G. N. Priyadarshani; Aya Elderini; Yan Cheng; Site Luo; Yuan Qin; Ping Zheng (Functional & Integrative Genomics, 2026)

Dynamics of coral rubble on reef flats: from individual clast mobilisation to rubble strip morphological change - Aitana Gea-Neuhaus; Tim Scott; Gerd Masselink; Ana Vila-Concejo; Paul S. Kench; Mathilde Lindhart; Floortje E. Roelvink; Tom Hamilton; Ke Lin; Xianfeng Wang (Marine Geology, 2026)

Enhanced simulations of overland-gully-sewer flow interactions in coupled three-layer dual drainage modeling - Chia-Ho Wang; Hsiang-Lin Yu; Tsang-Jung Chang; Albert S. Chen (Journal of Hydrology, 2026)

Rheology-computational fluid dynamics co-regulation and experimental validation of coaxial three-dimensional printing - Jinjin Huang; Min Zhang; Arun S. Mujumdar; Chunli Li; Jiacong Lin; Jingyuan Li (Journal of Food Engineering, 2026)

Vanadium salt inhibits osteoclast formation and preserves bone integrity in a rat model of type-1 diabetes associated bone loss - Joshua Greendyk; James Thornton; Darian Napoleon; Michael Greenberg; Anthony Lin; Mike Levidy; Jonathan R. Lopez; Maximilian Muñoz; Kevin Innella; Yazan Kadkoy; Maya Deza Culbertson; Jessica A. Cottrell; et al. (BioMetals, 2026)

Effects of Lactobacillus- and Bacillus-based probiotics on growth performance, intestinal barrier function, and microbiota modulation in nursery pigs: A meta-analysis - K. Sahatsanon; A. Jayanegara; S.W. Kim; Y. Ruangpanit; C.-S. Lin; P. Sivapirunthep; C. Chaosap (Animal Feed Science and Technology, 2026)

Evaluating the potential of thermal evaporation for onsite retention of per- and polyfluoroalkyl substances (PFAS) in landfill leachate - Alina S. Timshina; Allison R. Cerlanek; Ashley M. Lin; Timothy G. Townsend; John A. Bowden (Waste Management, 2026)

Transitional strategy for food waste management in Hong Kong: Towards 2035 scenarios using prospective life cycle assessment - Chenyang Wang; Yahui Miao; Xiaohui Hu; Huaimin Wang; Shauhrat S. Chopra; Lu Sun; Liang Dong; Carol Sze Ki Lin (Resources, Conservation and Recycling, 2026)

Associations of Placental Oxidative Stress with Exposure to Gestational Air Pollution: Evidence from the UPSIDE Cohort - Emily A. Craig; Yan Lin; Yihui Ge; Xiangtian Wang; Otgondelger Enkhtaivan; Don K. Harrington; Richard K. Miller; Susan K. Murphy; Sally W. Thurston; Philip K. Hopke; Emily S. Barrett; Thomas G. O'Connor; et al. (Environmental Research, 2026)

Synergistic Effects of Biochar and Biofertilizers on Sustainable Crop Production: A Systematic Review - S. M. Shamiul Alam; Lin Wei; Tochukwu Ozor; Saurav Marahatta (International Journal of Plant Production, 2026)
The growing demand for food and the environmental concerns raised by excessive chemical fertilizer use have increased interest in sustainable soil fertility management practices. Biofertilizers (BFs) contain beneficial microorganisms that improve nutrient cycling and support plant growth. Biochar (BC), a carbon (C) rich material produced from biomass pyrolysis, improves soil structure, nutrient retention, and soil health. Although both BF and BC have been extensively studied individually, few studies have examined their combined effects. This systematic review summarizes the results from 66 peer-reviewed studies published between 2015 and 2025. The studies were identified through the Web of Science Core Collection and screened following Preferred Reporting Items for Systematic Reviews and MetaAnalyses (PRISMA) guidelines. The review evaluates the combined effects of BC and BF application on soil quality, nutrient availability, crop growth, stress tolerance, and environmental emissions. It was found that the combined application of BC and BFs improved microbial activity, soil enzyme activity, nutrient uptake, crop biomass, and yield more effectively than single applications. The reported reductions in global warming potential (GWP) and greenhouse gas intensity (GHGI) also indicated their environmental benefits. However, the effectiveness of BC+BF co-application varied, depending on biochar feedstock, pyrolysis conditions, microbial strains, application methods, and soil properties. Current challenges for co-application of BC and BFs include determining optimal application rates, selecting suitable biochar materials, and the limited availability of long-term and large-scale field studies. Overall, BC and BFs co-application shows strong potential for improving agricultural sustainability and resilience. Future studies should focus on long-term field experiments across different agroecological conditions.

Preliminary Investigation of Phosphorus-Use Efficiency in Mungbean (Vigna radiata): A Comparative RNA-Seq Study - Deepali Kothari; Muraleedhar S. Aski; S. Premakumar; Bidwan Rath; Nirmala Pargaien; Lalit Mohan Tewari; Shouvik Das; Gyan Prakash Mishra; Gyanendra Singh; Prachi Shripatrao Yadav; Ya-Ping Lin; Roland Schafleitner; et al. (Indian Journal of Genetics and Plant Breeding, 2026)

Storage timescales and the crystal growth history recorded in the layered reservoir of the Unit 3 Kulanaokuaiki Tephra Member of the Uēkahuna Ash from Kīlauea volcano - Abigail R. Nalesnik; Kendra J. Lynn; Timothy R. Rose; Jessica M. Warren; Dawn C. S. Ruth; Kuan-Yu Lin; Donald A. Swanson (Contributions to Mineralogy and Petrology, 2026)
The Kulanaokuaiki Tephra Unit 3 (900 C.E.) was a subplinian basaltic scoria eruption, the largest known to have occurred at Kīlauea’s summit. The initiation mechanism and cause(s) of this highly hazardous eruption remain poorly understood, particularly as this style of activity has not been observed in the modern period. We use olivine diffusion timescales from Fe-Mg and lithium zoning to assess magma storage timescales and evaluate evidence for mixing prior to eruption. Of the 200 crystals assessed, 55% are normally zoned for forsterite and 45% are non-zoned. Zoned crystals (> 1 mm) ( n = 96) have average compositions of Fo 89 cores and Fo 81 rims, while small crystals 0.5–1 mm ( n = 14) have Fo 85 cores and Fo 82 rims. Modeled Fo diffusion timescales range from n = 17), reflecting growth processes and precluding their use for diffusion studies. Overall, our Unit 3 olivine dataset displays no evidence of magmatic priming shortly prior to eruption, unlike prior observations for the basaltic subplinian eruption of the Keanakāko‘i Tephra Unit E (1650 C.E.). Thus, explosive eruption magmas may be stored for considerably longer than previously thought, and magmatic priming is not a necessary precursor for Kīlauea’s explosive eruptions. We hypothesize that gas-driven filter pressing from crystallization of microlites and macrocrysts in the reservoir slurry contributed to the explosivity of the Unit 3 eruption.

Toward improved conservation risk assessments in the marine aquarium fish trade: Reply to Biondo and Calado (2026) - Bing Lin; Andrew L. Rhyne; Michael Tlusty; Yiwen Zeng; Bryan To; Robert J. Holmberg; David S. Wilcove (Conservation Biology, 2026)

Magmatic evolution characteristics and heterogeneity of the outer zone of the Emeishan Large Igneous Province: a case study of basalts from the Tianquan and Huayingshan areas - C. C. Li; S. Yang; Z. Y. Lin; Y. P. Jing; Y. Xia; Y. H. Chen; J. T. Liao; C. D. Nie (Australian Journal of Earth Sciences, 2026)

The Associations of cerebral blood flow and white matter hyperintensities with tau and amyloid-beta across the Alzheimer’s disease spectrum - Keshuo Lin; Perminder S. Sachdev; Jiyang Jiang (Brain Imaging and Behavior, 2026)
Although the associations between cerebrovascular dysfunctions and Alzheimer’s disease are increasingly appreciated, the relationship of cerebral blood flow and white matter hyperintensities with tau and amyloid-β pathology remains unclear, particularly in the longitudinal context. This study investigated cross-sectional and longitudinal associations of cerebral blood flow and white matter hyperintensities with tau and amyloid-β pathology using multimodal imaging and blood biomarkers in 179 participants from the ADNI3 cohort. Participants underwent structural (T1-weighted, T2-weighted FLAIR) and arterial spin labelling perfusion MRI, tau and amyloid-β PET, and plasma assay tests for amyloid-β 42, amyloid-β 40, and phosphorylated tau-217. Tau from PET was negatively associated with cerebral blood flow both cross-sectionally and longitudinally in the posterior brain, independent of amyloid-β quantified from PET. Higher white matter hyperintensities volumes were associated with higher levels of tau and amyloid-β at baseline, but the associations were significantly attenuated after further adjusting for amyloid-β and tau, respectively. Plasma amyloid-β 42/40 ratio was negatively associated with white matter hyperintensity volumes both cross-sectionally and longitudinally. In conclusion, tau pathology showed spatially specific associations with cerebral hypoperfusion, independent of amyloid-β, particularly in posterior regions. The attenuation of associations of white matter hyperintensities with amyloid-β and tau after adjustment may reflect shared disease-related variance rather than distinct independent effects.

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Dietary Patterns Associated With Weight Loss Among Patients With Colorectal Cancer During the First 6 Months After Diagnosis: A Cross-Sectional Analysis From the ColoCare Study - Rachel Hoobler; Fred K. Tabung; Tengda Lin; Biljana Gigic; Kristen S. Smith; Kary Woodruff; Sylvia L. Crowder; Sheetal Hardikar; Doratha A. Byrd; Adriana M. Coletta; Alejandro Sanchez; Amandine Chaix; et al. (Journal of the Academy of Nutrition and Dietetics, 2026)

Structure-activity relationships governing the membrane targeted antimicrobial mechanisms of essential oils for food pathogen control - Jinming Dai; Shuang Xue; Mei Bai; Terence Chiu; Tariq Aziz; Fahad Al-Asmari; Rewaa S. Jalal; Haiying Cui; Lin Lin (Food Bioscience, 2026)

Wild bees occupy temporally stable pollen nutritional niches - Anthony D. Vaudo; Jillian A. Luthy; Eva Lin; Sonja K. Glasser; Anne S. Leonard (Oecologia, 2026)
As bees’ primary source of protein and lipids, pollen is a nutritional resource key to the persistence of wild populations. Because bee taxa may differ in their pollen macronutrient requirements, and pollen is a limited resource that varies chemically across plants, nutritional niches may shape bees’ ecological interactions. To explore whether members of bee communities occupy pollen nutritional niches, we analysed the protein and lipid content of pollen collected by abundant bee subgenera ( Nomadopsis , Melanosmia , Eumelissodes , Pyrobombus ) and observed their pollen-collecting visitation to plant species at a single Sierra Nevada meadow across three years. We compared pollen nutrition and host plant visitation among subgenera, and at the species level within Pyrobombus. Subgenera exhibited clear and temporally consistent separation of pollen load macronutrition each year, achieved by either host-plant fidelity or flexibility when foraging. Pyrobombus species shared a nutritional niche, potentially creating competition for pollen macronutrients among species relieved by their taxonomic flexibility. These results offer some of the first evidence that nutritional niches among wild bee taxa are annually stable and demonstrate how different taxa may forage to achieve nutritional consistency. Relevant to bee conservation, our findings emphasize that a nutritionally diverse array of plants may be required to support wild bee communities.

Matriptase proteolysis selectively drives disassembly and internalization of the claudin-7 complex while preserving E-cadherin - Yu-Ling A. Kao; He-Yu Huang; Yin S. Yu; Nanxi Huang; Ya-Chin Chan; Chen-Ray Lee; Michael D. Johnson; Chen-Yong Lin (Human Cell, 2026)

A comprehensive review of phage immobilization and encapsulation for the application in food safety - Pankaj Koirala; Yen-Te Liao; Meng-Wei Lin; Shyam S. Sablani; Vivian C. H. Wu (Critical Reviews in Food Science and Nutrition, 2026)

Computational approaches for identifying quorum sensing inhibitors - Lin Zhong; Shwetlaxmi Patil; B. Lakshmi; Pratibha Singh; Satish Kumar Rajasekharan; S. L. Rath; Vinothkannan Ravichandran (Molecular Diversity, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Optimized continuous bioproduction of ectoine from carbon dioxide and industrial contaminants using Guyparkeria halophila - E. Huang-Lin; S. Cantera; R. Lebrero (Journal of Environmental Chemical Engineering, 2026)

Solvent effects on quercetin incorporation, release behavior, and antibacterial efficacy in gelatin/dialdehyde cellulose composite films: A comparative study - Myat Noe Khin; Shabbir Ahammed; Chong Yuen Yuen; Tariq Aziz; Maryam M. Alomran; Ashwag Shami; Fahad Al-Asmari; Maher S. Alwethaynani; Lin Lin (Food Hydrocolloids, 2026)

Redox-active benzo[1,2-b:4,5-b’]dithiophene-4,8-dione-linked conjugated microporous polymers for high-rate, long-life lithium and zinc batteries - Bo-Chen Yeh; Bo-Chun Chen; Ijaz Ali; Sung-En Lin; Trakarn Yimtrakarn; Anton S. Pozdeev; Alexander S. Ivanov; Watchareeya Kaveevivitchai; Ahmed F.M. EL-Mahdy (Chemical Engineering Journal, 2026)

The learning efficiency of the ant Anoplolepis gracilipes (Hymenoptera: Formicidae) varies with temperature - C.-H. Chan; T.-S. Lin; H.-D. Lin; C.-I. Chiu (Insectes Sociaux, 2026)

Optimization of pediatric dosing regimens for aztreonam and amoxicillin/clavulanate combination therapy against multidrug-resistant bacteria - Lili Wang; Mengyuan Wu; Lin Qu; Pengfei Wang; Ziwei Yu; Hua Deng; Frederico S. Martins; Jiayuan Zhang; Da Rong; Mingming Yu; Zhihua Lv; Sherwin K. B. Sy; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Assessing Potential Data Sources for Landscape-scale Terrestrial Biodiversity Indicators - Tom Bradfer-Lawrence; Meriel Harrison; Adham Ashton-Butt; Sophie Bennett; Robin J. Boyd; Ella Browning; Graeme Buchanan; Adam Fraser; Sian E. Green; Robert Hawkes; Becky E. Heath; Pen-Yuan Hsing; et al. (Environmental Management, 2026)

Correction: Quantifying the effectiveness of superposed roughness elements to reduce dust emissions at the Salton Sea using computational fluid dynamics simulations - E. Furtak-Cole; J. A. Gillies; G. Nikolich; Y. Lin; S. Roy; J. Harrington (Air Quality, Atmosphere & Health, 2026)

An Empirical Test of Scale‐Dependence of β‐Diversity in a Large Temperate Forest Region - Liqi Lu; Philip S. Barton; Senxuan Lin; Minhui Hao; Chunyu Fan; Klaus von Gadow; Xiuhai Zhao; Chunyu Zhang (Journal of Biogeography, 2026)
Aim Variation in species composition among locations (β‐diversity) is of fundamental interest in ecology, yet its dependence on spatial extent and grain has rarely been assessed empirically. This study provides a systematic empirical test of the spatial scaling of β‐diversity and highlights the importance of study design for detecting the role of environmental filtering in shaping regional β‐diversity. Location Northeastern China. Taxon Tree in forest ecosystems. Methods We constructed regional communities to define six gradients of spatial extent and grain. We investigated how two types of spatial scale affect a range of aggregate measures of β‐diversity and corresponding β ‐deviations, as well as the distance‐decay relationship (DDR). Variation in β ‐deviations was further partitioned into habitat heterogeneity, spatial aggregation and their joint effects across scales. Results Raw β‐diversity did not exhibit consistent trends with extent across metrics, but it consistently decreased with increasing grain. Both raw β‐diversity and β ‐deviations were strongly influenced by sampling effort. The decreasing trend in Sørensen differentiation ( q = 0) with increasing extent, predicted by theory, was removed after controlling for sampling effort. Notably, only abundance‐based measures showed a significant increase with spatial extent that was unaffected by sampling effort. Sørensen differentiation also decreased with increasing grain, contrary to theoretical expectations. The DDR was sensitive to grain size, and the proportion of variation in β ‐deviations explained by habitat heterogeneity increased with both spatial extent and grain. Main Conclusion The response of raw β‐diversity to extent depended on the metric used and was sensitive to sampling effort. Pairwise abundance‐based measures may provide a more reliable basis for cross‐scale comparisons. The DDR may only be able to capture scale‐specific ecological processes. Environmental filtering emerges as the dominant driver of community assembly at larger spatial scales, highlighting how analytical choices influence inference about assembly mechanisms.

Feasibility of home-based, remotely delivered exercise training to improve physical function in older sepsis survivors: a pilot randomized controlled trial - Yi Lin; Rola S. Zeidan; Rezvan Ghaderpanah; Margaret K. Ohama; Min-Han Jung; Naveen Baskaran; Juan Sarmiento Delgado; Stephen D. Anton; Barbara K. Smith; Christiaan Leeuwenburgh; Fang-Chi Hsu; Philip A. Efron; et al. (GeroScience, 2026)
Sepsis survivors frequently experience post-discharge physical function decline and encounter logistical barriers to participation in traditional outpatient rehabilitation. This pilot study examined the feasibility, safety, and preliminary efficacy of a remotely delivered, home-based exercise program on physical function in older sepsis survivors. In this single-blinded, randomized controlled trial (RCT), sepsis survivors aged ≥ 55 years were randomized to (a) 12 weeks of avatar-guided, progressive exercise training group (EX) or (b) a standard care control group (CO). Primary outcomes were feasibility (retention, adherence) and safety (adverse events), whereas secondary outcomes were changes in the 30-s Sit-to-Stand (30SSTS), 4-Stage Balance Test (4SBT), Timed Up-and-Go (TUG) tests, and Eastern Cooperative Oncology Group/Zubrod's (ECOG/Zubrod) performance status score. Twenty-one participants were randomized to either EX ( n = 10, mean age = 69.6 ± 8.5 years, 40% females) or CO ( n = 11, mean age = 72.3 ± 7.9 years, 45% females). Mean retention was 95% and adherence to exercise training was 76%. Thirty-four adverse events (AEs) occurred (EX = 11; CO = 16; consented but not randomized = 7 events), including four serious AEs that were unrelated to the study. The EX group showed trends toward improvements in lower-extremity strength (30SSTS: 1.14 ± 2.91 repetitions, Cohen’s d = 0.393) and balance (4SBT: 5.07 ± 4.75 s, d = 1.07), whereas the CO group showed no change in balance on the 4SBT (0.01 ± 4.38 s, d = 0.003) and trends toward decline in lower-extremity strength on the 30SSTS (− 0.88 ± 0.99 repetitions, d = − 0.883). TUG performance showed modest trends toward reductions in completion time in both groups (EX: − 1.42 ± 6.58 s, d = − 0.216; CO: − 1.27 ± 2.73 s, d = − 0.466). ECOG/Zubrod scores showed a modest trend toward improvement in the EX group subset. This pilot RCT demonstrated that a 12-week, remotely delivered exercise program was safe and feasible for older sepsis survivors and showed preliminary signals of positive change in lower-extremity strength, balance, and functional status, which warrants testing efficacy in an adequately powered Phase IIb RCT. ClinicalTrials.gov NCT05568511.

Long-term nitrogen and phosphorus amendments reshape arbuscular mycorrhizal regulation of hyphosphere microbial communities and functions in grassland soils - Dandan LI; Wenhui YAN; He YANG; Tao ZHANG; Timothy S. GEORGE; Stéphane DECLERCK; Lin ZHANG (Pedosphere, 2026)

Outbreak of Salmonella Typhimurium ST19 linked to passerine birds and cats in Norway, March to July 2024 - Hilde Marie Lund; Lin T. Brandal; Liz Ertzeid Ødeskaug; Heidi Lange; Polina Katsiouleri; Gro S. Johannessen; Bjarne Bergsjø; Åsne Sangolt; Rikard Dryselius; Nadja Karamehmedovic; Henry Kuronen; Anni Vainio; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Purpose In June 2024, a genomic cluster of seven Salmonella Typhimurium - sequence type 19, and cluster type 21092 - was detected in Norway, triggering a national outbreak investigation. Methods Information about new cases was collected from the Norwegian Surveillance System for Communicable Diseases and the database at the National Reference Laboratory for Enteropathogenic Bacteria (NRL) at the Norwegian Institute of Public Health (NIPH). Microbiological analyses were conducted by NRL at NIPH for human samples and at the Norwegian Veterinary Institute for animal samples. Epidemiological data was collected through interviews. International notification was sent via EpiPulse. Results Eleven cases in total, sampled between March 6 and July 11, 2024, were identified across Norway. The median age of affected individuals was three years. Notably, 73% of the cases reported prior contact with cats or passerine birds. The outbreak strain was also detected in a faecal sample from a cat belonging to one of the affected households, suggesting an animal source. Concurrently, Finland and Sweden reported five and six cases, respectively, involving the same outbreak strain. Several of these individuals also reported contact with cats or birds. Conclusions Passerine birds are a well-documented reservoir for S. Typhimurium in the Nordic region, often leading to transmission to both cats and humans. This outbreak highlights the role of animal exposure in the spread of S. Typhimurium and emphasize the need for timely, targeted public health communication on infection prevention measures.

Host and Environmental Drivers of Gut Microbiome Variation in Wild Anolis Lizards - Yanileth F. López Tacoaman; Maria Alcivar; Karla Alujević; Leah Bakewell; John David Curlis; Anabarbara Gonzalez; Noah D. Gripshover; Samir Gulati; Renata M. Pirani; Noa Ratia; Daniel Romero; Kelly Lin Wuthrich; et al. (Molecular Ecology, 2026)
Animals maintain close associations with diverse microbiota that inhabit their digestive tracts, and these associations can profoundly affect host physiology and fitness. Gut microbiome composition is shaped by both host traits and environmental factors, yet the relative importance of these forces remains unclear in many taxa, including squamate reptiles (lizards and snakes). To address this gap, we analysed the gut microbiomes of seven species of Anolis lizards in the lowland tropical rainforest of central Panama. We sought to determine how environmental and host species characteristics shaped gut microbiome composition. Specifically, we examined (1) interspecific variation in the anole gut microbiome, (2) the relative roles of environment and host species in shaping gut microbiomes across two study locations, and (3) patterns of phylosymbiosis. We found that host‐related factors (species identity, body size, and phylogenetic distance) were significant predictors of the composition of Anolis gut microbiomes. However, environmental factors, including locality and year of sampling (associated with temperature, humidity, and precipitation), also exerted significant effects. We detected evidence of phylosymbiosis, but this pattern was moderate, possibly due to the strong effect of environmental variation. Our work contributes to the growing body of literature on lizard gut microbiomes by using comparative observations across habitats and species to identify the factors that shape these communities in the wild.

Metabarcoding Chironomid Pupal Exuviae Enables Scalable Biomonitoring With High Comparability to Morphotaxonomy - Wu Han; Chu‐Ming Zhang; Cheng Qian; Tsz‐Ying Chan; Thilina S. Nimalrathna; Bai‐an Lin; Xiao‐Long Lin; Hong‐Qu Tang; Peter S. Cranston; Mathew Seymour (Molecular Ecology, 2026)
Conventional morphotaxonomy‐based biomonitoring requires modernization to enable timely assessments in the face of an accelerating freshwater biodiversity crisis. The Chironomid Pupal Exuviae Technique (CPET) is an established biomonitoring approach with considerable potential for integration with molecular methods, as the shed pupal skins of emerging adults provide a source of DNA. We tested the performance of DNA metabarcoding for detecting species richness, recovering beta‐diversity patterns and assessing biodiversity responses to environmental gradients using 15 mock communities and 12 natural chironomid pupal exuviae samples collected from Hong Kong streams. Additionally, the effects of primer choice were assessed by comparing a chironomid‐specific primer set (COI‐S) against a universal, highly degenerate primer set (COI‐V). Our results show that both primer sets achieved high species detection rates in mock communities (86% and 84%, respectively) and consistently recovered predefined community dissimilarities. In natural community samples, however, only COI‐S produced beta‐diversity patterns significantly congruent with that of the morphological dataset (Procrustes r = 0.74, p = 0.003). Both metabarcoding datasets effectively captured seasonal community shifts and demonstrated greater sensitivity to environmental gradients than traditional morphological identification. Notably, the COI‐S dataset explained the highest proportion of community variation (adjusted R 2 = 44.3%), along the environmental gradient, outperforming both the morphotaxonomy (32.5%) and the COI‐V (29.0%) analyses. Here we propose Meta‐CPET, an integrated framework that combines the ecological relevance of CPET with the efficiency, scalability, and resolution of DNA metabarcoding. Our findings show that bulk‐sample metabarcoding enables practical, standardized and large‐scale freshwater biomonitoring while maintaining strong comparability with conventional methods.

Levels of 129I in coastal Pacific Ocean waters from southern California, 2011–2020 and the legacy of Fukushima - A. J. Timothy Jull; Ching-Chih Chang; George S. Burr; Li Cheng; Joellen Russell; Mang Lin; Daniel R. Crocker; Mark Thiemens; Dana Biddulph; Marc W. Caffee; Tom Woodruff; Christopher Glynn; et al. (Frontiers in Marine Science, 2026)
The Fukushima Daiichi Nuclear Power Plant accident released radionuclides directly into the ocean as a result of the Great East Japan Earthquake on March 11, 2011. This material has been transported across the Pacific Ocean and detected in the northeastern Pacific. We began a surface ocean 129 I monitoring program a few months after this disaster in June 2011, with samples from Scripps Pier, La Jolla, California, USA, with the expectation that surface currents originating off the east coast of Japan could eventually carry radionuclides to the La Jolla site. We could not identify a significant distinct signal that can be traced to Fukushima from the record from 2011-2020. We have however recorded a systematic seasonal 129 I time series record that appears to be due to surface circulation variations along the California coast, or perhaps other unexplained effects. We have reported on some of these effects previously, where we summarized results up to 2018. Since then, we have analyzed additional samples obtained during our sampling program for 2018–2020 from Scripps and also report other results collected during 2015–2016 from Newport Beach, CA, which had not been reported. These results support and expand on the previously published dataset.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

A stable environmental niche for humans in the southern Levant 70–40 ka - Mahmoud Abbas; Zhongping Lai; Hua Tu; Xianjiao Ou; Paul A. Carling; Penghui Lin; Mohammad Alqudah; Bety S. Al-Saqarat; Ting Qiu; Michael D. Petraglia; Zeljko Rezek; John D. Jansen (Quaternary Science Reviews, 2026)

High-throughput fingerprinting of hydrolysable tannins in wine and oak wood using in-source fragmentation on QTOF and QQQ platforms - Yanxin Lin; Bruce S. Pan; Robert (Qiang) Sui; Ping Yu; Misha T. Kwasniewski (Food Chemistry, 2026)

School greenspace and myopia incidence and burden in Chinese children and adolescents: The Guangzhou children and adolescents cohort study - Xiao-Qi Zhu; Yi Sun; Rong Lin; Ya-Na Luo; Jia-Xin Li; Yi-Dan Zhang; Michael S. Bloom; Matthew H.E.M. Browning; Sam SS. Lau; Shu-Jun Fan; Zhi-Qi Li; Ming-Deng Xiang; et al. (Environmental Research, 2026)

Machine learning and spatial regression approaches to estimating willingness to pay for ecosystem services in Jakarta and Taoyuan - Shafira Wuryandani; Yu-Pin Lin; Pei-Chen Lin; Dirk S. Schmeller; Gerard H. Ros (Ecosystem Services, 2026)

Contrasting behaviour in geogenic degassing along an active segment of the East Anatolian fault zone (Türkiye) - G. Yüce; W. D'Alessandro; C.C. Fu; F. Italiano; M. İçhedef; H. Elmacı; B. Kürkcüoğlu; B. Kahraman; A. Demirtaş; L.H. Lin; D. Yasin; Ş. Gürboğa; et al. (Applied Geochemistry, 2026)

Mapping the Spatial Scales of Australian Extreme Precipitation Using Daily Rain Gauges - Dongqi Lin; Kate R. Saunders; Martin S. Singh (International Journal of Climatology, 2026)
The impacts of extreme precipitation events (EPEs) on society are strongly influenced by their spatial footprint, yet the spatial scales of such events remain underexplored. Here we present the first continent‐wide analysis of the spatial scales of daily EPEs in Australia. We estimate the characteristic spatial scale of EPEs seasonally across the Australian continent using daily station observations and semivariograms. A semivariogram is a spatial statistical function that measures how spatial autocorrelation in precipitation decays with distance. Consistent with global analyses of satellite data, EPEs generally have larger spatial scales at higher latitudes. However, our analysis reveals complex seasonal and geographical dependencies that highlight the role of topography and meteorological regimes. We also analyse EPE spatial scales under different phases of the El Niño–Southern Oscillation (ENSO). In SON and DJF, southeastern Australia exhibits larger spatial scales during La Niña, although no uniform pattern is observed across the continent. Long‐term changes were analysed using 2070 stations with continuous operation between 1960 and 2023. Southwestern Australia shows a notable reduction in median EPE length scale in most seasons, while eastern regions exhibit a decrease in MAM and an increase in SON. Together, these findings provide a new climatological reference for the spatial scale of EPEs in Australia. These results also highlight the need to better understand the physical factors controlling the spatial scale of precipitation extremes in current and future climates.

Rapid Onset and Short Duration of TrenibotulinumtoxinE for Treatment of Moderate to Severe Glabellar Lines: Efficacy and Safety Results from a Phase 3 Study - Marion Moers-Carpi; Cheryl Burgess; Brian Biesman; Deirdre Hooper; Alexander Rivkin; Chung-Yi Chiang; Grace S. Park; Amy Weitzenfeld; Joan-En Chang-Lin (Toxicon, 2026)

Relationship of serum polycyclic aromatic hydrocarbon (PAHs) and lung function in adults: Evidence from a large community-based population in Guangzhou, China - Jing-Lin Zhang; Nuo Chen; Shui-Yue Lu; Michael S. Bloom; Shao Lin; Lu-Yin Wu; Li-Xia Liang; Yun-Ting Zhang; Jing-Wen Huang; Muhammad Amjad; Yong-Xiang Tang; Zhao-Huan Gui; et al. (Environmental Research, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

A systematic review on the uses of red mud as feedstock to make catalysts, coagulants and conditioners for treatment of contaminated water - Harsha S. Rangappa; Samuel Ogechi Eke; Mohit Kumar; Phyu Phyu Cho; Shashidhar Thatikonda; Ch Subrahmanyam; Chuxia Lin (Chemosphere, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Beyond temperature: predictive modelling of range shifts in benthic peracarids across the northern North Pacific under future climate scenarios - Stefanie Kaiser; Anna M. Jażdżewska; Sarah Gerken; Anne Helene S. Tandberg; Chih-Lin Wei; Davide Di Franco; Hanieh Saeedi; Hannah Owens; Henry Knauber; Emma Palacios Theil; Angelika Brandt; Pedro Martinez Arbizu; et al. (Progress in Oceanography, 2026)

Time-resolved fluorescence imaging of methylene blue reveals heterogeneous polarity in living cells - Andrey V. Belashov; Anna A. Zhikhoreva; Zhenlong Huang; Fangrui Lin; Irina V. Semenova; Oleg S. Vasyutinskii; Junle Qu (Journal of Photochemistry and Photobiology B: Biology, 2026)

Artificial neural network modeling for adsorption processes in carbon capture from wet flue gas - H. Si; J.K. Wu; S. Chen; J.Y. Yong; X.J. Lin; M.X. Fang; L. Jiang (Gas Science and Engineering, 2026)

Extent of threats to marine fish from the online aquarium trade in the United States - Bing Lin; Yiwen Zeng; Bryan To; Robert J. Holmberg; Andrew L. Rhyne; Michael Tlusty; David S. Wilcove (Conservation Biology, 2026)
The global marine aquarium hobby is a multibillion‐dollar industry, largely driven by demand from the United States. Much of this trade occurs online. We web scraped 4 major US‐based e‐commerce platforms selling marine aquarium fish to determine the retail price and source (wild capture, aquaculture, or both) of 13 families of ray‐finned marine fish ( Actinopterygii ). We supplemented this with ecological and economic trait data from FishBase and the International Union for Conservation of Nature (IUCN). Across all platforms and 13 popular fish taxonomic families, we found 734 unique species for sale, 89.2% (655 species) of which were sourced exclusively from the wild. A total of 45 species were of conservation concern (20 threatened species and 25 additional species with decreasing population trends), 38 of which were sourced solely from the wild. Retail price was significantly correlated with source, body length, minimum occupied depth, and schooling behavior. A further 100 species for sale were not listed as being in the aquarium trade in FishBase or by the IUCN, indicating incomplete information on this fishery in 2 important databases. For 58 species (encompassing 71 variants) with both wild‐caught and captive‐bred individuals for sale, aquaculture fish were a mean 28.1% (95% confidence interval 15.3) cheaper than their wild‐caught counterparts.

Optimising light intensity and ammonium enrichment enhances ex-situ growth and survival of the cultured boring Giant clam, Tridacna crocea - Li Keat Lee; Teresa S. Tay; H.R. Samuel Lee; K.E. Kayden Tong; M.Y. Beryl Chean; Yuchen Sun; Mei Lin Neo (Aquaculture, 2026)

Electrolytic hydrogen production from acidified wastewater effluent - Lin Du; Jinyue Jiang; Guangye Zhou; Yuqing Yan; Ryan S. Kingsbury; Anthony Y. Ku; Zhiyong Jason Ren (Water Research, 2026)

An in vitro-in silico workflow for predicting renal clearance of environmental chemicals and drugs - Courtney Sakolish; Hsing-Chieh Lin; Haley L. Moyer; Lucie C. Ford; Charles H. Christen; Barbara A. Wetmore; Michael J. DeVito; Philip Hewitt; Stephen S. Ferguson; Farah Raad; Ivan Rusyn; Weihsueh A. Chiu (Toxicology, 2026)

A summary of the Lucy Ashton resistance prediction workshop - Rui Lopes; Arash Eslamdoost; Rickard E. Bensow; Dmitriy Ponkratov; Anja Kömpe; Paolo Geremia; Çagan Birant Pekküçük; Cagri Aydin; Diego Villa; Dimitris Ntouras; Dong Cheol Seo; Gennaro Rosano; et al. (Ocean Engineering, 2026)

A new mineral quantification method via global feature fusion of plane-polarized and cross-polarized light images: MQM-p/xpl - W. Ma; Z.H. Xu; P. Lin; S. Li (Minerals Engineering, 2026)

Hybridization and incomplete lineage sorting characterize the evolutionary history of two East Asian clades of Stewartia (Theaceae) - Han-Yang Lin; Miao Sun; Jian-Jun Jin; Cheng-Xin Fu; Douglas E. Soltis; Pamela S. Soltis; Yun-Peng Zhao (Molecular Phylogenetics and Evolution, 2026)

Long-term ozone exposure and attention-deficit/hyperactivity disorder symptoms in school-aged children: Findings from a large multi-city study in China - Zhao-Huan Gui; Wan-Ting He; Yun-Ting Zhang; Joachim Heinrich; Michael S. Bloom; Shao Lin; Bin Jalaludin; Mohammed Zeeshan; Lidia Morawska; Tian-Yu Zhao; Shyamali Dharmage; Luke Knibbs; et al. (Journal of Hazardous Materials, 2026)

Differential associations of PFAS in follicular fluid and serum with reproductive hormones: Insights from a Chinese IVF cohort GIVES - Kun Zhao; Chu Chu; Michael S. Bloom; Jian-Ping Cong; Marjut Roponen; Pasi Jalava; Mo Yang; Wan-Ting He; Yun-Ting Zhang; Ming-Kun Sun; Jing-Wen Huang; Li-Xia Liang; et al. (Environmental Research, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Satellite mapping of emperor penguin habitat dispersal under climate extremes - Hong Lin; Xiao Cheng; Jinyang Du; John S. Kimball; Ziyu Yan; Teng Li; Tongwen Li; Yibo Li; Zilong Chen (Remote Sensing of Environment, 2025)

Association between prenatal exposures to per- and polyfluoroalkyl substances and early language development in the ECHO cohort - Patricia Cintora; Lesliam Quirós-Alcalá; Adaeze W. Nzegwu; Sudhi Upadhyaya; Megan Woodbury; Sarah Dee Geiger; Rachel Morello-Frosch; Anne L. Dunlop; Theresa M. Bastain; Anne P. Starling; Dana Dabelea; Carlos A. Camargo; et al. (NeuroToxicology, 2025)

A new externally coupled, physically-based multi-model framework for simulating subsurface and overland flow hydrological processes on hillslopes - A T M Sakiur Rahman; Jiří Šimůnek; Scott A. Bradford; Hoori Ajami; Menberu B. Meles; Lin Chen; Adam Szymkiewicz; Mateusz Pawlowicz; Juan S. Acero Triana; Alberto Casillas-Trasvina; Sahila Beegum (Journal of Hydrology, 2025)

How effective are green roofs as building carbon sinks? Empirical evidence linking substrate, depth, and vegetation dynamics in the U.S. Great Plains - M.M. Lekhon Alam; Lee R. Skabelund; Charles W. Rice; James S. Lin; Jaeyoung Ha (Journal of Environmental Management, 2025)

Effects of wheat gluten amyloid fibrils as reinforcement additives on the functional properties of polyvinyl alcohol-based and pectin-based films for fruit preservation - Chia-Yu Lin; You-Ren Lai; Chia-Jung Lee; Su-Chun How; Ta-Hsien Lin; Steven S.-S. Wang (Journal of Environmental Chemical Engineering, 2025)

Food 3D printing based on machine vision with dynamic control of extrusion to improve print quality - Lin Lin; Jiawei Liu; Xiaochen Chen; Tariq Aziz; Abdulhakeem S. Alamri; Walaa F. Alsanie; Majid Alhomrani; Haiying Cui (Innovative Food Science & Emerging Technologies, 2025)

Scalability potential of a pneumatic extrusion-based 3D printing system for food products - Jingfu Pan; Xiaochen Chen; Jingyao Liu; Ziyi Wang; Tariq Aziz; Majid Alhomrani; Walaa F. Alsanie; Abdulhakeem S. Alamri; Haiying Cui; Lin Lin (Innovative Food Science & Emerging Technologies, 2025)

Nanoengineered scheelite-structured SrWO4 decorated on MXene sheets: A novel platform for electrochemical sensing of the anti-cancer drug nilutamide with DFT insights - Akash Ashokrao Jagtap; Vaibhav Kanke; Rajalakshmi Sakthivel; Amar S. Katkar; Lu-Yin Lin; Yu-Chien Lin; Xinke Liu; Cihun-Siyong Gong; Ching-Wei Tung; Ren-Jei Chung (Environmental Research, 2025)

Meta-analysis on microplastics monitoring in global water resource recovery facilities: An emphasis on overlooked factors - Elinor S. Austin; Dana M. Austin; Linda Y. Tseng; Lin Liu; Zeth Kleinmeyer; Danielle Drake; Diego Rosso; Yian Sun (Environmental Pollution, 2025)

In situ deformation of antigorite-olivine two-phase mixtures: Implications for dynamics and seismic anisotropy in the mantle wedge - Rose Hurlow; Wenhao Su; Wen-Yi Zhou; Feng Lin; Lowell Miyagi; Timothy Officer; Tony Yu; Yanbin Wang; Meiqian Wu; Qin Wang; Jin S. Zhang (Earth and Planetary Science Letters, 2025)

Early Cenozoic source to sink relation between the Tula Basin and the surrounding ranges: Insights for the Tibetan Plateau growth - Jingzhen Peng; Feng Cheng; Dehai Zhang; Hongwei Zhou; Maomao Wang; Xiangzhong Li; Zhaojie Guo; A. K. Khudoley; A. S. Tesakov; Lin Wang; Yan Ma (Science China Earth Sciences, 2025)

Global Occurrence and Environmental Fate of Microplastics in Stormwater Runoff: Unlock the In-depth Knowledge on Nature-Based Removal Strategies - Van-Hiep Hoang; Minh-Ky Nguyen; Tuan-Dung Hoang; Hoang-Lam Nguyen; Chitsan Lin; Balal Yousaf; Minh Cuong Ha; Vu Khac Hoang Bui; Minh-Thuan Pham; S. Woong Chang; D. Duc Nguyen (Reviews of Environmental Contamination and Toxicology, 2025)

Quantifying the effectiveness of superposed roughness elements to reduce dust emissions at the Salton Sea using computational fluid dynamics simulations - E. Furtak-Cole; J. A. Gillies; G. Nikolich; Y. Lin; S. Roy; J. Harrington (Air Quality, Atmosphere & Health, 2025)

PM2.5 and NO2 exposure during pregnancy and measures of fetal size and attained size at birth - Nafisa Nawal Islam; Sally W. Thurston; Donald Harrington; Yihui Ge; Samuel Weisenthal; Jessica Brunner; Richard K. Miller; Philip K. Hopke; Yan Lin; Emily S. Barrett; Thomas G. O’Connor; Junfeng Zhang; et al. (Air Quality, Atmosphere & Health, 2025)

Correction: The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Barley fermentation on nutritional constituents: structural changes and structure–function correlations - Yufeng He; Tao Liu; Danaè S. Larsen; Yuexin Lei; Manchun Huang; Lin Zhu; Maria Daglia; Xiang Xiao (Critical Reviews in Food Science and Nutrition, 2025)

Analytical framework for fast identification of hydrogeological boundaries and aquifer parameters in confined aquifers - Fu-Kuo Huang; Ying-Fan Lin; Hund-Der Yeh; Grace S. Wang (Journal of Hydrology, 2025)

Walruses are potentially exposed to paralytic shellfish toxin concentrations that impact their health during Alexandrium blooms in the Alaskan Arctic - Patrick Charapata; Evangeline Fachon; Donald M. Anderson; Gay Sheffield; Emily K. Bowers; Robert S. Pickart; Peigen Lin; Kathi A. Lefebvre (Harmful Algae, 2025)

Hydrogen, single-carbon compounds, and thermal regime in the oceanic ultramafic-dominated lithosphere: insights from a deep borehole on the Atlantis Massif - Susan Q. Lang; C. Geoffrey Wheat; Kristin L. Dickerson; Mark K. Reagan; Ivan P. Savov; Jordyn A. Robare; William J. Brazelton; Johanna Suhonen; Oscar Cavazos; Andrew McCaig; Peter Blum; Natsue Abe; et al. (Geochimica et Cosmochimica Acta, 2025)

Effects of ice-binding protein from Leucosporidium sp. AY30 (LeIBP) on physicochemical quality, myofibrillar protein and ice crystal morphology of largemouth bass during air freezing - Junde Ren; Feifei Hu; Farooq Muhammad; Lihui Hu; Tao Song; Maninder Meenu; Jie Lin; Ying Liu; Hosahalli S. Ramaswamy; Yong Yu (Food Research International, 2025)

Fetal response to maternal exposures of environmental chemicals: Utility of a four-cell human feto-maternal interface organ-on-chip - Haley L. Moyer; SungJin Kim; Bowie P. Lam; Lauren S. Richardson; Han-Hsuan D. Tsai; Lucie C. Ford; Hsing-Chieh C. Lin; Weihsueh A. Chiu; Ramkumar Menon; Arum Han; Ivan Rusyn (Chemico-Biological Interactions, 2025)

Synergistic effects and mechanisms of ultrasonic, pH, and peracetic acid pretreatment on sludge anaerobic fermentation to stimulate short-chain fatty acid production - Eid S. Gaballah; Lei Gao; Richen Lin; Mahmoud M. Ali; Biao Yang; Mostafa Sobhi; Chongpeng Tang; Guangcan Zhu (Bioresource Technology, 2025)

Detection of unusually high transcriptomic and proteomic abundance of bromoform-synthesizing halogenase in marine macroalgae Asparagopsis taxiformis - Zhenjian Lin; Shahima Islam; Matthew S. Hargrave; Rakesh Singh; Lingjie Zhou; Ramon Xie; Jennifer E. Smith; Eric W. Schmidt; Vinayak Agarwal (Frontiers in Marine Science, 2025)
Halogenated molecules produced by marine algae are thought to be defensive secondary metabolites. The extraordinarily high concentration of bromoform in the seaweed Asparagopsis —up to 8% dry tissue weight—challenges the exclusivity of this paradigm. In this report, we provide evidence that the mbb1 gene which encodes the bromoform producing halogenase is among the most highly transcribed genes in Asparagopsis tissue, with the resulting Mbb1 protein abundance rivaling that of enzymes involved in photosynthesis and carbon fixation. When the seaweed was stressed with light, transcripts for both mbb1 and for proteins involved in photosynthesis were significantly downregulated. Conversely, heat stress modestly upregulated some photosynthesis genes but had no impact on mbb1 . Taken together, these findings allow us to posit that bromoform production is not solely a stress-response or self-defense mechanism for A. taxiformis . Instead, we propose that the halogenase Mbb1 likely fulfils a primary metabolic function in this red alga thusly reconceptualizing halogenation biochemistry and pulling it out of the domain of natural product biosynthesis alone.

Nitrous oxide emissions and mitigation strategies in a nitrite-accumulating partial denitrification wastewater treatment process using rope type biofilm media - Lin Sun; Wudneh Ayele Shewa; S Ahmad Shabir Razavi; Kevin Bossy; Martha Dagnew (Journal of Environmental Management, 2025)

Histopathological and immunohistochemical characterisation of inflammatory lesions in flying foxes naturally infected with Australian Bat Lyssavirus (ABLV). - Y. Lin Tan; M. Gimeno; P. Pinczowski; S. Gestier; E. Hall; M. Krockenberger (Journal of Comparative Pathology, 2025)

Mechanistic insights into cross-modal aroma-taste interactions mediating sweetness perception enhancement in Fu brick tea - Zhihui Hu; Amr M. Bakry; Lin Shi; Ping Zhan; Wanying He; Walaa A.M. Eid; Hussein Ferweez; Yahya S. Hamed; Hesham A. Ismail; Honglei Tian; Peng Wang (Food Chemistry, 2025)

Exploring the anti-Listeria monocytogenes mechanisms of the postbiotics derived from Ligilactobacillus salivarius LSA-6 and its biopreservative effects on Inner Mongolian cheese - Ce Shi; Li Jia; Jinlong Xu; Na Guo; Haiying Cui; Tariq Aziz; Abdulhakeem S. Alamri; Walaa F. Alsanie; Majid Alhomrani; Changzhu Li; Lin Lin (Food Bioscience, 2025)

An innovative adaptive mineral segmentation method via augmentation and fusion of single and orthogonal polarized images: AMS-p/xpl - W. Ma; P. Lin; S. Li; Z.H. Xu (Computers & Geosciences, 2025)

Perhydroxylated benzoquinoid covalent triazine framework for ultra-high-density lithium-ion storage - Nhu T.H. Luu; Rajeshkumar Anbazhagan; Alexander S. Ivanov; Sung-En Lin; Chia-Hsin Chang; Chen-Yu Hung; Ilja Popovs; Jui-Chin Lee; Teng-Hao Chen; Watchareeya Kaveevivitchai (Chemical Engineering Journal, 2025)

Canagliflozin-driven cellular re-differentiation and migration inhibition in vascular smooth muscle cells via PTEN upregulation - Ming-Jer Hsieh; Dong-Yi Chen; Cheng-Hung Lee; Yu-Cih Liao; Miao‐Sui Lin; Jong-Hwei S. Pang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Subclinical atrial fibrillation prediction based on deep learning and strain analysis using echocardiography - Sung-Hao Huang; Ying-Chi Lin; Ling Chen; Sayan Unankard; Vincent S. Tseng; Hsuan-Ming Tsao; Gau-Jun Tang (Medical & Biological Engineering & Computing, 2025)
Subclinical atrial fibrillation (SCAF), also known as atrial high-rate episodes (AHREs), refers to asymptomatic heart rate elevations associated with increased risks of atrial fibrillation and cardiovascular events. Although deep learning (DL) models leveraging echocardiographic images from ultrasound are widely used for cardiac function analysis, their application to AHRE prediction remains unexplored. This study introduces a novel DL-based framework for automatic AHRE detection using echocardiograms. The approach encompasses left atrium (LA) segmentation, LA strain feature extraction, and AHRE classification. Data from 117 patients with cardiac implantable electronic devices undergoing echocardiography were analyzed, with 80% allocated to the development set and 20% to the test set. LA segmentation accuracy was quantified using the Dice coefficient, yielding scores of 0.923 for the LA cavity and 0.741 for the LA wall. For AHRE classification, metrics such as area under the curve (AUC), accuracy, sensitivity, and specificity were employed. A transformer-based model integrating patient characteristics demonstrated robust performance, achieving mean AUC of 0.815, accuracy of 0.809, sensitivity of 0.800, and specificity of 0.783 for a 24-h AHRE duration threshold. This framework represents a reliable tool for AHRE assessment and holds significant potential for early SCAF detection, enhancing clinical decision-making and patient outcomes. Graphical abstract

Non-extractant recycling of Ti, Fe, Ca and Al as value-added anatase, hematite, gypsum and nordstrandite from waste red mud - T. Su; S. Li; R. Bian; Y. Lin; S. Zhu (International Journal of Environmental Science and Technology, 2025)

Saxitoxin Linked to Deaths of Northern Fur Seals in the Southeast Bering Sea - Kathi A. Lefebvre; Chelsea M. Campbell; Lauren M. Divine; Paul Melovidov; Hanna Hellen; Kathy Burek Huntington; Emily K. Bowers; Natalie Rouse; Evangeline Fachon; Thomas J. Farrugia; Robert S. Pickart; Peigen Lin; et al. (Marine Mammal Science, 2025)
In August 2024, a northern fur seal mortality event was observed on St. Paul Island, AK in the southeast (SE) Bering Sea. Ten seals in good body condition were found dead along with large accumulations of dead fish on Benson Beach located on St. Paul Island. Full necropsies of the five available adult seals, one pup, and several fish did not reveal any overt causes of death. Testing of tissues for the algal neurotoxins domoic acid (DA) and saxitoxin (STX) confirmed the presence of STX in multiple tissues and physiological exposure in all five adult NFS and the two fish available for testing. DA was not detected in any samples. Complimentary samples of the SE Bering Sea ecosystem during the same time frame and location as the die off revealed bloom densities of Alexandrium catenella (the dinoflagellate that produces STX), large A. catenella cyst beds, and high prevalences of STX in fish (100%, n = 22), zooplankton (93%, n = 28), clams (100%, n = 10) and worms (93% n = 15) in the foraging area of NFS. High STX concentrations were observed in fish, clams, worms, and NFS urine, providing compelling evidence for a STX poisoning event.

Industrial waste-derived biochar composites for the removal of water-borne 4-nitrophenol: assessing cost-effectiveness and sustainability - Harsha S. Rangappa; Phyu Phyu Mon; Baalamurugan Jayaraman; Giridhar Madras; Chuxia Lin; Subrahmanyam Challapalli (Environmental Science and Pollution Research, 2025)

Impaired early type I interferon responses to influenza virus infection in aged mice are associated with subsequent increased pulmonary inflammation - Wenxin Wu; Jeremy S. Alexander; J. Leland Booth; Chaoqun Huang; Lin Liu; Craig A. Miller; Douglas A. Drevets; Jordan P. Metcalf (GeroScience, 2025)

Navigating disclosure in new romantic partnerships as an adolescent or young adult with Li-Fraumeni syndrome - Camella J. Rising; Chloe O. Huelsnitz; Rowan Forbes Shepherd; Catherine Wilsnack; Patrick Boyd; Alix G. Sleight; Ashley S. Thompson; Sadie P. Hutson; Payal P. Khincha; Allison Werner-Lin (Familial Cancer, 2025)
Li-Fraumeni syndrome (LFS) is an early-onset cancer syndrome caused by pathogenic germline TP53 variants. Adolescents and young adults (AYAs) with LFS may have challenges navigating new romantic partnerships given the significant effects of LFS on multiple life domains that also affect partners (e.g., reproductive decision-making). Disclosing LFS-related information to new partners may be especially difficult given the uncertainty, complexity, and chronicity of LFS. This qualitative-descriptive study aimed to explore AYAs’ LFS disclosure decisions and experiences in new romantic partnerships. Participants were individuals with LFS aged 15–39 years at enrollment in a National Cancer Institute study. The analytic sample included 33 AYAs who completed at least one telephone interview. Greene’s disclosure decision-making model guided thematic analysis. Participants were mostly female (67%) and married/in a long-term relationship (58%), with mean age 29 years and ≥ 1 primary cancer (61%). Key factors in LFS disclosure decision-making included perceived relevancy to partners (e.g., future children’s genetic risk), partner traits (e.g., trustworthiness), and relationship quality (e.g., closeness). AYAs described LFS disclosures in new partnerships as a process. Disclosing LFS diagnosis often occurred early to fulfill a sense of moral obligation and emotionally self-protect from future rejection, while subsequent LFS disclosures depended on relationship quality and the topic’s emotional valence or complexity. Partners often earned AYAs’ trust by demonstrating a willingness to learn about and try to understand LFS. Clinicians and LFS communities could support AYAs by providing opportunities to discuss, normalize, and ameliorate challenges with LFS disclosures in new romantic partnerships (e.g., peer support groups, psychotherapy).

P22-09 Toxicological Profiling of ZnO Nanoparticles: A Genotoxicity Mechanistic Study Using Alternative Test Methods - R.J. Chen; O. Lautan; S.-N. Chen; T.-Y. Lin; R. Pranata (Toxicology Letters, 2025)

P20-17 Polyethylene terephthalate (PET) nanoplastics induce acute pulmonary inflammation in mice - Ø.P. Haugen; L.M.A. Camassa; H.F. Berntsen; F.-C. Lin; V. Alcolea-Rodriguez; R. Portela; F. Barbero; O.A.H. Foss; H. Sadeghiankaffash; Ø. Skare; S. Alsaedi; A.L. Moen; et al. (Toxicology Letters, 2025)

Revealing region-specific drivers of tire and road wear particle composition and sources in road dust from two western Chinese cities - Yunfei Ma; Elisabeth S. Rødland; Jingyuan Li; Wei Chen; Yan Lin (Journal of Hazardous Materials, 2025)

A new chemical marker method for determining heating patterns in microwave pasteurization - Xu Zhou; Huimin Lin; Cheng-You Wu; Shyam S. Sablani; Juming Tang (Journal of Food Engineering, 2025)

Impact of U-10Mo HALEU fuel element tolerances on the Massachusetts Institute of Technology reactor safety and operational performance – Thermal hydraulics - Sero Yang; Valerio Mascolino; Laura M. Jamison; Kyle E. Anderson; Lin-wen Hu; Dhongik S. Yoon; John A. Stillman; Walid M. Mohamed; Erik H. Wilson (Annals of Nuclear Energy, 2025)

Impact of U-10Mo HALEU Fuel Element Tolerances on the Massachusetts Institute of Technology Reactor safety and operational performance – Neutronics - Valerio Mascolino; Sero Yang; Laura M. Jamison; Kyle E. Anderson; Lin-wen Hu; Dhongik S. Yoon; John A. Stillman; Walid Mohamed; Erik H. Wilson (Annals of Nuclear Energy, 2025)

Nicotinamide riboside combined with exercise to treat hypertension in middle-aged and older adults: a pilot randomized clinical trial - Yi Lin; Rola S. Zeidan; Stephanie Lapierre-Nguyen; Hannah M. Costello; Stephen D. Anton; Thomas W. Buford; Demetra D. Christou; Michelle L. Gumz; Christiaan Leeuwenburgh; Christopher R. Martens; Mary M. McDermott; Marie E. Migaud; et al. (GeroScience, 2025)
Aerobic exercise lowers blood pressure (BP) with varying effects in hypertensive adults, potentially due to age-related nicotinamide adenine dinucleotide (NAD) metabolism dysregulation. This pilot randomized clinical trial (RCT) tested the efficacy of combining aerobic exercise with the NAD booster nicotinamide riboside (NR) to enhance BP control. In this double-blinded RCT, 54 sedentary adults (≥ 55 years) with mean daytime systolic BP (SBP) ≥ 130 mmHg were randomized to 6 weeks of 1000 mg/day of NR combined with 3 days/week of supervised 30-min walking exercise (NR + Ex), Placebo combined with the same exercise regimen (PL + Ex), or NR alone (NR). The primary outcome was daytime SBP. Other outcomes included pulse wave velocity (PWV), NAD catabolites, and nighttime BP. The primary comparison was between NR + Ex and PL + Ex. Of 54 participants (mean age 67 years, 61% female), 49 (NR + Ex: n = 15, PL + Ex: n = 16, NR: n = 18) completed all study visits (93% adherence to exercise and 90% to supplementation). NR + Ex (mean change = 5.19 ± 13.2 mmHg) did not reduce SBP more than PL + Ex (− 2.71 ± 10.5 mmHg). NR + Ex (− 0.31 ± 0.77 m/s) showed a trend toward a greater reduction in PWV. Levels of NAD catabolites were higher in NR groups. In a post hoc analysis, NR + Ex showed a trend toward greater nighttime BP reductions (systolic: − 9.6 ± 9.22; diastolic: − 4.51 ± 7.12 mmHg) in participants without antihypertensive medications. NR + Ex was not superior to PL + Ex in reducing BP in hypertensive middle-aged and older. However, trends toward greater nighttime BP reduction in NR + Ex in participants without antihypertensive medication warrant further investigation in a Phase IIb RCT. Graphical Abstract

Enhancing the stability of quercetin by loading into dual-layered hydrogel-emulsion gel using coaxial 3D food printing - Min Feng; Min Zhang; Arun S. Mujumdar; Chunli Li; Jiacong Lin (Innovative Food Science & Emerging Technologies, 2025)

Revealing how urban morphology at urban planning and design stage influence energy using urban building energy model - F. Lin; L. Luo; Q. Gu; S. Hao; W. Wang (International Journal of Environmental Science and Technology, 2025)

Status quo and predictions of the most and least discussed sustainable development goals - H.-H. Chung; F.-L. Chung; S.-M. Lin (International Journal of Environmental Science and Technology, 2025)

Driving factors of summer diurnal surface thermal environment in subtropical coastal cities: a Shenzhen case study - Q. Guo; Y. Lin; S. Zhong; X. Zhang (International Journal of Environmental Science and Technology, 2025)

Intact reinforcement learning in healthy ageing - Wei-Hsiang Lin; Karin S. Pilz; Michael H. Herzog; Marina Kunchulia (Experimental Brain Research, 2025)
What changes with age? Results in reinforcement learning (RL) are mixed. Some studies found deteriorated RL performance in older participants compared to younger controls whereas other studies did not. Daniel et al. (J Neurosci 40(5):1084–1096, 2020. 10.1523/JNEUROSCI.0254-19.2019) suggested that task demand can explain these differences, with less demanding tasks showing no effect of age. Compared to classic, simple RL tasks, we used a navigation task to increase overall complexity. We found that older adults performed less efficiently initially; however, with sufficient trials, they performed as well as young adults. Our results support the idea that ageing does not universally impair performance and that even higher-level cognitive tasks remain largely intact.

Revealing Lactiplantibacillus Plantarum K25 Derived (Z)-18-Octadec-9-Enolide in Modulating Aquaporin-8 in Colorectal Cancer by Bridging the Gut Microbiome and Membrane Biology - Tariq Aziz; Muhammad Aqib Shabbir; Abid Sarwar; Zhennai Yang; Lin Lin; Wafa Abdullah I. Al-Megrin; Ashwag Shami; Maher S. Alwethaynani; Areej A Alhhazmi; Fahad Al-Asmari; Fakhria A. Al-Joufi; Deema Fallatah (Cell Biochemistry and Biophysics, 2025)

The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Spinocerebellar Ataxia Type 27B can be Suspected Based on Clinical Phenotype: The Massachusetts General Hospital Ataxia Center Experience - Leigh A. Rettenmaier; Jin Yun Helen Chen; Jason MacMore; Anoopum S. Gupta; Chih-Chun Lin; Christopher D. Stephen; David Pellerin; Bernard Brais; Jeremy D. Schmahmann (The Cerebellum, 2025)

Upper-layer circulation at the mouth of Amundsen Gulf, Arctic Ocean - Peigen Lin; Robert S. Pickart; Maria Pisareva; Bill Williams (Progress in Oceanography, 2025)

Transfer patterns of human blood to follicular fluid of per- and polyfluoroalkyl substances with distinct molecular structures and physico-chemical properties - Yun-Ting Zhang; Michael S. Bloom; Yang Zhou; Saif Ur Rehman; Chu Chu; Kun Zhao; Biao Yin; Zhong Lin; Yuan-Yuan Fan; Li-Zi Lin; Ru-Qing Liu; Weihong Tan; et al. (Journal of Hazardous Materials, 2025)

AI technology in smart drying of foods: A critical review of research and applications - Zhe Wang; Min Zhang; Arun S. Mujumdar; Jiacong Lin; Dongxing Yu (Innovative Food Science & Emerging Technologies, 2025)

International Consortium on Ageing-Related Pathologies (ICCARP) Audiovestibular Group: fostering international consensus to refine International Classification of Diseases (ICD-11) codes for hearing loss across the life course - Dialechti Tsimpida; Michael A. Akeroyd; Barry L. Bentley; Shuvarthi Bhattacharjee; Michael R. Bowl; Emma Broome; Stuart R. G. Calimport; Sian Calvert; Gary Christopher; Tom Dening; Silvia Di Bonaventura; Ankita Goswami; et al. (GeroScience, 2025)

Clearance of particles from regular-flavored little cigar smoke across lung lobes in female Sprague-Dawley rats - Kaisen Lin; Christopher Wallis; Patricia Edwards; Austin Cole; Laura Van Winkle; Anthony S. Wexler (Journal of Aerosol Science, 2025)

3D printing based soy protein isolate-flaxseed gum-catechin as a potential strategy to regulate hypertension - Dongbei Shen; Min Zhang; Arun S. Mujumdar; Chunli Li; Jiacong Lin (Food Bioscience, 2025)

Microplastic characteristics, transport, risks, and remediation in groundwater: a review - Van-Hiep Hoang; Minh-Ky Nguyen; Tuan-Dung Hoang; Nelson Rangel-Buitrago; Chitsan Lin; Minh-Thuan Pham; Minh Cuong Ha; Tan Phong Nguyen; Muhammad Shaaban; S. Woong Chang; D. Duc Nguyen (Environmental Chemistry Letters, 2025)

Diaporthe manilkarae sp. nov. ( Diaporthaceae ) on Manilkara zapota (Sapotaceae) from Guangdong Province, China - Yanhong Lin; Indunil C. Senanayake; Ishara S. Manawasinghe; Yunxia Zhang (New Zealand Journal of Botany, 2025)
Manilkara zapota (L.) P. Royen is an evergreen ornamental and fruit tree distributed in tropical and subtropical regions. In 2022, a leaf spot disease was observed on M . zapota plants in Guangdong Province, China. The putative pathogen was isolated and identified based on morphology and multi‐locus phylogenetic analyses of tub2 , ITS, tef1‐α , cal and his3 . Based on morphology and phylogenetic analyses, the causal agent was identified as a novel species namely Diaporthe manilkarae . Furthermore, pathogenicity essays were conducted using potted seedlings to confirm the pathogenicity. The results revealed that this fungus was able to infect wounded M. zapota leaves and develop typical symptoms similar to field symptoms whereas control and non‐wounded leaves remained asymptomatic. This study will contribute to the knowledge of fungi associated with M. zapota . Further studies are required to understand the pathogenicity of this fungi on other fruit crops.

Retraction notice to ‘Applications of engineered biochar in remediation of heavy metal(loid)s pollution from wastewater: Current perspectives toward sustainable development goals’ [Sci. Total Environ., 926 (2024) 171859] - Thien-Khanh Tran; Loan Huynh; Hoang-Lam Nguyen; Minh-Ky Nguyen; Chitsan Lin; Tuan-Dung Hoang; Nguyen Tri Q. Hung; X. Hoan Nguyen; S. Woong Chang; D. Duc Nguyen (Science of The Total Environment, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Tidal signal propagation in coastal aquifers considering semi-permeable boundaries and partial penetration effects - Fu-Kuo Huang; Ying-Fan Lin; Grace S. Wang; Barret L. Kurylyk (Journal of Hydrology, 2025)

Root exudates of Salix cupularis orchestrate the accumulation of soil carbon and nitrogen in the rhizosphere during the restoration of a desertified alpine meadow - Qi Li; Fei Yan; Dongming Chen; Jiqiong Zhou; Zhouwen Ma; Yanfu Bai; Xingpeng Hu; Congyu Ma; Abeer S. Aloufi; Feida Sun; Anna Gunina; Jian Zhang; et al. (Applied Soil Ecology, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Soil Carbon Saturation: What Do We Really Know? - Katerina Georgiou; Denis Angers; Ryan E. Champiny; M. Francesca Cotrufo; Matthew E. Craig; Sebastian Doetterl; A. Stuart Grandy; Jocelyn M. Lavallee; Yang Lin; Emanuele Lugato; Christopher Poeplau; Katherine S. Rocci; et al. (Global Change Biology, 2025)
Managing soils to increase organic carbon storage presents a potential opportunity to mitigate and adapt to global change challenges, while providing numerous co‐benefits and ecosystem services. However, soils differ widely in their potential for carbon sequestration, and knowledge of biophysical limits to carbon accumulation may aid in informing priority regions. Consequently, there is great interest in assessing whether soils exhibit a maximum capacity for storing organic carbon, particularly within organo–mineral associations given the finite nature of reactive minerals in a soil. While the concept of soil carbon saturation has existed for over 25 years, recent studies have argued for and against its importance. Here, we summarize the conceptual understanding of soil carbon saturation at both micro‐ and macro‐scales, define key terminology, and address common concerns and misconceptions. We review methods used to quantify soil carbon saturation, highlighting the theory and potential caveats of each approach. Critically, we explore the utility of the principles of soil carbon saturation for informing carbon accumulation, vulnerability to loss, and representations in process‐based models. We highlight key knowledge gaps and propose next steps for furthering our mechanistic understanding of soil carbon saturation and its implications for soil management.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Genesis of the Hamash gold deposit, eastern desert, Egypt: Inferences from new studies on mineral chemistry and fluid inclusions - Islam.A. Dourgham; Safwat S. Gabr; Lin-Fei Qiu; Masoud A. Omar; Fatma Deshesh (Journal of African Earth Sciences, 2025)

Plastic wastes for carbon-based materials: Investigations on recent applications towards environmentally sustainable, carbon dioxide capture and green energy - The-Anh Luu; Van-Giang Le; Van-Anh Thai; Minh-Ky Nguyen; Chitsan Lin; Minh-Thuan Pham; S. Woong Chang; D. Duc Nguyen (Environmental Pollution, 2025)

CAR-NK cell therapy: a potential antiviral platform - Ming-Hao Lin; Li-Juan Hu; Jeffrey S. Miller; Xiao-Jun Huang; Xiang-Yu Zhao (Science Bulletin, 2025)

Deoxygenation preceding the Carnian Pluvial Episode (Late Triassic) in the Qiangtang Basin (Tibetan Plateau): Implications for organic and inorganic geochemistry and petrography - Fei Lin; Jian Wang; Ahmed Mansour; Xiugen Fu; Shaohua Su; Ying Nie; Mohamed S. Ahmed; Shengqiang Zeng; Xueren Li (Marine and Petroleum Geology, 2025)

Aggregation-induced emission and absorption enhancement of mixed-valent rhenium oxide quantum dots by triethylamine: Implications for food safety monitoring - Manivannan Madhu; Aravindan Varatharajan; S Santhoshkumar; Wei-Bin Tseng; Po-Chiao Lin; Wei-Lung Tseng (Journal of Hazardous Materials, 2025)

The effect of ice-binding protein from Leucosporidium sp. AY30 (LeIBP) on physicochemical quality and microstructure of largemouth bass during frozen storage - Junde Ren; Feifei Hu; Maninder Meenu; Lihui Hu; Yuxiao Mao; Tao Song; Jie Lin; Ying Liu; Hosahalli S. Ramaswamy; Yong Yu (Innovative Food Science & Emerging Technologies, 2025)

Social conditions alter the growth, metabolic rate, behavioral traits, and food-shelter preferences in the juvenile qingbo Spinibarbus sinensis - Yu-Lin Zhang; Wen-Qian Zhou; Shi-Jian Fu; Lauren E. Nadler; Shaun S. Killen; Ke-Ying Zhou; Shi-Long Zheng; Cheng Fu (Behavioral Ecology and Sociobiology, 2025)

Hyphosphere core taxa link plant-arbuscular mycorrhizal fungi combinations to soil organic phosphorus mineralization - Letian Wang; Lin Zhang; Timothy S. George; Gu Feng (Soil Biology and Biochemistry, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Innovative microencapsulation of hemp seed oil using plant-based biopolymers: A comparative analysis of dehydration techniques on core stability, digestibility and release pattern - Somayeh Gholivand; Tai Boon Tan; Masni Mat Yusoff; Mohammed S. Qoms; Yong Wang; Yuanfa Liu; Kar Lin Nyam; Chin Ping Tan (Food Hydrocolloids, 2025)

Antibacterial mechanisms of diacetyl on Listeria monocytogenes and its application in Inner Mongolian cheese preservation via gelatin-based edible films - Haiying Cui; Yangyang Chen; Tariq Aziz; Fahad Al-Asmari; Maher S. Alwethaynani; Ce Shi; Lin Lin (Food Control, 2025)

Undrained dynamic behavior of geogrid-reinforced coral sand - Stephen Akosah; Lin Zhou; Jianfeng Chen; Ting Yao; Solomon S. R. Gidigasu (Marine Georesources & Geotechnology, 2025)

Correction to: Do past and present abiotic conditions explain variation in the nutritional quality of wildflower pollens for bees? - Anthony D. Vaudo; Eva Lin; Jillian A. Luthy; Anne S. Leonard; Eliza M. Grames (Evolutionary Ecology, 2025)

Relational characteristics and dynamics between high-tech firms in the Pearl River Delta and the empowerment for technological innovation by Hong Kong - Jili Xu; Anthony G. O. Yeh; George C. S. Lin; Xingjian Liu; Fan Fiona Yang; Zixin Luo (Journal of Geographical Sciences, 2025)

Surgical Parameters During Reverse Shoulder Arthroplasty Predict Post-Surgical Kinematics During the Hand-to-Head Motion - Ajinkya A. Rai; Clarissa M. LeVasseur; Gillian E. Kane; Maria A. Munsch; Christopher J. Como; Alexandra S. Gabrielli; Jonathan D. Hughes; William J. Anderst; Albert Lin (Annals of Biomedical Engineering, 2025)

Identification and hazard prioritization of hydrophobic organic chemicals in flowback and produced water particles: Implications for water management - Huiju Lin; Cheng Zhong; Ran Wen; Tsz Hin Ma; Ding He; Jonathan W. Martin; Greg G. Goss; Daniel S. Alessi; Yuhe He (Water Research, 2025)

A web-based histology atlas for the freshwater sentinel species Daphnia magna - Mee S. Ngu; Daniel J. Vanselow; Carolyn R. Zaino; Alex Y. Lin; Jean E. Copper; Margaret J. Beaton; Luisa Orsini; John K. Colbourne; Keith C. Cheng; Khai C. Ang (Science of The Total Environment, 2025)

Evaluation of sustainable waste management: An analysis of techno-economic and life cycle assessments of municipal solid waste sorting and decontamination - Maria A. Herrera Diaz; Yingqian Lin; Pralhad H. Burli; Tasmin Hossain; Damon S. Hartley; Vicki S. Thompson (Resources, Conservation and Recycling, 2025)

Sulfur-functionalized sawdust biochar for enhanced cadmium adsorption and environmental remediation: A multidisciplinary approach and density functional theory insights - M.M.M. Ahmed; Chih-Hao Liao; S. Venkatesan; Yu-Ting Liu; Yu-Min Tzou; Shih-Hao Jien; Ming-Chang Lin; Yi-Cheng Hsieh; Ahmed I. Osman (Journal of Environmental Management, 2025)

Enhanced rock weathering boosts ecosystem multifunctionality via improving microbial networks complexity in a tropical forest plantation - Xing Wang; Guochen Li; Arshad Ali; Camelia Algora; Manuel Delgado-Baquerizo; Daniel S. Goll; Sara Vicca; Tongtong Xu; Boyuan Bi; Qiong Chen; Luxiang Lin; Yunting Fang; et al. (Journal of Environmental Management, 2025)

Additive manufacturing technology in the development of easy to swallow and digest foods for the elderly - Dongbei Shen; Min Zhang; Arun S. Mujumdar; Chunli Li; Jiacong Lin (Food Research International, 2025)

Eco-friendly encapsulation: Investigating plant-based protein-alginate shells for efficient delivery and digestion of hemp seed oil encapsulated via supercritical CO2 dispersion - Somayeh Gholivand; Tai Boon Tan; Masni Mat Yusoff; Mohammed S. Qoms; Yong Wang; Yuanfa Liu; Kar Lin Nyam; Chin Ping Tan (Food Chemistry, 2025)

Organonickel complex J-aggregation on interfacial evaporator promotes broadband absorption and salt rejection for efficient solar-powered desalination - Yi-Ting Lin; Joanna S. Lin; Yung-Cong Yang; Jen-Shyang Ni (Desalination, 2025)

Development and use of DJ-1 affinity microcolumns to screen and study small drug candidates for Parkinson's disease - Jacob C. Jones; Jiusheng Lin; Sadia Sharmeen; Md Masudur Rahman; Ha H. Truong; Ting-Rong Chern; Mark A. Wilson; David S. Hage (Analytica Chimica Acta, 2025)

Comparison of numerosity concept in a freshwater turtle after a two-year retention interval - Feng-Chun Lin; Stephanie S. Godfrey; Si-Min Lin (Behavioral Ecology and Sociobiology, 2025)

Challenges to and importance of considering early and intermediate ontogenetic stages in mangrove forest recovery and restoration - Taylor M. Sloey; Sean P. Charles; Lin Xiong; Edward Castañeda-Moya; Erik S. Yando; David Lagomasino (Marine Pollution Bulletin, 2024)

Cigarette butts in Vietnam's marine environments: From pollution to solutions and prospects - Pham Minh Thuan; Minh-Ky Nguyen; Chitsan Lin; Nelson Rangel-Buitrago; Francois Galgani; S. Woong Chang; D. Duc Nguyen (Science of The Total Environment, 2024)

Analysis of contaminant residues in honey bee hive matrices - Donna A. Glinski; S. Thomas Purucker; Jeffrey M. Minucci; Rodney T. Richardson; Chia-Hua Lin; Reed M. Johnson; W. Matthew Henderson (Science of The Total Environment, 2024)

Spaceborne high-spectral-resolution lidar ACDL/DQ-1 measurements of the particulate backscatter coefficient in the global ocean - Yichen Yang; Yudi Zhou; Iwona S. Stachlewska; Yongxiang Hu; Xiaomei Lu; Weibiao Chen; Jiqiao Liu; Wenbo Sun; Suhui Yang; Yuting Tao; Lei Lin; Weige Lv; et al. (Remote Sensing of Environment, 2024)

Bioaerosols downwind from animal feeding operations: A comprehensive review - Pradeep Kumar; Shalini Tiwari; Seyit Uguz; Zonggang Li; Jose Gonzalez; Lin Wei; Ryan S. Samuel; Yuanhui Zhang; Xufei Yang (Journal of Hazardous Materials, 2024)

Sulfur-functionalized rice straw biochar for enhanced cadmium sorption: Spectroscopic, kinetic and computational insights - M.M.M. Ahmed; Chih-Hao Liao; Yu-Ting Liu; S. Venkatesan; Yi-Chen Hsieh; H.M. Nail; Hui-Min David Wang; Ming-Chang Lin; Shih-Hao Jien; Yu-min Tzou (Journal of Cleaner Production, 2024)

Development of two-dimensional amyloid fibril/carboxymethyl cellulose hybrid membranes for effective adsorption of hexavalent chromium - You-Ren Lai; Xiao-Xuan Hou; Su-Chun How; Ta-Hsien Lin; Steven S.-S. Wang (Journal of Environmental Chemical Engineering, 2024)

Tracing the stepwise warming trend in the tropical Indian Ocean through a 40-year record of oxygen isotope composition in Maldives corals - Ke Lin; Tao Han; Kyle Morgan; Paul S. Kench; Yue-Gau Chen; Xianfeng Wang (Earth and Planetary Science Letters, 2024)

Do past and present abiotic conditions explain variation in the nutritional quality of wildflower pollens for bees? - Anthony D. Vaudo; Eva Lin; Jillian A. Luthy; Anne S. Leonard; Eliza M. Grames (Evolutionary Ecology, 2024)

The potential of biochar incorporation into agricultural soils to promote sustainable agriculture: insights from soil health, crop productivity, greenhouse gas emission mitigation and feasibility perspectives—a critical review - Muhammad Saif Ullah; Raheleh Malekian; Gurjit S. Randhawa; Yuvraj Sing Gill; Sundeep Singh; Travis J. Esau; Qamar U. Zaman; Hassan Afzaal; Dao Lin Du; Aitazaz A. Farooque (Reviews in Environmental Science and Bio/Technology, 2024)

Construction and Behavioral Comparison of Two Mouse Models of Cerebral Palsy - Y. Tang; Y. Li; S. Lin; W. Wei; H. Chen (Bulletin of Experimental Biology and Medicine, 2024)

Two F-18 radiochemistry methods to synthesize a promising transient receptor potential canonical 5 (TRPC5) radioligand - Yanbo Yu; Sandip B. Jadhav; Zhimin Xing; Hao Jiang; Lin Qiu; Tianyu Huang; Joel S. Perlmutter; Zibo Li; Zhude Tu (Journal of Fluorine Chemistry, 2024)

A paradoxical perspective on the time dimension of corporate sustainability: Having both finite and infinite mindsets to play the game - Lin Wu; Nachiappan Subramanian; Kulwant S. Pawar; Miao Wang; Ajay Kumar; Kim Hua Tan (Journal of Cleaner Production, 2024)

Soil nitrous oxide emissions from wheat-based rotations with different types of pulse crops - K. Liu; P.V.F. Machado; S. Lin; C.F. Drury; R.L. Lemke (Journal of Environmental Management, 2024)

Structure and transport properties of FeS at planetary core conditions - E. Edmund; T. Bi; Z.M. Geballe; K. Brugman; J.-F. Lin; S. Chariton; V.B. Prakapenka; J. Minár; R.E. Cohen; A.F. Goncharov (Earth and Planetary Science Letters, 2024)

Fluid inclusion characteristics and mechanisms of tin mineralisation in the Jialong tin polymetallic deposits, Jiuwandashan–Yuanbaoshan, northern Guangxi, China - C-L. Meng; L-A. Bai; Z-H. Yue; S-Y. Zhou; Y. Dai; Z-H. Feng; X-J. Liu; H. Zhang; L-Z. Lin (Australian Journal of Earth Sciences, 2024)

Sustainable location-routing problem for medical waste management using electric vehicles - Keyong Lin; S. Nurmaya Musa; Hai Yen Lee; Hwa Jen Yap (Sustainable Cities and Society, 2024)

Speciation, phytoavailability, and accumulation of toxic elements and sulfur by humic acid-fertilized lemongrass and common sage in a sandy soil treated with heavy oil fly ash: A trial for management of power stations wastes - Samir G. Al-Solaimani; Abdulrahman Al-Qureshi; Sherif S. Hindi; Omer H. Ibrahim; Magdi A.A. Mousa; Yen-Lin Cho; Noha E.E. Hassan; Yu-Ting Liu; Shan-Li Wang; Vasileios Antoniadis; Jörg Rinklebe; Sabry M. Shaheen (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Nitrogen-doped porous carbon-tubes decorated with Co/CoO nanocomposite material derived from covalent organic framework for energy storage application - Narayanamoorthi Easwaran; N.S.K. Gowthaman; Uma Shankar Veerasamy; Pei-Chien Tsai; Veeramani Mangala Gowri; Sirikanjana Thongmee; S. Abraham John; K.P. Elango; Yuan-Chung Lin; Vinoth Kumar Ponnusamy (Process Safety and Environmental Protection, 2024)

Unveiling the anti-listerial effect of Citrus bergamia essential oil: Mechanism of membrane disruption and anti-hemolytic activity - Hafiz Abdul Rasheed; Abdur Rehman; Xiaochen Chen; Tariq Aziz; Fahad Al-Asmari; Majid Alhomrani; Abdulhakeem S. Alamri; Haiying Cui; Lin Lin (Food Bioscience, 2024)

Estimating ambient air pollutant concentrations outside and inside homes in the Subpopulations and Intermediate outcomes in COPD air pollution (SPIROMICS air) cohort - Kipruto Kirwa; Amanda J. Gassett; Coralynn Sack; Laura M. Paulin; Cheryl S. Pirozzi; R. Graham Barr; Prescott G. Woodruff; MeiLan Han; May-Lin Wilgus; Igor Barjaktarevic; Stephen Peters; Nadia N. Hansel; et al. (Environmental Research, 2024)

A methodology for gene level omics-WAS integration identifies genes influencing traits associated with cardiovascular risks: the Long Life Family Study - Sandeep Acharya; Shu Liao; Wooseok J. Jung; Yu S. Kang; Vaha Akbary Moghaddam; Mary F. Feitosa; Mary K. Wojczynski; Shiow Lin; Jason A. Anema; Karen Schwander; Jeff O. Connell; Michael A. Province; et al. (Human Genetics, 2024)
The Long Life Family Study (LLFS) enrolled 4953 participants in 539 pedigrees displaying exceptional longevity. To identify genetic mechanisms that affect cardiovascular risks in the LLFS population, we developed a multi-omics integration pipeline and applied it to 11 traits associated with cardiovascular risks. Using our pipeline, we aggregated gene-level statistics from rare-variant analysis, GWAS, and gene expression-trait association by Correlated Meta-Analysis (CMA). Across all traits, CMA identified 64 significant genes after Bonferroni correction (p ≤ 2.8 × 10 –7 ), 29 of which replicated in the Framingham Heart Study (FHS) cohort. Notably, 20 of the 29 replicated genes do not have a previously known trait-associated variant in the GWAS Catalog within 50 kb. Thirteen modules in Protein–Protein Interaction (PPI) networks are significantly enriched in genes with low meta-analysis p-values for at least one trait, three of which are replicated in the FHS cohort. The functional annotation of genes in these modules showed a significant over-representation of trait-related biological processes including sterol transport, protein-lipid complex remodeling, and immune response regulation. Among major findings, our results suggest a role of triglyceride-associated and mast-cell functional genes FCER1A , MS4A2 , GATA2 , HDC , and HRH4 in atherosclerosis risks. Our findings also suggest that lower expression of ATG2A , a gene we found to be associated with BMI, may be both a cause and consequence of obesity. Finally, our results suggest that ENPP3 may play an intermediary role in triglyceride-induced inflammation. Our pipeline is freely available and implemented in the Nextflow workflow language, making it easily runnable on any compute platform ( https://nf-co.re/omicsgenetraitassociation ) .

Residential Proximity to Metal-Emitting Industries and Toenail Metal Concentration in the US Gulf States - Joyce J. Y. Lin; Emily J. Werder; Kaitlyn G. Lawrence; W. Braxton Jackson; Dale P. Sandler; Aisha S. Dickerson; Lawrence S. Engel; Ana M. Rule (Exposure and Health, 2024)

Toxicity and metabolism of deoxynivalenol and its reversal by Bacillus subtilis in broiler chickens - Y. Lin; S. Wang; X. Deng; N. Liu; J. Wang (Animal Feed Science and Technology, 2024)

Effect of electrolyte composition on electrocatalytic transformation of perfluorooctanoic acid (PFOA) in high pH medium - Lama Saleh; Zunhui Lin; Mahmut S. Ersan; Christophe Coutanceau; Paul Westerhoff; Jean-Philippe Croué (Chemosphere, 2024)

P21-52 Paraquat disrupts KIF5A-mediated axonal mitochondrial transport in midbrain neurons and its antagonism by melatonin - H. Hong; J. Li; T. Tong; X. Lin; Y. Xu; J. Lin; S. Liu; K. Luo; Z. Zhou (Toxicology Letters, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Effects of static magnetic fields freezing on starch-based prepared fried rice as staple foods - Yanzhen Long; Min Zhang; Arun S. Mujumdar; Jiacong Lin (International Journal of Refrigeration, 2024)

Systemic oxidative stress levels during the course of pregnancy: Associations with exposure to air pollutants - Xiangtian Wang; Yan Lin; Yihui Ge; Emily Craig; Xiaodong Liu; Richard K. Miller; Sally W. Thurston; Jessica Brunner; Emily S. Barrett; Thomas G. O'Connor; David Q. Rich; Junfeng (Jim) Zhang (Environmental Pollution, 2024)

Guyparkeria halophila: Novel cell platform for the efficient valorization of carbon dioxide and thiosulfate into ectoine - E. Huang-Lin; D. Tamarit; R. Lebrero; S. Cantera (Bioresource Technology, 2024)

A review on the characterization of microwave-induced biowaste-derived activated carbons for dye adsorption - T. Kopac; S. D. Lin (International Journal of Environmental Science and Technology, 2024)

Identification of pollution sources in rivers by downstream analysis of low-concentration elements associated with wastewater - H.-C. Lin; P.-Y. Hsieh; G.-S. Wang; D.-W. Wang; T.-H. Wang; Y.-C. Hsu; C.-F. Wu (International Journal of Environmental Science and Technology, 2024)

A Review of Urban Planning Approaches to Reduce Air Pollution Exposures - Dung-Ying Lin; S. Travis Waller; Ming-Yeng Lin (Current Environmental Health Reports, 2024)

An in vitro-in silico workflow for predicting renal clearance of PFAS - Hsing-Chieh Lin; Courtney Sakolish; Haley L. Moyer; Paul L. Carmichael; Maria T. Baltazar; Stephen S. Ferguson; Jason P. Stanko; Philip Hewitt; Ivan Rusyn; Weihsueh A. Chiu (Toxicology and Applied Pharmacology, 2024)

Evolution of volcanic activity and its impact on continental weathering, paleoproductivity, and runoff during the early Aptian in southern Tibet (eastern Tethys): Implications for regional to global environmental perturbations - Ying Nie; Xiugen Fu; Ahmed Mansour; Shengqiang Zeng; Mohamed S. Ahmed; Fangzhi Hu; Fei Lin; Zhe Qi; Qiangwang Wu; Manuel Rigo (Sedimentary Geology, 2024)

Valorisation of food waste into bio-based polyurethane rigid foams: From experimental investigation to techno-economic analysis - Zi-Hao Qin; Anda Fridrihsone; Jin-Hua Mou; Ralfs Pomilovskis; Daniela Godina; Yahui Miao; Ziyao Liu; Chi-Wing Tsang; Lin Zhang; Chunbao Xu; Shauhrat S. Chopra; Eliza Kaulina; et al. (Chemical Engineering Journal, 2024)

Soil freeze/thaw dynamics strongly influences runoff regime in a Tibetan permafrost watershed: Insights from a process-based model - Huiru Jiang; Yonghong Yi; Kun Yang; Lin Zhao; Deliang Chen; John S. Kimball; Fan Lu (CATENA, 2024)

Enhanced silicate weathering accelerates forest carbon sequestration by stimulating the soil mineral carbon pump - Tongtong Xu; Zuoqiang Yuan; Sara Vicca; Daniel S. Goll; Guochen Li; Luxiang Lin; Hui Chen; Boyuan Bi; Qiong Chen; Chenlu Li; Xing Wang; Chao Wang; et al. (Global Change Biology, 2024)
Enhanced silicate rock weathering (ERW) is an emerging strategy for carbon dioxide removal (CDR) from the atmosphere to mitigate anthropogenic climate change. ERW aims at promoting soil inorganic carbon sequestration by accelerating geochemical weathering processes. Theoretically, ERW may also impact soil organic carbon (SOC), the largest carbon pool in terrestrial ecosystems, but experimental evidence for this is largely lacking. Here, we conducted a 2‐year field experiment in tropical rubber plantations in the southeast of China to evaluate the effects of wollastonite powder additions (0, 0.25, and 0.5 kg m −2 ) on both soil organic and inorganic carbon at 0–10 cm depth. We found that ERW significantly increased the concentration of SOC and HCO 3 − , but the increases in SOC were four and eight times higher than that of HCO 3 − with low‐ and high‐level wollastonite applications. ERW had positive effects on the accrual of organic carbon in mineral‐associated organic matter (MAOM) and macroaggregate fractions, but not on particulate organic matter. Path analysis suggested that ERW increased MAOM mainly by increasing the release of Ca, Si, and Fe, and to a lesser extent by stimulating root growth and microbial‐derived carbon inputs. Our study indicates that ERW with wollastonite can promote SOC sequestration in stable MOAM in surface soils through both the soil mineral carbon pump and microbial carbon pump. These effects may have been larger than the inorganic CDR during our experiment. We argue it is essential to account for the responses of SOC in the assessments of CDR by ERW.

Elucidating the bacterial communities and their hydrolytic enzyme activities during the southwest monsoon season, along the west coast of India - Ashutosh S. Parab; Mayukhmita Ghose; Lin E. A. S. Da’Costa; Cathrine S. Manohar (Marine Biology Research, 2024)

First success in captive breeding of the Tiger Cowrie, Cypraea tigris (Gastropoda: Cypraeidae), with notes on its early life development - Teresa S. Tay; K.E. Kayden Tong; Yuchen Sun; Mei Lin Neo (Molluscan Research, 2024)

Associations of a toenail metal mixture with attention and memory in the Gulf long-term follow-up (GuLF) study - Joyce J.Y. Lin; Jordan R. Kuiper; Aisha S. Dickerson; Jessie P. Buckley; Heather E. Volk; Diane S. Rohlman; Kaitlyn G. Lawrence; W. Braxton Jackson; Dale P. Sandler; Lawrence S. Engel; Ana M. Rule (Science of The Total Environment, 2024)

Niche convergence and biogeographic history shape elevational tree community assembly in a subtropical mountain forest - Liang-Liang Ma; Sebastian Seibold; Marc W. Cadotte; Jia-Yun Zou; Jie Song; Zhi-Qiong Mo; Shao-Lin Tan; Lin-Jiang Ye; Wei Zheng; Kevin S. Burgess; Zhi-Fa Chen; De-Tuan Liu; et al. (Science of The Total Environment, 2024)

Arbuscular mycorrhizal fungi reduce soil N2O emissions by altering root traits and soil denitrifier community composition - Tangqing He; Wei Lin; Shuo Yang; Jiaqi Du; Bhoopander Giri; Cheng Feng; Frank S. Gilliam; Fuliang Zhang; Xiaoquan Zhang; Xuelin Zhang (Science of The Total Environment, 2024)

Investigating the partitioning behavior of per- and polyfluoroalkyl substances (PFAS) during thermal landfill leachate evaporation - Allison R. Cerlanek; Alina S. Timshina; Nicole Robey; Ashley M. Lin; Helena M. Solo-Gabriele; Timothy G. Townsend; John A. Bowden (Journal of Hazardous Materials, 2024)

Drying kinetics and moisture migration mechanism of yam slices by cold plasma pretreatment combined with far-infrared drying - Chen Shen; Wenqing Chen; Tariq Aziz; Ebtihal Khojah; Fahad Al-Asmari; Abdulhakeem S. Alamri; Majid Alhomrani; Haiying Cui; Lin Lin (Innovative Food Science & Emerging Technologies, 2024)

Development of validated sandwich ELISA for detecting peanut allergen Ara h 3 in food - Jia-Fong Lin; Kee-Lung Chang; Bau-Shan Hsieh; Yu-Chen Hu; Edward S. Huang; Hsu-Sheng Yu (Food Chemistry, 2024)

Associations between follicular fluid trace elements and ovarian response during in vitro fertilization - Rooshna Mohsin; Victor Y. Fujimoto; Aubrey L. Galusha; Patrick J. Parsons; Jenna R. Krall; Celeste D. Butts-Jackson; Evelyn Mok-Lin; Michael S. Bloom (Environmental Research, 2024)

Association between pre-diagnosis recreational physical activity and risk of breast cancer recurrence: the California Teachers Study - Dan Lin; Cheryl L. Thompson; Alaina Demalis; Rebecca Derbes; Laila Al-Shaar; Emma S. Spielfogel; Kathleen M. Sturgeon (Cancer Causes & Control, 2024)

Environmental evaluation of emerging bakery waste oil-derived sophorolipids production by performing a dynamic life cycle assessment - Yahui Miao; Xiaomeng Hu; Ming Ho To; Huaimin Wang; Zihao Qin; Jinhua Mou; Wei Yan; Guneet Kaur; Sophie L.K.W. Roelants; Carol Sze Ki Lin; Shauhrat S. Chopra (Sustainable Production and Consumption, 2024)

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

Enhanced detection of heavy metal ions using Ag nanoparticles and single-walled carbon nanotubes within Cu-based metal-organic frameworks - Gajanan A. Bodkhe; Mayuri S. More; Ahmad Umar; Ahmed A. Ibrahim; Subramanian Siva; Megha A. Deshmukh; Nikesh N. Ingle; Dhammajyot K. Gaikwad; Meng-Lin Tsai; Tibor Hianik; Myunghee Kim; Mahendra D. Shirsat (Journal of Environmental Chemical Engineering, 2024)

Biocontrol of strawberry Botrytis gray mold and prolong the fruit shelf-life by fumigant Trichoderma spp. - Q. S. Fan; H. J. Lin; Y. J. Hu; J. Jin; H. H. Yan; R. Q. Zhang (Biotechnology Letters, 2024)

RETRACTED: Applications of engineered biochar in remediation of heavy metal(loid)s pollution from wastewater: Current perspectives toward sustainable development goals - Thien-Khanh Tran; Loan Huynh; Hoang-Lam Nguyen; Minh-Ky Nguyen; Chitsan Lin; Tuan-Dung Hoang; Nguyen Tri Q. Hung; X. Hoan Nguyen; S. Woong Chang; D. Duc Nguyen (Science of The Total Environment, 2024)

Analytical methodology for determining the extent of pumped freshwater lenses in recharge-limited, circular islands - Barret L. Kurylyk; Yin-Fang Lin; S. Cristina Solórzano-Rivas; Adrian D. Werner (Advances in Water Resources, 2024)

Enhanced rock weathering increased soil phosphorus availability and altered root phosphorus‐acquisition strategies - Boyuan Bi; Guochen Li; Daniel S. Goll; Luxiang Lin; Hui Chen; Tongtong Xu; Qiong Chen; Chenlu Li; Xing Wang; Zhanqing Hao; Yunting Fang; Zuoqiang Yuan; et al. (Global Change Biology, 2024)
Enhanced rock weathering (ERW) has been proposed as a measure to enhance the carbon (C)‐sequestration potential and fertility of soils. The effects of this practice on the soil phosphorus (P) pools and the general mechanisms affecting microbial P cycling, as well as plant P uptake are not well understood. Here, the impact of ERW on soil P availability and microbial P cycling functional groups and root P‐acquisition traits were explored through a 2‐year wollastonite field addition experiment in a tropical rubber plantation. The results show that ERW significantly increased soil microbial carbon‐use efficiency and total P concentrations and indirectly increased soil P availability by enhancing organic P mobilization and mineralization of rhizosheath carboxylates and phosphatase, respectively. Also, ERW stimulated the activities of P‐solubilizing ( gcd , ppa and ppx ) and mineralizing enzymes ( phoADN and phnAPHLFXIM ), thus contributing to the inorganic P solubilization and organic P mineralization. Accompanying the increase in soil P availability, the P‐acquisition strategy of the rubber fine roots changed from do‐it‐yourself acquisition by roots to dependence on mycorrhizal collaboration and the release of root exudates. In addition, the direct effects of ERW on root P‐acquisition traits (such as root diameter, specific root length, and mycorrhizal colonization rate) may also be related to changes in the pattern of belowground carbon investments in plants. Our study provides a new insight that ERW increases carbon‐sequestration potential and P availability in tropical forests and profoundly affects belowground plant resource‐use strategies.

Enhanced removal of rare earth elements from aqueous media: exploring the potential of AM-3 and AM-4 titanosilicates - Joana C. Almeida; Cátia Sousa; Daniela S. Tavares; João Pinto; Bruno Henriques; Zhi Lin; João Rocha; Eduarda Pereira (Environmental Science and Pollution Research, 2024)
This study investigates the impact of three key variables on the performance of nanoporous AM-3 and layered AM-4 titanosilicates in removing nine REEs (Y, La, Ce, Pr, Nd, Eu, Gd, Tb, and Dy) from natural mineral water and identifies optimal operational conditions using Response Surface Methodology (RSM). The experimental conditions were determined by a Box-Behnken Design of 3 factors-3 levels (pH 4, 6, and 8; sorbent dose 20, 100, and 180 mg/L; and element concentration 1, 3, and 5 μmol/L). Three-dimensional response surfaces were used to assess the linear, quadratic, and interaction influences of each factor on the REEs’ removal percentage. The pH was the most significant factor in the removal process using AM-3, while the sorbent dose was more important for AM-4. The results highlighted the sorbents’ strong capacity for REE removal. The optimal operating conditions obtained by RSM were applied to aqueous solutions with salinity 10 (common in coastal and transitional systems) and 30 (average seawater salinity). The results showed that AM-3 has a strong potential for removing REEs in solutions with salinity 10 and 30, while AM-4 was less efficient due to competition between REEs and other ions present in the solution.

Adding plant metabolites improve plant phosphorus uptake by altering the rhizosphere bacterial community structure - Siji Wang; Shilong Duan; Timothy S. George; Gu Feng; Lin Zhang (Plant and Soil, 2024)

Clinical Investigation of Large Volume Subcutaneous Delivery up to 25 mL for Lean and Non-Lean Subjects - Xiangnan Dang; Han Shih; Rakesh Sharma; Daneen T. Angwin-Kaerner; Kathleen Lin; Shiven Kapur; Nagarajan R. Thyagarajapuram; Galen H. Shi; David S. Collins (Pharmaceutical Research, 2024)

FDA-approved disulfiram as a novel treatment for aggressive leukemia - Mawar Karsa; Lin Xiao; Emma Ronca; Angelika Bongers; Dayna Spurling; Ayu Karsa; Sandra Cantilena; Anna Mariana; Tim W. Failes; Greg M. Arndt; Laurence C. Cheung; Rishi S. Kotecha; et al. (Journal of Molecular Medicine, 2024)
Acute leukemia continues to be a major cause of death from disease worldwide and current chemotherapeutic agents are associated with significant morbidity in survivors. While better and safer treatments for acute leukemia are urgently needed, standard drug development pipelines are lengthy and drug repurposing therefore provides a promising approach. Our previous evaluation of FDA-approved drugs for their antileukemic activity identified disulfiram, used for the treatment of alcoholism, as a candidate hit compound. This study assessed the biological effects of disulfiram on leukemia cells and evaluated its potential as a treatment strategy. We found that disulfiram inhibits the viability of a diverse panel of acute lymphoblastic and myeloid leukemia cell lines ( n = 16) and patient-derived xenograft cells from patients with poor outcome and treatment-resistant disease ( n = 15). The drug induced oxidative stress and apoptosis in leukemia cells within hours of treatment and was able to potentiate the effects of daunorubicin, etoposide, topotecan, cytarabine, and mitoxantrone chemotherapy. Upon combining disulfiram with auranofin, a drug approved for the treatment of rheumatoid arthritis that was previously shown to exert antileukemic effects, strong and consistent synergy was observed across a diverse panel of acute leukemia cell lines, the mechanism of which was based on enhanced ROS induction. Acute leukemia cells were more sensitive to the cytotoxic activity of disulfiram than solid cancer cell lines and non-malignant cells. While disulfiram is currently under investigation in clinical trials for solid cancers, this study provides evidence for the potential of disulfiram for acute leukemia treatment. Key messages Disulfiram induces rapid apoptosis in leukemia cells by boosting oxidative stress. Disulfiram inhibits leukemia cell growth more potently than solid cancer cell growth. Disulfiram can enhance the antileukemic efficacy of chemotherapies. Disulfiram strongly synergises with auranofin in killing acute leukemia cells by ROS induction. We propose testing of disulfiram in clinical trial for patients with acute leukemia.

Dynamic efficiency evaluation of electric power and environmental treatment efficiency in China - Y. Li; Y. Chiu; T.-Y. Lin; S.-M. Wang; T.-H. Chang (International Journal of Environmental Science and Technology, 2024)

Effects of lianas on forest biogeochemistry during their lives and afterlives - Gbadamassi G. O. Dossa; Hong‐Lin Li; Bo Pan; Tial C. Ling; Douglas A. Schaefer; Mareike Roeder; Denis M. Njoroge; Juan Zuo; Liang Song; Bismark Ofosu‐Bamfo; Stefan A. Schnitzer; Rhett D. Harrison; et al. (Global Change Biology, 2024)
Climate change and other anthropogenic disturbances are increasing liana abundance and biomass in many tropical and subtropical forests. While the effects of living lianas on species diversity, ecosystem carbon, and nutrient dynamics are receiving increasing attention, the role of dead lianas in forest ecosystems has been little studied and is poorly understood. Trees and lianas coexist as the major woody components of forests worldwide, but they have very different ecological strategies, with lianas relying on trees for mechanical support. Consequently, trees and lianas have evolved highly divergent stem, leaf, and root traits. Here we show that this trait divergence is likely to persist after death, into the afterlives of these organs, leading to divergent effects on forest biogeochemistry. We introduce a conceptual framework combining horizontal, vertical, and time dimensions for the effects of liana proliferation and liana tissue decomposition on ecosystem carbon and nutrient cycling. We propose a series of empirical studies comparing traits between lianas and trees to answer questions concerning the influence of trait afterlives on the decomposability of liana and tree organs. Such studies will increase our understanding of the contribution of lianas to terrestrial biogeochemical cycling, and help predict the effects of their increasing abundance.

Advancing ecological assessment of the Arabian Gulf through eDNA metabarcoding: opportunities, prospects, and challenges - Thadickal V. Joydas; Seerangan Manokaran; Jayanath Gopi; Jayachandran P. Rajakumar; Lin Yu-Jia; Moritz Heinle; Mazen K. Nazal; Karuppasamy P. Manikandan; Maryam Qashqari; Sowmya P. Mohandas; Syed A. Hussain; Rommel H. Maneja; et al. (Frontiers in Marine Science, 2024)
The Arabian Gulf (hereafter ‘the Gulf’) is renowned for its unique ecological characteristics and distinct marine life. It offers a diverse range of ecosystems that have adapted to the impacts posed by natural stress and human activities. Regular biomonitoring and diversity assessments are necessary to document the health of the Gulf ecosystem and to implement appropriate measures for effective conservation and management. Recently, environmental DNA (eDNA), a total pool of DNA isolated from environmental samples, has emerged as a highly effective tool for ecological studies. This review explores the opportunities, prospects, and challenges associated with employing eDNA metabarcoding in the ecological assessment and biomonitoring of the Gulf. It provides an overview of the status of the Gulf ecosystem and discusses the potential applications of eDNA metabarcoding in assessing biodiversity, monitoring invasive species, and evaluating ecosystem health. Additionally, the investigation addresses the challenges inherent in implementing this technique, considering environmental complexities, methodological intricacies, and data interpretation. Overall, this review emphasizes the immense potential of eDNA metabarcoding in advancing ecological assessment in the Gulf and calls for further research and collaboration to harness its benefits in this unique marine ecosystem.

Relative leg-to-arm skeletal strength proportions in orangutans by species and sex - Alexandra E. Kralick; Babette S. Zemel; Clara Nolan; Phillip Lin; Matthew W. Tocheri (Journal of Human Evolution, 2024)

A novel packing-coupled stress-strain model for confined concrete - M.H. Lai; J.L. Lin; J. Cui; F.M. Ren; S. Kitipornchai; J.C.M. Ho (Engineering Structures, 2024)

Contrasting range changes of Bergenia (Saxifragaceae) species under future climate change in the Himalaya and Hengduan Mountains Region - Li Qiu; Qing-Li Fu; Hans Jacquemyn; Kevin S. Burgess; Jia-Jing Cheng; Zhi-Qiong Mo; Xiao-Dong Tang; Bo-Yun Yang; Shao-Lin Tan (Theoretical and Applied Climatology, 2024)

Characterization and evaluation of the morphological attributes of Ethiopian mustard (Brassica carinata A. Braun) landraces - Rahiel Hagos Abraha; Abdulwahab S. Shaibu; Jianli Liang; Jian Wu; Runmao Lin; Xiaowu Wang (Euphytica, 2024)
Ethiopian mustard ( Brassica carinata A. Braun) is one of the Brassica leafy vegetables and oilseed crops, which can withstand adverse environmental conditions. This study was conducted to characterize and evaluate the leaf attributes of 313 Ethiopian mustard accessions grown in the greenhouse and field in 2018/19 in Beijing, China. Data on 18 different leaf morphological attributes were collected based on the IBPGR for Brassica and Raphanus descriptor format and Fiji Image J. The collected data were subjected to descriptive statistics using JMP version 14 software. Results indicate that the majority of the accessions had serrated leaf margin, intermediate juvenile development, rounded apex leaf shape, absence of leaf pubescence, number of lobes > 5 and had intermediate number of leaves per plant with frequencies of 101, 213, 223, 244, 183 and 289, respectively. The accessions had also white midrib color, light green leaf color, purple petiole color, purple stem color and purple apex leaf color pigments with frequencies of 168, 165, 104, 113 and 122, respectively. Significant differences were observed among the accessions for leaf size attributes ( p < 0.001) indicating their potential as leafy vegetables. Furthermore, there were significant accession × environment effects for the laminal length, total leaf length, leaf area, leaf weight and petiole length. Notably, 71% of the accessions had an average of 81 days flowering time. The multivariate cluster and principal component analyses divided the 313 accessions into eight groups with distinctive information; consisting of 81, 37, 79, 38, 14, 11, 6 and 47 accessions. Thus, this study provides important information about Ethiopian mustard germplasms that is vital for further advancement and genetic improvement of the crop.

Review on fate, transport, toxicity and health risk of nanoparticles in natural ecosystems: Emerging challenges in the modern age and solutions toward a sustainable environment - Thien-Khanh Tran; Minh-Ky Nguyen; Chitsan Lin; Tuan-Dung Hoang; Thanh-Cong Nguyen; Aasif Mohmad Lone; Akhil Pradiprao Khedulkar; Mohamed S. Gaballah; Jagpreet Singh; W. Jin Chung; D. Duc Nguyen (Science of The Total Environment, 2024)

Ambient heat and diabetes hospitalizations: Does the timing of heat exposure matter? - Donghong Gao; Samantha Friedman; Akiko S. Hosler; Scott Sheridan; Wangjian Zhang; Fangqun Yu; Shao Lin (Science of The Total Environment, 2024)

A metallic phenolic network-enhanced bentonite for ammonical nitrogen removal from black-odorous water - Jialin Lin; Baihua Luo; Peng Wan; Jian Wang; Andrew S. Hursthouse; Si Li; Guocheng Zhu (Process Safety and Environmental Protection, 2024)

Vegetation−fire feedbacks increase subtropical wildfire risk in scrubland and reduce it in forests - P. Wei; B. Lamont; T. He; W. Xue; P.C. Wang; W. Song; R. Zhang; A.B. Keyhani; S. Zhao; W. Lu; F. Dong; R. Gao; et al. (Journal of Environmental Management, 2024)

Exploring the potential of zinc oxide nanoparticles against pathogenic multi-drug resistance Staphylococcus aureus from ready-to-eat meat and its proposed mechanism - Mabrouk Sobhy; Sameh S. Ali; Maha A. Khalil; Xiaochen Chen; Haiying Cui; Lin Lin; Shimaa El-Sapagh (Food Control, 2024)

Industrial waste-based adsorbents as a new trend for removal of water-borne emerging contaminants - Harsha S Rangappa; Indika Herath; Chuxia Lin; Subrahmanyam Ch (Environmental Pollution, 2024)

Maternal serum neonicotinoids during early-mid pregnancy and congenital heart diseases in offspring: An exploratory study - Yanji Qu; Adela Jing Li; Xiaoqing Liu; Shao Lin; Michael S. Bloom; Ximeng Wang; Xiaohong Li; Hui Wang; Fengzhen Han; Xiangmin Gao; Yong Wu; Kaiqin Huang; et al. (Environmental Pollution, 2024)

Synthesis of nano-MgO hybrid SDB hydrophobic catalyst carriers and its adsorption behavior of Fe3+ - Y. Fan; H. R. Peng; C. Li; K. Fu; X. Y. Ren; H. J. Yang; S. D. Lin; C. L. Liu (International Journal of Environmental Science and Technology, 2024)

Global change progressively increases foliar nitrogen–phosphorus ratios in China's subtropical forests - Yuan Lai; Songbo Tang; Hans Lambers; Peter Hietz; Wenguang Tang; Frank S. Gilliam; Xiankai Lu; Xianzhen Luo; Yutong Lin; Shu Wang; Feiyan Zeng; Qi Wang; et al. (Global Change Biology, 2024)
Globally increased nitrogen (N) to phosphorus (P) ratios (N/P) affect the structure and functioning of terrestrial ecosystems, but few studies have addressed the variation of foliar N/P over time in subtropical forests. Foliar N/P indicates N versus P limitation in terrestrial ecosystems. Quantifying long‐term dynamics of foliar N/P and their potential drivers is crucial for predicting nutrient status and functioning in forest ecosystems under global change. We detected temporal trends of foliar N/P, quantitatively estimated their potential drivers and their interaction between plant types (evergreen vs. deciduous and trees vs. shrubs), using 1811 herbarium specimens of 12 widely distributed species collected during 1920–2010 across China's subtropical forests. We found significant decreases in foliar P concentrations (23.1%) and increases in foliar N/P (21.2%). Foliar N/P increased more in evergreen species (22.9%) than in deciduous species (16.9%). Changes in atmospheric CO 2 concentrations (), atmospheric N deposition and mean annual temperature (MAT) dominantly contributed to the increased foliar N/P of evergreen species, while , MAT, and vapor pressure deficit, to that of deciduous species. Under future Shared Socioeconomic Pathway (SSP) scenarios, increasing MAT and would continuously increase more foliar N/P in deciduous species than in evergreen species, with more 12.9%, 17.7%, and 19.4% versus 6.1%, 7.9%, and 8.9% of magnitudes under the scenarios of SSP1‐2.6, SSP3‐7.0, and SSP5‐8.5, respectively. The results suggest that global change has intensified and will progressively aggravate N–P imbalance, further altering community composition and ecosystem functioning of subtropical forests.

Review of risk assessment for navigational safety and supported decisions in arctic waters - X. Yang; Z.Y. Lin; W.J. Zhang; S. Xu; M.Y. Zhang; Z.D. Wu; B. Han (Ocean & Coastal Management, 2024)

Efficacy and Safety of a Novel Formulation Liquid Botulinum Toxin, RelabotulinumtoxinA, When used for Combination Treatment of Glabellar and Lateral Canthal Lines - Vince Bertucci; Joel Schlessinger; John Joseph; Ava Shamban; Z. Paul Lorenc; Robert Weiss; Leslie Baumann; Mark S. Nestor; Heidi B. Prather; Derek Jones; Alexander S. Donath; Rebecca Kazin; et al. (Toxicon, 2024)

Topography-driven differences in soil N transformation constrain N availability in karst ecosystems - Dongni Wen; Lin Yang; Kang Ni; Xingliang Xu; Longfei Yu; Ahmed S. Elrys; Lei Meng; Jinxing Zhou; Tongbin Zhu; Christoph Müller (Science of The Total Environment, 2024)

Exploring the therapeutic potential of layered double hydroxides and transition metal dichalcogenides through the convergence of rheumatology and nanotechnology using generative adversarial network - Suxian Lin; Weiwei Chen; Mohammed S. Alqahtani; Dalia H. Elkamchouchi; Yisu Ge; Yanjie Lu; Guodao Zhang; Mudan Wang (Environmental Research, 2024)

Biogeochemical behavior of selenium in soil-air-water environment and its effects on human health - Z. N. Xu; Z. Q. Lin; G. S. Zhao; Y. B. Guo (International Journal of Environmental Science and Technology, 2024)

Population genomics of the muskox' resilience in the near absence of genetic variation - Patrícia Pečnerová; Edana Lord; Genís Garcia‐Erill; Kristian Hanghøj; Malthe Sebro Rasmussen; Jonas Meisner; Xiaodong Liu; Tom van der Valk; Cindy G. Santander; Liam Quinn; Long Lin; Shanlin Liu; et al. (Molecular Ecology, 2024)
Genomic studies of species threatened by extinction are providing crucial information about evolutionary mechanisms and genetic consequences of population declines and bottlenecks. However, to understand how species avoid the extinction vortex, insights can be drawn by studying species that thrive despite past declines. Here, we studied the population genomics of the muskox ( Ovibos moschatus ), an Ice Age relict that was at the brink of extinction for thousands of years at the end of the Pleistocene yet appears to be thriving today. We analysed 108 whole genomes, including present‐day individuals representing the current native range of both muskox subspecies, the white‐faced and the barren‐ground muskox ( O. moschatus wardi and O. moschatus moschatus ) and a ~21,000‐year‐old ancient individual from Siberia. We found that the muskox' demographic history was profoundly shaped by past climate changes and post‐glacial re‐colonizations. In particular, the white‐faced muskox has the lowest genome‐wide heterozygosity recorded in an ungulate. Yet, there is no evidence of inbreeding depression in native muskox populations. We hypothesize that this can be explained by the effect of long‐term gradual population declines that allowed for purging of strongly deleterious mutations. This study provides insights into how species with a history of population bottlenecks, small population sizes and low genetic diversity survive against all odds.

The relationship between greenspace exposure and telomere length in the National Health and Nutrition Examination Survey - S. Scott Ogletree; Jing-Huei Huang; David Reif; Lin Yang; Christopher Dunstan; Nnamdi Osakwe; Jae In Oh; J. Aaron Hipp (Science of The Total Environment, 2023)

A comprehensive review of micro- and nano-plastics in the atmosphere: Occurrence, fate, toxicity, and strategies for risk reduction - Van-Giang Le; Minh-Ky Nguyen; Hoang-Lam Nguyen; Chitsan Lin; Mohammed Hadi; Nguyen Tri Quang Hung; Hong-Giang Hoang; Khoi Nghia Nguyen; Huu-Tuan Tran; Deyi Hou; Tao Zhang; Nanthi S. Bolan (Science of The Total Environment, 2023)

A review on sterilization methods of environmental decontamination to prevent the coronavirus SARS-CoV-2 (COVID-19 virus): A new challenge towards eco-friendly solutions - Nguyen Trung Hiep; Minh-Ky Nguyen; Huynh Tan Nhut; Nguyen Tri Quang Hung; Nguyen Cong Manh; Chitsan Lin; S. Woong Chang; Myoung Jin Um; D. Duc Nguyen (Science of The Total Environment, 2023)

Sustainability assessment and pathways for U.S. domestic paper recycling - Enze Jin; Stijn van Ewijk; Koichi S. Kanaoka; Yohannes A. Alamerew; Hui Lin; Zhi Cao; Banafsheh Jabarivelisdeh; Kornel F. Ehmann; Marian R. Chertow; Eric Masanet (Resources, Conservation and Recycling, 2023)

The Pacific water flow branches in the eastern Chukchi Sea - Robert S. Pickart; Peigen Lin; Frank Bahr; Leah T. McRaven; Jie Huang; Astrid Pacini; Kevin R. Arrigo; Carin J. Ashjian; Catherine Berchok; Mark F. Baumgartner; Kyoung-Ho Cho; Lee W. Cooper; et al. (Progress in Oceanography, 2023)

Intrinsic and extrinsic factors influencing Populus water use: A literature review - Elizabeth R. Rogers; Ronald S. Zalesny; Chung-Ho Lin; Ryan A. Vinhal (Journal of Environmental Management, 2023)

Intercomparison between sentinel-1, sentinel-2, and landsat-8 on reservoir water level estimation - Manikandan Sathianarayanan; Ajay Saraswat; A. S. Mohammed Abdul Athick; Hung-Ming Lin (Sustainable Water Resources Management, 2023)

Nuts and berries from agroforestry systems in temperate regions can form the foundation for a healthier human diet and improved outcomes from diet-related diseases - Sarah Taylor Lovell; Kiruba Krishnaswamy; Chung-Ho Lin; Nicholas Meier; Ronald S. Revord; Andrew L. Thomas (Agroforestry Systems, 2023)
Agroforestry is a specific type of agroecosystem that includes trees and shrubs with the potential to yield nutrient-rich products that contribute to human health. This paper reviews the literature on the human health benefits of tree nut and berry species commonly associated with agroforestry systems of the United States, considering their potential for preventing certain diet-related diseases. Emphasis is placed on those diseases that are most closely associated with poor outcomes from COVID-19, as they are indicators of confounding health prognoses. Results indicate that tree nuts reduce the risk of coronary heart disease, and walnuts ( Juglans species) are particularly effective because of their unique fatty acid profile. Berries that are grown on shrubs have the potential to contribute to mitigation of hypertension, prevention of Type II diabetes, and reduced risk of cardiovascular disease. To optimize human health benefits, plant breeding programs can focus on the traits that enhance the naturally-occurring phytochemicals, through biofortification. Value-added processing techniques should be selected and employed to preserve the phytonutrients, so they are maintained through the point of consumption. Agroforestry systems can offer valuable human health outcomes for common diet-related diseases, in addition to providing many environmental benefits, particularly if they are purposefully designed with that goal in mind. The food system policies in the U.S. might be reoriented to prioritize these food production systems based on the health benefits.

Occurrence, fate, and potential risk of pharmaceutical pollutants in agriculture: Challenges and environmentally friendly solutions - Minh-Ky Nguyen; Chitsan Lin; Hoang-Lam Nguyen; Nguyen Tri Quang Hung; D. Duong La; X. Hoan Nguyen; S. Woong Chang; W. Jin Chung; D. Duc Nguyen (Science of The Total Environment, 2023)

Challenging Dietary Research Measures, Concepts, and Definitions to Promote Greater Inclusivity of Immigrant Experiences: Considerations and Practical Recommendations - Shahmir H. Ali; Nelson F. Lin; Stella S. Yi (Journal of the Academy of Nutrition and Dietetics, 2023)

Bibliometric analysis of publications on biodegradation of plastics: Explosively emerging research over 70 years - Shan-Shan Yang; Wei-Min Wu; Ji-Wei Pang; Lei He; Meng-Qi Ding; Mei-Xi Li; Yi-Lin Zhao; Han-Jun Sun; De-Feng Xing; Nan-Qi Ren; Jun Yang; Craig S. Criddle; et al. (Journal of Cleaner Production, 2023)

Ecotoxicity of micro- and nanoplastics on aquatic algae: Facts, challenges, and future opportunities - Minh-Ky Nguyen; Chitsan Lin; Hoang-Lam Nguyen; Van-Giang Le; S. Haddout; Myoung-Jin Um; Soon W. Chang; D. Duc Nguyen (Journal of Environmental Management, 2023)

A state-of-the-art analysis of pharmacological delivery and artificial intelligence techniques for inner ear disease treatment - Wanqing Li; Nan Zheng; Qiang Zhou; Mohammed S. Alqahtani; Dalia H. Elkamchouchi; Huajun Zhao; Sen Lin (Environmental Research, 2023)

Nepalese indoor cookstove smoke extracts alter human airway epithelial gene expression, DNA methylation and hydroxymethylation - Poojitha Rajasekar; Robert J. Hall; K.C. Binaya; Parth S. Mahapatra; Siva P. Puppala; Dhruma Thakker; Julia L. MacIsaac; David Lin; Michael Kobor; Charlotte E. Bolton; Ian Sayers; Ian P. Hall; et al. (Environmental Pollution, 2023)

A review from material functionalization to process feasibility on advanced mixed matrix membranes for gas separations - Zhihong Lin; Ziyi Yuan; Zhongde Dai; Lu Shao; Moris S. Eisen; Xuezhong He (Chemical Engineering Journal, 2023)

Contrasting range changes of terrestrial orchids under future climate change in China - Li Qiu; Hans Jacquemyn; Kevin S. Burgess; Li-Guo Zhang; Ya-Dong Zhou; Bo-Yun Yang; Shao-Lin Tan (Science of The Total Environment, 2023)

Did Early Pleistocene hominins control hammer strike angles when making stone tools? - Li Li; Jonathan S. Reeves; Sam C. Lin; David R. Braun; Shannon P. McPherron (Journal of Human Evolution, 2023)

Promotion of the catalytic polymerization of hydroquinone towards humic-like substances by graphitic carbon nitride - M.M.M. Ahmed; Yu-Ting Liu; S. Venkatesan; Min Chien Wu; Howida M. Nail; Der-Lii M. Tzou; Ming-Chang Lin; Kai-Yue Chen; Yu-min Tzou (Journal of Environmental Chemical Engineering, 2023)

Association of greenness surrounding school with aggression among adolescents: A multi-site study in China - Yi Zhang; Yanqi Li; Xinyi Xie; Xiaoyi Lin; Mengxin Huang; Huihang Fu; Weiju Zhou; John S. Ji; Yizhen Yu; Jie Tang (Environmental Research, 2023)

Cloud condensation nuclei activation properties of Mediterranean pollen types considering organic chemical composition and surface tension effects - A. Casans; F. Rejano; J. Maldonado-Valderrama; J.A. Casquero-Vera; S. Ruiz-Peñuela; B.L. van Drooge; H. Lyamani; A. Cazorla; E. Andrews; Jack J. Lin; F. Mirza-Montoro; D. Pérez-Ramírez; et al. (Atmospheric Environment, 2023)

Pandemic gardening: A narrative review, vignettes and implications for future research - Jonathan Kingsley; Kelly Donati; Jill Litt; Naomi Shimpo; Chris Blythe; Jan Vávra; Silvio Caputo; Paul Milbourne; Lucy O. Diekmann; Nick Rose; Runrid Fox-Kämper; Agnes van den Berg; et al. (Urban Forestry & Urban Greening, 2023)

Genetic characterisation of Felis catus papillomavirus type 7, a rare infection of cats that may be associated with skin cancer - John S. Munday; Kristene Gedye; Matthew A. Knox; Hayley Pfeffer; Xiaoxiao Lin (Veterinary Microbiology, 2023)

Enzymatically hydrolyzed fluorescence-based chemical probe enables in situ mapping of chitinase activity in the rhizosphere - Elias K. Zegeye; Vivian S. Lin; Jamie R. Nuñez; Nick A. Sconzo; Samuel O. Purvine; Aaron T. Wright; James J. Moran (Soil Biology and Biochemistry, 2023)

Succession of biochar addition for soil amendment and contaminants remediation during co-composting: A state of art review - Huu-Tuan Tran; Nanthi S. Bolan; Chitsan Lin; Quach An Binh; Minh-Ky Nguyen; The Anh Luu; Van-Giang Le; Cham Q. Pham; Hong-Giang Hoang; Dai-Viet N. Vo (Journal of Environmental Management, 2023)

The impact of education level on residents’ carbon consumption in China - Y.-N. Lin; Y.-H. Chiu; T.-H. Chang; T.-Y. Lin; S.-Y. Chiu (International Journal of Environmental Science and Technology, 2023)

Physiological responses and antioxidant properties of spiny coriander (Eryngium foetidum L.) under shading and nitrogen fertilization - Renê A. S. Campos; Santino Seabra Júnior; Gabriela G. Gonçalves; Franciele da S. Ponce; Ana Claudia Macedo; Chau Ming Lin; Giuseppina P. P. Lima (Acta Physiologiae Plantarum, 2023)

Temporal Prediction of Coastal Water Quality Based on Environmental Factors with Machine Learning - Junan Lin; Qianqian Liu; Yang Song; Jiting Liu; Yixue Yin; Nathan S. Hall (Journal of Marine Science and Engineering, 2023)
The accurate forecast of algal blooms can provide helpful information for water resource management. However, the complex relationship between environmental variables and blooms makes the forecast challenging. In this study, we build a pipeline incorporating four commonly used machine learning models, Support Vector Regression (SVR), Random Forest Regression (RFR), Wavelet Analysis (WA)-Back Propagation Neural Network (BPNN) and WA-Long Short-Term Memory (LSTM), to predict chlorophyll-a in coastal waters. Two areas with distinct environmental features, the Neuse River Estuary, NC, USA—where machine learning models are applied for short-term algal bloom forecast at single stations for the first time—and the Scripps Pier, CA, USA, are selected. Applying the pipeline, we can easily switch from the NRE forecast to the Scripps Pier forecast with minimum model tuning. The pipeline successfully predicts the occurrence of algal blooms in both regions, with more robustness using WA-LSTM and WA-BPNN than SVR and RFR. The pipeline allows us to find the best results by trying different numbers of neuron hidden layers. The pipeline is easily adaptable to other coastal areas. Experience with the two study regions demonstrated that enrichment of the dataset by including dominant physical processes is necessary to improve chlorophyll prediction when applying it to other aquatic systems.

Emerging polycyclic aromatic hydrocarbon (PAH) and trace metal leachability from reclaimed asphalt pavement (RAP) - Ashley M. Lin; Alina S. Timshina; Jordan K. Magnuson; John A. Bowden; Timothy G. Townsend (Chemosphere, 2023)

Formation and circulation of newly ventilated winter water in the western Beaufort Sea - Peigen Lin; Robert S. Pickart; Thomas J. Weingartner; Harper L. Simmons; Motoyo Itoh; Takashi Kikuchi (Progress in Oceanography, 2023)

A monitoring system for CO2-EOR and storage based on reactive transport simulation of CO2 migration in groundwater - L. Li; Y. Wu; Q. Lin; Q. Wen; S. Chong (International Journal of Environmental Science and Technology, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

Simulation of CO2 capture from natural gas by cyclic pressure swing adsorption process using activated carbon - Haitao Lin; Jianbo Lu; Azher M. Abed; Kaushik Nag; Mohamed Fayed; Ahmed Deifalla; Abdullah S. Bin Mahfouz; Ahmed M. Galal (Chemosphere, 2023)

Geological controls on the distribution of gas hydrates in the shallow parts of the gas hydrate stability zone – constraints from seafloor drilling off Taiwan - G. Bohrmann; C. Berndt; S. Lin; T.-H. Tu; A.T. Lin; H.-H. Hsu; M.-C. Lai; W.-C. Chi; C. Deusner; J. Elger; K. Wallmann; T. Freudenthal; et al. (Marine and Petroleum Geology, 2023)

Cost-effective and accurate monitoring of flowering across multiple tropical tree species over two years with a time series of high-resolution drone imagery and deep learning - Calvin Ka Fai Lee; Guangqin Song; Helene C. Muller-Landau; Shengbiao Wu; S. Joseph Wright; K.C. Cushman; Raquel Fernandes Araujo; Stephanie Bohlman; Yingyi Zhao; Ziyu Lin; Zounachuan Sun; Peter Chuen Yan Cheng; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Corrigendum to “Tree species diversity enhances plant-soil interactions in a temperate forest in northeast China” [For. Ecol. Manage. (2021) 119160] - Anvar Sanaei; Zuoqiang Yuan; Arshad Ali; Michel Loreau; Akira S. Mori; Peter B. Reich; Tommaso Jucker; Fei Lin; Ji Ye; Shuai Fang; Zhanqing Hao; Xugao Wang (Forest Ecology and Management, 2023)

Up in the air: Polyfluoroalkyl phosphate esters (PAPs) in airborne dust captured by air conditioning (AC) filters - Alina S. Timshina; William J. Sobczak; Emily K. Griffin; Ashley M. Lin; Timothy G. Townsend; John A. Bowden (Chemosphere, 2023)

Drought-vulnerable vegetation increases exposure of disadvantaged populations to heatwaves under global warming: A case study from Los Angeles - Chunyu Dong; Yu Yan; Jie Guo; Kairong Lin; Xiaohong Chen; Gregory S. Okin; Thomas W. Gillespie; Jake Dialesandro; Glen M. MacDonald (Sustainable Cities and Society, 2023)

Efficient adsorption and photocatalytic degradation of water emerging contaminants through nanoarchitectonics of pore sizes and optical properties of zirconium-based MOFs - Jia-Xuan Tan; Zih-Yu Chen; Celine H. Chen; Ming-Feng Hsieh; Angela Yu-Chen Lin; Season S. Chen; Kevin C.-W. Wu (Journal of Hazardous Materials, 2023)

Can urban polycentricity improve air quality? Evidence from Chinese cities - Will W. Qiang; Haowen Luo; Yuxuan Xiao; David W.H. Wong; Alex S. Shi; Ziwei Lin; Bo Huang; Harry F. Lee (Journal of Cleaner Production, 2023)

Evaluating the removal and impacts of combined tetracycline, oxytetracycline, sulfadiazine, and norfloxacin during swine manure storage process at ambient temperatures - Mohamed S. Gaballah; Mostafa Sobhi; Jianbin Guo; Mperejekumana Philbert; Lin Min; Yonghui Zheng; Mohamed A. Ghorab; Renjie Dong (Journal of Environmental Chemical Engineering, 2023)

BasinMaker 3.0: A GIS toolbox for distributed watershed delineation of complex lake-river routing networks - Ming Han; Hongren Shen; Bryan A. Tolson; James R. Craig; Juliane Mai; Simon G.M. Lin; Nandita B. Basu; Frezer S. Awol (Environmental Modelling & Software, 2023)

A Letter to Your Care Providers: Implementation and Analysis of a Letter-based Advance Care Planning Initiative for Gynecologic Oncology Patients - Catherine N. Zivanov; Anne Coogan; Robin R. Lane; Sara G. Lin; Sarah C. Reed; Marc A. Robinson; Mohana Karlekar; Lauren S. Prescott; Alaina J. Brown (Journal of Cancer Education, 2023)

Macroalgae exhibit diverse responses to human disturbances on coral reefs - Sara E. Cannon; Simon D. Donner; Angela Liu; Pedro C. González Espinosa; Andrew H. Baird; Julia K. Baum; Andrew G. Bauman; Maria Beger; Cassandra E. Benkwitt; Matthew J. Birt; Yannick Chancerelle; Joshua E. Cinner; et al. (Global Change Biology, 2023)
Scientists and managers rely on indicator taxa such as coral and macroalgal cover to evaluate the effects of human disturbance on coral reefs, often assuming a universally positive relationship between local human disturbance and macroalgae. Despite evidence that macroalgae respond to local stressors in diverse ways, there have been few efforts to evaluate relationships between specific macroalgae taxa and local human‐driven disturbance. Using genus‐level monitoring data from 1205 sites in the Indian and Pacific Oceans, we assess whether macroalgae percent cover correlates with local human disturbance while accounting for factors that could obscure or confound relationships. Assessing macroalgae at genus level revealed that no genera were positively correlated with all human disturbance metrics. Instead, we found relationships between the division or genera of algae and specific human disturbances that were not detectable when pooling taxa into a single functional category, which is common to many analyses. The convention to use percent cover of macroalgae as an indication of local human disturbance therefore likely obscures signatures of local anthropogenic threats to reefs. Our limited understanding of relationships between human disturbance, macroalgae taxa, and their responses to human disturbances impedes the ability to diagnose and respond appropriately to these threats.

Interactions between marine megafauna and plastic pollution in Southeast Asia - Lucy C.M. Omeyer; Emily M. Duncan; Neil Angelo S. Abreo; Jo Marie V. Acebes; Lea A. AngSinco-Jimenez; Sabiqah T. Anuar; Lemnuel V. Aragones; Gonzalo Araujo; Luis R. Carrasco; Marcus A.H. Chua; Muhammad R. Cordova; Lantun P. Dewanti; et al. (Science of The Total Environment, 2023)

Whole bone subcutaneous transplantation as a strategy to study precisely the bone marrow niche - Caroline C. Picoli; Patrícia Rocha Martins; Xiao Lin Casey Wong; Thamires Righi; Pedro P. G. Guimarães; Mauro C. X. Pinto; Jaime H. Amorim; Vasco A. C. Azevedo; Silma Regina Pereira; Alexandre Kanashiro; Fabio Cardoso Cruz; Rodrigo R. Resende; et al. (Stem Cell Reviews and Reports, 2023)

Plant and fungal species interactions differ between aboveground and belowground habitats in mountain forests of eastern China - Teng Yang; Leho Tedersoo; Pamela S. Soltis; Douglas E. Soltis; Miao Sun; Yuying Ma; Yingying Ni; Xu Liu; Xiao Fu; Yu Shi; Han-Yang Lin; Yun-Peng Zhao; et al. (Science China Life Sciences, 2023)

Late Tonian (ca. 785 Ma) subduction-related mafic-ultramafic cumulates in the West Cathaysia terrane, South China - Lijun Wang; Kexin Zhang; Shoufa Lin; Jean H. Bédard; Gabriel S. Santos; Weihong He; Changqing Yin; Wenjiao Xiao (Precambrian Research, 2023)

Vanadium isotope fractionation of alkali basalts during mantle melting - Zhenwu Chen; Xin Ding; Ekaterina S. Kiseeva; Xiaobao Lin; Jian Huang; Fang Huang (Lithos, 2023)

The diversity of mycorrhiza‐associated fungi and trees shapes subtropical mountain forest ecosystem functioning - Ya‐Huang Luo; Liang‐Liang Ma; Sebastian Seibold; Marc W. Cadotte; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Wei Zheng; Jia‐Yun Zou; Zhi‐Fa Chen; De‐Tuan Liu; Guang‐Fu Zhu; et al. (Journal of Biogeography, 2023)
Aim Mycorrhiza play key roles for ecosystem structure and functioning in forests. However, how different mycorrhizal types influence mountain forest biodiversity–ecosystem functioning (BEF) relationships are largely unknown. We evaluate how the diversity of distinct mycorrhiza‐associated fungi and trees shapes forest carbon storage along elevational gradients. Location Gaoligong Mountains within Hengduan Mountains, Southwest China. Taxon Seed plants and mycorrhizal fungi. Methods We used the data from 31 subtropical forest plots along elevational gradients on two aspects (east and west) of the mountain. We quantified species richness of trees and symbiotic fungi and assigned both to their mycorrhizal type (arbuscular mycorrhiza [AM], ectomycorrhiza [EcM] and ericoid mycorrhiza [ErM]). We then examined the diversity effects of mycorrhiza‐associated fungi and trees on above‐ground carbon stored in trees and organic carbon stored in soils. Results Species richness was highest for AM trees (79.5%), followed by ErM trees (13.4%) and then EcM trees (7.1%). Species richness of AM‐associated trees and fungi decreased with increasing elevation, while ErM‐associated trees and fungi showed an opposite trend. EcM‐associated diversity followed a hump‐shaped relationship with elevation. Positive relationships between diversity and above‐ground carbon were detected in all three mycorrhizal associations, but despite low species number, canopy‐dominating EcM trees comprised 64.4% of the amount of above‐ground carbon. Furthermore, community‐weighted means of height exhibited positive correlations with forest above‐ground carbon, indicating that positive selection effects occur. Soil organic carbon was positively related to EcM‐associated fungi diversity, above‐ground carbon mass and soil nitrogen availability, with the latter having strongest direct effects. Main Conclusions The distributions of forest biodiversity and carbon storage can be modulated by distinct mycorrhizal fungi and trees. Moreover, future global changes (e.g. climate warming, intensifying nitrogen deposition) could alter the mycorrhizal‐mediated BEF relationships in mountain forests.

Centenarian clocks: epigenetic clocks for validating claims of exceptional longevity - Eric Dec; James Clement; Kaiyang Cheng; George M. Church; Michael B. Fossel; David H. Rehkopf; Luis Rosero-Bixby; Michael S. Kobor; David TS. Lin; Ake T. Lu; Zhe Fei; Wei Guo; et al. (GeroScience, 2023)
Claims surrounding exceptional longevity are sometimes disputed or dismissed for lack of credible evidence. Here, we present three DNA methylation-based age estimators (epigenetic clocks) for verifying age claims of centenarians. The three centenarian clocks were developed based on n = 7039 blood and saliva samples from individuals older than 40, including n = 184 samples from centenarians, 122 samples from semi-supercentenarians (aged 105 +), and 25 samples from supercentenarians (aged 110 +). The oldest individual was 115 years old. Our most accurate centenarian clock resulted from applying a neural network model to a training set composed of individuals older than 40. An epigenome-wide association study of age in different age groups revealed that age effects in young individuals (age < 40) are correlated ( r = 0.55) with age effects in old individuals (age > 90). We present a chromatin state analysis of age effects in centenarians. The centenarian clocks are expected to be useful for validating claims surrounding exceptional old age.

Associations of per- and polyfluoroalkyl substances and their alternatives with bone mineral density levels and osteoporosis prevalence: A community-based population study in Guangzhou, Southern China - Shujun Fan; Yan Wu; Michael S. Bloom; Jiayun Lv; Li Chen; Weiping Wang; Zhi Li; Qinqin Jiang; Li Bu; Jie Shi; Tongxing Shi; Xiaowen Zeng; et al. (Science of The Total Environment, 2023)

Thermomechanically micronized sugar beet pulp: Emulsification performance and the contribution of soluble elements and insoluble fibrous particles - Jiawei Lin; Zhong-Sheng Tang; Charles S. Brennan; Jayani Chandrapala; Wenhong Gao; Zhong Han; Xin-An Zeng (Food Research International, 2023)

A systematic evidence map for the evaluation of noncancer health effects and exposures to polychlorinated biphenyl mixtures - Laura M. Carlson; Krista Christensen; Sharon K. Sagiv; Pradeep Rajan; Carolyn R. Klocke; Pamela J. Lein; Evan Coffman; Rachel M. Shaffer; Erin E. Yost; Xabier Arzuaga; Pam Factor-Litvak; Alexander Sergeev; et al. (Environmental Research, 2023)

DOK7 Promotes NMJ Regeneration After Nerve Injury - Ethan D. Kosco; Hongyang Jing; Peng Chen; Wen-Cheng Xiong; Ivy S. Samuels; Lin Mei (Molecular Neurobiology, 2023)

Pyrolysis and Gasification Characteristics of Galdieria sulphuraria Microalgae - Fateme Banihashemi; Amr F. M. Ibrahim; Shuguang Deng; Jerry Y. S. Lin (BioEnergy Research, 2023)

Soil organic carbon, aggregation and fungi community after 44 years of no-till and cropping systems in the Central Great Plains, USA - James S. Lin; Marcos V. M. Sarto; Tiffany L. Carter; Dallas E. Peterson; Colleen Gura; Laura Mino; Megan Rohrs; Hallie Lucas; Jamie Clark; Charles W. Rice (Archives of Microbiology, 2023)

Establishing the Safe Space via Physiologically Based Biopharmaceutics Modeling. Case Study: Fevipiprant/QAW039 - Alexandros Kourentas; Monika Gajewska; Wen Lin; Sundeep S. Dhareshwar; Caroline Steib-Lauer; Swarupa Kulkarni; Stefan Hirsch; Tycho Heimbach; Martin Mueller-Zsigmondy (The AAPS Journal, 2023)

Deep eutectic solvents in the transformation of biomass into biofuels and fine chemicals: a review - Kassian T. T. Amesho; Yuan-Chung Lin; S. Venkata Mohan; Subham Halder; Vinoth Kumar Ponnusamy; Syu-Ruei Jhang (Environmental Chemistry Letters, 2023)

Constant-temperature predictions underestimate growth of a fungal amphibian pathogen under individual host thermal profiles - Sasha E. Greenspan; Elizabeth A. Roznik; Lexie Edwards; Richard Duffy; Lee Berger; Deborah S. Bower; David A. Pike; Lin Schwarzkopf; Ross A. Alford (Journal of Thermal Biology, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

Valorization of nano-based lignocellulosic derivatives to procure commercially significant value-added products for biomedical applications - Vickram AS; Gopalakrishnan Kumar; Nibedita Dey; Rohini Karunakaran; Anbarasu K; Anil Kumar Patel; Thanigaivel S; Gangadhar Andaluri; Yuan-Chung Lin; Deena Santhana Raj; Vinoth Kumar Ponnusamy (Environmental Research, 2023)

Triggering of ST-elevation myocardial infarction by ultrafine particles in New York: Changes following Tier 3 vehicle introduction - Catherine S. Yount; Mark J. Utell; Philip K. Hopke; Sally W. Thurston; Shao Lin; Frederick S. Ling; Yunle Chen; David Chalupa; Xinlei Deng; David Q. Rich (Environmental Research, 2023)

The role of copper crystallization and segregation toward enhanced methanol synthesis via CO2 hydrogenation over CuZrO2 catalysts: A combined experimental and computational study - Francielle C.F. Marcos; Raphael S. Alvim; Lili Lin; Luis E. Betancourt; Davi D. Petrolini; Sanjaya D. Senanayake; Rita M.B. Alves; José M. Assaf; Jose A. Rodriguez; Reinaldo Giudici; Elisabete M. Assaf (Chemical Engineering Journal, 2023)

Elastoplastic Modelling of Porous Limestones with Porosity Dependency - B. Han; Q. M. Gong; X. L. Du; Y. Gao; W. Q. Shen; S. Lin (Rock Mechanics and Rock Engineering, 2022)

Exploring the secrets of hyphosphere of arbuscular mycorrhizal fungi: processes and ecological functions - Fei Wang; Lin Zhang; Jiachao Zhou; Zed Rengel; Timothy S. George; Gu Feng (Plant and Soil, 2022)

Recent Developments in Additive-Manufactured Intermetallic Compounds for Bio-Implant Applications - Po-Yuan Yeh; Jacob C. Huang; Jason S. C. Jang; Cheng-Tang Pan; Chung-Hwan Chen; Che-Hsin Lin (Journal of Medical and Biological Engineering, 2022)
Purpose This paper reviews the recent developments of two newly developed intermetallic compounds (IMCs) of metallic glasses (MGs) and high-entropy alloys (HEAs) as potential implantable biomaterials. Methods The paper commences by summarizing the fundamental properties of recently developed MGs and high-entropy alloys (HEAs). A systematic review is presented of the recent literature about the use of AM technology in fabricating MG and HEA components for biological implant applications. Results The high strength, low Young’s modulus, and excellent corrosion resistance make these IMCs good candidates as bio-implantable materials. Recent studies have shown that additive manufacturing (AM) techniques provide an advantageous route for the preparation of glassy metallic components due to their intrinsically rapid cooling rates and ability to fabricate parts with virtually no size or complexity constraints. A practical example is conducted by AM producing a porous gradient Ti-based MG spinal cage. The produced MG powders and the in vivo test results on an 18 M-old Lanyu pig confirm the feasibility of the AM technique for producing implantable IMC-based prosthesis. Conclusion The non-crystalline structure of MGs alloy and the random crystalline composition of HEAs provide unique material properties that will substantially impact the development of future implantable prostheses.

GATA4 and estrogen receptor alpha bind at SNPs rs9921222 and rs10794639 to regulate AXIN1 expression in osteoblasts - Sarocha Suthon; Rachel S. Perkins; Jianjian Lin; John R. Crockarell; Gustavo A. Miranda-Carboni; Susan A. Krum (Human Genetics, 2022)

A flocculation tensor to monitor water quality using a deep learning model - Guocheng Zhu; Jialin Lin; Haiquan Fang; Fang Yuan; Xiaoshang Li; Cheng Yuan; Andrew S. Hursthouse (Environmental Chemistry Letters, 2022)
The increasing quantities of polluted waters are calling for advanced purification methods. Flocculation is an essential component of the water purification process, yet flocculation is commonly not optimal due to our poor understanding of the flocculation process. In particular, there is little knowledge on the mechanisms ruling the migration of pollutants during treatment. Here we have created the first tensor diagram, a mathematical framework for the flocculation process, analyzed its properties with a deep learning model, and developed a classification scheme for its relationship with pollutants. The tensor was constructed by combining pixel matrices from a variety of floc images, each with a particular flocculation period. Changing the factors used to make flocs images, such as coagulant dose and pH, resulted in tensors, which were used to generate matrices, that is the tensor diagram. Our deep learning algorithm employed a tensor diagram to identify pollution levels. Results show tensor map attributes with over 98% of sample images correctly classified. This approach offers potential to reduce the time delay of feedback from the flocculation process with deep learning categorization based on its clustering capabilities. The advantage of the tensor data from the flocculation process improves the efficiency and speed of response for commercial water treatment.

BCL11B Upregulates the Expression of RelA in T Cells Stimulated with Staphylococcal Enterotoxin A - Y. Yan; S. Wang; C. Lin (Bulletin of Experimental Biology and Medicine, 2022)

Evaluation and multimodel projection of seasonal precipitation extremes over central Asia based on CMIP6 simulations - Victor Nnamdi Dike; Zhaohui Lin; Kece Fei; Gaby S. Langendijk; Debashis Nath (International Journal of Climatology, 2022)
Central Asia faces an increasing challenge related to water resources arising from severe droughts and floods that have impacted the region in the past decades. Using a comprehensive set of extreme precipitation indices, we assess the performance of CMIP6 models in representing observed precipitation extremes and investigate future responses of these extremes to greenhouse gas emissions under four shared socioeconomic pathways (SSP). Particularly, this study identifies robust signals of projected changes in spring and summer precipitation extremes over central Asia. Results show that the CMIP6 models reasonably reproduced the spatial distribution and variability of precipitation extremes over southern central Asia (SCA) and northern central Asia (NCA) during the spring and summer seasons, respectively. Across the SSPs, the CMIP6 models project a decrease in total spring wet‐day precipitation amount (PRCPTOT) over SCA and a significant increase in PRCPTOT over the NCA. The projected changes are characterized by a significant increase in maximum consecutive 5‐day precipitation (RX5day), wet‐day intensity (SDII), and the number of heavy precipitation days (R10mm); these suggest that the spring will be characterized by intense precipitation extremes. Moreover, no significant change is projected for consecutive wet days (CWD) and dry spells (CDD) over SCA. Nonetheless, the CMIP6 models project a significant increase in summer PRCPTOT over SCA and a decrease in summer PRCPTOT, RX5day, R10mm, SDII, and CWD over NCA while projecting a significant and robust increase in dry spells. It is also found that the severity of the projected dry spell deepens across the SSP spectra and gets more pronounced towards the end of the 21st century. Notably, the intermodel spread of the precipitation extremes is smaller during the spring over SCA, larger during the summer season over NCA, and more probable in the warmer future.

A comprehensive review on water stable metal-organic frameworks for large-scale preparation and applications in water quality management based on surveys made since 2015 - R. Y. Li; Z. S. Wang; Z. Y. Yuan; Constance Van Horne; Viatcheslav Freger; M. Lin; R. K. Cai; J. P. Chen (Critical Reviews in Environmental Science and Technology, 2022)

An overview of cotton and polyester, and their blended waste textile valorisation to value-added products: A circular economy approach – research trends, opportunities and challenges - Karpagam Subramanian; Manas Kumar Sarkar; Huaimin Wang; Zi-Hao Qin; Shauhrat S. Chopra; Mushan Jin; Vinod Kumar; Chao Chen; Chi-Wing Tsang; Carol Sze Ki Lin (Critical Reviews in Environmental Science and Technology, 2022)

A 10-miRNA risk score-based prediction model for pathological complete response to neoadjuvant chemotherapy in hormone receptor-positive breast cancer - Chang Gong; Ziliang Cheng; Yaping Yang; Jun Shen; Yingying Zhu; Li Ling; Wanyi Lin; Zhigang Yu; Zhihua Li; Weige Tan; Chushan Zheng; Wenbo Zheng; et al. (Science China Life Sciences, 2022)

Long‐term drought aggravates instability of alpine grassland productivity to extreme climatic event - Yun L. He; Jin S. Wang; Da S. Tian; Quan Quan; Lin Jiang; Fang F. Ma; Lu Yang; Fang Y. Zhang; Qing P. Zhou; Shu L. Niu (Ecology, 2022)
The frequency and severity of extreme weather events are increasing and expected to increase more in the future, together with global change. However, how extreme events and global change factors interactively influence community structures and ecosystem processes is largely unknown. Here, we investigated the responses of the temporal stability and resilience of aboveground net primary productivity (ANPP) of an alpine meadow to an extreme flooding event under different treatments of experimental drought and clipping. We found that ecosystems that were exposed to drought treatments for 3 years significantly decreased the temporal stability of community productivity but increased resilience to flooding, whereas their resistance to or recovery from flooding did not change. Neither clipping nor its interaction with drought altered the responses of these community stability metrics to flooding. Drought treatments significantly decreased plant species richness and asynchrony and dominant species stability, leading to a decrease in temporal stability and an increase in resilience in response to the extreme flooding event. The study also revealed that the change in species asynchrony was the dominant impact pathway determining the responses of resilience and temporal stability to flooding. Our results highlight that alpine grassland that experiences a multiyear drought may aggravate the instability of community productivity to extreme climatic events by reducing species asynchrony.

Coastal upwelling enhances abundance of a symbiotic diazotroph (UCYN-A) and its haptophyte host in the Arctic Ocean - Corday R. Selden; Sveinn V. Einarsson; Kate E. Lowry; Katherine E. Crider; Robert S. Pickart; Peigen Lin; Carin J. Ashjian; P. Dreux Chappell (Frontiers in Marine Science, 2022)
The apparently obligate symbiosis between the diazotroph Candidatus Atelocyanobacterium thalassa (UCYN-A) and its haptophyte host, Braarudosphaera bigelowii , has recently been found to fix dinitrogen (N 2 ) in polar waters at rates (per cell) comparable to those observed in the tropical/subtropical oligotrophic ocean basins. This study presents the novel observation that this symbiosis increased in abundance during a wind-driven upwelling event along the Alaskan Beaufort shelfbreak. As upwelling relaxed, the relative abundance of B. bigelowii among eukaryotic phytoplankton increased most significantly in waters over the upper slope. As the host’s nitrogen demands are believed to be supplied primarily by UCYN-A, this response suggests that upwelling may enhance N 2 fixation as displaced coastal waters are advected offshore, potentially extending the duration of upwelling-induced phytoplankton blooms. Given that such events are projected to increase in intensity and number with ocean warming, upwelling-driven N 2 fixation as a feedback on climate merits investigation.

OpenAltimetry - rapid analysis and visualization of Spaceborne altimeter data - Siri Jodha S. Khalsa; Adrian Borsa; Viswanath Nandigam; Minh Phan; Kai Lin; Christopher Crosby; Helen Fricker; Chaitan Baru; Luis Lopez (Earth Science Informatics, 2022)
NASA’s Ice, Cloud, and land Elevation Satellite-2 (ICESat-2) carries a laser altimeter that fires 10,000 pulses per second towards Earth and records the travel time of individual photons to measure the elevation of the surface below. The volume of data produced by ICESat-2, nearly a TB per day, presents significant challenges for users wishing to efficiently explore the dataset. NASA’s National Snow and Ice Data Center (NSIDC) Distributed Active Archive Center (DAAC), which is responsible for archiving and distributing ICESat-2 data, provides search and subsetting services on mission data products, but providing interactive data discovery and visualization tools needed to assess data coverage and quality in a given area of interest is outside of NSIDC’s mandate. The OpenAltimetry project, a NASA-funded collaboration between NSIDC, UNAVCO and the University of California San Diego, has developed a web-based cyberinfrastructure platform that allows users to locate, visualize, and download ICESat-2 surface elevation data and photon clouds for any location on Earth, on demand. OpenAltimetry also provides access to elevations and waveforms for ICESat (the predecessor mission to ICESat-2). In addition, OpenAltimetry enables data access via APIs, opening opportunities for rapid access, experimentation, and computation via third party applications like Jupyter notebooks. OpenAltimetry emphasizes ease-of-use for new users and rapid access to entire altimetry datasets for experts and has been successful in meeting the needs of different user groups. In this paper we describe the principles that guided the design and development of the OpenAltimetry platform and provide a high-level overview of the cyberinfrastructure components of the system.

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Multitrophic diversity and biotic associations influence subalpine forest ecosystem multifunctionality - Ya‐Huang Luo; Marc W. Cadotte; Jie Liu; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Jia‐Yun Zou; Zhong‐Zheng Chen; Xue‐Long Jiang; Juan Li; Kun Xu; De‐Zhu Li; et al. (Ecology, 2022)
Biodiversity across multiple trophic levels is required to maintain multiple ecosystem functions. Yet it remains unclear how multitrophic diversity and species interactions regulate ecosystem multifunctionality. Here, combining data from 9 different trophic groups (including trees, shrubs, herbs, leaf mites, small mammals, bacteria, pathogenic fungi, saprophytic fungi, and symbiotic fungi) and 13 ecosystem functions related to supporting, provisioning, and regulating services, we used a multitrophic perspective to evaluate the effects of elevation, diversity, and network complexity on scale‐dependent subalpine forest multifunctionality. Our results demonstrated that elevation and soil pH significantly modified species composition and richness across multitrophic groups and influenced multiple functions simultaneously. We present evidence that species richness across multiple trophic groups had stronger effects on multifunctionality than species richness at any single trophic level. Moreover, biotic associations, indicating the complexity of trophic networks, were positively associated with multifunctionality. The relative effects of diversity on multifunctionality increased at the scale of the larger community compared to a scale accounting for neighboring interactions. Our results highlight the paramount importance of scale‐ and context‐dependent multitrophic diversity and interactions for a better understanding of mountain ecosystem multifunctionality in a changing world.

Quantifying knapping actions: a method for measuring the angle of blow on flakes - Li Li; Jonathan S. Reeves; Sam C. Lin; Claudio Tennie; Shannon P. McPherron (Archaeological and Anthropological Sciences, 2022)
Stone artifacts are critical for investigating the evolution of hominin behavior—they are among our only proxies for hominin behavior in deep time. Hominin cognition and skill are often inferred by reconstructing the technical decisions hominins made throughout the knapping process. However, despite many advancements in understanding how hominins knapped, some of the key factors involved in past flake production cannot be easily/readily derived from stone artifacts. In particular, the angle at which the knapper strikes the hammer against the core to remove the flake, or the angle of blow, is a key component of the knapping process that has up to now remained unmeasurable on archeological assemblages. In this study, we introduce a new method for estimating the angle of blow from the ventral surface of flakes. This method was derived from a controlled experiment that explicitly connects fracture mechanics to flake variability. We find that a feature of the flake’s bulb of percussion, what we call the bulb angle, is a measurable indicator of the angle of blow. Our experimental finding is further validated in two additional datasets from controlled and replicative knapping experiments. These results demonstrate the utility of continuing to link flake variation with technical decision-making to fracture mechanics. In addition, they also provide a useful and relatively simple means to capture a currently invisible aspect of hominin stone tool production behavior.

Registered clinical trials investigating treatment of long COVID: a scoping review and recommendations for research - Felicia Ceban; Alexia Leber; Muhammad Youshay Jawad; Mathew Yu; Leanna M. W. Lui; Mehala Subramaniapillai; Joshua D. Di Vincenzo; Hartej Gill; Nelson B. Rodrigues; Bing Cao; Yena Lee; Kangguang Lin; et al. (Infectious Diseases, 2022)

A Brief Educational Intervention to Increase ED Initiation of Buprenorphine for Opioid Use Disorder (OUD) - Utsha G. Khatri; Kathleen Lee; Theodore Lin; Joseph L. D’Orazio; Mitesh S. Patel; Frances S. Shofer; Jeanmarie Perrone (Journal of Medical Toxicology, 2022)

Factors associated with changes in exercise behaviors during the COVID-19 pandemic - Caroline Himbert; Cassandra A. Hathaway; Bailee Daniels; Karen Salas; Anjelica Ashworth; Biljana Gigic; Tengda Lin; Richard Viskochil; Anne C. Kirchhoff; Douglas Grossman; Jennifer Ose; Jonathan Tward; et al. (Cancer Causes & Control, 2022)

Historical trend of probable maximum precipitation in Utah and associated weather types - Hongping Gu; S.‐Y. Simon Wang; Yen‐Heng Lin; Jonathan Meyer; Robert Gillies; Everett Taylor; Binod Pokharel (International Journal of Climatology, 2022)
This study assesses the impact global climate change has had on the theoretical upper limit of precipitation for Utah's watersheds by examining historical trends in probable maximum precipitation (PMP), a metric widely used for dam construction and management. Trends in the factors of PMP driven by both frontal and monsoonal storm scenarios were studied using two networks of surface weather stations and modern gridded datasets spanning 1981–2018. It was found that the historical trend in both 3‐hr and 24‐hr PMP estimations exhibited a statistically significant increasing trend, despite that the magnitude of the trend was sensitive to which dataset was examined and the data's spatial resolution. Over the 24‐hr time scale, an interesting deviation in PMP trends was found where frontal storm events demonstrated increasing PMP trends compared to decreasing PMP trends for monsoonal storm events. However, both storm types demonstrated increasing trends over shorter 3‐hr durations, suggesting a universal increase in convective storm intensity. PMP estimates also demonstrated a dependency on the type and resolution of meteorological data used, where higher‐resolution data generally produced greater PMP values and weaker trends. A discussion on the potential causes of these dependencies is provided. This study implies the need to take the historical PMP trend into account for future PMP estimates, especially when coarse‐resolution data are used for conventional PMP studies.

TREM-2 mediates dendritic cell–induced NO to suppress Th17 activation and ameliorate chronic kidney diseases - Ching-Cheng Lin; Ti-Yung Chang; Yong-Chen Lu; Yun-Syuan Wu; Wei Huang; Wei-Chi Lo; Guan-Fu Liu; Wei-Chan Hsu; Pamela S. Ohashi; Tak W. Mak; Jong-Ling Fuh; Hui-Chen Chen; et al. (Journal of Molecular Medicine, 2022)

HIV, pathology and epigenetic age acceleration in different human tissues - Steve Horvath; David T. S. Lin; Michael S. Kobor; Joseph A. Zoller; Jonathan W. Said; Susan Morgello; Elyse Singer; William H. Yong; Beth D. Jamieson; Andrew J. Levine (GeroScience, 2022)
Epigenetic clocks based on patterns of DNA methylation have great importance in understanding aging and disease; however, there are basic questions to be resolved in their application. It remains unknown whether epigenetic age acceleration (EAA) within an individual shows strong correlation between different primary tissue sites, the extent to which tissue pathology and clinical illness correlate with EAA in the target organ, and if EAA variability across tissues differs according to sex. Considering the outsized role of age-related illness in Human Immunodeficiency Virus-1 (HIV), these questions were pursued in a sample enriched for tissue from HIV-infected individuals. We used a custom methylation array to generate DNA methylation data from 661 samples representing 11 human tissues (adipose, blood, bone marrow, heart, kidney, liver, lung, lymph node, muscle, spleen and pituitary gland) from 133 clinically characterized, deceased individuals, including 75 infected with HIV. We developed a multimorbidity index based on the clinical disease history. Epigenetic age was moderately correlated across tissues. Blood had the greatest number and degree of correlation, most notably with spleen and bone marrow. However, blood did not correlate with epigenetic age of liver. EAA in liver was weakly correlated with EAA in kidney, adipose, lung and bone marrow. Clinically, hypertension was associated with EAA in several tissues, consistent with the multiorgan impacts of this illness. HIV infection was associated with positive age acceleration in kidney and spleen. Male sex was associated with increased epigenetic acceleration in several tissues. Preliminary evidence indicates that amyotrophic lateral sclerosis is associated with positive EAA in muscle tissue. Finally, greater multimorbidity was associated with greater EAA across all tissues. Blood alone will often fail to detect EAA in other tissues. While hypertension is associated with increased EAA in several tissues, many pathologies are associated with organ-specific age acceleration.

Delayed rFGF21 Administration Improves Cerebrovascular Remodeling and White Matter Repair After Focal Stroke in Diabetic Mice - Yinghua Jiang; Jinrui Han; Yadan Li; Yinga Wu; Ning Liu; Samuel X. Shi; Li Lin; Jing Yuan; Shusheng Wang; Ming-Ming Ning; Aaron S. Dumont; Xiaoying Wang (Translational Stroke Research, 2022)

Diversity and Zonation of Benthic Amphipod Crustaceans Affected by the Mississippi Submarine Canyon in the Northern Gulf of Mexico - Yousria S. Soliman; Gilbert T. Rowe; Mary Wicksten; Chih-Lin Wei (Frontiers in Marine Science, 2022)
Amphipod crustacean diversity and zonation are described from the large Mississippi Canyon that extends from the continental shelf across the entire continental margin. Benthic amphipods were sampled on four cruises from 2000 to 2004 from six locations in the Mississippi Canyon from depths of 480 through 2,750 m, and compared with five locations in a second transect on the open continental slope approximately 100 km west of the canyon to assess the canyon effect on the structure and composition of amphipod assemblages. Five replicates were collected from each location using 0.2 m –2 GOMEX box corer. Amphipods amounted to 40% of the total faunal abundance within the canyon compared to only 4% in the non-canyon samples. Of the seventy-two species (19 families) collected, 61 were encountered in the canyon compared to 38 on the non-canyon transect. The trough-like head of the canyon (480 m) supported high densities (4,446–26,933 ind./m 2 ) of the filter feeding, tube dwelling ampeliscid amphipod ( Ampelisca mississippiana ), the highest densities sampled compared to any other single species, at any other location, either within or outside the canyon, reflecting extreme flux of organic detritus from the continental shelf. The dominance by this single species suppressed the within – habitat (alpha) diversity and evenness, compared to relatively high diversity within the 1,000–1,500 m depths interval both in and outside the canyon. The species richness and alpha diversity exhibited mid-depth maxima at ca. 1,100 m both in and out of the canyon. High species richness (61) over the entire length of the canyon is presumed to be a function of greater topographic complexity and intermittent mass wasting of sediment down the canyon axis. The absence of nestedness is attributed to the amphipod reproductive pattern that lacks dispersive larval stages and brooding comparatively small numbers of eggs in this taxon. Despite depressed diversity at the head of the canyon, the fact that the number of amphipod species in the Mississippi Canyon was 1.5 times their numbers on the adjacent slope suggests that this physiographic feature enriches geographic-scale species diversity.

Effect of pyrolysis temperature on pyrolysis of pine saw dust and application of bio-char - J. Lin; Q. Zhang; H. Xia; S. Cheng (International Journal of Environmental Science and Technology, 2022)

An assessment of the health risks associated with shared sanitation: a case study of the community ablution blocks in Durban, South Africa - Preshod S. Ramlal; Johnson Lin; Christopher A. Buckley; Thor Axel Stenström; Isaac D. Amoah (Environmental Monitoring and Assessment, 2022)

P75 neurotrophin receptor controls subventricular zone neural stem cell migration after stroke - Sachin S. Deshpande; Subash C. Malik; Pasquale Conforti; Jia-di Lin; Yu-Hsuan Chu; Suvra Nath; Franziska Greulich; Meike-Ast Dumbach; N. Henriette Uhlenhaut; Christian Schachtrup (Cell and Tissue Research, 2022)
Stroke is the leading cause of adult disability. Endogenous neural stem/progenitor cells (NSPCs) originating from the subventricular zone (SVZ) contribute to the brain repair process. However, molecular mechanisms underlying CNS disease-induced SVZ NSPC-redirected migration to the lesion area are poorly understood. Here, we show that genetic depletion of the p75 neurotrophin receptor ( p75 NTR−/− ) in mice reduced SVZ NSPC migration towards the lesion area after cortical injury and that p75 NTR−/− NSPCs failed to migrate upon BDNF stimulation in vitro. Cortical injury rapidly increased p75 NTR abundance in SVZ NSPCs via bone morphogenetic protein (BMP) receptor signaling. SVZ-derived p75 NTR−/− NSPCs revealed an altered cytoskeletal network- and small GTPase family-related gene and protein expression. In accordance, BMP-treated non-migrating p75 NTR−/− NSPCs revealed an altered morphology and α-tubulin expression compared to BMP-treated migrating wild-type NSPCs. We propose that BMP-induced p75 NTR abundance in NSPCs is a regulator of SVZ NSPC migration to the lesion area via regulation of the cytoskeleton following cortical injury.

Effects of short-term decomposition on isotope values of fish tissues under natural conditions - Kathryn S. Peiman; Hsien-Yung Lin; Michael Power; Scott G. Hinch; David A. Patterson; Steven J. Cooke (Aquatic Ecology, 2022)

Gene duplication to the Y chromosome in Trinidadian Guppies - Yuying Lin; Iulia Darolti; Benjamin L. S. Furman; Pedro Almeida; Benjamin A. Sandkam; Felix Breden; Alison E. Wright; Judith E. Mank (Molecular Ecology, 2022)
Differences in allele frequencies at autosomal genes between males and females in a population can result from two scenarios. First, unresolved sexual conflict over survival can produce allelic differentiation between the sexes. However, given the substantial mortality costs required to produce allelic differences between males and females at each generation, it remains unclear how many loci within the genome experience significant sexual conflict over survival. Alternatively, recent studies have shown that similarity between autosomal and Y sequences can create perceived allelic differences between the sexes. However, Y duplications are most likely in species with large nonrecombining regions, in part because they simply represent larger targets for duplications. We assessed the genomes of 120 wild‐caught guppies, which experience extensive predation‐ and pathogen‐induced mortality and have a relatively small ancestral Y chromosome. We identified seven autosomal genes that show allelic differences between male and female adults. Five of these genes show clear evidence of whole or partial gene duplication between the Y chromosome and the autosomes. The remaining two genes show evidence of partial homology to the Y. Overall, our findings suggest that the guppy genome experiences a very low level of unresolved sexual conflict over survival, and instead the Y chromosome, despite its small ancestral size and recent origin, may nonetheless accumulate genes with male‐specific functions.

Microbiome Associated With Gambierdiscus balechii Cultures Under Different Toxicity Conditions - Zhen Wu; Wai Hin Lee; Zijian Liu; Senjie Lin; Paul K. S. Lam (Frontiers in Marine Science, 2022)
Dinoflagellates, including harmful algal bloom species, are known to co-exist with and rely upon bacteria but how the microbiome changes with the physiologies of the cognate dinoflagellates is poorly understood. Here, we used 16S rRNA gene meta-barcoding to characterize the bacterial community in the cultures of Gambierdiscus balechii , a ciguatoxin-producing benthic dinoflagellate, under different nitrogen (N)-nutrient conditions and at different ciguatoxin-producing growth. The high-throughput sequencing of a total of 12 libraries generated 926,438 reads which were classified into 16 phyla. We observed a shift of the G. balechii -associated microbiome from N-replete to low-N conditions and from the early (low toxin) to the late exponential (high toxin) growth stage. Common across these conditions were species from families Rhodobacteraceae and Flavobacteriaceae. Species abundant in the low-N condition mainly included Planctomyces , Ekhidna , and Lactobacillus. Dominant or highly abundant microbial taxa in the high toxin-producing stage (N-replete, late exponential stage) were Oceanococcus and Marinoscillum . Under this condition, one Rhizobiales bacterium, Oricola , also increased in relative abundance. Our study documents the high diversity and dynamics of the G. balechii -associated microbiome, and identifies condition-specific sub-communities: the core (constitutive) microbiome that stably co-exists with G. balechii , the bacterial lineages that are responsive to N-nutrient variations, and species whose abundances are correlated with toxin content of the dinoflagellate. These findings demonstrate that particular bacterial groups are responsive to N-nutrient or toxicity changes of G. balechii and thus will be useful for further investigations on the associated microbiome’s interactions with benthic dinoflagellates and functions in the course of benthic harmful algae blooms.

Pathogen resistance in Sphagneticola trilobata (Singapore daisy): molecular associations and differentially expressed genes in response to disease from a widespread fungus - Shan-Shan Qi; Bharani Manoharan; Vignesh Dhandapani; Sridharan Jegadeesan; Susan Rutherford; Justin S. H. Wan; Ping Huang; Zhi-Cong Dai; Dao-Lin Du (Genetica, 2022)

Species richness and generalists–specialists mosaicism of symbiodiniacean symbionts in corals from Hong Kong revealed by high-throughput ITS sequencing - Osama S. Saad; Xin Lin; Tsz Yan Ng; Ling Li; Put Ang; Senjie Lin (Coral Reefs, 2022)

Overall and central obesity and prostate cancer risk in African men - Ilir Agalliu; Wei-Kaung Jerry Lin; Janice S. Zhang; Judith S. Jacobson; Thomas E. Rohan; Ben Adusei; Nana Yaa F. Snyper; Caroline Andrews; Elkhansa Sidahmed; James E. Mensah; Richard Biritwum; Andrew A. Adjei; et al. (Cancer Causes & Control, 2022)

A bibliometric review of peripartum cardiomyopathy compared to other cardiomyopathies using artificial intelligence and machine learning - M. Grosser; H. Lin; M. Wu; Y. Zhang; S. Tipper; D. Venter; J. Lu; C. G. dos Remedios (Biophysical Reviews, 2022)

Novel wing display and divergent agonistic behaviors of two incipient Psolodesmus damselflies - Leocris S. Batucan; Yu-Hsun Hsu; Jak W. Maliszewski; Liang-Jong Wang; Chung-Ping Lin (The Science of Nature, 2021)

Determining tolerance levels for quality assurance of 3D printed bolus for modulated arc radiotherapy of the nose - T. Kairn; S. Talkhani; P. H. Charles; B. Chua; C. Y. Lin; A. G. Livingstone; S. K. Maxwell; T. Poroa; E. Simpson-Page; E. Spelleken; M. Vo; S. B. Crowe (Physical and Engineering Sciences in Medicine, 2021)

Realization of Natural Human Motion on a 3D Biped Robot For Studying the Exoskeleton Effective - Chi-Ying Lee; Shih Chieh Lan; Jung-Ji Lin; Yu-Ting Lin; Po-Shen Chiang; Wei-Li Hsu; Kuo-Kuang Jen; Andy Y. S. Huang; Jia-Yush Yen (Journal of Medical and Biological Engineering, 2021)

Association between exposure to road traffic noise and hearing impairment: a case-control study - Tang-Chuan Wang; Ta-Yuan Chang; Richard S. Tyler; Bing-Fang Hwang; Yi-Hung Chen; Che-Ming Wu; Chiu-Shong Liu; Kuang-Chao Chen; Chia-Der Lin; Ming-Hsui Tsai (Journal of Environmental Health Science and Engineering, 2021)

Antigen production and development of an indirect ELISA based on the nucleocapsid protein to detect human SARS-CoV-2 seroconversion - Marcelo S. Conzentino; Karl Forchhammer; Emanuel M. Souza; Fábio O. Pedrosa; Meri B. Nogueira; Sônia M. Raboni; Fabiane G. M. Rego; Dalila L. Zanette; Mateus N. Aoki; Jeanine M. Nardin; Bruna Fornazari; Hugo M. P. Morales; et al. (Brazilian Journal of Microbiology, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Recovery from hybrid breakdown reveals a complex genetic architecture of mitonuclear incompatibilities - Ricardo J. Pereira; Thiago G. Lima; N. Tessa Pierce‐Ward; Lin Chao; Ronald S. Burton (Molecular Ecology, 2021)
Reproductive isolation is often achieved when genes that are neutral or beneficial in their genomic background become functionally incompatible in a foreign genomic background, causing inviability, sterility or other forms of low fitness in hybrids. Recent studies suggest that mitonuclear interactions are among the initial incompatibilities to evolve at early stages of population divergence across taxa. Yet, the genomic architecture of mitonuclear incompatibilities has rarely been elucidated. We employ an experimental evolution approach starting with low‐fitness F 2 interpopulation hybrids of the copepod Tigriopus californicus , in which frequencies of compatible and incompatible nuclear alleles change in response to an alternative mitochondrial background. After about nine generations, we observe a generalized increase in population size and in survivorship, suggesting efficiency of selection against maladaptive phenotypes. Whole genome sequencing of evolved populations showed some consistent allele frequency changes across three replicates of each reciprocal cross, but markedly different patterns between mitochondrial backgrounds. In only a few regions (~6.5% of the genome), the same parental allele was overrepresented irrespective of the mitochondrial background. About 33% of the genome showed allele frequency changes consistent with divergent selection, with the location of these genomic regions strongly differing between mitochondrial backgrounds. In 87% and 89% of these genomic regions, the dominant nuclear allele matched the associated mitochondrial background, consistent with mitonuclear co‐adaptation. These results suggest that mitonuclear incompatibilities have a complex polygenic architecture that differs between populations, potentially generating genome‐wide barriers to gene flow between closely related taxa.

A Rhizobium bacterium and its population dynamics under different culture conditions of its associated toxic dinoflagellate Gambierdiscus balechii - Zhen Wu; Xiaohong Yang; Senjie Lin; Wai Hin Lee; Paul K. S. Lam (Marine Life Science & Technology, 2021)

Dietary inflammatory index and risk of colorectal adenoma: effect measure modification by race, nonsteroidal anti-inflammatory drugs, cigarette smoking and body mass index? - Fangcheng Yuan; Lin Deng; Xiangqing Sun; Zhengyi Chen; Nitin Shivappa; Ashutosh K. Sheth; Gregory S. Cooper; James R. Hebert; Li Li (Cancer Causes & Control, 2021)

Effect of water regime and harvest stage on essential oil accumulation in basil plant growing in sandy soil - João V. R. S. Souza; Lin Chau Ming; Marcos A. L. Santos; James E. Simon; Hector R. Juliani; João C. C. Saad (Irrigation Science, 2021)

Activation of Ca2+/Calmodulin-Dependent Protein Kinase II (CaMKII) with Lidocaine Provokes Pyroptosis of Glioblastoma Cells - B. Zhou; Y. Lin; S. Chen; J. Cai; Z. Luo; S. Yu; J. Lu (Bulletin of Experimental Biology and Medicine, 2021)

Low diversity of a key phytoplankton group along the West Antarctic Peninsula - Michael S. Brown; Jeff S. Bowman; Yajuan Lin; Colette J. Feehan; Carly M. Moreno; Nicolas Cassar; Adrian Marchetti; Oscar M. Schofield (Limnology and Oceanography, 2021)
The West Antarctic Peninsula (henceforth “Peninsula”) is experiencing rapid warming and melting that is impacting the regional marine food web. The primary phytoplankton groups along the Peninsula are diatoms and cryptophytes. Relative to diatoms, there has been little focus on regional cryptophytes, and thus our understanding of their diversity and ecology is limited, especially at the species level. This gap is important, as diatoms and cryptophytes play distinct roles in the regional marine food web and biogeochemistry. Here, we use a phylogenetic placement approach with 18S rRNA gene amplicon sequence variants to assess surface ocean cryptophyte diversity and its drivers at a high taxonomic resolution along the Peninsula. Data were collected over 5 years (2012–2016) during the regional research cruises of the Palmer Long‐Term Ecological Research program. Our results indicate that there are two major cryptophyte taxa along the Peninsula, consisting of distinct Geminigera spp., which in aggregate always comprise nearly 100% of the cryptophyte community (indicating low taxa evenness). The primary taxon dominates the cryptophyte community across all samples/years, which span a broad range of oceanographic conditions. A shift in cryptophyte community composition between a lower (higher) primary (secondary) taxon percentage is associated with distinct oceanographic conditions, including lower (higher) temperature, salinity, nutrients, and cryptophyte relative abundance (phytoplankton biomass and diatom relative abundance). These results emphasize the need for a full characterization of the ecology of these two taxa, as it is predicted that cryptophytes will increase along the Peninsula given projections of continued regional environmental change.

Peptide KED: Molecular-Genetic Aspects of Neurogenesis Regulation in Alzheimer’s Disease - V. Kh. Khavinson; N. S. Lin’kova; R. S. Umnov (Bulletin of Experimental Biology and Medicine, 2021)

From zero to infinity: Minimum to maximum diversity of the planet by spatio‐parametric Rao’s quadratic entropy - Duccio Rocchini; Matteo Marcantonio; Daniele Da Re; Giovanni Bacaro; Enrico Feoli; Giles M. Foody; Reinhard Furrer; Ryan J. Harrigan; David Kleijn; Martina Iannacito; Jonathan Lenoir; Meixi Lin; et al. (Global Ecology and Biogeography, 2021)
Aim The majority of work done to gather information on the Earth's biodiversity has been carried out using in‐situ data, with known issues related to epistemology (e.g., species determination and taxonomy), spatial uncertainty, logistics (time and costs), among others. An alternative way to gather information about spatial ecosystem variability is the use of satellite remote sensing. It works as a powerful tool for attaining rapid and standardized information. Several metrics used to calculate remotely sensed diversity of ecosystems are based on Shannon’s information theory, namely on the differences in relative abundance of pixel reflectances in a certain area. Additional metrics like the Rao’s quadratic entropy allow the use of spectral distance beside abundance, but they are point descriptors of diversity, that is they can account only for a part of the whole diversity continuum. The aim of this paper is thus to generalize the Rao’s quadratic entropy by proposing its parameterization for the first time. Innovation The parametric Rao’s quadratic entropy, coded in R, (a) allows the representation of the whole continuum of potential diversity indices in one formula, and (b) starting from the Rao’s quadratic entropy, allows the explicit use of distances among pixel reflectance values, together with relative abundances. Main conclusions The proposed unifying measure is an integration between abundance‐ and distance‐based algorithms to map the continuum of diversity given a satellite image at any spatial scale. Being part of the rasterdiv R package, the proposed method is expected to ensure high robustness and reproducibility.

Optimisation using the finite element method of a filter-based microfluidic SERS sensor for detection of multiple pesticides in strawberry - Sara Asgari; Guangfu Wu; S. Ali Aghvami; Yi Zhang; Mengshi Lin (Food Additives & Contaminants: Part A, 2021)

Genetic architecture of wild soybean (Glycine soja Sieb. and Zucc.) populations originating from different East Asian regions - Muhammad Amjad Nawaz; Xiao Lin; Ting-Fung Chan; Hon-Ming Lam; Faheem Shehzad Baloch; Muhammad Amjad Ali; Kirill S. Golokhvast; Seung Hwan Yang; Gyuhwa Chung (Genetic Resources and Crop Evolution, 2021)

A global collaboration to study intimate partner violence-related head trauma: The ENIGMA consortium IPV working group - Carrie Esopenko; Jessica Meyer; Elisabeth A. Wilde; Amy D. Marshall; David F. Tate; Alexander P. Lin; Inga K. Koerte; Kimberly B. Werner; Emily L. Dennis; Ashley L. Ware; Nicola L. de Souza; Deleene S. Menefee; et al. (Brain Imaging and Behavior, 2021)

The ENIGMA sports injury working group:– an international collaboration to further our understanding of sport-related brain injury - Inga K. Koerte; Carrie Esopenko; Sidney R. Hinds; Martha E. Shenton; Elena M. Bonke; Jeffrey J. Bazarian; Kevin C. Bickart; Erin D. Bigler; Sylvain Bouix; Thomas A. Buckley; Meeryo C. Choe; Paul S. Echlin; et al. (Brain Imaging and Behavior, 2021)
Sport-related brain injury is very common, and the potential long-term effects include a wide range of neurological and psychiatric symptoms, and potentially neurodegeneration. Around the globe, researchers are conducting neuroimaging studies on primarily homogenous samples of athletes. However, neuroimaging studies are expensive and time consuming, and thus current findings from studies of sport-related brain injury are often limited by small sample sizes. Further, current studies apply a variety of neuroimaging techniques and analysis tools which limit comparability among studies. The ENIGMA Sports Injury working group aims to provide a platform for data sharing and collaborative data analysis thereby leveraging existing data and expertise. By harmonizing data from a large number of studies from around the globe, we will work towards reproducibility of previously published findings and towards addressing important research questions with regard to diagnosis, prognosis, and efficacy of treatment for sport-related brain injury. Moreover, the ENIGMA Sports Injury working group is committed to providing recommendations for future prospective data acquisition to enhance data quality and scientific rigor.

The influence of vector‐borne disease on human history: socio‐ecological mechanisms - Tejas S. Athni; Marta S. Shocket; Lisa I. Couper; Nicole Nova; Iain R. Caldwell; Jamie M. Caldwell; Jasmine N. Childress; Marissa L. Childs; Giulio A. De Leo; Devin G. Kirk; Andrew J. MacDonald; Kathryn Olivarius; et al. (Ecology Letters, 2021)
Vector‐borne diseases (VBDs) are embedded within complex socio‐ecological systems. While research has traditionally focused on the direct effects of VBDs on human morbidity and mortality, it is increasingly clear that their impacts are much more pervasive. VBDs are dynamically linked to feedbacks between environmental conditions, vector ecology, disease burden, and societal responses that drive transmission. As a result, VBDs have had profound influence on human history. Mechanisms include: (1) killing or debilitating large numbers of people, with demographic and population‐level impacts; (2) differentially affecting populations based on prior history of disease exposure, immunity, and resistance; (3) being weaponised to promote or justify hierarchies of power, colonialism, racism, classism and sexism; (4) catalysing changes in ideas, institutions, infrastructure, technologies and social practices in efforts to control disease outbreaks; and (5) changing human relationships with the land and environment. We use historical and archaeological evidence interpreted through an ecological lens to illustrate how VBDs have shaped society and culture, focusing on case studies from four pertinent VBDs: plague, malaria, yellow fever and trypanosomiasis. By comparing across diseases, time periods and geographies, we highlight the enormous scope and variety of mechanisms by which VBDs have influenced human history.

The conduction velocity-potassium relationship in the heart is modulated by sodium and calcium - D. Ryan King; Michael Entz; Grace A. Blair; Ian Crandell; Alexandra L. Hanlon; Joyce Lin; Gregory S. Hoeker; Steven Poelzing (Pflügers Archiv - European Journal of Physiology, 2021)
The relationship between cardiac conduction velocity (CV) and extracellular potassium (K + ) is biphasic, with modest hyperkalemia increasing CV and severe hyperkalemia slowing CV. Recent studies from our group suggest that elevating extracellular sodium (Na + ) and calcium (Ca 2+ ) can enhance CV by an extracellular pathway parallel to gap junctional coupling (GJC) called ephaptic coupling that can occur in the gap junction adjacent perinexus. However, it remains unknown whether these same interventions modulate CV as a function of K + . We hypothesize that Na + , Ca 2+ , and GJC can attenuate conduction slowing consequent to severe hyperkalemia. Elevating Ca 2+ from 1.25 to 2.00 mM significantly narrowed perinexal width measured by transmission electron microscopy. Optically mapped, Langendorff-perfused guinea pig hearts perfused with increasing K + revealed the expected biphasic CV-K + relationship during perfusion with different Na + and Ca 2+ concentrations. Neither elevating Na + nor Ca 2+ alone consistently modulated the positive slope of CV-K + or conduction slowing at 10-mM K + ; however, combined Na + and Ca 2+ elevation significantly mitigated conduction slowing at 10-mM K + . Pharmacologic GJC inhibition with 30-μM carbenoxolone slowed CV without changing the shape of CV-K + curves. A computational model of CV predicted that elevating Na + and narrowing clefts between myocytes, as occur with perinexal narrowing, reduces the positive and negative slopes of the CV-K + relationship but do not support a primary role of GJC or sodium channel conductance. These data demonstrate that combinatorial effects of Na + and Ca 2+ differentially modulate conduction during hyperkalemia, and enhancing determinants of ephaptic coupling may attenuate conduction changes in a variety of physiologic conditions.

Atrial fibrillation rhythm is associated with marked changes in metabolic and myofibrillar protein expression in left atrial appendage - Julie H. Rennison; Ling Li; Cheryl R. Lin; Beth S. Lovano; Laurie Castel; Sojin Youn Wass; Catherine C. Cantlay; Meghan McHale; A. Marc Gillinov; Reena Mehra; Belinda B. Willard; Jonathan D. Smith; et al. (Pflügers Archiv - European Journal of Physiology, 2021)

Object Detection and Tracking with UAV Data Using Deep Learning - A. Ancy Micheal; K. Vani; S. Sanjeevi; Chao-Hung Lin (Journal of the Indian Society of Remote Sensing, 2021)

Characterization and validation of QTLs for adult plant stripe rust resistance in Chinese wheat landrace Dabaimai - M. Y. Wang; M. R. Xu; F. T. Wang; S. J. A. Shah; J. Feng; R. M. Lin; S. C. Xu (Cereal Research Communications, 2021)

Fracture Propagation of Rock like Material with a Fluid-Infiltrated Pre-existing Flaw Under Uniaxial Compression - C. Wei; B. Zhang; W. Zhu; S. Wang; J. Li; ·L. Yang; C. Lin (Rock Mechanics and Rock Engineering, 2021)

Machine learning prediction of neurocognitive impairment among people with HIV using clinical and multimodal magnetic resonance imaging data - Yunan Xu; Yizi Lin; Ryan P. Bell; Sheri L. Towe; John M. Pearson; Tauseef Nadeem; Cliburn Chan; Christina S. Meade (Journal of NeuroVirology, 2021)

Structural analysis of glycosaminoglycans from Oviductus ranae - Haiyue Huang; Jin Mao; Quntao Liang; Jianghui Lin; Lilong Jiang; Shutao Liu; Joshua S. Sharp; Zheng Wei (Glycoconjugate Journal, 2021)

Influences of Physical Vegetation Management on Odonata Abundance in Urbanized Ecosystem: a Case Study in Northern Taiwan - Pin-Yuan Chen; Cheng-Tao Lin; Rita S. W. Yam; Hsiao-Wei Yuan (Wetlands, 2020)

Magnesium biofortification of Italian ryegrass (Lolium multiflorum L.) via agronomy and breeding as a potential way to reduce grass tetany in grazing ruminants - Diriba B. Kumssa; J. Alan Lovatt; Neil S. Graham; Sarah Palmer; Rory Hayden; Lolita Wilson; Scott D. Young; R. Murray Lark; Beth Penrose; E. Louise Ander; Russell Thompson; Lin-Xi Jiang; et al. (Plant and Soil, 2020)
Aim Magnesium (Mg) deficiency (known as grass tetany) is a serious metabolic disorder that affects grazing ruminants. We tested whether Mg-fertiliser can increase Mg concentration of Italian ryegrasses ( Lolium multiflorum L.) including a cultivar (cv. Bb2067; ‘Magnet’), bred to accumulate larger concentrations of Mg. Methods Under controlled environment (CE) conditions, three cultivars (cv. Bb2067, cv. Bb2068, cv. RvP) were grown in low-nutrient compost at six fertiliser rates (0–1500 μM MgCl 2 .6H 2 O). Under field conditions, the three cultivars in the CE condition and cv. Alamo were grown at two sites, and four rates of MgSO 4 fertiliser application rates (0–200 kg ha −1 MgO). Multiple grass cuts were taken over two-years. Results Grass Mg concentration increased with increasing Mg-fertiliser application rates in all cultivars and conditions. Under field conditions, cv. Bb2067 had 11–73% greater grass Mg concentration and smaller forage tetany index (FTI) than other cultivars across the Mg-fertiliser application rates, sites and cuts. Grass dry matter (DM) yield of cv. Bb2067 was significantly ( p < 0.05) smaller than cv. Alamo. The effect of Mg-fertiliser rate on DM yield was not significant ( p ≥ 0.05). Conclusions Biofortification of grass with Mg through breeding and agronomy can improve the forage Mg concentration for grazing ruminants, even in high-growth spring grass conditions when hypomagnesaemia is most prevalent. Response to agronomic biofortification varied with cultivar, Mg-fertiliser rate, site and weather. The cost:benefit of these approaches and farmer acceptability, and the impact on cattle and sheep grazing on grasses biofortified with Mg requires further investigation.

Exposure to a high dose of amoxicillin causes behavioral changes and oxidative stress in young zebrafish - Cinara L. Gonçalves; Francine F. P. Vasconcelos; Leticia B. Wessler; Isabela S. Lemos; Gabriela Candiotto; Jaime Lin; Mariane B. D. Matias; Eduardo P. Rico; Emilio L. Streck (Metabolic Brain Disease, 2020)

Assessment of Applications of Design of Experiments in Pharmaceutical Development for Oral Solid Dosage Forms - Ge Bai; Zhijin Chen; Kimberly Raines; Hansong Chen; Kaushalkumar Dave; Ho-Pi Lin; Banu S. Zolnik (Journal of Pharmaceutical Innovation, 2020)

Dietary exposure assessment of cadmium, arsenic, and lead in market rice from Sri Lanka - Lin Liu; Jialiang Han; Xiaohang Xu; Zhidong Xu; Kasun S. Abeysinghe; Anjana J. Atapattu; P. Mangala C. S. De Silva; Qinhui Lu; Guangle Qiu (Environmental Science and Pollution Research, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Regional drivers of diversification in the late Quaternary in a widely distributed generalist species, the common pheasant Phasianus colchicus - Simin Liu; Yang Liu; Edouard Jelen; Mansour Alibadian; Cheng‐Te Yao; Xintong Li; Nasrin Kayvanfar; Yutao Wang; Farhad S. M. Vahidi; Jian‐Lin Han; Gombobaatar Sundev; Zhengwang Zhang; et al. (Journal of Biogeography, 2020)
Aim Pleistocene climate and associated environmental changes have influenced phylogeographic patterns of many species. These not only depend on a species’ life history but also vary regionally. Consequently, populations of widespread species that occur in several biomes might display different evolutionary trajectories. We aimed to identify regional drivers of diversification in the common pheasant, a widely distributed ecological generalist. Location Asia. Taxon Common pheasant Phasianus colchicus . Methods Using a comprehensive geographical sampling of 204 individuals from the species’ entire range genotyped at seven nuclear and two mitochondrial loci, we reconstructed spatio‐temporal diversification and demographic history of the common pheasant. We applied Bayesian phylogenetic inference to describe phylogeographic structure, generated a species tree and inferred demographic history within and migration between lineages. Moreover, to establish a taxonomic framework, we conducted a species delimitation analysis. Results The common pheasant diversified during the Late Pleistocene into eight distinct lineages. It originated at the edge of the Qinghai–Tibetan plateau and spread to East and Central Asia. Only the widely distributed lowland lineage of East Asia displayed recent range expansion. Greater phylogeographic structure was identified elsewhere, with lineages showing no sign of recent demographic changes. One lineage in south‐central China is the result of long‐term isolation within a climatically stable but topographically complex region. In lineages from arid Central Asia and China, range expansions were impeded by repeated population fragmentation during dry glacial periods and by recent aridification. Main conclusions Spatio‐temporal phylogeographic frameworks of widespread taxa such as the common pheasant provide valuable opportunities to identify divergent drivers of regional diversification. Our results suggest that diversification and population histories in the eight distinct evolutionary lineages were shaped by regionally variable effects of past climate and associated environmental changes. The evolutionary history of the common pheasant is best reflected by its being split into three species.

Effect of Liposome-Encapsulated Zoledronic Acid on Microenvironment of Hepatocellular Carcinoma May Depend on the Ratio Between M1 and M2 Polarized Macrophages - S. Wu; X. Lin; X. Cui (Bulletin of Experimental Biology and Medicine, 2020)

Advanced psychometric testing on a clinical screening tool to evaluate insomnia: sleep condition indicator in patients with advanced cancer - Chung-Ying Lin; Andy S. K. Cheng; Vida Imani; Mohsen Saffari; Maurice M. Ohayon; Amir H. Pakpour (Sleep and Biological Rhythms, 2020)
Purpose To examine the psychometric properties of the Sleep Condition Indicator (SCI) using different psychometric approaches [including classical test theory, Rasch models, and receiver operating characteristics (ROC) curve] among patients with advanced cancer. Methods Through convenience sampling, patients with cancer at stage III or IV ( n = 859; 511 males; mean ± SD age = 67.4 ± 7.5 years) were recruited from several oncology units of university hospitals in Iran. All the participants completed the SCI, Insomnia Severity Index (ISI), Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale (ESS), Hospital Anxiety and Depression Scale (HADS), General Health Questionnaire (GHQ), and Edmonton Symptom Assessment Scale (ESAS). In addition, 491 participants wore an actigraph device to capture objective sleep. Results Classical test theory [factor loadings from confirmatory factor analysis = 0.76–0.89; test–retest reliability = 0.80–0.93] and Rasch analysis [infit mean square (MnSq) = 0.63–1.31; outfit MnSq = 0.61–1.23] both support the construct validity of the SCI. The SCI had significant associations with ISI, PSQI, ESS, HADS, GHQ, and ESAS. In addition, the SCI has satisfactory area under ROC curve (0.92) when comparing a gold standard of insomnia diagnosis. Significant differences in the actigraphy measure were found between insomniacs and non-insomniacs based on the SCI score defined by ROC. Conclusion With the promising psychometric properties shown in the SCI, healthcare providers can use this simple assessment tool to target the patients with advanced cancer who are at risk of insomnia and subsequently provide personalized care efficiently.

Peripheral ProBDNF Delivered by an AAV Vector to the Muscle Triggers Depression-Like Behaviours in Mice - L. Y. Lin; S. Kelliny; L. C. Liu; M. Al-Hawwas; X. F. Zhou; L. Bobrovskaya (Neurotoxicity Research, 2020)

Zooplankton in a continuous waterscape: environmental and spatial factors shaping spring zooplankton community structure in a large canyon reservoir at the tropic of cancer - Eric Zeus C. Rizo; Ping Liu; Haiyu Niu; Yang Yang; Qiuqi Lin; Rey Donne S. Papa; Henri J. Dumont; Bo-Ping Han (Hydrobiologia, 2020)

A magnetic resonance spectroscopy investigation in symptomatic former NFL players - Michael L. Alosco; Yorghos Tripodis; Benjamin Rowland; Alicia S. Chua; Huijun Liao; Brett Martin; Johnny Jarnagin; Christine E. Chaisson; Ofer Pasternak; Sarina Karmacharya; Inga K. Koerte; Robert C. Cantu; et al. (Brain Imaging and Behavior, 2020)

PBPK modeling of CYP3A and P-gp substrates to predict drug–drug interactions in patients undergoing Roux-en-Y gastric bypass surgery - Kuan-Fu Chen; Lingtak-Neander Chan; Yvonne S. Lin (Journal of Pharmacokinetics and Pharmacodynamics, 2020)

Enhanced Biosorption of Sb(III) onto Living Rhodotorula mucilaginosa Strain DJHN070401: Optimization and Mechanism - Chang-sheng Jin; Ren-jian Deng; Bo-zhi Ren; Bao-lin Hou; Andrew S. Hursthouse (Current Microbiology, 2020)

Climate change considerations are fundamental to management of deep‐sea resource extraction - Lisa A. Levin; Chih‐Lin Wei; Daniel C. Dunn; Diva J. Amon; Oliver S. Ashford; William W. L. Cheung; Ana Colaço; Carlos Dominguez‐Carrió; Elva G. Escobar; Harriet R. Harden‐Davies; Jeffrey C. Drazen; Khaira Ismail; et al. (Global Change Biology, 2020)
Climate change manifestation in the ocean, through warming, oxygen loss, increasing acidification, and changing particulate organic carbon flux (one metric of altered food supply), is projected to affect most deep‐ocean ecosystems concomitantly with increasing direct human disturbance. Climate drivers will alter deep‐sea biodiversity and associated ecosystem services, and may interact with disturbance from resource extraction activities or even climate geoengineering. We suggest that to ensure the effective management of increasing use of the deep ocean (e.g., for bottom fishing, oil and gas extraction, and deep‐seabed mining), environmental management and developing regulations must consider climate change. Strategic planning, impact assessment and monitoring, spatial management, application of the precautionary approach, and full‐cost accounting of extraction activities should embrace climate consciousness. Coupled climate and biological modeling approaches applied in the water and on the seafloor can help accomplish this goal. For example, Earth‐System Model projections of climate‐change parameters at the seafloor reveal heterogeneity in projected climate hazard and time of emergence (beyond natural variability) in regions targeted for deep‐seabed mining. Models that combine climate‐induced changes in ocean circulation with particle tracking predict altered transport of early life stages (larvae) under climate change. Habitat suitability models can help assess the consequences of altered larval dispersal, predict climate refugia, and identify vulnerable regions for multiple species under climate change. Engaging the deep observing community can support the necessary data provisioning to mainstream climate into the development of environmental management plans. To illustrate this approach, we focus on deep‐seabed mining and the International Seabed Authority, whose mandates include regulation of all mineral‐related activities in international waters and protecting the marine environment from the harmful effects of mining. However, achieving deep‐ocean sustainability under the UN Sustainable Development Goals will require integration of climate consideration across all policy sectors.

Cytotoxicity, cellular localization and photophysical properties of Re(I) tricarbonyl complexes bound to cysteine and its derivatives - Miles S. Capper; Alejandra Enriquez Garcia; Nicolas Macia; Barry Lai; Jian-Bin Lin; Masaharu Nomura; Amir Alihosseinzadeh; Sathish Ponnurangam; Belinda Heyne; Carrie S. Shemanko; Farideh Jalilehvand (JBIC Journal of Biological Inorganic Chemistry, 2020)

Correction to: Potato Cultivar Susceptibility to Pythium Leak as Influenced by Harvest and Early Storage Temperatures - Andrew K Hollingshead; Nora L. Olsen; Mike Thornton; Jeff S. Miller; Amy Hui-Mei Lin (American Journal of Potato Research, 2020)

Potato Cultivar Susceptibility to Pythium Leak as Influenced by Harvest and Early Storage Temperatures - Andrew K Hollingshead; Nora L. Olsen; Mike Thornton; Jeff S. Miller; Amy Hui-Mei Lin (American Journal of Potato Research, 2020)

A System Level Analysis of Coastal Ecosystem Responses to Hurricane Impacts - C. J. Patrick; L. Yeager; A. R. Armitage; F. Carvallo; V. M. Congdon; K. H. Dunton; M. Fisher; A. K. Hardison; J. D. Hogan; J. Hosen; X. Hu; B. Kiel Reese; et al. (Estuaries and Coasts, 2020)

Oxidation of nine petroleum hydrocarbon compounds by combined hydrogen peroxide/sodium persulfate catalyzed by siderite - YueHua Li; Lin Zhao; Fulong Chen; Kylan S. Jin; Paul H. Fallgren; Liang Chen (Environmental Science and Pollution Research, 2020)

A Major Hydrothermal Reservoir Underneath the Tatun Volcano Group of Taiwan: Clues from a Dense Linear Geophone Array - C. H. Lin; Y. C. Lai; M. H. Shih; C. J. Lin; J. S. Ku; Y. C. Huang (Pure and Applied Geophysics, 2020)
A dense linear geophone array is deployed across the Tatun volcano group (TVG) at the northern tip of Taiwan, where more than 7 million residents live in the Taipei metropolis. The array is composed of 50 geophones with a station spacing of ~ 200 m in average, and it is designed for striking in the NW–SE direction to record the many earthquakes in eastern Taiwan, where the Philippine Sea plate subducted beneath the Eurasia plate. The detailed examination of felt earthquakes shows consistent P-wave delays are recorded at particular stations of the array. The further forward modeling indicates there is a low-velocity zone (LVZ) at depths between ~ 0.5 and ~ 2.5 km beneath the major fumarole sites. Combining this preliminary result with previous studies including clustering seismicity, volcanic earthquakes, low-resistivity zone, strong degassing processes and shallow velocity structures, we suggest that the LVZ might be associated with the major hydrothermal reservoir at the TVG. The identification of the hydrothermal reservoir by the LVZ not only implies a potential volcanic threat, such as phreatic eruptions, in the future, but also provides the possibility of sustainable geothermal resources for replacing traditional nuclear and fossil fuel power plants. Detailed images of the LVZ and other volcanic structures will be obtained soon when dense geophone arrays with more than 600 geophones are deployed from 2020 to 2022.

Leaf-mimicking katydids from the Middle Miocene of Yunnan, southwestern China (Orthoptera: Tettigoniidae) - André Nel; Bo Wang; Michael S. Engel; Jian Huang; Lin-Bo Jia; Tao Su; Torsten Wappler (PalZ, 2020)

DNA methylation and histone acetylation changes to cytochrome P450 2E1 regulation in normal aging and impact on rates of drug metabolism in the liver - Mohamad M. Kronfol; Fay M. Jahr; Mikhail G. Dozmorov; Palak S. Phansalkar; Lin Y. Xie; Karolina A. Aberg; MaryPeace McRae; Elvin T. Price; Patricia W. Slattum; Philip M. Gerk; Joseph L. McClay (GeroScience, 2020)

Non-Invasive Quantification of Ventricular Contractility, Arterial Elastic Function and Ventriculo-Arterial Coupling from a Single Diagnostic Encounter Using Simultaneous Arterial Tonometry and Magnetic Resonance Imaging - Mayooran Namasivayam; Audrey Adji; Linda Lin; Christopher S. Hayward; Michael P. Feneley; Michael F. O’Rourke; David W. M. Muller; Andrew Jabbour (Cardiovascular Engineering and Technology, 2020)

Coupling virio- and bacterioplankton populations with environmental variable changes in the Bohai Sea - Caixia Wang; Lin Wu; Yibo Wang; James S. Paterson; James G. Mitchell; Xiaoke Hu (Acta Oceanologica Sinica, 2020)

Assessment of ammonium fertilization as a stimulus for proline accumulation in Oryza sativa L. during cyanide assimilation - W. Liu; X.-Z. Yu; S.-Y. Lei; L. Yang; Y.-J. Lin (International Journal of Environmental Science and Technology, 2020)

Formation mechanism of a rainfall triggered complex landslide in southwest China - Qiu-xiang Huang; Xiang-tao Xu; P. H. S. W. Kulatilake; Feng Lin (Journal of Mountain Science, 2020)

A deep-level region-based visual representation architecture for detecting strawberry flowers in an outdoor field - P. Lin; W. S. Lee; Y. M. Chen; N. Peres; C. Fraisse (Precision Agriculture, 2020)

Protein Arginine Methyltransferases in Cardiovascular and Neuronal Function - Alexandre Couto e Silva; Celeste Yin-Chieh Wu; Cristiane T. Citadin; Garrett A. Clemons; HarLee E. Possoit; Mychal S. Grames; Chih-Feng Lien; Alireza Minagar; Reggie Hui-Chao Lee; Adam Frankel; Hung Wen Lin (Molecular Neurobiology, 2020)

A new slice-based method for calculating the minimum safe thickness for a filled-type karst cave - Z. H. Xu; X. Huang; S. C. Li; P. Lin; X. S. Shi; J. Wu (Bulletin of Engineering Geology and the Environment, 2020)

Allelopathy confers an invasive Wedelia higher resistance to generalist herbivore and pathogen enemies over its native congener - Shan-Shan Qi; Yan-Jie Liu; Zhi-Cong Dai; Ling-Yun Wan; Dao-Lin Du; Rui-Ting Ju; Justin S. H. Wan; Stephen P. Bonser (Oecologia, 2020)

Association between lifestyle, dietary, reproductive, and anthropometric factors and circulating 27-hydroxycholesterol in EPIC-Heidelberg - Charlotte Le Cornet; Theron S. Johnson; Da-Lin Lu; Rudolf Kaaks; Renée Turzanski Fortner (Cancer Causes & Control, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

Inflammation-related genes are associated with epigenetic aging in HIV - Erin E. Sundermann; Mariam A. Hussain; David J. Moore; Steven Horvath; David T. S. Lin; Michael S. Kobor; Andrew Levine (Journal of NeuroVirology, 2019)

The Impact of Satellite Radiance Data Assimilation within a Frequently Updated Regional Forecast System Using a GSI-based Ensemble Kalman Filter - Kefeng Zhu; Ming Xue; Yujie Pan; Ming Hu; Stanley G. Benjamin; Stephen S. Weygandt; Haidao Lin (Advances in Atmospheric Sciences, 2019)

A changed post‐flood management strategy enables the culture‐based fishery of the Liangzi Lake, Yangtze River Basin, China, to remain economically and environmentally viable - Qidong Wang; Zhongjie Li; Mingli Lin; Shaowe Ye; Wei Li; Chuanbo Guo; Geng Huang; Jing Yuan; Jiashou Liu; Sena S. De Silva (Fisheries Management and Ecology, 2019)
The culture‐based fishery of Liangzi Lake, Yangtze River Basin, established in 1992, yielded 2,652 t/year (±167) between 2005 and 2015, dominated by stocked carps [ Hypophthalmichthys molitrix (Val.) and Hypophthalmichthys nobilis (Richardson)] and mitten crab Eriocheir sinensis (Milne Edwards), accounting for 53% and 23% of the production and 20% and 52% in value, respectively. The lake had a macrophyte cover dominated by Vallisneria natans (Lour.) Hara with a cumulative biomass of 10,647 g/m 2 that disappeared after a major flood in 2010 and changed its ecology. Management changes in stocking strategies introduced in the post‐flood period enabled the culture‐based fishery to maintain viability and sustainability to combat the major ecological change in the lake. The stocked species contributed significantly to nutrient removal of 24.71 ± 5.12 t/yr and 6.29 ± 0.87 t/yr of total nitrogen and total phosphorus, respectively.

Effect of Peptide AEDG on Telomere Length and Mitotic Index of PHA-Stimulated Human Blood Lymphocytes - V. Kh. Khavinson; A. A. Pendina; O. A. Efimova; A. V. Tikhonov; A. S. Koltsova; M. I. Krapivin; A. V. Petrovskaia-Kaminskaia; L. I. Petrova; N. S. Lin’kova; V. S. Baranov (Bulletin of Experimental Biology and Medicine, 2019)

Variance in the response of silcrete to rapid heating complicates assumptions about past heat treatment methods - Alex Mackay; Sam C. Lin; Lachlan S. Kenna; Alex F. Blackwood (Archaeological and Anthropological Sciences, 2019)

Bismuth(III) interactions with Desulfovibrio desulfuricans: inhibition of cell energetics and nanocrystal formation of Bi2S3 and Bi0 - Larry L. Barton; Alex S. Granat; Seungyeol Lee; Huifang Xu; Nathaniel L. Ritz; Robert Hider; Henry C. Lin (BioMetals, 2019)

Organic Carbon in the Surface Sediments from the Intensive Mariculture Zone of Sanggou Bay: Distribution, Seasonal Variations and Sources - Juanjuan Sui; Jihong Zhang; S. Jeffrey Ren; Fan Lin (Journal of Ocean University of China, 2019)

Forest community assembly is driven by different strata‐dependent mechanisms along an elevational gradient - Ya‐Huang Luo; Marc W. Cadotte; Kevin S. Burgess; Jie Liu; Shao‐Lin Tan; Kun Xu; De‐Zhu Li; Lian‐Ming Gao (Journal of Biogeography, 2019)
Aim The mechanisms driving forest community assembly along elevational gradients remain elusive. The distinct strata in heterogeneous forest are subject to differing assembly mechanisms. This study aims to evaluate how different ecological mechanisms driving forest community assembly across strata and spatial scales, and to identify how these assemblages respond to different abiotic or biotic variables along an elevational gradient. Location Yulong Mountain within Hengduan Mountains, Southwest China. Taxon Seed plants. Methods We sampled plant species along a 1,200 m elevational gradient across forest strata (trees, shrubs and herbs) at different spatial scales (neighbourhood and community). We integrated phylogenetic and functional diversity to disentangle the roles of ecological mechanisms in structuring community assembly. We also determined the relative effects of climatic, soil and biotic variables and their interactions on these community assemblages. Results The phylogenetic and functional diversity of trees were lower at the extremes of the elevational gradient, where they were constrained by water availability or temperature. While communities with higher species diversity exhibited an overdispersed structure at mid‐elevations. For shrubs, overdispersion was exhibited at high elevations despite low species richness, which could be consistent with facilitative interactions or competition exclusion. However, most communities of herbs appear to have a markedly random structure, despite some incongruence between phylogenetic divergence and functional convergence, as well as influences from overstorey trees and local light conditions. The relative effects of abiotic variables on community structure were larger at the community scale than at the neighbourhood scale. Main conclusions Our study emphasises the importance of considering phylogenies and traits in understanding the strata‐ and scale‐dependent mechanisms of forest community assembly. Collectively, results indicate that contrasting assembly mechanisms interact across different strata along elevational gradients to shape diverse forest communities.

Crops For the Future (CFF): an overview of research efforts in the adoption of underutilised species - Peter J. Gregory; Sean Mayes; Chai Hui Hui; Ebrahim Jahanshiri; Advina Julkifle; Giva Kuppusamy; Ho Wai Kuan; Tan Xin Lin; Festo Massawe; T. A. S. T. M. Suhairi; Sayed N. Azam-Ali (Planta, 2019)

The Long-Term Effects of Ethanol and Corticosterone on the Mood-Related Behaviours and the Balance Between Mature BDNF and proBDNF in Mice - L. Y. Lin; S. Y. Luo; M. Al-Hawwas; M. F. Herselman; X. F. Zhou; Larisa Bobrovskaya (Journal of Molecular Neuroscience, 2019)

Assessment of formaldehyde levels in relation to respiratory and allergic symptoms in children from Alba County schools, Romania - Iulia A. Neamtiu; Shao Lin; Menglan Chen; Carmen Roba; Eva Csobod; Eugen S. Gurzau (Environmental Monitoring and Assessment, 2019)

The Eurasian Jet Streams as Conduits for East Asian Monsoon Variability - Jasti S. Chowdary; Kaiming Hu; G. Srinivas; Yu Kosaka; Lin Wang; K. Koteswara Rao (Current Climate Change Reports, 2019)

Greater than the sum of the parts: how the species composition in different forest strata influence ecosystem function - Ya‐Huang Luo; Marc W. Cadotte; Kevin S. Burgess; Jie Liu; Shao‐Lin Tan; Jia‐Yun Zou; Kun Xu; De‐Zhu Li; Lian‐Ming Gao (Ecology Letters, 2019)
The mechanisms underpinning forest biodiversity‐ecosystem function relationships remain unresolved. Yet, in heterogeneous forests, ecosystem function of different strata could be associated with traits or evolutionary relationships differently. Here, we integrate phylogenies and traits to evaluate the effects of elevational diversity on above‐ground biomass across forest strata and spatial scales. Community‐weighted means of height and leaf phosphorous concentration and functional diversity in specific leaf area exhibited positive correlations with tree biomass, suggesting that both positive selection effects and complementarity occur. However, high shrub biomass is associated with greater dissimilarity in seed mass and multidimensional trait space, while species richness or phylogenetic diversity is the most important predictor for herbaceous biomass, indicating that species complementarity is especially important for understory function. The strength of diversity‐biomass relationships increases at larger spatial scales. We conclude that strata‐ and scale‐ dependent assessments of community structure and function are needed to fully understand how biodiversity influences ecosystem function.

ARID1A, Prostaglandin E2, and Its Receptor as Possible Predictors of Malignant Transformation of the Endometrium in Endometriosis - A. S. Dyatlova; N. S. Lin’kova; V. O. Polyakova; N. G. Samoshkin; I. M. Kvetnoi (Bulletin of Experimental Biology and Medicine, 2019)

Ocean Climate Observing Requirements in Support of Climate Research and Climate Information - Detlef Stammer; Annalisa Bracco; Krishna AchutaRao; Lisa Beal; Nathaniel L. Bindoff; Pascale Braconnot; Wenju Cai; Dake Chen; Matthew Collins; Gokhan Danabasoglu; Boris Dewitte; Riccardo Farneti; et al. (Frontiers in Marine Science, 2019)

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

The return of the frogs: The importance of habitat refugia in maintaining diversity during a disease outbreak - Donald T. McKnight; Monal M. Lal; Deborah S. Bower; Lin Schwarzkopf; Ross A. Alford; Kyall R. Zenger (Molecular Ecology, 2019)
Recent decades have seen the emergence and spread of numerous infectious diseases, often with severe negative consequences for wildlife populations. Nevertheless, many populations survive the initial outbreaks, and even undergo recoveries. Unfortunately, the long‐term effects of these outbreaks on host population genetics are poorly understood; to increase this understanding, we examined the population genetics of two species of rainforest frogs ( Litoria nannotis and Litoria serrata ) that have largely recovered from a chytridiomycosis outbreak at two national parks in the Wet Tropics of northern Australia. At the wetter, northern park there was little evidence of decreased genetic diversity in either species, and all of the sampled sites had high minor allele frequencies (mean MAF = 0.230–0.235), high heterozygosity (0.318–0.325), and few monomorphic markers (1.4%–4.0%); however, some recovered L. nannotis populations had low N e values (59.3–683.8) compared to populations that did not decline during the outbreak (1,537.4–1,756.5). At the drier, southern park, both species exhibited lower diversity (mean MAF = 0.084–0.180; heterozygosity = 0.126–0.257; monomorphic markers = 3.7%–43.5%; N e = 18.4–676.1). The diversity patterns in this park matched habitat patterns, with both species having higher diversity levels and fewer closely related individuals at sites with higher quality habitat. These patterns were more pronounced for L. nannotis, which has lower dispersal rates than L. serrata . These results suggest that refugia with high quality habitat are important for retaining genetic diversity during disease outbreaks, and that gene flow following disease outbreaks is important for re‐establishing diversity in populations where it was reduced.

Transcription Factor 2I Regulates Neuronal Development via TRPC3 in 7q11.23 Disorder Models - Marielle H. S. Deurloo; Ekaterina Turlova; Wen-Liang Chen; You Wei Lin; Elaine Tam; Nardos G. Tassew; Michael Wu; Ya-Chi Huang; Jacqueline N. Crawley; Philippe P. Monnier; Alexander J. A. Groffen; Hong-Shuo Sun; et al. (Molecular Neurobiology, 2019)

Climate of the weakly-forced yet high-impact convective storms throughout the Ohio River Valley and Mid-Atlantic United States - Binod Pokharel; S.-Y. Simon Wang; Jonathan Meyer; Robert Gillies; Yen-Heng Lin (Climate Dynamics, 2019)

Skin Fibroblasts as the Object for Clinical Diagnosis of Parkinson’s Disease in Persons of Different Ages - V. A. Zuev; A. S. Dyatlova; N. S. Lin’kova; I. M. Kvetnoi; N. N. Belushkina; V. A. Pal’tsev (Bulletin of Experimental Biology and Medicine, 2019)

The Gramian Method of Joint Inversion of the Gravity Gradiometry and Seismic Data - Wei Lin; Michael S. Zhdanov (Pure and Applied Geophysics, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Bioavailability of selenium in soil-plant system and a regulatory approach - Quang Toan Dinh; Mengke Wang; Thi Anh Thu Tran; Fei Zhou; Dan Wang; Hui Zhai; Qin Peng; Mingyue Xue; Zekun Du; Gary S. Bañuelos; Zhi-Qing Lin; Dongli Liang (Critical Reviews in Environmental Science and Technology, 2019)

Precipitable water and CAPE dependence of rainfall intensities in China - Wenhao Dong; Yanluan Lin; Jonathon S. Wright; Yuanyu Xie; Xungang Yin; Jianping Guo (Climate Dynamics, 2019)

Exposure of consumers and farmers to organophosphate and synthetic pyrethroid insecticides in Northern Thailand - Surat Hongsibsong; Tippawan Prapamontol; Jie-Xian Dong; Candace S. Bever; Zhen-Lin Xu; Shirley J. Gee; Bruce D. Hammock (Journal of Consumer Protection and Food Safety, 2019)

Expression of Aβ42, τ-Protein, p16, p53 in Buccal Epithelium: Prospects for Use in the Diagnostics of Alzheimer’s Disease and Rate of Aging - V. A. Zuev; A. S. Dyatlova; N. S. Lin’kova; T. V. Kvetnaya (Bulletin of Experimental Biology and Medicine, 2019)

Tropical Pacific Observing System - Neville Smith; William S. Kessler; Sophie Cravatte; Janet Sprintall; Susan Wijffels; Meghan F. Cronin; Adrienne Sutton; Yolande L. Serra; Boris Dewitte; Peter G. Strutton; Katherine Hill; Alex Sen Gupta; et al. (Frontiers in Marine Science, 2019)

Genome-wide analysis identified 17 new loci influencing intraocular pressure in Chinese population - Lulin Huang; Yuhong Chen; Ying Lin; Pancy O. S. Tam; Yilian Cheng; Yi Shi; Bo Gong; Fang Lu; Jialiang Yang; Haixin Wang; Yi Yin; Yong Cao; et al. (Science China Life Sciences, 2019)

A possible mechanism for the occurrence of wintertime extreme precipitation events over South China - Wenyu Huang; Zifan Yang; Xinsheng He; Daiyu Lin; Bin Wang; Jonathon S. Wright; Ruyan Chen; Wenqian Ma; Feifei Li (Climate Dynamics, 2019)

Identify a shared neural circuit linking multiple neuropsychiatric symptoms with Alzheimer’s pathology - Xixi Wang; Ping Ren; Mark Mapstone; Yeates Conwell; Anton P. Porsteinsson; John J. Foxe; Rajeev D. S. Raizada; Feng Lin (Brain Imaging and Behavior, 2019)

Investigation of infiltration rate for soil-biochar composites of water hyacinth - Phani Gopal; Sanandam Bordoloi; Raval Ratnam; Peng Lin; Weiling Cai; Poly Buragohain; Ankit Garg; S. Sreedeep (Acta Geophysica, 2019)

Influence of soil variability on single and competitive interaction of ammonium and potassium: experimental study on seven different soils - Poly Buragohain; S. Sreedeep; Peng Lin; Junjun Ni; Ankit Garg (Journal of Soils and Sediments, 2019)

The contribution of parent-to-offspring transmission of telomeres to the heritability of telomere length in humans - Dayana A. Delgado; Chenan Zhang; Kevin Gleason; Kathryn Demanelis; Lin S. Chen; Jianjun Gao; Shantanu Roy; Justin Shinkle; Mekala Sabarinathan; Maria Argos; Lin Tong; Alauddin Ahmed; et al. (Human Genetics, 2019)

What Promotes the Recovery of Salt Marsh Infauna After Oil Spills? - J. W. Fleeger; M. R. Riggio; I. A. Mendelssohn; Q. Lin; D. R. Deis; D. S. Johnson; K. R. Carman; S. A. Graham; S. Zengel; A. Hou (Estuaries and Coasts, 2019)

Unidirectional monosynaptic connections from auditory areas to the primary visual cortex in the marmoset monkey - Piotr Majka; Marcello G. P. Rosa; Shi Bai; Jonathan M. Chan; Bing-Xing Huo; Natalia Jermakow; Meng K. Lin; Yeonsook S. Takahashi; Ianina H. Wolkowicz; Katrina H. Worthy; Ramesh Rajan; David H. Reser; et al. (Brain Structure and Function, 2019)

Evaluation of lead release potential of new premise plumbing materials - Iat-Leong Lei; Ding-Quan Ng; Shailesh S. Sable; Yi-Pin Lin (Environmental Science and Pollution Research, 2018)

Black race and distant recurrence after neoadjuvant or adjuvant chemotherapy in breast cancer - Jessica M. Pastoriza; George S. Karagiannis; Juan Lin; Sonali Lanjewar; David Entenberg; John S. Condeelis; Joseph A. Sparano; Xiaonan Xue; Thomas E. Rohan; Maja H. Oktay (Clinical & Experimental Metastasis, 2018)

Aeromonas shuberti as a cause of multi‐organ necrosis in internal organs of Nile tilapia, Oreochromis niloticus - C Liu; O Q Chang; D F Zhang; K B Li; F Wang; M H Lin; C B Shi; L Jiang; Q Wang; S M Bergmann (Journal of Fish Diseases, 2018)
A disease with white spots in internal organs of Nile tilapia occurred in Zhanjiang, southern China. Multiple, white nodules, 0.8–2.2 mm in diameter, were scattered throughout the liver, spleen and kidney of diseased fish. Signs of nodules reproduced after artificial infection with the isolated strain. Isolated bacteria were Gram‐negative, facultative anaerobic, motile, short rod‐shaped, with a length of 1.2–2.2 μm. Morphological and biochemical tests, as well as phylogenetic analysis, all strongly indicated that the isolate from tilapia is identical to Aeromonas schubertii ( A. schubertii) which temporary named LF 1708 strain. Antibiotic sensitivity assays showed the LF 1708 is sensitive to 24 of 27 tested antibiotics. Pathogenicity test revealed that the isolate at the dose of 3.75 × 10 6 CFU /g killed 100% of experimental tilapia within 2 days and the dose of 1 × 10 7 CFU /g killed 100% of experimental zebrafish within 1 day. Histopathology of diseased tilapia infected with A. schubertii showed numerous necrotic lesions widely distributed in spleen, liver and kidney, and infiltration with a large number of bacteria. To our knowledge, this was the first report that associated A. schubertii with mortality in tilapia.

A Comparative Placebo-Controlled Clinical Trial of the Efficacy and Safety of Interferon β-1a Formulations for S.C. Administration in Patients with Remitting Multiple Sclerosis: First-Year Results - A. N. Boiko; L. P. Bosenko; V. V. Vasilovskii; L. I. Volkova; M. N. Zakharova; S. V. Kotov; E. V. Lekomtseva; T. I. Negrich; E. V. Parshina; O. P. Patrusheva; S. V. Prokopenko; D. V. Sazonov; et al. (Neuroscience and Behavioral Physiology, 2018)

An Attempt to Find a Suitable Biomass for Biochar-Based Polypropylene Biocomposites - Oisik Das; Nam Kyeun Kim; Mikael S. Hedenqvist; Richard J. T. Lin; Ajit K. Sarmah; Debes Bhattacharyya (Environmental Management, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Diversity of the cyrtophorid genus Chlamydodon (Protista, Ciliophora): its systematics and geographic distribution, with taxonomic descriptions of three species - Zhishuai Qu; Lifang Li; Xiaofeng Lin; Thorsten Stoeck; Hongbo Pan; Khaled A. S. Al-Rasheid; Weibo Song (Systematics and Biodiversity, 2018)

Attenuated cocaine-seeking after oxytocin administration in male and female rats - Amy S. Kohtz; Belle Lin; Michael E. Smith; Gary Aston-Jones (Psychopharmacology, 2018)

Effects of acute morphine withdrawal on ultrasonic vocalizations in adult rats: unchanged 50-kHz call rate and altered subtype profile - YiQi C. Lin; Leah L. Zhao; Paul B. S. Clarke (Psychopharmacology, 2018)

Design of alternate solvent for recovery of residual palm oil: simultaneous optimization of process performance with environmental, health and safety aspects - Sarah Sue Lin Chang; Yuan Lin Kong; Wei Xuen Lim; Jecksin Ooi; Denny K. S. Ng; Nishanth G. Chemmangattuvalappil (Clean Technologies and Environmental Policy, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Arbuscular mycorrhizal fungi stimulate organic phosphate mobilization associated with changing bacterial community structure under field conditions - Lin Zhang; Ning Shi; Jiequn Fan; Fei Wang; Timothy S. George; Gu Feng (Environmental Microbiology, 2018)
Summary The extraradical hyphae of arbuscular mycorrhizal fungi (AMF) harbour and interact with a microbial community performing multiple functions. However, how the AMF‐microbiome interaction influences the phosphorus (P) acquisition efficiency of the mycorrhizal pathway is unclear. Here we investigated whether AMF and their hyphal microbiome play a role in promoting organic phosphorus (P) mineralizing under field conditions. We developed an AMF hyphae in‐growth core system for the field using PVC tubes sealed with membrane with different size of pores (30 or 0.45 μm) to allow or deny AMF hyphae access to a patch of organic P in root‐free soil. AMF and their hyphae associated microbiome played a role in enhancing soil organic P mineralization in situ in the field, which was shown to be a function of the change in bacteria community on the hyphae surface. The bacterial communities attached to the AMF hyphae surface were significantly different from those in the bulk soil. Importantly, AMF hyphae recruited bacteria that produced alkaline phosphatase and provided a function that was absent from the hyphae. These results demonstrate the importance of understanding trophic interactions to be able to gain insight into the functional controls of nutrient cycles in the rhizosphere.

The effect of temperature on the developmental rates of seedling emergence and leaf-unfolding in two dwarf bamboo species - Shuyan Lin; Lijuan Shao; Cang Hui; Hardev S. Sandhu; Tingting Fan; Li Zhang; Fang Li; Yulong Ding; Peijian Shi (Trees, 2018)

Bacillus Probiotic Supplementations Improve Laying Performance, Egg Quality, Hatching of Laying Hens, and Sperm Quality of Roosters - Maria S. Mazanko; Ivan F. Gorlov; Evgeniya V. Prazdnova; Maxim S. Makarenko; Alexander V. Usatov; Anzhelika B. Bren; Vladimir A. Chistyakov; Alexey V. Tutelyan; Zoya B. Komarova; Natalia I. Mosolova; Denis N. Pilipenko; Olga E. Krotova; et al. (Probiotics and Antimicrobial Proteins, 2018)

DNA Barcoding for Identification of Sugarcane Borers in China - J- D Wang; W- Z Wang; Z- L Lin; A Ali; H- Y Fu; M- T Huang; S- J Gao; R Wang (Neotropical Entomology, 2018)

Trade-offs between defence and competition in gregarious juvenile fluted giant clams (Tridacna squamosa L.) - Darren Z. H. Sim; Mei Lin Neo; Ambert C. F. Ang; Lynette S. M. Ying; Peter A. Todd (Marine Biology, 2018)

Impact of mixed anthropogenic and natural emissions on air quality and eco-environment—the major water-soluble components in aerosols from northwest to offshore isle - Yilun Jiang; Guoshun Zhuang; Qiongzhen Wang; Kan Huang; Congrui Deng; Guangyuan Yu; Chang Xu; Qingyan Fu; Yanfen Lin; Joshua S. Fu; Mei Li; Zhen Zhou (Air Quality, Atmosphere & Health, 2018)

Temporal Profile and Severity Correlation of a Panel of Rat Spinal Cord Injury Protein Biomarkers - Zhihui Yang; Helen M. Bramlett; Ahmed Moghieb; Dongnan Yu; Ping Wang; Fan Lin; Carl Bauer; Tyler M. Selig; Emily Jaalouk; Amanda S. Weissman; Disa S. Rathore; Pammela Romo; et al. (Molecular Neurobiology, 2018)

Assessing associations between indoor environment and health symptoms in Romanian school children: an analysis of data from the SINPHONIE project - Jillian R. Palumbo; Shao Lin; Ziqiang Lin; Iulia A. Neamtiu; Wangjian Zhang; Eva Csobod; Eugen S. Gurzau (Environmental Science and Pollution Research, 2018)

Matrix Metalloproteinases MMP-1 and MMP-9 and Their Inhibitor TIMP-1 as Markers of Dilated Cardiomyopathy in Patients of Different Age - I. B. Antonov; K. L. Kozlov; E. M. Pal’tseva; O. V. Polyakova; N. S. Lin’kova (Bulletin of Experimental Biology and Medicine, 2018)

Evidence that NF-κB and MAPK Signaling Promotes NLRP Inflammasome Activation in Neurons Following Ischemic Stroke - David Yang-Wei Fann; Yun-An Lim; Yi-Lin Cheng; Ker-Zhing Lok; Prasad Chunduri; Sang-Ha Baik; Grant R. Drummond; S. Thameem Dheen; Christopher G. Sobey; Dong-Gyu Jo; Christopher Li-Hsian Chen; Thiruma V. Arumugam (Molecular Neurobiology, 2018)

Microbial dolomite in the sabkha environment of the middle Cambrian in the Tarim Basin, NW China - X. L. You; S. Sun; C. S. Lin; J. Q. Zhu (Australian Journal of Earth Sciences, 2018)

Molecular screening of multidrug-resistance tuberculosis by a designated public health laboratory in Taiwan - H.-C. Lin; C.-L. Perng; Y.-W. Lai; F.-G. Lin; C.-J. Chiang; H.-A. Lin; R. Jou; T.-S. Chiueh (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Effects of emerging infectious diseases on host population genetics: a review - Donald T. McKnight; Lin Schwarzkopf; Ross A. Alford; Deborah S. Bower; Kyall R. Zenger (Conservation Genetics, 2017)

Characterization of Eptesipoxvirus, a novel poxvirus from a microchiropteran bat - Shin-Lin Tu; Yoshinori Nakazawa; Jinxin Gao; Kimberly Wilkins; Nadia Gallardo-Romero; Yu Li; Ginny L. Emerson; Darin S. Carroll; Chris Upton (Virus Genes, 2017)

Fighting an uphill battle: the recovery of frogs in Australia's Wet Tropics - Donald T. McKnight; Ross A. Alford; Conrad J. Hoskin; Lin Schwarzkopf; Sasha E. Greenspan; Kyall R. Zenger; Deborah S. Bower (Ecology, 2017)

Teacher respiratory health symptoms in relation to school and home environment - Shao Lin; Wayne R. Lawrence; Ziqiang Lin; Melissa Francois; Iulia A. Neamtiu; Qiaoxuan Lin; Eva Csobod; Eugen S. Gurzau (International Archives of Occupational and Environmental Health, 2017)

Identification of Peptide AEDG in the Polypeptide Complex of the Pineal Gland - V. Kh. Khavinson; A. T. Kopylov; B. V. Vaskovsky; G. A. Ryzhak; N. S. Lin’kova (Bulletin of Experimental Biology and Medicine, 2017)

Role of LIF Cytokine and CD34 Angiogenesis Marker in Non-Developing Pregnancy - E. S. Popravka; A. S. Dyatlova; N. S. Lin’kova; Yu. S. Krylova; V. O. Polyakova; I. M. Kvetnoi (Bulletin of Experimental Biology and Medicine, 2017)

Development of a two-stage washing and biodegradation system to remediate octachlorinated dibenzo-p-dioxin-contaminated soils - J. L. Lin; C. D. Dong; C. W. Chen; S. H. Chen; T. E. Hsieh; C. M. Kao (International Journal of Environmental Science and Technology, 2017)

Helicobacter pylori infection increases the risk of adult-onset asthma: a nationwide cohort study - Y-C Wang; T-Y Lin; S-T Shang; H-J Chen; C-H Kao; C-C Wu; T-Y Yang (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Correction to: Tripeptides Restore the Number of Neuronal Spines under Conditions of In Vitro Modeled Alzheimer’s Disease - N. A. Kraskovskaya; E. O. Kukanova; N. S. Lin’kova; E. A. Popugaeva; V. Kh. Khavinson (Bulletin of Experimental Biology and Medicine, 2017)

Formation of chlorite rims and the impact of pore-lining chlorite on reservoir quality: a case study from Shiqianfeng sandstones in upper Permian of Dongpu Depression, Bohai Bay Basin, eastern China - P. J. Ma; C. Y. Lin; S. Q. Zhang; C. M. Dong; Y. F. Xu (Australian Journal of Earth Sciences, 2017)

Evolution of landslide hotspots in Taiwan - S. C. Lin; M. C. Ke; C. M. Lo (Landslides, 2017)

Tripeptides Restore the Number of Neuronal Spines under Conditions of In Vitro Modeled Alzheimer’s Disease - N. A. Kraskovskaya; E. O. Kukanova; N. S. Lin’kova; E. A. Popugaeva; V. Kh. Khavinson (Bulletin of Experimental Biology and Medicine, 2017)

Expression of Signal Molecules in Culture of Human Endothelial Cells in Atherosclerosis and Restenosis - K. L. Kozlov; I. I. Bolotov; N. S. Lin’kova; A. O. Drobintseva (Bulletin of Experimental Biology and Medicine, 2017)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Controlled Release of Vanadium from a Composite Scaffold Stimulates Mesenchymal Stem Cell Osteochondrogenesis - S. D. Schussler; K. Uske; P. Marwah; F. W. Kemp; J. D. Bogden; S. S. Lin; Treena Livingston Arinzeh (The AAPS Journal, 2017)

Detection of mycobacterial and viral DNA in Kikuchi-Fujimoto disease: an analysis of 153 Chinese pediatric cases - Zhe Xu; Ying Liu; Haijing Li; Shufang Meng; Alan S. Boyd; Charles W. Stratton; Lin Ma; Yi-Wei Tang (Science China Life Sciences, 2017)

Analysis of tandem repeat units of the promoter of capsanthin/capsorubin synthase (Ccs) gene in pepper fruit - Shi-Lin Tian; Zheng Li; Li Li; S. N. M. Shah; Zhen-Hui Gong (Physiology and Molecular Biology of Plants, 2017)

Cardiotoxicity Associated with Nicotinamide Phosphoribosyltransferase Inhibitors in Rodents and in Rat and Human-Derived Cells Lines - D. L. Misner; M. A. Kauss; J. Singh; H. Uppal; A. Bruening-Wright; B. M. Liederer; T. Lin; B. McCray; N. La; T. Nguyen; D. Sampath; P. S. Dragovich; et al. (Cardiovascular Toxicology, 2017)

Nephroprotective Effect of EDL Peptide at Acute Injury of Kidneys of Different Genesis - I. I. Zamorskii; T. S. Shchudrova; N. S. Lin’kova; T. E. Nichik; V. Kh. Khavinson (Bulletin of Experimental Biology and Medicine, 2017)

Development of In situ hybridization and real‐time PCR assays for the detection of Hepatospora eriocheir , a microsporidian pathogen in the Chinese mitten crab Eriocheir sinensis - Z F Ding; J Q Chen; J Lin; X S Zhu; G H Xu; R L Wang; Q G Meng; W Wang (Journal of Fish Diseases, 2017)
A microsporidian parasite, Hepatospora eriocheir , is an emerging pathogen for the Chinese mitten crab Eriocheir sinensis . Currently, there is scant information about the way it transmits infection in the crustacean of commercial importance, including its pathogenesis, propagation and infection route in vivo . In this study, chromogenic in situ hybridization ( ISH ) and quantitative real‐time PCR ( qPCR ) assays were developed to address this pressing need, and we provided an advance in the detection methods available. Pathogens can be seen in situ with associated lesions using ISH . Positive hybridization signals were noted inside the epithelial cells of the hepatopancreas, and putative free parasite spores were observed within the tubule lumen, which were associated with lesions detected by electron microscopy and haematoxylin and eosin (H&E) analysis. qPCR allows the determination of parasite loads in infected tissues, which is important for understanding disease progression and transmission. The hepatopancreas displayed the biggest statistical copy numbers among different tissues of infected crabs, confirming a tissue‐specific pathogen infection characteristic. The qPCR assay also proved to be suitable for the diagnosis of asymptomatic carrier crabs. Combination of the two methods could facilitate the study of H. eriocheir infection mechanism in E. sinensis , enhance the early diagnosis of the pathogen and improve the management of microsporidian diseases in commercial crustaceans.

Gonorrhea infection increases the risk of prostate cancer in Asian population: a nationwide population-based cohort study - Y.-C. Wang; C.-H. Chung; J.-H. Chen; M.-H. Chiang; Ti-Yin; C.-H. Tsao; F.-H. Lin; W.-C. Chien; S.-T. Shang; F.-Y. Chang (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Identification of diverse bacterial communities for potential bio-aids capable of troubleshooting for wastewater biological treatment processes - H-W Kuo; C-Y Huang; C-N Chang; P-L Lee; Y-W Chen; C-F Huang; H-H Chang; Y-H Tang; S-Z Zeng; G-Y Li; C-R Lin; L-Z Chen (International Journal of Environmental Science and Technology, 2017)

A bacterial infection by Vibrio harveyi causing heavy reduction of cultured lined seahorse Hippocampus erectus - G Qin; X Wang; S Tan; Q Lin (Journal of Fish Diseases, 2017)

Therapeutic potential of pro-angiogenic BPC157 is associated with VEGFR2 activation and up-regulation - Ming-Jer Hsieh; Hsien-Ta Liu; Chao-Nin Wang; Hsiu-Yun Huang; Yuling Lin; Yu-Shien Ko; Jong-Shyan Wang; Vincent Hung-Shu Chang; Jong-Hwei S. Pang (Journal of Molecular Medicine, 2017)

Cytotoxic effects of the anthraquinone derivatives 1′-deoxyrhodoptilometrin and (S)-(−)-rhodoptilometrin isolated from the marine echinoderm Comanthus sp. - Wim Wätjen; Sherif S. Ebada; Anja Bergermann; Yvonni Chovolou; Frank Totzke; Michael H. G. Kubbutat; Wenhan Lin; Peter Proksch (Archives of Toxicology, 2017)

Variability of hydrological extreme events in East Asia and their dynamical control: a comparison between observations and two high-resolution global climate models - N. Freychet; A. Duchez; C.-H. Wu; C.-A. Chen; H.-H. Hsu; J. Hirschi; A. Forryan; B. Sinha; A. L. New; T. Graham; M. B. Andrews; C.-Y. Tu; et al. (Climate Dynamics, 2017)

Effect of Polypeptides on Cell Proliferation and Apoptosis during Aging - A.P. Ryzhak; N. I. Chalisova; N. S. Lin’kova; T. E. Nichik; A.V. Dudkov; N. V. Kolchina; G. A. Ryzhak; R. I. Khalimov (Bulletin of Experimental Biology and Medicine, 2017)

Angiopoietins as serum biomarkers for lymphatic anomalies - Timothy D. Le Cras; Paula S. Mobberley-Schuman; Mary Broering; Lin Fei; Cameron C. Trenor; Denise M. Adams (Angiogenesis, 2017)

3D Layer-Integrated Modelling of Morphodynamic Processes Near River Regulated Structures - S. Faghihirad; B. Lin; R. A. Falconer (Water Resources Management, 2017)

Short Peptides Regulate Gene Expression - V. Kh. Khavinson; N. S. Lin’kova; S. I. Tarnovskaya (Bulletin of Experimental Biology and Medicine, 2016)

Allergy symptoms, serum total immunoglobulin E, and risk of head and neck cancer - Hsiao-Chen Liao; Shang-Yin Wu; Chun-Yen Ou; Jenn-Ren Hsiao; Jehn-Shyun Huang; Sen-Tien Tsai; Cheng-Chih Huang; Tung-Yiu Wong; Wei-Ting Lee; Ken-Chung Chen; Sheen-Yie Fang; Jiunn-Liang Wu; et al. (Cancer Causes & Control, 2016)

Greater nitrogen dioxide concentrations at child versus adult breathing heights close to urban main road kerbside - Hannah S. Kenagy; Chun Lin; Hao Wu; Mathew R. Heal (Air Quality, Atmosphere & Health, 2016)

Changes in Sulforaphane and Selenocysteine Methyltransferase Transcript Levels in Broccoli Treated with Sodium Selenite - K. Huang; J. C. Lin; Q. Y. Wu; J. Y. Yan; M. Y. Liu; S. Zhang; W. J. Xiao (Plant Molecular Biology Reporter, 2016)

The Aggregation Pheromone of Phyllotreta striolata (Coleoptera: Chrysomelidae) Revisited - Franziska Beran; Guillermo H. Jiménez-Alemán; Mei-ying Lin; Yun-Che Hsu; Inga Mewis; Ramasamy Srinivasan; Christian Ulrichs; Wilhelm Boland; Bill S. Hansson; Andreas Reinecke (Journal of Chemical Ecology, 2016)

Changes in Sympathetic Innervation of Rat Caudal Artery in Experimental Myocardial Infarction. Effect of Semax Peptide - A. M. Gorbacheva; A. B. Berdalin; A. N. Stulova; A. D. Nikogosova; M. D. Lin; S. V. Buravkov; S. A. Gavrilova; V. B. Koshelev (Bulletin of Experimental Biology and Medicine, 2016)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

Deep sequencing of banana bract mosaic virus from flowering ginger (Alpinia purpurata) and development of an immunocapture RT-LAMP detection assay - Jingxin Zhang; Wayne B. Borth; Birun Lin; Kishore K. Dey; Michael J. Melzer; Huifang Shen; Xiaoming Pu; Dayuan Sun; John S. Hu (Archives of Virology, 2016)

Functional Genomic Analysis of the Impact of Camelina (Camelina sativa) Meal on Atlantic Salmon (Salmo salar) Distal Intestine Gene Expression and Physiology - Tyler D. Brown; Tiago S. Hori; Xi Xue; Chang Lin Ye; Derek M. Anderson; Matthew L. Rise (Marine Biotechnology, 2016)

Copper(II) binding properties of hepcidin - Kanokwan Kulprachakarn; Yu-Lin Chen; Xiaole Kong; Maria C. Arno; Robert C. Hider; Somdet Srichairatanakool; Sukhvinder S. Bansal (JBIC Journal of Biological Inorganic Chemistry, 2016)

Early detection of Mycobacterium tuberculosis complex in BACTEC MGIT cultures using nucleic acid amplification - S. Y. Lin; S. C. Hwang; Y. C. Yang; C. F. Wang; Y. H. Chen; T. C. Chen; P. L. Lu (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Macrobenthos in the central Arabian Gulf: a reflection of climate extremes and variability - Chih-Lin Wei; Gilbert T. Rowe; Mohsin Al-Ansi; Ibrahim Al-Maslamani; Yousria Soliman; Nehad Nour El-Din; Ibrahim S. Al-Ansari; Ismail Al-Shaikh; Antonietta Quigg; Clifton Nunnally; Mohamed A. Abdel-Moati (Hydrobiologia, 2016)

Peptide Regulation of Skin Fibroblast Functions during Their Aging In Vitro - N. S. Lin’kova; A. O. Drobintseva; O. A. Orlova; E. P. Kuznetsova; V. O. Polyakova; I. M. Kvetnoy; V. Kh. Khavinson (Bulletin of Experimental Biology and Medicine, 2016)

Strong inhibition of betanodavirus replication by ribavirin targeting RNA ‐dependent RNA polymerase - Y‐C Huang; T‐S Lin; C Peng; N‐L Chan; Y‐S Han (Journal of Fish Diseases, 2016)

Bismuth(III) deferiprone effectively inhibits growth of Desulfovibrio desulfuricans ATCC 27774 - Larry L. Barton; Daniel A. Lyle; Nathaniel L. Ritz; Alex S. Granat; Ali N. Khurshid; Nada Kherbik; Robert Hider; Henry C. Lin (BioMetals, 2016)

Poly(lactic-co-glycolide) polymer constructs cross-linked with human BMP-6 and VEGF protein significantly enhance rat mandible defect repair - Anusuya Das; Brian A. Fishero; J. Jared Christophel; Ching-Ju Li; Nikita Kohli; Yong Lin; Abhijit S. Dighe; Quanjun Cui (Cell and Tissue Research, 2016)

Blockade of CD127 Exerts a Dichotomous Clinical Effect in Marmoset Experimental Autoimmune Encephalomyelitis - Jordon Dunham; Li-Fen Lee; Nikki van Driel; Jon D. Laman; Irene Ni; Wenwu Zhai; Guang-Huan Tu; John C. Lin; Jan Bauer; Bert A. ‘t Hart; Yolanda S. Kap (Journal of Neuroimmune Pharmacology, 2016)

Validation of self-reported comorbidity status of breast cancer patients with medical records: the California Breast Cancer Survivorship Consortium (CBCSC) - Cheryl Vigen; Marilyn L. Kwan; Esther M. John; Scarlett Lin Gomez; Theresa H. M. Keegan; Yani Lu; Salma Shariff-Marco; Kristine R. Monroe; Allison W. Kurian; Iona Cheng; Bette J. Caan; Valerie S. Lee; et al. (Cancer Causes & Control, 2016)

Static and dynamic posterior cingulate cortex nodal topology of default mode network predicts attention task performance - Pan Lin; Yong Yang; Jorge Jovicich; Nicola De Pisapia; Xiang Wang; Chun S. Zuo; James Jonathan Levitt (Brain Imaging and Behavior, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Drought tolerance as a driver of tropical forest assembly: resolving spatial signatures for multiple processes - M. K. Bartlett; Y. Zhang; J. Yang; N. Kreidler; S.‐W. Sun; L. Lin; Y.‐H. Hu; K.‐F. Cao; L. Sack (Ecology, 2016)
Spatial patterns in trait variation reflect underlying community assembly processes, allowing us to test hypotheses about their trait and environmental drivers by identifying the strongest correlates of characteristic spatial patterns. For 43 evergreen tree species (>1 cm dbh) in a 20‐ha seasonal tropical rainforest plot in Xishuangbanna, China, we compared the ability of drought‐tolerance traits, other physiological traits, and commonly measured functional traits to predict the spatial patterns expected from the assembly processes of habitat associations, niche‐overlap‐based competition, and hierarchical competition. We distinguished the neighborhood‐scale (0–20 m) patterns expected from competition from larger‐scale habitat associations with a wavelet method. Species’ drought tolerance and habitat variables related to soil water supply were strong drivers of habitat associations, and drought tolerance showed a significant spatial signal for influencing competition. Overall, the traits most strongly associated with habitat, as quantified using multivariate models, were leaf density, leaf turgor loss point (π tlp ; also known as the leaf wilting point), and stem hydraulic conductivity ( r 2 range for the best fit models = 0.27–0.36). At neighborhood scales, species spatial associations were positively correlated with similarity in π tlp , consistent with predictions for hierarchical competition. Although the correlation between π tlp and interspecific spatial associations was weak ( r 2

Histological analysis of somatic embryogenesis in pineapple: AcSERK1 and its expression validation under stress conditions - J. Ma; Y. H. He; Z. Y. Hu; S. Kanakala; W. T. Xu; J. X. Xia; C. H. Guo; S. Q. Lin; C. J. Chen; C. H. Wu; J. L. Zhang (Journal of Plant Biochemistry and Biotechnology, 2016)

Soil Nitrous oxide and Carbon dioxide emissions following incorporation of above- and below-ground biomass of green bean - M. Shaaban; Q. Peng; R. Hu; S. Lin; J. Zhao (International Journal of Environmental Science and Technology, 2016)

Evaluation of soil erosion risk for watershed management in Shenmu watershed, central Taiwan using USLE model parameters - B. S. Lin; K. Thomas; C. K. Chen; H. C. Ho (Paddy and Water Environment, 2016)

Short Peptides and Telomere Length Regulator Hormone Irisin - V. Kh. Khavinson; B. I. Kuznik; S. I. Tarnovskaya; N. S. Lin’kova (Bulletin of Experimental Biology and Medicine, 2016)

Trends in land surface evapotranspiration across China with remotely sensed NDVI and climatological data for 1981–2010 - X. Mo; S. Liu; Z. Lin; S. Wang; S. Hu (Hydrological Sciences Journal, 2015)

Prior human polyomavirus and papillomavirus infection and incident lung cancer: a nested case–control study - Danny V. Colombara; Lisa E. Manhart; Joseph J. Carter; Stephen E. Hawes; Noel S. Weiss; James P. Hughes; Matt J. Barnett; Gary E. Goodman; Jennifer S. Smith; You-Lin Qiao; Denise A. Galloway (Cancer Causes & Control, 2015)

Freshwater aquaculture in PR C hina: trends and prospects - Qidong Wang; Lin Cheng; Jiashou Liu; Zhongjie Li; Shouqi Xie; Sena S. De Silva (Reviews in Aquaculture, 2015)
It is acknowledged that China is the mainstay in global aquaculture, contributing for example, 65.7 (of 76 321 310 t) and 63.6 (of 38 994 913 t) per cent to total global and freshwater aquaculture production, respectively, in 2011, significantly increasing the corresponding contributions from 36.1 and 38.5% of the global total (7 359 881 t) and global freshwater (2 342 706 t) aquaculture production in 1980. Overall, aquaculture production in China in turn has enabled to reduce our dependence on food fish supplies from a hunted to a farmed origin, like all the other staples. However, there are very few accounts on different subsectors of aquaculture in China and even less on variations in aquaculture developments within the country. This review attempts to trace the development trends in inland aquaculture in China in time and space and includes aspects on production, types and modes of culture, species cultured and marketing. It is evident that though inland aquaculture is practised in most provinces of China, the great bulk of it occurs in the area that lies approximately between 110 and 120 °E and 19 and 35 °N, in the Yangtze and Pearl River basins. The review also addresses emerging issues on freshwater aquaculture and possible ways of achieving sustainability in the long term.

Pharmacodynamic Activity of Dapivirine and Maraviroc Single Entity and Combination Topical Gels for HIV-1 Prevention - Charlene S. Dezzutti; Sarah Yandura; Lin Wang; Bernard Moncla; Elizabeth A. Teeple; Brid Devlin; Jeremy Nuttall; Elizabeth R. Brown; Lisa C. Rohan (Pharmaceutical Research, 2015)

Sodium channels in the Cx43 gap junction perinexus may constitute a cardiac ephapse: an experimental and modeling study - Rengasayee Veeraraghavan; Joyce Lin; Gregory S. Hoeker; James P. Keener; Robert G. Gourdie; Steven Poelzing (Pflügers Archiv - European Journal of Physiology, 2015)

Two New Species of the Genus Criotettix Bolivar (Orthoptera: Tetrigidae), with a Key to the Species of the Genus from China - W A Deng; Z M Zheng; S Z Wei; M P Lin; L L Lin (Neotropical Entomology, 2015)

Rapid generation and analysis of expressed sequence tags to uncovering inflorescence secondary metabolism of Bougainvillea spectabilis ‘Speciosas’ by pyrosequencing - S. X. Xu; Q. Y. Huang; C. S. Lin; F. C. Lin; L. X. Lin; Q. Y. Shen (Euphytica, 2015)

A biodegradable ocular implant for long-term suppression of intraocular pressure - Xu Wen Ng; Kerh Lin Liu; Amutha Barathi Veluchamy; Nyein Chan Lwin; Tina T. Wong; Subbu S. Venkatraman (Drug Delivery and Translational Research, 2015)

The most frequent interfaces in olivine aggregates: the GBCD and its importance for grain boundary related processes - Katharina Marquardt; Gregory S. Rohrer; Luiz Morales; Erik Rybacki; Hauke Marquardt; Brian Lin (Contributions to Mineralogy and Petrology, 2015)

The influence of shelf-sea fronts on winter monsoon over East China Sea - L.-Y. Oey; M.-C. Chang; S.-M. Huang; Y.-C. Lin; M.-A. Lee (Climate Dynamics, 2015)

Neurology of the H1N1 pandemic in Singapore: a nationwide case series of children and adults - Asha Prerna; Jocelyn Y. X. Lim; Natalie W. H. Tan; Mas Suhaila Isa; Helen May-Lin Oh; Norazieda Yassin; Chian-Yong Low; Derrick W. S. Chan; Chia-Yin Chong; Yee-Sin Leo; Angela Li-Ping Chow; Paul Ananth Tambyah; et al. (Journal of NeuroVirology, 2015)

Peptides Restore Functional State of the Kidneys During Cisplatin-Induced Acute Renal Failure - I. I. Zamorskii; T. S. Shchudrova; N. S. Lin’kova; T. E. Nichik; V. Kh. Khavinson (Bulletin of Experimental Biology and Medicine, 2015)

Identification and characterization of a late gene encoded by grouper iridovirus 2L (GIV‐2L) - H‐Y Lin; C‐F Cheng; P P Chiou; C‐J Liou; J‐C Yiu; Y‐S Lai (Journal of Fish Diseases, 2015)
Grouper iridovirus (GIV) belongs to the Ranavirus genus and is one of the most important viral pathogens in grouper, particularly at the fry and fingerling stages. In this study, we identified and characterized the GIV‐2L gene, which encodes a protein of unknown function. GIV‐2L is 1242 bp in length, with a predicted protein mass of 46.2 kDa. It displayed significant identity only with members of the Ranavirus and Iridovirus genera. We produced mouse monoclonal antibodies against the GIV‐2L protein by immunizing mice with GIV‐2L‐His‐tag recombinant protein. By inhibiting de novo protein and DNA synthesis in GIV‐infected cells, we showed that GIV‐2L was a late gene during the viral replication. Finally, immunofluorescence microscopy revealed that GIV‐2L protein accumulated in both the nucleus and cytoplasm of infected cells. These results offer important insights into the pathogenesis of GIV.

Identification of a novel cyprinid herpesvirus 3 genotype detected in koi from the East Asian and South‐East Asian Regions - J Chen; D Chee; Y Wang; G Y Lim; S M Chong; Y N Lin; T Huangfu (Journal of Fish Diseases, 2015)
Cyprinid herpesvirus 3 (Cy HV ‐3) is a highly contagious virus that causes significant morbidity and mortality in common carp Cyprinus carpio L. and considered to be one of the most important pathogens of koi and common carp worldwide. Cyprinid herpesvirus 3 infected consignments imported from East Asian and South‐East Asian regions were identified during quarantine period in Singapore, and virus from a 2005 consignment was successfully isolated in koi fin cells. A combination of sequence analyses and duplex PCR were used to characterize 15 Cy HV ‐3 isolates detected in koi consignments between 2005 and 2011. Sequence analyses of the enlarged 9/5, SphI‐5 and TK gene regions identified both the Asian 1 ( n = 11) and European 4 ( n = 4) genotypes. Duplex PCR analysis of two variable marker regions between ORF 29 and ORF 30 (marker I) as well as ORF 133 and its upstream region (marker II ) revealed viruses of genotypes J (I ++ II + ), U/I (I −− II − ), an intermediate genotype (I ++ II − ) and a novel genotype, I ++ II +Δ , which was identified in viruses from seven different consignments. This novel genotype has a 13‐bp deletion in marker II , while maintaining the I ++ allele of marker I. The I ++ II +Δ genotype may have emerged from East Asian and South‐East Asian regions in recent years.

Crustal thickening and extension induced by the Great Sumatra–Andaman earthquake of 26 December 2004: revealed by the seismic moment tensor element Mrr - J.-Y. Lin; C.-L. Lo; W.-N. Wu; J.-C. Sibuet; S.-K. Hsu; Y.-Y. Wen (Marine Geophysical Research, 2015)

Ambient air concentrations of PCDD/Fs, coplanar PCBs, PBDD/Fs, and PBDEs and their impacts on vegetation and soil - Y.-C. Kuo; Y.-C. Chen; M.-Y. Lin; L.-H. Young; H.-T. Hsu; S.-H. Liou; T.-N. Wu; L.-C. Wang; P.-J. Tsai (International Journal of Environmental Science and Technology, 2015)

Quaternary high-Mg ultrapotassic rocks from the Qal’eh Hasan Ali maars, southeastern Iran: petrogenesis and geodynamic implications - Kwan-Nang Pang; Sun-Lin Chung; Mohammad Hossein Zarrinkoub; Fei Wang; Vadim S. Kamenetsky; Hao-Yang Lee (Contributions to Mineralogy and Petrology, 2015)

The suppression of brain activation in post-deployment military personnel with posttraumatic stress symptoms - Randall S. Scheibel; Nicholas J. Pastorek; Maya Troyanskaya; Jan E. Kennedy; Joel L. Steinberg; Mary R. Newsome; Xiaodi Lin; Harvey S. Levin (Brain Imaging and Behavior, 2015)

Molecular phylogenetic lineage of Plagiopogon and Askenasia (Protozoa, Ciliophora) revealed by their gene sequences - An Liu; Zhenzhen Yi; Xiaofeng Lin; Xiaozhong Hu; Saleh A. Al-Farraj; Khaled A. S. Al-Rasheid (Journal of Ocean University of China, 2015)

Overexpression of AT14A confers tolerance to drought stress-induced oxidative damage in suspension cultured cells of Arabidopsis thaliana - Lin Wang; Jie He; Haidong Ding; Hui Liu; Bing Lü; Jiansheng Liang; L. Wang; J. He; H. D. Ding; H. Liu; B. Lü; J. S. Liang (Protoplasma, 2015)

Statins can increase the risk of herpes zoster infection in Asia - H.-H. Chen; C.-L. Lin; C.-J. Yeh; S.-Y. Yeh; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

A Systematic Study of Topography Effect of ERT Based on 3-D Modeling and Inversion - De-Bao Lu; Qi-You Zhou; S. A. Junejo; An-Lin Xiao (Pure and Applied Geophysics, 2015)

Recognizing the importance of exposure–dose–response dynamics for ecotoxicity assessment: nitrofurazone-induced antioxidase activity and mRNA expression in model protozoan Euplotes vannus - Yazhen Hong; Shuxing Liu; Xiaofeng Lin; Jiqiu Li; Zhenzhen Yi; Khaled A. S. Al-Rasheid (Environmental Science and Pollution Research, 2015)

Infections of nervous necrosis virus in wild and cage‐reared marine fish from S outh C hina S ea with unexpected wide host ranges - X D Liu; J N Huang; S P Weng; X Q Hu; W J Chen; Z D Qin; X X Dong; X L Liu; Y Zhou; M Asim; W M Wang; J G He; et al. (Journal of Fish Diseases, 2015)
The concerns about the impact of the nervous necrosis virus ( NNV ) infections in wild fish have been raised. This paper presents the results of quarterly surveys of NNV in wild and cage‐reared marine fish from South China Sea. Samples of 892 wild fish belonging to 69 species and 381 cage‐reared fish belonging to 11 species were collected and were detected by seminested PCR and nested PCR . In the case of seminested PCR , the positive signal was detected in 3.0% and 3.1% samples of wild and cage‐reared fish, respectively. However, by nested RT ‐ PCR , the positive signal was observed in 42.3% and 63.0% samples of wild and cage‐reared fish, respectively. If the fish species were considered, the positive signal was detected in 21.7% and 72.7% species of wild and cage‐reared fish by seminested PCR assay, respectively. However, by nested RT ‐ PCR , the positive signal was observed in 65.2% and 100% species of wild and cage‐reared fish, respectively. The nucleotide sequences of the nested PCR products were determined. Phylogenetic tree showed that all the obtained viral isolates belonged to the red‐spotted grouper nervous necrosis virus ( RGNNV ) genotype. Thirty‐five species of the marine fish were the new hosts of NNV .

Peptide Regulation of Cells Renewal Processes in Kidney Tissue Cultures from Young and Old Animals - N. I. Chalisova; N. S. Lin’kova; T. E. Nichik; A. P. Ryzhak; A. V. Dudkov; G. A. Ryzhak (Bulletin of Experimental Biology and Medicine, 2015)

Mass mortality associated with a viral‐induced anaemia in cage‐reared large yellow croaker, Larimichthys crocea (Richardson) - W J Xu; Z D Qin; H Shi; N Jiang; Y Zhou; X L Liu; J J Xie; G S Wang; W M Wang; M Asim; L B Zeng; L Lin (Journal of Fish Diseases, 2015)

Clustering of Clinical and Environmental Escherichia coli O104 Isolates Using the DiversiLab™ Repetitive Sequence-Based PCR System - N. M. Herbold; L. M. Clotilde; K. M. Anderson; J. Kase; G. L. Hartman; S. Himathongkham; A. Lin; C. R. Lauzon (Current Microbiology, 2015)

Clinical manifestations and prognostic factors of Morganella morganii bacteremia - T.-Y. Lin; M.-C. Chan; Y.-S. Yang; Y. Lee; K.-M. Yeh; J.-C. Lin; F.-Y. Chang (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Establishment of a novel, eco-friendly transgenic pig model using porcine pancreatic amylase promoter-driven fungal cellulase transgenes - Y. S. Lin; C. C. Yang; C. C. Hsu; J. T. Hsu; S. C. Wu; C. J. Lin; W. T. K. Cheng (Transgenic Research, 2015)

Role of Peptide Bond in the Realization of Biological Activity of Short Peptides - V. Kh. Khavinson; S. I. Tarnovskaya; N. S. Lin’kova; N. A. Chervyakova; T. E. Nichik; E. V. Elashkina; N. I. Chalisova (Bulletin of Experimental Biology and Medicine, 2015)

ICE1 demethylation drives the range expansion of a plant invader through cold tolerance divergence - H. J. Xie; H. Li; D. Liu; W. M. Dai; J. Y. He; S. Lin; H. Duan; L. L. Liu; S. G. Chen; X. L. Song; B. E. Valverde; S. Qiang (Molecular Ecology, 2015)
Cold tolerance adaption is a crucial determinant for the establishment and expansion of invasive alien plants into new cold environments; however, its evolutionary mechanism is poorly understood. Crofton weed ( Ageratina adenophora ), a highly invasive alien plant, is continuously spreading across subtropical areas in China, north‐eastward from the first colonized south‐western tropical regions, through cold tolerance evolution. Close relations between the cold tolerance levels of 34 populations, represented by 147 accessions, and the latitude, extreme lowest temperature, coldest month average temperature, and invasion period have provided direct insight into its cold tolerance divergence. A comparative study of the CBF pathway, associated with the cold tolerance enhancement of cold‐susceptible CBF 1 ‐transgenic plant, among four geographically distinct crofton weed populations revealed that the CBF pathway plays a key role in the observed cold tolerance divergence. Four epialleles of the cold response regulator ICE 1 ranged from 66 to 50 methylated cytosines, representing a 4.4% to 3.3% methylation rate and significantly corresponding to the lowest to highest cold tolerance levels among these different populations. The significant negative relation between the transcription levels of the primary CBF pathway members, except for CBF 2 , and the methylation levels among the four populations firstly demonstrates that the demethylation‐upregulated transcription level of CBF pathway is responsible for this evolution. These facts, combined with the cold tolerance variation and methylation found among three native and two other introduced populations, indicate that the ICE 1‐ demethylated upregulation of cold tolerance may be the underlying evolutionary mechanism allowing crofton weed to expand northward in China.

Taxonomy and molecular phylogeny of four Strombidium species, including description of S. pseudostylifer sp. nov. (Ciliophora, Oligotrichia) - Wen Song; Jiamei Li; Weiwei Liu; Khaled A. S. Al-rasheid; Xiaozhong Hu; Xiaofeng Lin (Systematics and Biodiversity, 2015)

Genetic variation in estrogen and progesterone pathway genes and breast cancer risk: an exploration of tumor subtype-specific effects - Sarah J. Nyante; Marilie D. Gammon; Jay S. Kaufman; Jeannette T. Bensen; Dan Yu Lin; Jill S. Barnholtz-Sloan; Yijuan Hu; Qianchuan He; Jingchun Luo; Robert C. Millikan (Cancer Causes & Control, 2015)

Accumulation of arsenic in rice plant: a study of an arsenic-contaminated site in Taiwan - S.-C. Lin; T.-K. Chang; W.-D. Huang; H.-S. Lur; G.-S. Shyu (Paddy and Water Environment, 2015)

Transynaptic Changes Evident in Peripheral Axonal Function After Acute Cerebellar Infarct - William Huynh; Cindy S-Y. Lin; Arun V. Krishnan; Steve Vucic; Matthew C. Kiernan (The Cerebellum, 2014)

AdeRS combination codes differentiate the response to efflux pump inhibitors in tigecycline-resistant isolates of extensively drug-resistant Acinetobacter baumannii - J.-R. Sun; C.-L. Perng; J.-C. Lin; Y.-S. Yang; M.-C. Chan; T.-Y. Chang; F.-M. Lin; T.-S. Chiueh (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Smoking, alcohol, diabetes, obesity, socioeconomic status, and the risk of colorectal cancer in a population-based case–control study - Terry Boyle; Lin Fritschi; Seyed Mehdi Tabatabaei; Kathrin Ringwald; Jane S. Heyworth (Cancer Causes & Control, 2014)

Molecular Aspects of Anti-Atherosclerotic Effects of Short Peptides - V. Kh. Khavinson; N. S. Lin’kova; E. V. Evlashkina; A. O. Durnova; K. L. Kozlov; O. E. Gutop (Bulletin of Experimental Biology and Medicine, 2014)

Characterization of baseline sensitivity and resistance risk of Colletotrichum gloeosporioides complex isolates from strawberry and grape to two demethylation-inhibitor fungicides, prochloraz and tebuconazole - X. F. Xu; T. Lin; S. K. Yuan; D. J. Dai; H. J. Shi; C. Q. Zhang; H. D. Wang (Australasian Plant Pathology, 2014)

The first record, tagging and release of a neonatal whale shark Rhincodon typus in Taiwan - H. H. Hsu; C. Y. Lin; S. J. Joung (Journal of Fish Biology, 2014)
On 27 October 2013, a Rhincodon typus was apparently chased by a group of Caranx ignobilis into nearshore waters near Green Island (Ludao), east of Taiwan. A fisherman brought it back to port where it was kept in a small sea pen until release. The R. typus was 78 cm total length, and was tagged and released on 29 October 2013.

Comparison of interpolation methods for estimating spatial distribution of precipitation in Ontario, Canada - S. Wang; G. H. Huang; Q. G. Lin; Z. Li; H. Zhang; Y. R. Fan (International Journal of Climatology, 2014)
In this study, different interpolation techniques in a geographical information system ( GIS ) environment are analysed and compared for estimating the spatial distribution of precipitation in the province of Ontario, Canada. A high‐resolution regional climate modelling system [Providing Regional Climates for Impacts Studies ( PRECIS )] is used to simulate the present (1961–1990) and future (2071–2100) precipitation events for 12 meteorological stations over Ontario. The results verify that for the present case PRECIS simulates well the precipitation events when compared with observed data. The future precipitation events can be projected after the validation of PRECIS . Six interpolation methods are then used to generate spatial distribution of precipitation based on the projections of future precipitation of 12 meteorological stations; they include inverse distance weighting ( IDW ), global polynomial interpolation ( GPI ), local polynomial interpolation ( LPI ), radial basis functions ( RBF ), ordinary kriging ( OK ), and universal kriging ( UK ). Cross‐validation is applied to evaluate the accuracy of interpolation methods in terms of the root mean square error ( RMSE ). The results indicate that LPI is the optimal method with the least RMSE for interpolating the PRECIS precipitation. LPI is then used to analyse spatial variations of the average annual precipitation for the period of 2071–2100 over Ontario.

Association between herpes zoster and end stage renal disease entrance in chronic kidney disease patients: a population-based cohort study - S.-Y. Lin; J.-H. Liu; H.-C. Yeh; C.-L. Lin; I.-J. Tsai; P.-C. Chen; F.-C. Sung; Y.-F. Yang; C.-C. Huang; D. E. Morisky; Y.-J. Chang; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Advanced multivariate analysis to assess remediation of hydrocarbons in soils - Deborah S. Lin; Peter Taylor; Mark Tibbett (Environmental Science and Pollution Research, 2014)

TM4SF1: a new vascular therapeutic target in cancer - Chi-Iou Lin; Anne Merley; Tracey E. Sciuto; Dan Li; Ann M. Dvorak; Juan M. Melero-Martin; Harold F. Dvorak; Shou-Ching S. Jaminet (Angiogenesis, 2014)

The Melanogenesis-Inhibitory Effect and the Percutaneous Formulation of Ginsenoside Rb1 - Lin Wang; Ai-Ping Lu; Zhi-Ling Yu; Ricky N. S. Wong; Zhao-Xiang Bian; Hoi-Hin Kwok; Patrick Ying-Kit Yue; Li-Min Zhou; HuBiao Chen; Min Xu; Zhijun Yang (AAPS PharmSciTech, 2014)

The association between chronic osteomyelitis and increased risk of diabetes mellitus: a population-based cohort study - S.-Y. Lin; C.-L. Lin; C.-H. Tseng; I.-K. Wang; S.-M. Wang; C.-C. Huang; Y.-J. Chang; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Erratum to: Increased risk of chronic fatigue syndrome following herpes zoster: a population-based study - S.-Y. Tsai; T.-Y. Yang; H.-J. Chen; C.-S. Chen; W.-M. Lin; W.-C. Shen; C.-N. Kuo; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Increased risk of pulmonary tuberculosis among patients with appendectomy in Taiwan - S.-W. Lai; C.-L. Lin; K.-F. Liao; S.-M. Tsai (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Increased risk of chronic fatigue syndrome following herpes zoster: a population-based study - S.-Y. Tsai; T.-Y. Yang; H.-J. Chen; C.-S. Chen; W.-M. Lin; W.-C. Shen; C.-N. Kuo; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Peptides Stimulate Expression of Signal Molecules in Neuronal Cultures from Animals of Different Age - R. S. Umnov; N. S. Lin’kova; V. Kh. Khavinson (Bulletin of Experimental Biology and Medicine, 2014)

Molecular characterization of a new member of the 16SrV group of phytoplasma associated with Bischofia polycarpa (Levl.) Airy Shaw witches’ -broom disease in China by a multiple gene-based analysis - F. Lai; C. S. Song; Z. G. Ren; C. L. Lin; Q. C. Xu; Y. Li; C. G. Piao; S. S. Yu; M. W. Guo; G. Z. Tian (Australasian Plant Pathology, 2014)

The contribution of understory light availability and biotic neighborhood to seedling survival in secondary versus old-growth temperate forest - Fei Lin; Liza S. Comita; Xugao Wang; Xuejiao Bai; Zuoqiang Yuan; Dingliang Xing; Zhanqing Hao (Plant Ecology, 2014)

A Review of the Genus Pielomastax Chang (Orthoptera: Eumastacoidea) from China with Description of a New Species - L L Lin; Z M Zheng; R Yang; S Q Xu (Neotropical Entomology, 2014)

Sulfur sources of sedimentary “buckshot” pyrite in the Auriferous Conglomerates of the Mesoarchean Witwatersrand and Ventersdorp Supergroups, Kaapvaal Craton, South Africa - B. M. Guy; S. Ono; J. Gutzmer; Y. Lin; N. J. Beukes (Mineralium Deposita, 2014)

Nanomedicine for glaucoma: sustained release latanoprost offers a new therapeutic option with substantial benefits over eyedrops - Tina T. Wong; Gary D. Novack; Jayaganesh V. Natarajan; Ching Lin Ho; Hla M. Htoon; Subbu S. Venkatraman (Drug Delivery and Translational Research, 2014)

Inhibitory Effect of Selenium Against Penicillium expansum and Its Possible Mechanisms of Action - Zhi-lin Wu; Xue-bin Yin; Zhi-qing Lin; Gary S. Bañuelos; Lin-xi Yuan; Ying Liu; Miao Li (Current Microbiology, 2014)

Development of a selective and differential medium for capsulated L actococcus garvieae - C‐I Chang; C‐F Lee; J‐M Tsai; C‐C Wu; L‐H Chen; S‐C Chen; K‐J Lin (Journal of Fish Diseases, 2014)
A selective and differential medium termed ‘ LG agar’ was developed for the isolation and presumptive identification of L actococcus garvieae that results in black colonies with red halos. In this study, all 14 strains of L . garvieae and only 9 of the 148 strains representing 38 other species were able to grow on the LG agar. The nine viable strains on LG agar plates (including E nterococcus faecalis , E nterococcus faecium , L actococcus lactis , V ibrio fluvialis , V ibrio furnissii , V ibrio mimicus and V ibrio salmonicida ) were further differentiated from L . garvieae by various colours or colony features. Colonies isolated from the mixing culture and the infected giant sea perch using LG agar plates were all positively identified as L . garvieae by conventional tests and 16 S r DNA sequencing. Furthermore, LG agar discriminated capsulated strains of L . garvieae , which were believed to be correlated with pathogens of fish and shellfish, from non‐capsulated ones by colony appearances. The specificity and differentiating ability of LG agar suggest that this medium displays considerable potential for primary isolation and presumptive identification of L . garvieae from pathological and environmental samples.

Eutrophication as a driver of r ‐selection traits in a freshwater fish - M. Lin; M. Chevalier; S. Lek; L. Zhang; R. E. Gozlan; J. Liu; T. Zhang; S. Ye; W. Li; Z. Li (Journal of Fish Biology, 2014)
This study tested whether eutrophication could influence life‐history traits of a cyprinid, Chanodichthys erythropterus , in 10 Chinese lakes. Using the von Bertalanffy growth model, the asymptotic length ( L ∞ ) and the growth performance index ( I GRO ) were significantly affected by eutrophication. The gonado‐somatic index ( I G ) and relative fecundity ( F R ) were significantly lower in mesotrophic lakes than in eutrophic and hypertrophic lakes. These results indicate that increasing eutrophication affects the life‐history tactics of a freshwater fish.

Characterization, tissue distribution and regulation of neuropeptideY in Schizothorax prenanti - R. Wei; C. Zhou; D. Yuan; T. Wang; F. Lin; H. Chen; H. Wu; Z. Xin; S. Yang; Y. Wang; D. Chen; J. Liu; et al. (Journal of Fish Biology, 2014)
In this study, the full‐length neuropeptide Y ( npy ) complementary (c) DNA was cloned in ya fish Schizothorax prenanti . npy cDNA was composed of 789 nucleotides with a 288 nucleotide open reading frame encoding a protein of 96 amino acids. The deduced amino acid sequences contained a 28 amino acids signal peptide followed by a 36 amino acids mature neuropeptide Y (NPY). The npy mRNA was expressed mainly in the brain and eye as detected by real‐time quantitative polymerase chain reaction RT‐PCR ( rt‐qPCR ). The S. prenanti NPY was detectable from blastulation to hatch, suggesting that npy might be involved in the late embryonic development of S. prenanti . An experiment was conducted to determine the expression profile of npy during feeding of a single meal and during long‐term fasting. The expression level of npy in fed fish was significantly decreased at 0·5, 1·5, 3 and 9 h post‐feeding (hpf) than in fasting fish. Fasting for 14 days induced an increase in npy messenger (m) RNA expression in the brain. Overall, the results suggest that NPY is a conserved peptide that might be involved in the regulation of feeding and other physiological function in S. prenanti .

Characterization of Schizothorax prenanti cgnrhII gene: fasting affects cgnrhII expression - T. Wang; D. Yuan; C. Zhou; F. Lin; H. Chen; H. Wu; R. Wei; Z. Xin; J. Liu; Y. Gao; D. Chen; S. Yang; et al. (Journal of Fish Biology, 2014)
In this study, the role of chicken gonadotropin‐releasing hormone II ( cgnrhII ) in feeding regulation was investigated in Schizothorax prenanti . First, the full‐length S. prenanti cgnrhII cDNA consisted of 693 bp with an open reading frame of 261 bp encoding a protein of 86 amino acids. Next, cgnrhII was widely expressed in the central and peripheral tissues. Last, there were significant changes in cgnrhII mRNA expression in the fasted group compared to the fed group in the S. prenanti hypothalamus during 24 h fasting ( P cgnrhII gene expression presented a significant decrease in the fasted group compared with the fed group ( P cgnrhII mRNA expression level between refed and fed group on day 9 ( P > 0·05). Thus, the results suggest that cGnRH II expression is influenced by fasting and the gene may be involved in feeding regulation in S. prenanti.

Mechanism-Based Pharmacokinetic Modeling to Evaluate Transporter-Enzyme Interplay in Drug Interactions and Pharmacogenetics of Glyburide - Manthena V. S. Varma; Renato J. Scialis; Jian Lin; Yi-An Bi; Charles J. Rotter; Theunis C. Goosen; Xin Yang (The AAPS Journal, 2014)

Temporal variability of forest communities: empirical estimates of population change in 4000 tree species - Ryan A. Chisholm; Richard Condit; K. Abd. Rahman; Patrick J. Baker; Sarayudh Bunyavejchewin; Yu‐Yun Chen; George Chuyong; H. S. Dattaraja; Stuart Davies; Corneille E. N. Ewango; C. V. S. Gunatilleke; I. A. U. Nimal Gunatilleke; et al. (Ecology Letters, 2014)
Long‐term surveys of entire communities of species are needed to measure fluctuations in natural populations and elucidate the mechanisms driving population dynamics and community assembly. We analysed changes in abundance of over 4000 tree species in 12 forests across the world over periods of 6–28 years. Abundance fluctuations in all forests are large and consistent with population dynamics models in which temporal environmental variance plays a central role. At some sites we identify clear environmental drivers, such as fire and drought, that could underlie these patterns, but at other sites there is a need for further research to identify drivers. In addition, cross‐site comparisons showed that abundance fluctuations were smaller at species‐rich sites, consistent with the idea that stable environmental conditions promote higher diversity. Much community ecology theory emphasises demographic variance and niche stabilisation; we encourage the development of theory in which temporal environmental variance plays a central role.

Effects of Dietary Selenium Deficiency on mRNA Levels of Twenty-One Selenoprotein Genes in the Liver of Layer Chicken - C. P. Liu; J. Fu; S. L. Lin; X. S. Wang; S. Li (Biological Trace Element Research, 2014)

Peptides Regulate Expression of Signaling Molecules in Kidney Cell Cultures during In Vitro Aging - V. Kh. Khavinson; N. S. Lin’kova; V. O. Polyakova; A. O. Durnova; T. E. Nichik; I. M. Kvetnoi (Bulletin of Experimental Biology and Medicine, 2014)

Short Peptides Stimulate Serotonin Expression in Cells of Brain Cortex - V. Kh. Khavinson; N. S. Lin’kova; S. I. Tarnovskaya; R. S. Umnov; E. V. Elashkina; A. O. Durnova (Bulletin of Experimental Biology and Medicine, 2014)

Early Airway Structural Changes in Cystic Fibrosis Pigs as a Determinant of Particle Distribution and Deposition - Maged Awadalla; Shinjiro Miyawaki; Mahmoud H. Abou Alaiwa; Ryan J. Adam; Drake C. Bouzek; Andrew S. Michalski; Matthew K. Fuld; Karen J. Reynolds; Eric A. Hoffman; Ching-Long Lin; David A. Stoltz (Annals of Biomedical Engineering, 2014)

Lasting neurobehavioral abnormalities in rats after neonatal activation of serotonin 1A and 1B receptors: possible mechanisms for serotonin dysfunction in autistic spectrum disorders - Nidhi Khatri; Kimberly L. Simpson; Rick C. S. Lin; Ian A. Paul (Psychopharmacology, 2014)

Association analysis of 9,560 prostate cancer cases from the International Consortium of Prostate Cancer Genetics confirms the role of reported prostate cancer associated SNPs for familial disease - Craig C. Teerlink; Stephen N. Thibodeau; Shannon K. McDonnell; Daniel J. Schaid; Antje Rinckleb; Christiane Maier; Walther Vogel; Geraldine Cancel-Tassin; Christophe Egrot; Olivier Cussenot; William D. Foulkes; Graham G. Giles; et al. (Human Genetics, 2014)

Trends in the susceptibility of methicillin-resistant Staphylococcus aureus to nine antimicrobial agents, including ceftobiprole, nemonoxacin, and tyrothricin: results from the Tigecycline In Vitro Surveillance in Taiwan (TIST) study, 2006–2010 - Y.-H. Chen; C.-Y. Liu; W.-C. Ko; C.-H. Liao; P.-L. Lu; C.-H. Huang; C.-T. Lu; Y.-C. Chuang; S.-M. Tsao; Y.-S. Chen; Y.-C. Liu; W.-Y. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Evacuees’ information sources and reentry decision making in the aftermath of Hurricane Ike - Chih-Chun Lin; Laura K. Siebeneck; Michael K. Lindell; Carla S. Prater; Hao-Che Wu; Shih-Kai Huang (Natural Hazards, 2014)

Motor Cortex Excitability in Acute Cerebellar Infarct - William Huynh; Arun V. Krishnan; Steve Vucic; Cindy S-Y. Lin; Matthew C. Kiernan (The Cerebellum, 2013)

Molecular Evolutionary Analysis of Vertebrate Transducins: A Role for Amino Acid Variation in Photoreceptor Deactivation - Yi G. Lin; Cameron J. Weadick; Francesco Santini; Belinda S. W. Chang (Journal of Molecular Evolution, 2013)

Pharmaceutical residues in tidal surface sediments of three rivers in southeastern China at detectable and measurable levels - Yongshan S. Chen; Shen Yu; Youwei W. Hong; Qiaoying Y. Lin; Hongbo B. Li (Environmental Science and Pollution Research, 2013)

Recommendations for the processing and storage of water samples before polymerase chain reaction (PCR) analysis - BJ Gilpin; M Devane; F Nourozi; B Robson; P Scholes; S Lin (New Zealand Journal of Marine and Freshwater Research, 2013)
A range of options for the storage and partial processing of water samples before polymerase chain reaction (PCR) analysis were evaluated. In addition, temporal storage of extracted DNA at 4 °C was investigated. Filtering the water sample and then storing that filter at −20 °C for up to six months before DNA extraction was equivalent to extracting DNA immediately. Freezing a water sample resulted in an immediate 1 log loss of PCR signal, although thereafter the sample was stable for at least three months. A rapid loss of detectable PCR product was found when storing a water sample at 4 °C for longer than one week. Extracted DNA could be stored at 4 °C for at least six months without considerable loss of PCR signal.

White spot syndrome virus epizootic in cultured P acific white shrimp L itopenaeus vannamei (Boone) in T aiwan - L Cheng; W‐H Lin; P‐C Wang; M‐A Tsai; J‐P Hsu; S‐C Chen (Journal of Fish Diseases, 2013)
White spot syndrome virus ( WSSV ) has caused significant losses in shrimp farms worldwide. Between 2004 and 2006, Pacific white shrimp L itopenaeus vannamei (Boone) were collected from 220 farms in T aiwan to determine the prevalence and impact of WSSV infection on the shrimp farm industry. Polymerase chain reaction ( PCR ) analysis detected WSSV in shrimp from 26% of farms. Juvenile shrimp farms had the highest infection levels (38%; 19/50 farms) and brooder shrimp farms had the lowest (5%; one of 20 farms). The average extent of infection at each farm was as follows for WSSV ‐positive farms: post‐larvae farms, 71%; juvenile farms, 61%; subadult farms, 62%; adult farms, 49%; and brooder farms, 40%. Characteristic white spots, hypertrophied nuclei and basophilic viral inclusion bodies were found in the epithelia of gills and tail fans, appendages, cephalothorax and hepatopancreas, and virions of WSSV were observed. Of shrimp that had WSSV lesions, 100% had lesions on the cephalothorax, 96% in gills and tail fans, 91% on appendages and 17% in the hepatopancreas. WSSV was also detected in copepoda and crustaceans from the shrimp farms. Sequence comparison using the pms146 gene fragment of WSSV showed that isolates from the farms had 99.7–100% nucleotide sequence identity with four strains in the G en B ank database – China ( AF332093 ), T aiwan ( AF440570 and U50923 ) and Thailand ( AF369029 ). This is the first broad study of WSSV infection in L . vannamei in T aiwan.

Potential use of chitosan nanoparticles for oral delivery of DNA vaccine in black seabream Acanthopagrus schlegelii Bleeker to protect from Vibrio parahaemolyticus - L Li; S‐L Lin; L Deng; Z‐G Liu (Journal of Fish Diseases, 2013)
To develop an effective and easy‐to‐administer vaccine against vibriosis of fish, the chitosan nanoparticles‐loaded DNA vaccine against Vibrio parahaemolyticus was studied. A DNA vaccine was constructed using the outer membrane protein K ( ompK ) gene of V. parahaemolyticus strain (OS4) and pEGFP ‐N 2 , a eukaryotic expression vector, and the construct was named pEGFP ‐N 2 ‐OMPK ( pDNA ). The pDNA was encapsulated in chitosan particles (chitosan/ pDNA ). The effective diameter, mean diameter and polydispersity of the particles were 284.4 nm, 218.9 nm and 0.160, respectively. Scanning electron microscopy showed that the particles are dispersed as individual nanoparticles with spherical shape of around 200 nm and are homogeneously distributed. Encapsulation efficiency and loading percentage of nanoparticles were 91.5% and 2.08%, respectively. Reverse transcription–polymerase chain reaction (RT‐PCR) showed that RNA‐containing information of the ompK gene existed in mid‐intestine, liver, kidney and muscle 3 weeks after oral administration in black seabream Acanthopagrus schlegelii Bleeker. Expression of the reporter gene, green fluorescent protein ( GFP ), was observed in the above‐mentioned tissues by fluorescence microscopy. Expression of the ompK gene within 3 weeks evoked an immune response. Black seabream was protected from V. parahaemolyticus (OS4), with 72.3% relative percentage survival (RPS) 3 weeks post‐vaccination with chitosan/ pDNA . The direct agglutination test indicated that oral administration with chitosan/ pDNA induced an antibody immune response in fish against V. parahaemolyticus (OS4). Data obtained, here and in other related studies, suggest that chitosan nanoparticles are promising carriers for an oral pDNA vaccine.

Photosynthesis of temperate E ucalyptus globulus trees outside their native range has limited adjustment to elevated CO 2 and climate warming - Kristine Y. Crous; Audrey G. Quentin; Yan‐Shih Lin; Belinda E. Medlyn; David G. Williams; Craig V. M. Barton; David S. Ellsworth (Global Change Biology, 2013)
E ucalyptus species are grown widely outside of their native ranges in plantations on all vegetated continents of the world. We predicted that such a plantation species would show high potential for acclimation of photosynthetic traits across a wide range of growth conditions, including elevated [ CO 2 ] and climate warming. To test this prediction, we planted temperate E ucalyptus globulus Labill. seedlings in climate‐controlled chambers in the field located >700 km closer to the equator than the nearest natural occurrence of this species. Trees were grown in a complete factorial combination of elevated CO 2 concentration ( eC ; ambient [ CO 2 ] +240 ppm) and air warming treatments ( eT ; ambient +3 °C) for 15 months until they reached ca. 10 m height. There was little acclimation of photosynthetic capacity to eC and hence the CO 2 ‐induced photosynthetic enhancement was large (ca. 50%) in this treatment during summer. The warming treatment significantly increased rates of both carboxylation capacity ( V cmax ) and electron transport ( J max ) (measured at a common temperature of 25 °C) during winter, but decreased them significantly by 20–30% in summer. The photosynthetic CO 2 compensation point in the absence of dark respiration ( Γ *) was relatively less sensitive to temperature in this temperate eucalypt species than for warm‐season tobacco. The temperature optima for photosynthesis and J max significantly changed by about 6 °C between winter and summer, but without further adjustment from early to late summer. These results suggest that there is an upper limit for the photosynthetic capacity of E . globulus ssp. globulus outside its native range to acclimate to growth temperatures above 25 °C. Limitations to temperature acclimation of photosynthesis in summer may be one factor that defines climate zones where E . globulus plantation productivity can be sustained under anticipated global environmental change.

Isolation and molecular analysis of genes Stpk-V2 and Stpk-V3 homologous to powdery mildew resistance gene Stpk-V in a Dasypyrum villosum accession and its derivatives - Z. S. Lin; Y. L. Zhang; M. J. Wang; J. R. Li; K. Wang; X. Chen; Q. F. Xu; X. S. Zhang; X. G. Ye (Journal of Applied Genetics, 2013)

Effect of aging on inter-joint synergies during machine-paced assembly tasks - Xu Xu; Jin Qin; Robert D. Catena; Gert S. Faber; Jia-Hua Lin (Experimental Brain Research, 2013)

The California Breast Cancer Survivorship Consortium (CBCSC): prognostic factors associated with racial/ethnic differences in breast cancer survival - Anna H. Wu; Scarlett Lin Gomez; Cheryl Vigen; Marilyn L. Kwan; Theresa H. M. Keegan; Yani Lu; Salma Shariff-Marco; Kristine R. Monroe; Allison W. Kurian; Iona Cheng; Bette J. Caan; Valerie S. Lee; et al. (Cancer Causes & Control, 2013)

High Sensitivity Micro-Elastometry: Applications in Blood Coagulopathy - Gongting Wu; Charles R. Krebs; Feng-Chang Lin; Alisa S. Wolberg; Amy L. Oldenburg (Annals of Biomedical Engineering, 2013)

Human white adipose tissue vasculature contains endothelial colony-forming cells with robust in vivo vasculogenic potential - Ruei-Zeng Lin; Rafael Moreno-Luna; Rocio Muñoz-Hernandez; Dan Li; Shou-Ching S. Jaminet; Arin K. Greene; Juan M. Melero-Martin (Angiogenesis, 2013)

Core–shell magnetite-silica dithiocarbamate-derivatised particles achieve the Water Framework Directive quality criteria for mercury in surface waters - C. B. Lopes; P. Figueira; D. S. Tavares; Z. Lin; A. L. Daniel-da-Silva; A. C. Duarte; J. Rocha; T. Trindade; E. Pereira (Environmental Science and Pollution Research, 2013)

Soluble interleukin‐1 receptor, a potential negative regulator of orange‐spotted grouper Epinephelus coioides interleukin‐1 system - D. Q. Lu; M. Yao; S. B. Yi; Y. W. Li; X. C. Liu; Y. Zhang; H. R. Lin (Journal of Fish Biology, 2013)
In this study, the cDNA sequence encoding interleukin‐1 ( Il ‐1) receptor‐like protein of orange‐spotted grouper Epinephelus coioides was obtained. The newly identified sequence was named soluble type I Il ‐1 receptor ( sIl‐1rI ) owing to its structural composition, which had two Ig‐like domains, lack of transmembrane region and the Toll/interleukin‐1 receptor ( TIR ) domain, similar to the brown rat Rattus norvegicus soluble Il‐1rI . In addition, sequence comparison and phylogenetic analysis indicated that E. coioides sequence had a closer relationship with Il‐1rI than Il‐1rII . Real‐time PCR revealed that sil‐1rI mRNA expression presented a process of decrease, restoration and increase in Cryptocaryon irritans ‐infected E. coioides . The negative correlation between Il ‐1β and sil‐1rI mRNA in C. irritans ‐infected head‐kidney implied the potential negative regulatory role of sil‐1rI in E. coioides Il ‐1 system. The leucocytes incubated with lipopolysaccharide or polyriboinosinic polyribocytidylic acid exhibited different expression profiles of sil‐1rI . Recombinant Il ‐1β ( rIl ‐1β) protein was capable of inducing sil‐1rI mRNA under the concentration of 100 ng ml −1 , suggesting that high dosage or excess Il ‐1β would stimulate the expression of sil‐1rI to maintain the homoeostasis of E. coioides Il ‐1 system. For the first time, the role of teleost Il‐1rI in parasite infection has been identified, and soluble Il‐1r was found in fish.

Warming up to climate change: a participatory approach to engaging with agricultural stakeholders in the Southeast US - Wendy-Lin Bartels; Carrie A. Furman; David C. Diehl; Fred S. Royce; Daniel R. Dourte; Brenda V. Ortiz; David F. Zierden; Tracy A. Irani; Clyde W. Fraisse; James W. Jones (Regional Environmental Change, 2013)

Rural livelihoods and climate variability in Ningxia, Northwest China - Yue Li; D. Conway; Yanjuan Wu; Qingzhu Gao; S. Rothausen; Wei Xiong; Hui Ju; Erda Lin (Climatic Change, 2013)

The use of procalcitonin in the diagnosis of bone and joint infection: a systemic review and meta-analysis - C.-J. Shen; M.-S. Wu; K.-H. Lin; W.-L. Lin; H.-C. Chen; J.-Y. Wu; M. C.-H. Lee; C.-C. Lee (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Outcome of metastatic breast cancer in selected women with or without deleterious BRCA mutations - S. Bayraktar; A. M. Gutierrez-Barrera; H. Lin; N. Elsayegh; T. Tasbas; J. K. Litton; N. K. Ibrahim; P. K. Morrow; M. Green; V. Valero; D. J. Booser; G. N. Hortobagyi; et al. (Clinical & Experimental Metastasis, 2013)

Characterization of a novel cell line from the caudal fin of koi carp Cyprinus carpio - S.‐L. Lin; Y.‐H. Cheng; C.‐M. Wen; S.‐N. Chen (Journal of Fish Biology, 2013)
A continuous cell line ( KF ‐101) derived from the caudal fin of the koi carp Cyprinus carpio was established and characterized. The KF ‐101 cell line multiplied abundantly in Leibovitz's L‐15 medium containing 10% foetal bovine serum at 25° C, and was subcultured for >90 passages over a period of 3 years. Immunocytochemistry revealed that the KF ‐101 cells contain keratin, junction proteins connexin‐43 and occludin, and ectodermal stem‐cell marker Pax‐6, but not vimentin. Furthermore, the KF ‐101 cells reacted with anti‐human DARPP ‐32 and anti‐human GATA ‐4 antibodies, and the labelling was regulated according to the cell cycle. The labels of the DARPP ‐32 and GATA ‐4 antibodies in the KF ‐101 cells were the suggested phosphatase‐1 inhibitor‐1 and GATA ‐3, respectively. In addition, the KF ‐101 cells were susceptible to koi herpesvirus but were resistant to eel herpesvirus, iridovirus, grouper nodavirus and chum salmon ( Oncorhynchus keta ) virus. The results indicate that the KF ‐101 cells are suitable materials for investigating biological and virological development.

Effectiveness of participatory training for prevention of musculoskeletal disorders: a randomized controlled trial - Wenzhou Yu; Ignatius T. S. Yu; Xiaorong Wang; Zhimin Li; Sabrina Wan; Hong Qiu; Hui Lin; Shaohua Xie; Trevor Sun (International Archives of Occupational and Environmental Health, 2013)

Assessing production of the ubiquitous archaeal diglycosyl tetraether lipids in marine subsurface sediment using intramolecular stable isotope probing - Yu‐Shih Lin; Julius S. Lipp; Marcus Elvert; Thomas Holler; Kai‐Uwe Hinrichs (Environmental Microbiology, 2013)
Summary The membrane lipids diglycosyl‐glycerol dibiphytanyl glycerol tetraethers ( 2G ‐ GDGTs ) in marine subsurface sediments are believed to originate from uncultivated benthic archaea, yet the production of 2G ‐ GDGTs from subseafloor samples has not been demonstrated in vitro . In order to validate sedimentary biosynthesis of 2G ‐ GDGTs , we performed a stable carbon isotope probing experiment on a subseafloor sample with six different 13 C ‐labelled substrates (bicarbonate, methane, acetate, leucine, glucose and S pirulina platensis biomass). After 468 days of anoxic incubation, only glucose and S . platensis resulted in label uptake in lipid moieties of 2G ‐ GDGTs , indicating incorporation of carbon from these organic substrates. The hydrophobic moieties of 2G ‐ GDGTs showed minimal label incorporation, with up to 4‰ 13 C enrichment detected in crenarchaeol‐derived tricyclic biphytane from the S . platensis ‐supplemented slurries. The 2G ‐ GDGT ‐derived glucose or glycerol moieties also showed 13 C incorporation (Δδ 13 C = 18–38‰) in the incubations with glucose or S . platensis , consistent with a lipid salvage mechanism utilized by marine benthic archaea to produce new 2G ‐ GDGTs . The production rates were nevertheless rather slow, even when labile organic matter was supplied. The 2G ‐ GDGT turnover times of 1700–20 500 years were much longer than those estimated for subseafloor microbial communities, implying that sedimentary 2G ‐ GDGTs as biomarkers of benthic archaea are cumulative records of past and present generations.

Genome-wide association study identified novel genetic variant on SLC45A3 gene associated with serum levels prostate-specific antigen (PSA) in a Chinese population - Jielin Sun; Sha Tao; Yong Gao; Tao Peng; Aihua Tan; Haiying Zhang; Xiaobo Yang; Xue Qin; Yanling Hu; Junjie Feng; Seong-Tae Kim; Xiaoling Lin; et al. (Human Genetics, 2013)

Prevalence of type-specific human papillomavirus and pap results in Chinese women: a multi-center, population-based cross-sectional study - En-Qi Wu; Bin Liu; Jian-Feng Cui; Wen Chen; Jian-Bing Wang; Liang Lu; Mayineur Niyazi; Chao Zhao; Sheng-Da Ren; Chang-Qing Li; Xiang-Zhen Gong; Jennifer S. Smith; et al. (Cancer Causes & Control, 2013)

FOXO1-mediated upregulation of pyruvate dehydrogenase kinase-4 (PDK4) decreases glucose oxidation and impairs right ventricular function in pulmonary hypertension: therapeutic benefits of dichloroacetate - Lin Piao; Vaninder K. Sidhu; Yong-Hu Fang; John J. Ryan; Kishan S. Parikh; Zhigang Hong; Peter T. Toth; Erik Morrow; Shelby Kutty; Gary D. Lopaschuk; Stephen L. Archer (Journal of Molecular Medicine, 2013)

Seismic health monitoring of RC frame structures using smart aggregates - Wen-I Liao; C. H. Lin; J. S. Hwang; G. Song (Earthquake Engineering and Engineering Vibration, 2013)

Sex identification in the Collared Scops Owl (Otus bakkamoena) with novel markers generated by random amplified polymorphic DNA - P. H. Wang; H. A. Hsu; M. C. Chao; F. T. Chan; L. M. Wang; P. I. Lin; H. S. Tsao; H. W. Yuan; C. C. Chen; S. T. Ding (Conservation Genetics Resources, 2013)

Climate trends in indices for temperature and precipitation across New York State, 1948–2008 - T. Z. Insaf; S. Lin; S. C. Sheridan (Air Quality, Atmosphere & Health, 2013)

HOXB13 is a susceptibility gene for prostate cancer: results from the International Consortium for Prostate Cancer Genetics (ICPCG) - Jianfeng Xu; Ethan M. Lange; Lingyi Lu; Siqun L. Zheng; Zhong Wang; Stephen N. Thibodeau; Lisa A. Cannon-Albright; Craig C. Teerlink; Nicola J. Camp; Anna M. Johnson; Kimberly A. Zuhlke; Janet L. Stanford; et al. (Human Genetics, 2013)

Water quality associated public health risk in Bo, Sierra Leone - David H. Jimmy; Abu J. Sundufu; Anthony P. Malanoski; Kathryn H. Jacobsen; Rashid Ansumana; Tomasz A. Leski; Umaru Bangura; Alfred S. Bockarie; Edries Tejan; Baochuan Lin; David A. Stenger (Environmental Monitoring and Assessment, 2013)

Reproductive hormones and interleukin-6 in serious leisure male athletes - Leah Z. FitzGerald; Wendie A. Robbins; James S. Kesner; Lin Xun (European Journal of Applied Physiology, 2012)

Role of obesity in a randomized placebo-controlled trial of difluoromethylornithine (DFMO) + sulindac for the prevention of sporadic colorectal adenomas - Jason A. Zell; Bruce S. Lin; Nikki Madson; Christine E. McLaren; Eugene W. Gerner; Frank L. Meyskens (Cancer Causes & Control, 2012)

Unincorporated iron pool is linked to oxidative stress and iron levels in Caenorhabditis elegans - Natalie A. Rangel; Lawrence Lin; Kanyasiri Rakariyatham; Albert Bach; Kim Trinh; Matthew H. S. Clement; Chandra Srinivasan (BioMetals, 2012)

Disease-modifying drugs for multiple sclerosis and JC virus expression - Craig S. Miller; Sidney A. Houff; Jason Hopper; Robert J. Danaher; Julie A. Gurwell; Yushun Lin; Nubia Vega; Joseph R. Berger (Journal of NeuroVirology, 2012)

Development of microsatellite markers in an ungulate mammal, the Formosan serow (Capricornis swinhoei) - Y. Y. Chang; M. C. Chao; S. T. Ding; E.-C. Lin; H. S. Tsao; H. W. Yuan; P. H. Wang (Conservation Genetics Resources, 2012)

Large-scale collection and annotation of gene models for date palm (Phoenix dactylifera, L.) - Guangyu Zhang; Linlin Pan; Yuxin Yin; Wanfei Liu; Dawei Huang; Tongwu Zhang; Lei Wang; Chengqi Xin; Qiang Lin; Gaoyuan Sun; Mohammed M. Ba Abdullah; Xiaowei Zhang; et al. (Plant Molecular Biology, 2012)

Chronic aspiration shifts the immune response from adaptive immunity to innate immunity in a murine model of asthma - Kuei-Ying Su; Anitra D. Thomas; Jui-Chih Chang; Jason H. Leung; Sean M. Lee; Zoie E. Holzknecht; Mary Lou Everett; W. Michael Foster; Monica Kraft; William Parker; R. Duane Davis; Shu S. Lin (Inflammation Research, 2012)

Characterization of carbapenem-nonsusceptible Klebsiella pneumoniae bloodstream isolates at a Taiwanese hospital: clinical impacts of lowered breakpoints for carbapenems - N. Y. Lee; J. J. Wu; S. H. Lin; W. C. Ko; L. H. Tsai; J. J. Yan (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Tetrapeptide H-Ala-Glu-Asp-Arg-OH Stimulates Expression of Cytoskeletal and Nuclear Matrix Proteins - V. Kh. Khavinson; N. S. Lin’kova; V. O. Polyakova; I. M. Kvetnoy; V. V. Benberin; M. M. D’yakonov; Yu. S. Titkov (Bulletin of Experimental Biology and Medicine, 2012)

Exploring the spatial and temporal relationships between mosquito population dynamics and dengue outbreaks based on climatic factors - Ching-Tsan Tsai; Fung-Chang Sung; Patrick S. Chen; Shu-Chiung Lin (Stochastic Environmental Research and Risk Assessment, 2012)

Validation of prostate cancer risk-related loci identified from genome-wide association studies using family-based association analysis: evidence from the International Consortium for Prostate Cancer Genetics (ICPCG) - Guangfu Jin; Lingyi Lu; Kathleen A. Cooney; Anna M. Ray; Kimberly A. Zuhlke; Ethan M. Lange; Lisa A. Cannon-Albright; Nicola J. Camp; Craig C. Teerlink; Liesel M. FitzGerald; Janet L. Stanford; Kathleen E. Wiley; et al. (Human Genetics, 2012)

Regional variation in otolith Sr:Ca ratios of African longfinned eel Anguilla mossambica and mottled eel Anguilla marmorata : a challenge to the classic tool for reconstructing migratory histories of fishes - Y.‐J. Lin; B. M. Jessop; O. L. F. Weyl; Y. Iizuka; S.‐H. Lin; W.‐N. Tzeng; C.‐L. Sun (Journal of Fish Biology, 2012)
Otolith Sr:Ca ratios of the African longfinned eel Anguilla mossambica and giant mottled eel Anguilla marmorata from nine freshwater sites in four rivers of South Africa were analysed to reconstruct their migratory life histories between freshwater and saltwater habitats. For A. mossambica , the Sr:Ca ratios in the otolith edge differed significantly among rivers and had large effect sizes, but did not differ among sites within a river. Otolith Sr:Ca ratios did not differ among rivers for A. marmorata . When rivers were pooled, the edge Sr:Ca ratios of A. mossambica were not significantly different from those of A. marmorata . According to the river‐specific critical Sr:Ca ratio distinguishing freshwater from saltwater residence, most A. mossambica and A. marmorata had saltwater habitat experience after settlement in fresh water. This was primarily during their elver stage or early in the yellow eel stage. During the middle and late yellow eel stage, freshwater residency was preferred and only sporadic visits were made to saltwater habitats. The data also suggest that regional variations in otolith Sr:Ca ratios affect the critical Sr:Ca value and are a challenge for the reconstruction of migratory life histories that should be explicitly considered to avoid bias and uncertainty.

Identification and expression analysis of major histocompatibility complex IIB gene in orange‐spotted grouper Epinephelus coioides - D. Q. Lu; S. B. Yi; M. Yao; Y. W. Li; X. C. Liu; Y. Zhang; H. R. Lin (Journal of Fish Biology, 2012)
In this study, complementary DNA (cDNA) and DNA sequences of major histocompatibility complex (MHC) class IIB genes ( mhcIIB ) were cloned from orange‐spotted grouper Epinephelus coioides . The gene structure of E. coioides mhcIIB consists of five exons and four introns, and its deduced amino acid sequence length is 249 amino acids, including a signal peptide, a peptide‐binding region, an IGC1 domain, a transmembrane region and a cytoplasmic tail. A phylogenetic study showed that E. coioides mhcIIB shared 32·0–79·1% identity with those of other teleosts and mammals. Real‐time reverse transcriptase (RT)‐PCR was performed to detect the class IIB gene expression in eight different tissues. To characterize the relationship between E. coioides mhcIIB gene and pathogens, in vivo and in vitro studies were performed. Challenge of Cryptocaryon irritans revealed that class IIB genes were down‐regulated after 24 and 48 h of challenge, and their expression was later restored at 72 h. Stimulation of isolated E. coioides leukocytes with lipopolysaccharide (LPS) and polyinosinic:polycytidylic acid (PolyI:C) significantly increased peripheral blood and spleen mhcIIB expression, while head kidney mhcIIB expression remained constant.

Enhancing a Cancer Prevention and Control Curriculum Through Interactive Group Discussions - L. P. Forsythe; S. M. Gadalla; J. G. Hamilton; B. M. Heckman-Stoddard; E. E. Kent; G. Y. Lai; S. W. Lin; P. Luhn; J. M. Faupel-Badger (Journal of Cancer Education, 2012)

Reemerging of enterovirus 71 in Taiwan: the age impact on disease severity - S.-M. Wang; T.-S. Ho; H.-C. Lin; H.-Y. Lei; J.-R. Wang; C.-C. Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Metabolic imaging of mild traumatic brain injury - A. P. Lin; H. J. Liao; S. K. Merugumala; S. P. Prabhu; W. P. Meehan; B. D. Ross (Brain Imaging and Behavior, 2012)

A review of magnetic resonance imaging and diffusion tensor imaging findings in mild traumatic brain injury - M. E. Shenton; H. M. Hamoda; J. S. Schneiderman; S. Bouix; O. Pasternak; Y. Rathi; M.-A. Vu; M. P. Purohit; K. Helmer; I. Koerte; A. P. Lin; C.-F. Westin; et al. (Brain Imaging and Behavior, 2012)

Mortality in a Chinese chrysotile miner cohort - Xiaorong Wang; Sihao Lin; Eiji Yano; Hong Qiu; Igtanius T. S. Yu; Lapah Tse; Yajia Lan; Mianzhen Wang (International Archives of Occupational and Environmental Health, 2012)

Aesthetascs in Lysmata spp. shrimp: sexual dimorphism and relationship with social environments - Jing Zhu; Dong Zhang; Junda Lin; Michael S. Grace (Marine Biology, 2012)

Seasonal Variation and Health Risk Assessment of Polycyclic Aromatic Hydrocarbons in Miaoli City, Taiwan - C. C. Wu; T. S. Lin; T. T. Yang; H. W. Hsu; C. L. Chang; C. H. Huang; W. Y. Lin (Bulletin of Environmental Contamination and Toxicology, 2012)

Peptidergic Regulation of Expression of Genes Encoding Antioxidant and Anti-Inflammatory Proteins - V. Kh. Khavinson; N. S. Lin’kova; A. V. Dudkov; V. O. Polyakova; I. M. Kvetnoi (Bulletin of Experimental Biology and Medicine, 2012)

Spatial dependence of alveolar angiogenesis in post-pneumonectomy lung growth - Moritz A. Konerding; Barry C. Gibney; Jan P. Houdek; Kenji Chamoto; Maximilian Ackermann; Grace S. Lee; Miao Lin; Akira Tsuda; Steven J. Mentzer (Angiogenesis, 2012)

Differential expression profiling of orange‐spotted grouper larvae, Epinephelus coioides (Hamilton), that survived a betanodavirus outbreak - M‐S Wu; C‐W Chen; C‐H Lin; C‐S Tzeng; C‐Y Chang (Journal of Fish Diseases, 2012)
Nervous necrosis virus (NNV), a piscine nodavirus, has caused serious viral nervous necrosis and viral encephalopathy and retinopathy in hatchery‐reared larvae and juveniles of a wide range of marine teleost species worldwide in the last two decades. Although the mortality of NNV‐infected larvae is nearly 100%, there are still some larvae that survive this catastrophe. To comprehensively understand the variations of these survivors at the molecular level, we collected orange‐spotted grouper larvae that survived an NNV outbreak in an indoor hatchery in southern Taiwan to study differential gene expression. Healthy larvae with high, medium and low levels of detected NNV were compared with morbid larvae using a 9600‐clone‐containing grouper larva cDNA microarray, and differential gene expression was further confirmed by a quantitative real‐time polymerase chain reaction. Significant variation exists in healthy larvae. The following genes were upregulated: adenylate kinase 1‐2, myosin binding protein H‐like, myosin light chain 2, myosin light chain 3, tropomyosin, fast/white muscle troponin T embryonic isoform, and parvalbumin 1 and 2 genes. The following genes were downregulated: apolipoprotein A‐I, trypsinogen, pyruvate kinase and astacin‐like metalloprotease. Moreover, immunoglobulin M heavy chain gene transcription was significantly higher in healthy larvae that had high virus levels, indicating that humoral immunity might protect organisms from viral infection. These results suggest that some non‐immune‐related genes may have played important roles in survival during the larval metamorphosis stage, after betanodavirus infection.

Germ cells and fertilization differences among Japanese flounder Paralichthys olivaceus , summer flounder Paralichthys dentatus and their first and second generations - J. Sui; D. Y. Ma; Q. H. Liu; S. H. Xu; Z. Z. Xiao; F. Lin; Y. S. Xiao; J. Li (Journal of Fish Biology, 2012)
The morphology of gametes and the fertilization biology of Japanese flounder Paralichthys olivaceus (Po), summer flounder Paralichthys dentatus (Pd) and their hybrids were examined. Multiple generations (two hybrids: Po♀× Pd♂ (F1) and Pd♀× Po♂; two backcrosses: F1♀× Po♂ and F1♀× Pd♂) were obtained by artificial insemination. Comparison of egg ultrastructure among Po, Pd and F1 showed the morphology of micropyle region and the distribution density of pores were species specific. There were c . 100–200 accessory openings around the micropyle in Po, but not in Pd and F1. The zona radiata thickness and number of parallel bands were similar between F1 and Po, which were different from Pd. Comparison of spermatozoa ultrastructure revealed a close relationship between Po and Pd. Cytologically, the six crosses obeyed normal fertilization and cleavage processes, and only one male pronucleus was observed in a fertilized egg, indicating a monospermic fertilization pattern. Analysis of the time distribution from fertilization to first cleavage revealed an obvious delay at pronucleus fusion in the Pd × Po cross. The delay might indicate some cytoplasmic‐nuclear incompatibility during the process of fertilization.

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Characteristics of Polycyclic Aromatic Hydrocarbon Emissions of Particles of Various Sizes from Smoldering Incense - T. T. Yang; T. S. Lin; J. J. Wu; F. J. Jhuang (Bulletin of Environmental Contamination and Toxicology, 2012)

Arsenic content, fractionation, and ecological risk in the surface sediments of lake - S. L. Wang; C. Y. Lin; X. Z. Cao; X. Zhong (International Journal of Environmental Science and Technology, 2012)

Comparing the benefits of screening for breast cancer and lung cancer using a novel natural history model - Ray S. Lin; Sylvia K. Plevritis (Cancer Causes & Control, 2012)

Biodegradation of Cypermethrin by a newly isolated actinomycetes HU-S-01 from wastewater sludge - Q. S. Lin; S. H. Chen; M. Y. Hu; M. R. Ul Haq; L. Yang; H. Li (International Journal of Environmental Science and Technology, 2011)

Increasing trend of primary NO2 exhaust emission fraction in Hong Kong - Linwei Tian; Sarah R. Hossain; Hualiang Lin; Kin Fai Ho; Shun Cheng Lee; Ignatius T. S. Yu (Environmental Geochemistry and Health, 2011)

Gold Nanoparticle Penetration and Reduced Metabolism in Human Skin by Toluene - Hagar I. Labouta; David C. Liu; Lynlee L. Lin; Margaret K. Butler; Jeffrey E. Grice; Anthony P. Raphael; Tobias Kraus; Labiba K. El-Khordagui; H. Peter Soyer; Michael S. Roberts; Marc Schneider; Tarl W. Prow (Pharmaceutical Research, 2011)

Time-Correlated Single Photon Counting For Simultaneous Monitoring Of Zinc Oxide Nanoparticles And NAD(P)H In Intact And Barrier-Disrupted Volunteer Skin - Lynlee L. Lin; Jeffrey E. Grice; Margaret K. Butler; Andrei V. Zvyagin; Wolfgang Becker; Thomas A. Robertson; H. Peter Soyer; Michael S. Roberts; Tarl W. Prow (Pharmaceutical Research, 2011)

cDNA cloning and characterization of a new member of the tumor necrosis factor receptor family gene from scallop, Chlamys farreri - Jianguo Su; Limei Qiu; Ling li; Lin Liu; Lingling Wang; Vinu S. Siva; Dahui Yu; Linsheng Song (Molecular Biology Reports, 2011)

Bacteremia caused by Brevundimonas species at a tertiary care hospital in Taiwan, 2000–2010 - M. R. Lee; Y. T. Huang; C. H. Liao; T. Y. Chuang; C. K. Lin; S. W. Lee; C. C. Lai; C. J. Yu; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Taxonomy, morphology and molecular systematics of a new oligotrich ciliate, Williophrya maedai gen. nov., sp. nov., with redescriptions of Strombidium basimorphum and Pseudotontonia simplicidens (Protozoa, Ciliophora, Oligotrichia) - WEIWEI LIU; ZHENZHEN YI; ALAN WARREN; KHALED A. S. AL-RASHEID; SALEH A. AL-FARRAJ; XIAOFENG LIN; WEIBO SONG (Systematics and Biodiversity, 2011)

Assessment of nitrogen contamination of groundwater in paddy and upland fields - Y. H. Kao; C.-W. Liu; C. S. Jang; S. W. Zanh; K. H. Lin (Paddy and Water Environment, 2011)

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

A multivalent vaccine for type 1 diabetes skews T cell subsets to Th2 phenotype in NOD mice - Ming S. Lin; Hubert M. Tse; Meghan M. Delmastro; Suzanne Bertera; Caterina T. Wong; Robert Lakomy; Jing He; Martha M. Sklavos; Gina M. Coudriet; Massimo Pietropaolo; Massimo M. Trucco; Jon D. Piganelli (Immunologic Research, 2011)

The development of soil organic matter in restored biodiverse Jarrah forests of South-Western Australia as determined by ASE and GCMS - Deborah S. Lin; Paul F. Greenwood; Suman George; Paul J. Somerfield; Mark Tibbett (Environmental Science and Pollution Research, 2011)

Peptides from the Pituitary Gland and Cortex Stimulate Differentiation of Polypotent Embryonic Tissue - N. S. Lin’kova; A. V. Trofimov; A. V. Dudkov (Bulletin of Experimental Biology and Medicine, 2011)

Learning Through Service: Student Perceptions on Volunteering at Interprofessional Hepatitis B Student-run Clinics - Leslie C. Sheu; Patricia Zheng; Anabelle D. Coelho; Lisa D. Lin; Patricia S. O’Sullivan; Bridget C. O’Brien; Albert Y. Yu; Cindy J. Lai (Journal of Cancer Education, 2011)

Diagnostic performance of an enzyme-linked immunospot assay for interferon-γ in skeletal tuberculosis - C.-C. Lai; C.-K. Tan; W.-L. Liu; S.-H. Lin; Y.-T. Huang; C.-H. Liao; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Clinical significance of nontuberculous mycobacteria isolates in elderly Taiwanese patients - C.-C. Lai; C. K. Tan; S. H. Lin; W. L. Liu; C. H. Liao; Y. T. Huang; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Peptidergic Regulation of Thymocyte Differentiation, Proliferation, and Apoptosis during Aging of the Thymus - N. S. Lin’kova; V. O. Polyakova; A. V. Trofimov; I. M. Kvetnoy; V. Kh. Khavinson (Bulletin of Experimental Biology and Medicine, 2011)

Traceless synthesis of diketopiperazine fused tetrahydro-β-carbolines on soluble polymer support - Kaushik Chanda; Cheng-Ting Chou; Jin-Ji Lai; Shu-Fen Lin; Gorakh S. Yellol; Chung-Ming Sun (Molecular Diversity, 2011)

The controlled in vitro susceptibility of gastrointestinal pathogens to the antibacterial effect of manuka honey - S. M. Lin; P. C. Molan; R. T. Cursons (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Quantitative trait loci for temperature-sensitive resistance to Puccinia striiformis f. sp. tritici in wheat cultivar Flinor - J. Feng; L. L. Zuo; Z. Y. Zhang; R. M. Lin; Y. Y. Cao; S. C. Xu (Euphytica, 2011)

Inheritance of stripe rust resistance to predominant Chinese races in six spring wheat cultivars from the pacific Northwest of the United States - Y. Gao; Q. Sun; R. Wang; J. Feng; F. Lin; N. Cui; X. Chen; S. Xu; Y. Bai; X. Xu (Cereal Research Communications, 2011)

Genomic sequence of an avian paramyxovirus type 1 strain isolated from Muscovy duck (Cairina moschata) in China - S.-H. Shi; Yu Huang; S.-J. Cui; L.-F. Cheng; G.-H. Fu; X. Li; Z. Chen; C.-X. Peng; F. Lin; J.-S. Lin; Jing-Liang Su (Archives of Virology, 2011)

Urban China in transformation: Hybrid economy, juxtaposed space, and new testing ground for geographical enquiries - George C S Lin (Chinese Geographical Science, 2011)

Suprachoroidal Drug Delivery to the Back of the Eye Using Hollow Microneedles - Samirkumar R. Patel; Angela S. P. Lin; Henry F. Edelhauser; Mark R. Prausnitz (Pharmaceutical Research, 2011)

A GIS-based Decision Support System for Typhoon Emergency Response in Taiwan - Ming-Hsi Hsu; Albert S. Chen; Liang-Chun Chen; Cheng-Shang Lee; Feng-Tyan Lin; Chen-Jia Huang (Geotechnical and Geological Engineering, 2011)

The impact of microphysical schemes on hurricane intensity and track - Wei-Kuo Tao; Jainn Jong Shi; Shuyi S. Chen; Stephen Lang; Pay-Liam Lin; Song-You Hong; Christa Peters-Lidard; Arthur Hou (Asia-Pacific Journal of Atmospheric Sciences, 2011)

Mobilization and transport of coarse woody debris to the oceans triggered by an extreme tropical storm - A. J. West; C.-W. Lin; T.-C. Lin; R. G. Hilton; S.-H. Liu; C.-T. Chang; K.-C. Lin; A. Galy; R. B. Sparkes; N. Hovius (Limnology and Oceanography, 2011)
A significant consequence of Typhoon Morakot in August 2009 was the production of vast volumes of driftwood in Pacific Asia. We have quantified the flux of this coarse woody debris (CWD) to the oceans from typhoon‐triggered landslides in Taiwan, where Morakot made landfall, by combining remote sensing (using FORMOSAT‐2 imagery and aerial photography), analysis of forest biomass, and field observations. A total of 3.8–8.4 Tg CWD was transported to the oceans, carrying 1.8–4.0 Tg of organic carbon. In addition to the local effects on the marine and coastal environment from such a highly concentrated flux of carbon and nutrients, storm‐driven mobilization of CWD may represent a significant, if infrequent, transfer of terrestrial biomass to the oceans. If the frequency of relatively rare, extreme storms such as Morakot increases in a changing climate, this transport mechanism may play an important role in feedbacks between global climate, storm intensity, and carbon cycling.

QTL analysis and candidate gene mapping for skin and flesh color in sweet cherry fruit (Prunus avium L.) - Suneth S. Sooriyapathirana; Amjad Khan; Audrey M. Sebolt; Dechun Wang; Jill M. Bushakra; Kui Lin-Wang; Andrew C. Allan; Susan E. Gardiner; David Chagné; Amy F. Iezzoni (Tree Genetics & Genomes, 2010)

Groundwater Assessment at Manukan Island, Sabah: Multidisplinary Approaches - S. M. Praveena; C. Y. Lin; A. Z. Aris; M. H. Abdullah (Natural Resources Research, 2010)

Genetic polymorphisms of the DNA repair geneMPG may be associated with susceptibility to rheumatoid arthritis - S. Y. Chen; L. Wan; C. M. Huang; Y. C. Huang; J. J. C. Sheu; Y. J. Lin; S. P. Liu; Y. C. Lan; C. H. Lai; C. W. Lin; C. H. Tsai; F. J. Tsai (Journal of Applied Genetics, 2010)

Development of EST-PCR markers for Thinopyrum intermedium chromosome 2Ai#2 and their application in characterization of novel wheat-grass recombinants - M. J. Wang; Y. Zhang; Z. S. Lin; X. G. Ye; Y. P. Yuan; W. Ma; Z. Y. Xin (Theoretical and Applied Genetics, 2010)

Declining drug resistance of Mycobacterium tuberculosis isolates from elderly patients in Taiwan, 2000–2008 - W.-L. Liu; C.-C. Lai; C.-K. Tan; S.-H. Lin; Y.-T. Huang; C.-H. Liao; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Tikhonov adaptively regularized gamma variate fitting to assess plasma clearance of inert renal markers - Carl A. Wesolowski; Richard C. Puetter; Lin Ling; Paul S. Babyn (Journal of Pharmacokinetics and Pharmacodynamics, 2010)

Ecological Restoration of Polluted Plain Rivers Within the Haihe River Basin in China - W. Wang; X. Q. Tang; S. L. Huang; S. H. Zhang; C. Lin; D. W. Liu; H. J. Che; Q. Yang; Miklas Scholz (Water, Air, & Soil Pollution, 2010)

Cultivation‐independent characterization of ‘ Candidatus Magnetobacterium bavaricum’ via ultrastructural, geochemical, ecological and metagenomic methods - C. Jogler; M. Niebler; W. Lin; M. Kube; G. Wanner; S. Kolinko; P. Stief; A. J. Beck; D. de Beer; N. Petersen; Y. Pan; R. Amann; et al. (Environmental Microbiology, 2010)
Summary ‘ Candidatus Magnetobacterium bavaricum’ is unusual among magnetotactic bacteria (MTB) in terms of cell size (8–10 µm long, 1.5–2 µm in diameter), cell architecture, magnetotactic behaviour and its distinct phylogenetic position in the deep‐branching Nitrospira phylum. In the present study, improved magnetic enrichment techniques permitted high‐resolution scanning electron microscopy and energy dispersive X‐ray analysis, which revealed the intracellular organization of the magnetosome chains. Sulfur globule accumulation in the cytoplasm point towards a sulfur‐oxidizing metabolism of ‘ Candidatus M. bavaricum’. Detailed analysis of ‘ Candidatus M. bavaricum’ microhabitats revealed more complex distribution patterns than previously reported, with cells predominantly found in low oxygen concentration. No correlation to other geochemical parameters could be observed. In addition, the analysis of a metagenomic fosmid library revealed a 34 kb genomic fragment, which contains 33 genes, among them the complete rRNA gene operon of ‘ Candidatus M. bavaricum’ as well as a gene encoding a putative type IV RubisCO large subunit.

Using hyperspectral remote sensing to estimate chlorophyll‐ a and phycocyanin in a mesotrophic reservoir - Lin Li; Rebecca E. Sengpiel; Denise L. Pascual; Lenore P. Tedesco; Jeffrey S. Wilson; Emmanuel Soyeux (International Journal of Remote Sensing, 2010)

The chondroprotective effects of ferulic acid on hydrogen peroxide-stimulated chondrocytes: inhibition of hydrogen peroxide-induced pro-inflammatory cytokines and metalloproteinase gene expression at the mRNA level - M. P. Chen; S. H. Yang; C. H. Chou; K. C. Yang; C. C. Wu; Y. H. Cheng; Feng-Huei Lin (Inflammation Research, 2010)

Clinical and microbiological characteristics of community-acquired thoracic empyema or complicated parapneumonic effusion caused by Klebsiella pneumoniae in Taiwan - Y.-T. Lin; T.-L. Chen; L. K. Siu; S.-F. Hsu; C.-P. Fung (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Positive culture for Klebsiella pneumoniae in relevant sputum samples as a predictor of rapidly fatal outcome in septic patients at medical intensive care units - T.-Y. Chuang; C.-J. Lin; T.-C. Chou; H.-H. Huang; S.-W. Lee; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Dopaminergic neurotoxicity following pulmonary exposure to manganese-containing welding fumes - Krishnan Sriram; Gary X. Lin; Amy M. Jefferson; Jenny R. Roberts; Rebecca S. Chapman; Bean T. Chen; Joleen M. Soukup; Andrew J. Ghio; James M. Antonini (Archives of Toxicology, 2010)

Optimization of product line design for environmentally conscious technologies in notebook industry - K. H. Lin; L. H. Shih; S. C. Lee (International Journal of Environmental Science and Technology, 2010)

Antibacterial effect of electrolysed acid water on the nasal discharge from patients with chronic rhinosinusitis - R.-S. Jiang; S.-H. Wu; K.-L. Liang; J.-F. Lin; M.-C. Su; W.-K. Chen; F.-J. Lu (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Clinical and genotypic characteristics of extensively drug-resistant and multidrug-resistant tuberculosis - C. C. Lai; C. K. Tan; S. H. Lin; C. H. Liao; Y. T. Huang; C. H. Chou; H. L. Hsu; C. Y. Wang; H. I. Lin; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Molecular phylogeny of three ambiguous ciliate genera: Kentrophoros , Trachelolophos and Trachelotractus (Alveolata, Ciliophora) - Shan Gao; Michaela C. Strüder-Kypke; Khaled A. S. Al-Rasheid; Xiaofeng Lin; Weibo Song (Zoologica Scripta, 2010)

Comparison of approaches for efficient gene silencing induced by microRNA-based short hairpin RNA and indicator gene expression - Z. X. Shan; Q. X. Lin; C. Y. Deng; Z. L. Zhou; H. H. Tan; Y. H. Fu; X. H. Li; J. N. Zhu; L. P. Mai; S. J. Kuang; S. G. Lin; X. Y. Yu (Molecular Biology Reports, 2010)

Impact of pneumococcal vaccines on invasive pneumococcal disease in Taiwan - W.-H. Liao; S.-H. Lin; C.-C. Lai; C.-K. Tan; C.-H. Liao; Y.-T. Huang; C.-Y. Wang; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

In vitro activities of doripenem and other carbapenems against clinically important bacteria isolated in intensive care units: nationwide data from the SMART Programme - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Rigorous pulse detection from full-waveform airborne laser scanning data - Yu-Ching Lin; J. P. Mills; S. Smith-Voysey (International Journal of Remote Sensing, 2010)

Molecular phylogeny of Nothoholosticha (Protozoa, Ciliophora, Urostylida) and systematic relationships of the Holosticha -complex - Zhenzhen Yi; Xiaofeng Lin; Alan Warren; Khaled A. S. Al-Rasheid; Weibo Song (Systematics and Biodiversity, 2010)

Velocity structure and gas hydrate saturation estimation on active margin off SW Taiwan inferred from seismic tomography - Win-Bin Cheng; S. S. Lin; T. K. Wang; C. S. Lee; C. S. Liu (Marine Geophysical Research, 2010)

Tri-directional shaking table tests of vibration sensitive equipment with static dynamics interchangeable-ball pendulum system - C. S. Tsai; Yung-Chang Lin; Wen-Shin Chen; H. C. Su (Earthquake Engineering and Engineering Vibration, 2010)

Artificial neural network analysis for reliability prediction of regional runoff utilization - S. C. Lee; H. T. Lin; T. Y. Yang (Environmental Monitoring and Assessment, 2010)

Establishment, characterization, virus susceptibility and transfection of cell lines from cobia, Rachycentron canadum (L.), brain and fin - T‐C Cheng; Y‐S Lai; I‐Y Lin; C‐P Wu; S‐L Chang; T‐I Chen; M‐S Su (Journal of Fish Diseases, 2010)
Establishment and characterization of two cobia, Rachycentron canadum, cell lines derived from cobia brain (CB) and cobia fin (CF) are described. Caudal fin and brain from juvenile cobia were dissociated for 30 and 10 min, respectively, in phosphate‐buffered saline containing 0.25% trypsin at 25 °C. The optimal culture condition for both dissociated cells (primary cell culture) was at 28 °C in Leibovitz‐15 medium containing 10% foetal bovine serum. The cells have been sub‐cultured at a ratio of 1:2 for more than 160 passages over a period of 3 years. Origin of the cultured cells was verified by comparison of their sequences of mitochondrial cytochrome oxidase subunit I genes ( cox I ) with the cox 1 sequence from cobia muscle tissue. The cell lines showed polyploidy. No mycoplasma contamination was detected. Susceptibility to grouper iridovirus was observed for the CB cell line but not the CF cell line. Both cell lines expressed green fluorescent protein after being transfected with green fluorescent reporter gene driven by the cytomegalovirus promoter.

Impact of GPS radio occultation data assimilation on regional weather predictions - Ching-Yuang Huang; Ying-Hwa Kuo; Shu-Ya Chen; Chuen-Tsyr Terng; Fang-Ching Chien; Pay-Liam Lin; Mien-Tze Kueh; Shu-Hua Chen; Ming-Jen Yang; Chieh-Ju Wang; Anisetty S. K. A. V. Prasad Rao (GPS Solutions, 2010)

Deformation of lower-mantle ferropericlase (Mg,Fe)O across the electronic spin transition - Jung-Fu Lin; Hans-Rudolf Wenk; Marco Voltolini; Sergio Speziale; Jinfu Shu; Thomas S. Duffy (Physics and Chemistry of Minerals, 2009)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

A note on reviving the Goddard Satellite-based Surface Turbulent Fluxes (GSSTF) dataset - Chung-Lin Shie; Long S. Chiu; Robert Adler; Eric Nelkin; I. -I. Lin; Pingping Xie; Feng-Chin Wang; R. Chokngamwong; William Olson; D. Allen Chu (Advances in Atmospheric Sciences, 2009)

Identification of three immunodominant regions on leukotoxin protein of Fusobacterium necrophorum - D. B. Sun; R. Wu; G. L. Li; J. S. Zheng; X. P. Liu; Y. C. Lin; D. H. Guo (Veterinary Research Communications, 2009)

The importance of myocardial amino acids during ischemia and reperfusion in dilated left ventricle of patients with degenerative mitral valve disease - A. Venturini; R. Ascione; H. Lin; E. Polesel; G. D. Angelini; M.-S. Suleiman (Molecular and Cellular Biochemistry, 2009)

Intercomparison, interpretation, and assessment of spring phenology in North America estimated from remote sensing for 1982–2006 - MICHAEL A. WHITE; KIRSTEN M. De BEURS; KAMEL DIDAN; DAVID W. INOUYE; ANDREW D. RICHARDSON; OLAF P. JENSEN; JOHN O'KEEFE; GONG ZHANG; RAMAKRISHNA R. NEMANI; WILLEM J. D. Van LEEUWEN; JESSLYN F. BROWN; ALLARD De WIT; et al. (Global Change Biology, 2009)
Shifts in the timing of spring phenology are a central feature of global change research. Long‐term observations of plant phenology have been used to track vegetation responses to climate variability but are often limited to particular species and locations and may not represent synoptic patterns. Satellite remote sensing is instead used for continental to global monitoring. Although numerous methods exist to extract phenological timing, in particular start‐of‐spring (SOS), from time series of reflectance data, a comprehensive intercomparison and interpretation of SOS methods has not been conducted. Here, we assess 10 SOS methods for North America between 1982 and 2006. The techniques include consistent inputs from the 8 km Global Inventory Modeling and Mapping Studies Advanced Very High Resolution Radiometer NDVIg dataset, independent data for snow cover, soil thaw, lake ice dynamics, spring streamflow timing, over 16 000 individual measurements of ground‐based phenology, and two temperature‐driven models of spring phenology. Compared with an ensemble of the 10 SOS methods, we found that individual methods differed in average day‐of‐year estimates by ±60 days and in standard deviation by ±20 days. The ability of the satellite methods to retrieve SOS estimates was highest in northern latitudes and lowest in arid, tropical, and Mediterranean ecoregions. The ordinal rank of SOS methods varied geographically, as did the relationships between SOS estimates and the cryospheric/hydrologic metrics. Compared with ground observations, SOS estimates were more related to the first leaf and first flowers expanding phenological stages. We found no evidence for time trends in spring arrival from ground‐ or model‐based data; using an ensemble estimate from two methods that were more closely related to ground observations than other methods, SOS trends could be detected for only 12% of North America and were divided between trends towards both earlier and later spring.

Mathematical modeling and full-scale shaking table tests for multi-curve buckling restrained braces - C. S. Tsai; Yungchang Lin; Wenshin Chen; H. C. Su (Earthquake Engineering and Engineering Vibration, 2009)

Nationwide surveillance of antimicrobial resistance among Haemophilus influenzae and Streptococcus pneumoniae in intensive care units in Taiwan - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

An Atlas of ShakeMaps and population exposure catalog for earthquake loss modeling - Trevor I. Allen; David J. Wald; Paul S. Earle; Kristin D. Marano; Alicia J. Hotovec; Kuowan Lin; Michael G. Hearne (Bulletin of Earthquake Engineering, 2009)

Prevalence of helminths in water buffaloes in Hunan Province, China - Y. Liu; F. Li; W. Liu; R. S. Dai; Y. M. Tan; D. S. He; R. Q. Lin; X. Q. Zhu (Tropical Animal Health and Production, 2009)

The in vitro susceptibility of Campylobacter spp. to the antibacterial effect of manuka honey - S. M. Lin; P. C. Molan; R. T. Cursons (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

PEG Hydrogels for the Controlled Release of Biomolecules in Regenerative Medicine - Chien-Chi Lin; Kristi S. Anseth (Pharmaceutical Research, 2009)

A quick and efficient approach for gene silencing by using triple putative microRNA-based short hairpin RNAs - Z. X. Shan; Q. X. Lin; M. Yang; C. Y. Deng; S. J. Kuang; Z. L. Zhou; D. Z. Xiao; X. Y. Liu; S. G. Lin; X. Y. Yu (Molecular and Cellular Biochemistry, 2009)

Nationwide surveillance of antimicrobial resistance among Enterobacteriaceae in intensive care units in Taiwan - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

High-frequency direct somatic embryogenesis from leaf tissues of Drimiopsis kirkii Baker (giant squill) - T. H. Lan; P. I. Hong; C. C. Huang; W. C. Chang; C. S. Lin (In Vitro Cellular & Developmental Biology - Plant, 2009)

Group A streptococcal infection caused by emm1 strains among children in southern Taiwan - H.-C. Lin; S.-M. Wang; Y.-L. Lin; Y.-S. Lin; J.-J. Wu; W.-J. Chuang; M. T. Lin; C.-C. Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Induction potential of clavulanic acid toward L1 and L2 β-lactamases of Stenotrophomonas maltophilia - C.-W. Lin; R.-M. Hu; S.-C. Huang; Y.-J. Hsiao; T.-C. Yang (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Mapping chromosomal regions affecting flowering time in a spring wheat RIL population - F. Lin; S. L. Xue; D. G. Tian; C. J. Li; Y. Cao; Z. Z. Zhang; C. Q. Zhang; Z. Q. Ma (Euphytica, 2008)

Identification and expression characterization of pepsinogen A in orange‐spotted grouper, Epinephelus coioides - S. Z. Feng; W. S. Li; H. R. Lin (Journal of Fish Biology, 2008)
To understand the molecular mechanisms associated with digestive physiology of the stomach of orange‐spotted grouper Epinephelus coioides , a cDNA library was constructed and 331 expressed sequence tags (EST) were generated and annotated. About 37·17% of 226 identified ESTs were possibly related to digestive enzymes. Two type‐A pepsinogens differing in putative isoelectric point were identified and characterized for the first time in E. coioides . The complete cDNAs were 1312 and 1314 bp in length, and the deduced polypeptide sequences comprised 376 and 377 amino acids, respectively. Both genes consisted of eight introns of various lengths. Alignment and a phylogenetic tree based on the amino acid sequences of pepsins indicated that pepsin A1 and A2 could be classified into two different subtypes. Northern blot hybridization showed that there were two forms of transcripts for pepsinogen A1 and three for pepsinogen A2. Reverse transcription‐PCR (RT‐PCR) followed by Southern blot analysis revealed that two type‐A pepsinogen mRNAs were present in the adult stomach tissue, and pepsinogen A2 was also detectable in the mid‐intestine. Furthermore, pepsinogen A1 transcript was first detected at 29 days post‐hatching, while pepsinogen A2 was continuously expressed through hatching to adult fish. These results imply that transcriptional regulation and physiological function of the two type‐A pepsinogens may be different.

Emission of fine organic aerosol from traditional charcoal broiling in China - Ximei Hou; Guoshun Zhuang; Yanfen Lin; Juan Li; Yilun Jiang; Joshua S. Fu (Journal of Atmospheric Chemistry, 2008)

Cloning and infection response of tumour‐necrosis factor alpha in large yellow croaker Pseudosciaena crocea (Richardson) - F. J. Xie; Z. P. Zhang; P Lin; S. H Wang; Z. H Zou; Y. L. Wang (Journal of Fish Biology, 2008)
In this article, reverse transcriptase polymerase chain reaction (RT‐PCR) and real‐time PCR were used to clone the tumour‐necrosis factor alpha (TNF‐α) gene of the large yellow croaker Pseudosciaena crocea (Richardson) and to analyse its response to bacterial infection. The full‐length cDNA of TNF‐α contained a 5′‐untranslated region (5′‐UTR) of 68 bp, followed by an open reading frame (ORF) of 759 bp and a 3′‐UTR of 512 bp. The ORF was capable of encoding 252 amino acids with an estimated molecular mass of 28 kDa. In the 3′‐UTR, there were two putative endotoxin‐responsive motifs and five mRNA instability motifs. The deduced peptide had a transmembrane domain and a TNF‐α family signature. Multiple sequence alignments indicated that P. crocea TNF‐α shares relatively high similarity with both teleost and mammalian TNF‐α. Phylogenetic analysis showed that teleost TNF‐α was located independently in a different branch compared with mammalian TNF‐α. Real‐time PCR analysis demonstrated that the expression of TNF‐α in the head kidney of the P. crocea injected with Vibrio parahaemolyticus was most significantly higher than that of the control group at 2 and 4 days. In blood, at 2 days post‐injection, TNF‐α expression was significantly higher than that of the control group, while at 4 days post‐injection, it was most significantly higher than that of the control group.

The chemistry of heavy haze over Urumqi, Central Asia - Juan Li; Guoshun Zhuang; Kan Huang; Yanfen Lin; Qiongzhen Wang; Yuhong Guo; Jinghua Guo; Shulong Yu; Caixia Cui; Joshua S. Fu (Journal of Atmospheric Chemistry, 2008)

DC-SIGN and L-SIGN: the SIGNs for infection - Ui-Soon Khoo; Kelvin Y. K. Chan; Vera S. F. Chan; C. L. Steve Lin (Journal of Molecular Medicine, 2008)

Yersinia enterocolitica infection in diarrheal patients - H. Zheng; Y. Sun; S. Lin; Z. Mao; B. Jiang (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Characterization of novel microsatellite loci in the great leaf-nosed bat, Hipposideros armiger and cross-amplification in other related species - T. T. Guo; P. Y. Hua; L. K. Lin; S. Y. Zhang (Conservation Genetics, 2008)

Relationships between physiological responses and presyncope symptoms during tilting up in patients with spinal cord injury - David S. Liu; Walter H. Chang; Alice M. K. Wong; Shih-Ching Chen; Kang-Ping Lin; Chien-Hung Lai (Medical & Biological Engineering & Computing, 2008)

Residential proximity to large airports and potential health impacts in New York State - S. Lin; J. P. Munsie; M. Herdt-Losavio; S. A. Hwang; K. Civerolo; K. McGarry; T. Gentile (International Archives of Occupational and Environmental Health, 2008)

Ethmoid sinus mycology of chronic rhinosinusitis - R. S. Jiang; K. L. Liang; J. Y. Shiao; J. F. Lin; M. C. Su; C. H. Hsin; F. J. Lu (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Determination of Particulate-Bound Formaldehyde from Burning Incense by Solid Phase Microextraction - S. W. Liou; C. Y. Chen; T. T. Yang; J. M. Lin (Bulletin of Environmental Contamination and Toxicology, 2008)

Expression and immunogenic comparison of VP2 and VP3 from marine birnavirus - H‐J Xu; J‐G Lin; C‐X Zhang; S Suzuki (Journal of Fish Diseases, 2008)
The coding regions for the major epitopes of structural protein VP2 ( vp2e ) and structural protein VP3 were amplified from marine birnavirus (MABV) cDNA and efficiently expressed as glutathione S‐transferase (GST) fusion proteins in Escherichia coli . Polyclonal antibodies against VP2e and VP3 were raised in rabbits and fish using the purified proteins of GST/VP2e and GST/VP3. The rabbit anti‐serum against VP3 was more sensitive than the rabbit anti‐VP2e serum in detecting virus in MABV‐infected fish, while fish anti‐VP2e serum showed a stronger neutralization response than fish anti‐VP3 serum.

Detection of quantitative trait loci controlling extremely early heading in rice - Y. Nonoue; K. Fujino; Y. Hirayama; U. Yamanouchi; S. Y. Lin; M. Yano (Theoretical and Applied Genetics, 2008)

Early developmental and stress responsive ESTs from mungbean, Vigna radiata (L.) Wilczek, seedlings - Li-Ru Chen; Albert H. Markhart; S. Shanmugasundaram; Tsai-Yun Lin (Plant Cell Reports, 2008)

Using FANP approach on selection of competitive priorities based on cleaner production implementation: a case study in PCB manufacturer, Taiwan - M. L. Tseng; Y. H. Lin; A. S. F. Chiu; J. C. H. Liao (Clean Technologies and Environmental Policy, 2008)

Effect of low-intensity laser radiation of the red spectrum on some properties of erythrocytes in Wistar rats - N. S. Lin’kova; O. P. Gorshkova; V. N. Shuvaeva; D. P. Dvoretskii (Bulletin of Experimental Biology and Medicine, 2008)

Development of a biofeedback tilt-table for investigating orthostatic syncope in patients with spinal cord injury - David S. Liu; Walter H. Chang; Alice M. K. Wong; Shih-Ching Chen; Kang-Ping Lin; Chien-Hung Lai (Medical & Biological Engineering & Computing, 2007)

The commonly used β-actin-GFP transgenic mouse strain develops a distinct type of glomerulosclerosis - Jian-Kan Guo; Ee-Chun Cheng; Lin Wang; E. Scott Swenson; Thomas A. Ardito; Michael Kashgarian; Lloyd G. Cantley; Diane S. Krause (Transgenic Research, 2007)

Dissipation of Pendimethalin in the Garlic (Allium sativum L.) under Subtropical Condition - H. T. Lin; S. W. Chen; C. J. Shen; C. Chu (Bulletin of Environmental Contamination and Toxicology, 2007)

Prostate cancer mortality in relation to screening by prostate-specific antigen testing and digital rectal examination: a population-based study in middle-aged men - Ilir Agalliu; Noel S. Weiss; Daniel W. Lin; Janet L. Stanford (Cancer Causes & Control, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Characteristics of Emissions of Volatile Organic Compounds from Smoldering Incense - T. T. Yang; T. S. Lin; M. Chang (Bulletin of Environmental Contamination and Toxicology, 2007)

Health behaviors of cancer survivors: data from an Australian population-based survey - Elizabeth G. Eakin; Danny R. Youlden; Peter D. Baade; Sheleigh P. Lawler; Marina M. Reeves; Jane S. Heyworth; Lin Fritschi (Cancer Causes & Control, 2007)

Image processing of FORMOSAT‐2 data for monitoring the South Asia tsunami - C.‐C. Liu; J.‐G. Liu; C.‐W. Lin; A.‐M. Wu; S.‐H. Liu; C.‐L. Shieh (International Journal of Remote Sensing, 2007)

Ganoderma lucidum polysaccharide peptide reduced the production of proinflammatory cytokines in activated rheumatoid synovial fibroblast - Y. W. Ho; J. S. L. Yeung; P. K. Y. Chiu; W. M. Tang; Z. B. Lin; R. Y. K. Man; C. S. Lau (Molecular and Cellular Biochemistry, 2007)

High expression of capsid protein of red‐spotted grouper nervous necrosis virus in an avian cell line requires viral RNA2 non‐coding regions - J N Huang; L Lin; S P Weng; J G He (Journal of Fish Diseases, 2007)

Endosperm-specific hypomethylation, and meiotic inheritance and variation of DNA methylation level and pattern in sorghum (Sorghum bicolor L.) inter-strain hybrids - M. S. Zhang; H. Y. Yan; N. Zhao; X. Y. Lin; J. S. Pang; K. Z. Xu; L. X. Liu; B. Liu (Theoretical and Applied Genetics, 2007)

Characteristics of Carbonaceous Aerosol at Taichung Harbor, Taiwan during Summer and Autumn Period of 2005 - Guor-Cheng Fang; S. C. Lee; Wen-Jhy Lee; Yan Cheng; I-Cherng Lin (Environmental Monitoring and Assessment, 2007)

Arsenic Distribution in a Tilapia (Oreochromis mossambicus) Water-Sediment Aquacultural Ecosystem in Blackfoot Disease Hyperendemic Areas - S. -W. Wang; K. -H. Lin; Y. -M. Hsueh; C. -W. Liu (Bulletin of Environmental Contamination and Toxicology, 2007)

Volatile Organic Compound Exposure of Suburban Elementary Students in Taiwan - C.-Y. Peng; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2007)

Volatile Organic Compound Exposure of Suburban Elementary Students in Taiwan - C.-Y. Peng; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2007)

Livestock Odour Dispersion as Affected by Natural Windbreaks - X.-J. Lin; S. Barrington; J. Nicell; D. Choinière; S. King (Water, Air, & Soil Pollution, 2007)

Accumulation of additive effects generates a strong photoperiod sensitivity in the extremely late-heading rice cultivar ‘Nona Bokra’ - Y. Uga; Y. Nonoue; Z. W. Liang; H. X. Lin; S. Yamamoto; U. Yamanouchi; M. Yano (Theoretical and Applied Genetics, 2007)

Soil Nutrient Load and Drain Water Quality in Seepage Fields Receiving Milk House Wastewater - S. Morin; J. K. Whalen; S. Barrington; X. Lin (Water, Air, & Soil Pollution, 2007)

A numerical study of the influence of urban expansion on monthly climate in dry autumn over the Pearl River Delta, China - W. S. Lin; C.-H. Sui; L. M. Yang; X. M. Wang; R. R. Deng; S. J. Fan; C. S. Wu; A. Y. Wang; S. K. Fong; H. Lin (Theoretical and Applied Climatology, 2007)

Apoptosis-dependent and -independent mechanisms mediate the phagocytic recognition/clearance of the HL60-A1 transfectants with prolonged survival - C.-L. Chou; L.-L. Chiang; C.-T. Yu; H.-C. Chen; K.-Y. Lee; S.-M. Lin; C.-D. Huang; W.-T. Liu; P.-C. Chou; C.-H. Wang; H.-C. Lin; H.-P. Kuo; et al. (Inflammation Research, 2007)

A dual site study of the rainwater chemistry within the Western Pacific region - K. M. Wai; S. H. Wang; P. A. Tanner; N. H. Lin (Journal of Atmospheric Chemistry, 2007)

Laboratory measurements of the 12C/13C kinetic isotope effects in the gas-phase reactions of unsaturated hydrocarbons with Cl atoms at 298 ± 3 K - Rebecca S. Anderson; Lin Huang; Richard Iannone; Jochen Rudolph (Journal of Atmospheric Chemistry, 2007)

Mitochondrial DNA phylogeography of Glyptothorax fokiensis and Glyptothorax hainanensis in Asia - X.‐L. Chen; T.‐Y. Chiang; H.‐D. Lin; H.‐S. Zheng; K.‐T. Shao; Q. Zhang; K.‐C. Hsu (Journal of Fish Biology, 2007)
Whole mitochondrial DNA cytochrome b sequences in 62 fish from 13 locations in Southeast China identified two major clades corresponding to two allopatric taxa, Glyptothorax fokiensis fokiensis and Glyptothorax fokiensis hainanensis . Reciprocal monophyly and a molecular clock separation between these two taxa of 2·3 million years indicate these taxa should be elevated to species. Mismatch distributions and Fu’s F S statistic suggest that both G. fokiensis and G. hainanensis have experienced recent population expansions. Analysis of molecular variance indicates that most of the genetic variation resides among populations within both species, with Φ ST = 0·645 for G. fokiensis and 0·801 for G. hainanensis , suggesting restricted gene flow among populations. Significant correlations between the geographic and the genetic distances provide support for the importance of geographic isolations between populations. Nested clade analysis also confirms low levels of genetic exchanges between the two major groups and between populations within each group. The phylogeographical pattern among populations of Glyptothorax in East Asia can be attributed to historical fragmentations, demographic expansions and occasional long‐distance dispersals stimulated by tectonic activity and Ice Age climate changes.

The contents and forms of solid-phase species of radioactive strontium and cesium in Taiwan soils - S. W. Chang Chien; M. C. Wang; C. L. Chiu; Yu-Ming Lin; Shu-Ying Lai (Environmental Monitoring and Assessment, 2007)

Numerical comparison study of cloud microphysical parameterization schemes for a moderate snowfall event in North China - W. S. Lin; C.-H. Sui; C. Bueh; A. Wang; S. Fan; C. Wu; S. Fong; J. Li; J. Meng (Meteorology and Atmospheric Physics, 2007)

Improved somatic embryo maturation in loblolly pine by monitoring ABA-responsive gene expression - Teresa Vales; Xiaorong Feng; Lin Ge; Nanfei Xu; John Cairney; Gerald S. Pullman; Gary F. Peter (Plant Cell Reports, 2007)

Cytotoxic kurubasch aldehyde from Trichilia emetica - Maminata Traore; Lin Zhai; Ming Chen; Carl Erik Olsen; Nacoulma Odile; Guissou I. Pierre; Ouédrago J. Bosco; Guigemdé T. Robert; S. Brøgger Christensen (Natural Product Research, 2007)

Introgression mapping in the grasses - Julie King; Ian P. Armstead; Iain S. Donnison; John A. Harper; Luned A. Roberts; Howard Thomas; Helen Ougham; Ann Thomas; Lin Huang; Ian P. King (Chromosome Research, 2007)

Responses of Metapopulation Dynamics to Two Different Kinds of Habitat Destruction Caused by Human Activities - H. Y. Liu; Z. S. Lin; T. Wen (Plant Ecology, 2006)

Isolation of Endophytic Actinomycetes from Different Cultivars of Tomato and their Activities Against Ralstonia solanacearum in Vitro - H. M. Tan; L. X. Cao; Z. F. He; G. J. Su; B. Lin; S. N. Zhou (World Journal of Microbiology and Biotechnology, 2006)

The Endo-β-Mannanase gene families in Arabidopsis, rice, and poplar - Joshua S. Yuan; Xiaohan Yang; Jingru Lai; Hong Lin; Zong-Ming Cheng; Hiroyuki Nonogaki; Feng Chen (Functional & Integrative Genomics, 2006)

Characterizing the severe turbulence environments associated with commercial aviation accidents. A real-time turbulence model (RTTM) designed for the operational prediction of hazardous aviation turbulence environments - M. L. Kaplan; J. J. Charney; K. T. Waight; K. M. Lux; J. D. Cetola; A. W. Huffman; A. J. Riordan; S. D. Slusser; M. T. Kiefer; P. S. Suffern; Y.-L. Lin (Meteorology and Atmospheric Physics, 2006)

Serum Heat Shock Protein (HSP70) and Its Antibody (Anti-HSP70) Levels in Male Foundry Workers in Taiwan - C.-J. Chen; H.-J. Wen; S.-H. Liu; M.-S. Lin; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2006)

Soil hydraulic manipulation and organic amendment for the enhancement of selenium volatilization in a soil–pickleweed system - B. Shrestha; S. Lipe; K. A. Johnson; T. Q. Zhang; W. Retzlaff; Z.-Q. Lin (Plant and Soil, 2006)

Coordination between manganese and nitrogen within the ligands in the manganese complexes facilitates the reconstitution of the water-oxidizing complex in manganese-depleted photosystem II preparations - Shuqin Li; Guiying Chen; Guangye Han; Lin Ling; Deguang Huang; A. A. Khorobrykh; S. K. Zharmukhamedov; Qiutian Liu; V. V. Klimov; Tingyun Kuang (JBIC Journal of Biological Inorganic Chemistry, 2006)

Computational Simulations of the Human Magneto- and Electroenterogram - A. S. Lin; M. L. Buist; L. K. Cheng; N. P. Smith; A. J. Pullan (Annals of Biomedical Engineering, 2006)

Tissue Accumulation of Arsenic Compounds in Aquacultural and Wild Mullet (Mugil cephalus) - C.-W. Liu; K.-H. Lin; C.-S. Jang (Bulletin of Environmental Contamination and Toxicology, 2006)

Albino inflorescence proliferation of Dendrocalamus latiflorus - C. S. Lin; M. C. Tseng; P. I. Hong; W. C. Chang (In Vitro Cellular & Developmental Biology - Plant, 2006)

Copper‐dependent iron transport in coastal and oceanic diatoms - Maria T. Maldonado; Andrew E. Allen; Joanne S. Chong; Kevin Lin; Dan Leus; Nataliya Karpenko; Shannon L. Harris (Limnology and Oceanography, 2006)
We investigated the presence of plasmalemma‐bound copper‐containing oxidases associated with the inducible iron (Fe) transport system in two diatoms of the genus Thalassiosira . Under Fe‐limiting conditions, Thalassiosira oceanica , an oceanic isolate, was able to enzymatically oxidize inorganic Fe(II) extracellularly. This oxidase activity was dependent on copper (Cu) availability and diminished by exposure to a multi‐Cu oxidase (MCO) inhibitor. The rates of Fe uptake from ferrioxamine B by Fe‐limited T. oceanica were also dependent on Cu availability in the growth media. The effects of Cu limitation on Fe(II) oxidation and Fe uptake from ferrioxamine B were partially reversed after a short exposure to a Cu addition, indicating that the putative oxidases contain Cu. Limited physiological experiments were also performed with the coastal diatom Thalassiosira pseudonana and provided some evidence for putative Cu‐containing oxidases in the high‐affinity Fe transport system of this isolate. To support these preliminary physiological data, we searched the newly available T. pseudonan a genome for a multi‐Cu‐containing oxidase gene and, using real‐time polymerase chain reaction (PCR), quantified its expression under various Fe and Cu levels. We identified a putative MCO gene with predicted transmembrane domains and found that transcription levels of this gene were significantly elevated in Fe‐limited cells relative to Fe‐replete cells. These data collectively suggest that putative MCOs are part of the inducible Fe transport system of Fe‐limited diatoms, which act to oxidize Fe(II) following reductive dissociation of Fe(III) from strong organic complexes.

Identification of elongation factor 1α as a potential associated binding partner for Akt2 - Janet Lau; Laura A. Castelli; Emme C. K. Lin; S. Lance Macaulay (Molecular and Cellular Biochemistry, 2006)

EMD analysis of solar insolation - Z. S. Lin; S. G. Wang (Meteorology and Atmospheric Physics, 2006)

Climatic Change, Wars and Dynastic Cycles in China Over the Last Millennium - David D. Zhang; C. Y. Jim; George C-S Lin; Yuan-Qing He; James J. Wang; Harry F. Lee (Climatic Change, 2006)

Potential Volatile Organic Compound Exposure from Dry Process Photocopiers in Operation-Idle Mode - D.-J. Hsu; H.-L. Huang; H.-Y. Lin; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2006)

Enhancement of chemosensitivity toward peplomycin by calpastatin-stabilized NF-κB p65 in esophageal carcinoma cells: possible involvement of Fas/Fas-L synergism - T.-L. Liu; H. Shimada; T. Ochiai; T. Shiratori; S.-E. Lin; M. Kitagawa; K. Harigaya; M. Maki; M. Oka; T. Abe; M. Takiguchi; T. Hiwasa (Apoptosis, 2006)

Enhanced viability of a nervous necrosis virus‐infected stable cell line over‐expressing a fusion product of the zfBcl‐x L and green fluorescent protein genes - S‐P Chen; H‐L Yang; H‐Y Lin; M‐C Chen; J‐L Wu; J‐R Hong (Journal of Fish Diseases, 2006)
Nervous necrosis virus (NNV) infection induces host cell apoptosis by an ill‐understood process. We utilized a fusion between enhanced green fluorescent protein (EGFP) and the zfBcl‐x L gene in GL‐av cells to select for zfBcl‐x L stable cell lines and to assess the effectiveness of the anti‐apoptotic protein Bcl‐x L in circumventing NNV‐induced cell death. Stable EGFP and EGFP‐Bcl‐x L ‐expressing clones were obtained at high purity within 2.5–3 months. In the latter, the EGFP‐Bcl‐x L fusion protein (approximately 58.2 kDa, as ascertained by Western blot) was predominantly targeted to mitochondria. We assayed for apoptosis in red‐spotted grouper NNV Tainan no. 1 (RGNNV TN1)‐infected cells with terminal deoxynucleotidyl transferase (TdT)‐mediated end labelling (TUNEL) of DNA at different virus doses. NNV infection of NNV Bcl‐x L GL‐av cell line revealed a protective effect, with a decrease in TUNEL‐positive cells of 7%, 8% and 31.8% at 24, 48 and 72 h, respectively. In addition, RGNNV infection of the Bcl‐x L GL‐av cell line revealed a protective effect, with an enhanced viability of 3%, 40% and 73% at 24, 48, and 72 h, respectively. We conclude that NNV‐induced apoptotic cell death can be lessened in transgenic grouper fish cells.

Renoprotective effects of combination of angiotensin converting enzyme inhibitor with mycophenolate mofetil in diabetic rats - Y. -G. Wu; H. Lin; H Qian; M. Zhao; X. -M. Qi; G. -Z. Wu; S. -T. Lin (Inflammation Research, 2006)

Seismo-Geochemical Variations in SW Taiwan: Multi-Parameter Automatic Gas Monitoring Results - T. F. Yang; C.-C. Fu; V. Walia; C.-H. Chen; L. L. Chyi; T.-K. Liu; S.-R. Song; M. Lee; C.-W. Lin; C.-C. Lin (Pure and Applied Geophysics, 2006)

Protoplast electrofusion between common wheat (Triticum aestivum L.) and Italian ryegrass (Lolium multiflorum Lam.) and regeneration of mature cybrids - T. M. Ge; X. H. Lin; F. L. Qin; S. W. Yu; Y. J. Yu (In Vitro Cellular & Developmental Biology - Plant, 2006)

Use of a fluorescent membrane probe to identify zooxanthellae in hospite among dissociated endoderm cell culture from coral - C.-S. Chen; H.-P. Lin; C.-C. Yeh; L.-S. Fang (Protoplasma, 2005)

Nucleotide sequence and mRNA expression analysis of β-actin gene in the orange-spotted grouper Epinephelus coioides - W. M. Zhang; Y. Zhang; L. H. Zhang; S. G. Wang; T. Y. Zhu; D. Lin; G. Z. Ma (Fish Physiology and Biochemistry, 2005)

Potential Exposure to VOCs Caused by Dry Process Photocopiers: Results From a Chamber Study - D.-J. Hsu; H.-L. Huang; C.-H. Chien; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2005)

Comparison of (−)-Epigallocatechin-3-Gallate Elicited Liver and Small Intestine Gene Expression Profiles Between C57BL/6J Mice and C57BL/6J/Nrf2 (−/−) Mice - Guoxiang Shen; Changjiang Xu; Rong Hu; Mohit R. Jain; Sujit Nair; Wen Lin; Chung S. Yang; Jefferson Y. Chan; A.-N. Tony Kong (Pharmaceutical Research, 2005)

Genetic and physical mapping of Pi36(t), a novel rice blast resistance gene located on rice chromosome 8 - X. Q. Liu; L. Wang; S. Chen; F. Lin; Q. H. Pan (Molecular Genetics and Genomics, 2005)

Industrial wideband noise reduction for hearing aids using a headset with adaptive-feedback active noise cancellation - J. -H. Lin; P. -C. Li; S. -T. Tang; P. -T. Liu; S. -T. Young (Medical & Biological Engineering & Computing, 2005)

Characterisation of the welsh onion isolate of Shallot yellow stripe virus from China - J. Chen; C.-B. Wei; H.-Y. Zheng; Y.-H. Shi; M. J. Adams; L. Lin; Q.-Y. Zhang; S.-J. Wang; J.-P. Chen (Archives of Virology, 2005)

Adaptive filtering of evoked potentials using higher-order adaptive signal enhancer with genetic-type variable step-size prefilter - B. -S. Lin; B. -S. Lin; F. -C. Chong; F. Lai (Medical & Biological Engineering & Computing, 2005)

Acute Toxicity of Thallium to Daphnia magna and Ceriodaphnia dubia - T.-S. Lin; P. Meier; J. Nriagu (Bulletin of Environmental Contamination and Toxicology, 2005)

Components of Honeybee Royal Jelly as Deterrents of the Parasitic Varroa Mite, Varroa destructor - F. P. Drijfhout; J. Kochansky; S. Lin; N. W. Calderone (Journal of Chemical Ecology, 2005)

Isolation and characterization of actinomycetes antagonistic to pathogenic Vibrio spp. from nearshore marine sediments - J. L. You; L. X. Cao; G. F. Liu; S. N. Zhou; H. M. Tan; Y. C. Lin (World Journal of Microbiology and Biotechnology, 2005)

Mining the structural knowledge of high-dimensional medical data using isomap - S. Weng; C. Zhang; Z. Lin; X. Zhang (Medical & Biological Engineering & Computing, 2005)

Thallium in Whole Blood Samples from College Students in Taiwan - T.-S. Lin; C.-L. Chang (Bulletin of Environmental Contamination and Toxicology, 2005)

Phylogenetic analysis of classical swine fever virus in Taiwan - C. H. Pan; M. H. Jong; T. S. Huang; H. F. Liu; S. Y. Lin; S. S. Lai (Archives of Virology, 2005)

Orographic effects on a conditionally unstable flow over an idealized three-dimensional mesoscale mountain - S.-H. Chen; Y.-L. Lin (Meteorology and Atmospheric Physics, 2005)

Trace Elements in Cultured Tilapia (Oreochromis mossambicus): Results from a Farm in Southern Taiwan - T.-S. Lin; C.-S. Lin; C.-L. Chang (Bulletin of Environmental Contamination and Toxicology, 2005)

Manganese Uptake and Accumulation by Two Populations of Phytolacca acinosa Roxb. (Phytolaccaceae) - S. G. Xue; Y. X. CHEN; A. J. M. Baker; R. D. Reeves; X. H. Xu; Q. Lin (Water, Air, & Soil Pollution, 2005)

Trace Metals in Mosquito Coil Smoke - T.-S. Lin; F.-M. Shen (Bulletin of Environmental Contamination and Toxicology, 2005)

Cocaine increases human immunodeficiency virus type 1 neuroinvasion through remodeling brain microvascular endothelial cells - Milan Fiala; Amy J Eshleman; John Cashman; Justin Lin; Albert S Lossinsky; Vannina Suarez; Wendy Yang; Jun Zhang; Waldemar Popik; Elyse Singer; Francesco Chiappelli; Eva Carro; et al. (Journal of NeuroVirology, 2005)

Mapping QTL associated with resistance to Fusarium head blight in the Nanda2419נWangshuibai population. I. TypeII resistance - F. Lin; Z. X. Kong; H. L. Zhu; S. L. Xue; J. Z. Wu; D. G. Tian; J. B. Wei; C. Q. Zhang; Z. Q. Ma (Theoretical and Applied Genetics, 2004)

Whole Blood Vanadium in Taiwanese College Students - T.-S. Lin; C.-L. Chang; F.-M. Shen (Bulletin of Environmental Contamination and Toxicology, 2004)

Acute Aquatic Toxicity of N-Methyl-2-Pyrrolidinone to Daphnia magna - C.-H. Lan; C.-Y. Peng; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2004)

Investigating Tendon Fascicle Structure–Function Relationships in a Transgenic-Age Mouse Model Using Multiple Regression Models - Paul S. Robinson; Tony W. Lin; Abbas F. Jawad; Renato V. Iozzo; Louis J. Soslowsky (Annals of Biomedical Engineering, 2004)

Acute Toxicity Assessment of 20 Herbicides to the Green Alga Scenedesmus quadricauda (Turp.) Breb. - J. Ma; F. Lin; S. Wang; L. Xu (Bulletin of Environmental Contamination and Toxicology, 2004)

Natural frequency assessment of stability of root keeper magnetic devices - H. -M. Huang; D. -Z. Liu; Y. -Y. Shiau; C. -Y. Yeh; C. -T. Lin; S. -Y. Lee (Medical & Biological Engineering & Computing, 2004)

Adaptive processing bandwidth adjustment for laser Doppler flowmetry - Y. Y. Chen; Y. H. Lin; I. C. Jan; R. S. Liu; N. K. Chou; G. -J. Jan (Medical & Biological Engineering & Computing, 2004)

Biological functions of the cytoplasmic TGBp1 inclusions of bamboo mosaic potexvirus - H.-T. Hsu; Y.-H. Hsu; I.-P. Bi; N.-S. Lin; B.-Y. Chang (Archives of Virology, 2004)

Predicted ATP-binding cassette systems in the phytopathogenic mollicute Spiroplasma kunkelii - Y. Zhao; H. Wang; R. W. Hammond; R. Jomantiene; Q. Liu; S. Lin; B. A. Roe; R. E. Davis (Molecular Genetics and Genomics, 2004)

Mycobacterium Reverse Hybridization Line-Probe Assay Used to Diagnose Disseminated Mycobacterium haemophilum Infection in a Child with Acute Lymphoblastic Leukemia - F. Bosma; J. M. Deckers-Kocken; S. S. N. de Graaf; T. Schlin; W. J. G. Melchers; J. A. Hoogkamp-Korstanje (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Mapping of quantitative trait loci controlling low-temperature germinability in rice (Oryza sativa L.) - K. Fujino; H. Sekiguchi; T. Sato; H. Kiuchi; Y. Nonoue; Y. Takeuchi; T. Ando; S. Y. Lin; M. Yano (Theoretical and Applied Genetics, 2004)

Elevated Exposure to Nitrogen Dioxide During Food Preparation: Results from a Cooking Laboratory - T.-S. Lin; Y.-L. Huang (Bulletin of Environmental Contamination and Toxicology, 2004)

Microbial biomass carbon, nitrogen and phosphorus in the soil profiles of different vegetation covers established for soil rehabilitation in a red soil region of southeastern China - F.E. Wang; Y.X. Chen; G.M. Tian; S. Kumar; Y.F. He; Q.L. Fu; Q. Lin (Nutrient Cycling in Agroecosystems, 2004)

An operational heat/health warning system in shanghai - Jianguo Tan; L. S. Kalkstein; Jiaxin Huang; Songbai Lin; Hebao Yin; Demin Shao (International Journal of Biometeorology, 2004)

Excavating Y-chromosome haplotype strata in Anatolia - Cengiz Cinnioglu; Roy King; Toomas Kivisild; Ersi Kalfoglu; Sevil Atasoy; Gianpiero L. Cavalleri; Anita S. Lillie; Charles C. Roseman; Alice A. Lin; Kristina Prince; Peter J. Oefner; Peidong Shen; et al. (Human Genetics, 2004)

Application of a ?Big-Tree? model to regional climate modeling: a sensitivity study - X.-M. Zeng; M. Zhao; R.-C. Yu; N.-S. Lin; Y.-Q. Zheng; L.-J. Zhang; R.-J. Zhang (Theoretical and Applied Climatology, 2003)

Fine linkage mapping enables dissection of closely linked quantitative trait loci for seed dormancy and heading in rice - Y. Takeuchi; S. Y. Lin; T. Sasaki; M. Yano (Theoretical and Applied Genetics, 2003)

Surfactant proteinA and B genetic variants predispose to idiopathic pulmonary fibrosis - Moises Selman; Hung-Mo Lin; Martha Montao; Audrey L. Jenkins; Andrea Estrada; Zhenwu Lin; Guirong Wang; Susan L. DiAngelo; Xiaoxuan Guo; Todd M. Umstead; C. Max Lang; Annie Pardo; et al. (Human Genetics, 2003)

Historical biogeography and phylogenetic relationships of the genus Chamaecyparis (Cupressaceae) inferred from chloroplast DNA polymorphism - W. P. Wang; C. Y. Hwang; T. P. Lin; S. Y. Hwang (Plant Systematics and Evolution, 2003)

Cariporide enhances lactate clearance upon reperfusion but does not alter lactate accumulation during global ischaemia - H. Lin; M.-S. Suleiman (Pflügers Archiv - European Journal of Physiology, 2003)

Small-angle X-ray scattering measurement of the internal microstructure of natural zircon crystals - A. P. Radlinski; J. Claou-Long; A. L. Hinde; E. Z. Radlinska; J.-S. Lin (Physics and Chemistry of Minerals, 2003)

Evidence for the existence of some dissociation in an otherwise strong linkage disequilibrium between mitochondrial and chloroplastic genomes in Cyclobalanopsis glauca - T.‐P. Lin; W.‐J. Chuang; S. S. F. Huang; S.‐Y. Hwang (Molecular Ecology, 2003)
Variations in mitochondrial DNA in Cyclobalanopsis glauca (Thunb. ex Murray) Oerst. were studied in 140 trees from 32 populations collected from within the tree's natural range. By sequencing two mitochondrial DNA intron fragments ( nad 4/3 ‐nad 4/4r and nad 7/2 ‐nad 7/3r), we revealed a total of 1788 bp and five polymorphic sites which allowed us to distinguish six mitotypes. The mitochondrial DNA markers provided replicated data to support population phylogeographical scenarios suggested previously using chloroplastic DNA markers. The gene genealogical tree of mitochondrial DNA was partially congruent with the chloroplastic DNA tree owing to the slower mutation rate and different mutational direction. Significant linkage disequilibrium existed between the two organellar genomes. Further paring analyses between fragments synthesized using different primers, accompanied by exclusion of polymorphic sites, showed that the random association could be attributed specifically to one of the polymorphic sites of the pet G‐ trn P fragment of the chloroplastic genome, and the three polymorphic sites of the nad 4/3‐ nad 4/4r fragment of the mitochondrial genome. The former was inferred to derive from paternal leakage, and the latter from recurrent mutation. These polymorphic sites were also responsible for uncoupling of the combined gene tree of mitotype and chlorotype. In conclusion, specific fragments found in this study contribute to the incomplete congruence of the two organellar lineages that otherwise associate well phylogeographically.

Nonrandom Intragenic Variations in Patterns of Codon Bias Implicate a Sequential Interplay Between Transitional Genetic Drift and Functional Amino Acid Selection - K. Lin; S. B. Tan; P. R. Kolatkar; R. J. Epstein (Journal of Molecular Evolution, 2003)

Toxicity of 21 Herbicides to the Green Alga Scenedesmus quadricauda - J. Ma; F. Lin; S. Wang; L. Xu (Bulletin of Environmental Contamination and Toxicology, 2003)

Prospective study of serum retinol, β-carotene, β-cryptoxanthin, and lutein/zeaxanthin and esophageal and gastric cancers in China - Christian C. Abnet; You-Lin Qiao; Sanford M. Dawsey; Dennis W. Buckman; Chung S. Yang; William J. Blot; Zhi-Wei Dong; Philip R. Taylor; Steven D. Mark (Cancer Causes & Control, 2003)

Gene content and organization of an 85-kb DNA segment from the genome of the phytopathogenic mollicute Spiroplasma kunkelii - Y. Zhao; R. W. Hammond; R. Jomantiene; E. L. Dally; I.-M. Lee; H. Jia; H. Wu; S. Lin; P. Zhang; S. Kenton; F. Z. Najar; A. Hua; et al. (Molecular Genetics and Genomics, 2003)

General Toxicity Prediction Approach for Mixtures Containing Polar Narcotic Chemicals - Z. Lin; C. Wu; P. Shi; L. Wang; S. Gao (Bulletin of Environmental Contamination and Toxicology, 2003)

Detection ofBurkholderia pseudomallei in rice fields with PCR-based technique - C. M. Kao; S. C. Chen; Y. S. Chen; H. M. Lin; Y. L. Chen (Folia Microbiologica, 2003)

Trace Metals in Chinese Joss Stick Smoke - T.-S. Lin; F.-M. Shen (Bulletin of Environmental Contamination and Toxicology, 2003)

A method for inflorescence proliferation - C.-S. Lin; C.-T. Chen; C.-C. Lin; W.-C. Chang (Plant Cell Reports, 2003)

Dissecting the pet18mutation in Saccharomyces cervisiae: HTL1encodes a 7-kDa polypeptide that interacts with components of the RSC complex - Y.-M. Lu; Y.-R. Lin; A. Tsai; Y.-S. Hsao; C.-c. Li; M. Y. Cheng (Molecular Genetics and Genomics, 2003)

Polychlorinated Biphenyls in Taiwanese Primipara Human Milk and Associated Factors - H.-R. Chao; S.-L. Wang; L.-Y. Lin; H.-Y. Yu; Y.-K. Lu; W.-L. Chou; Y.-L. Guo; L. W. Chang (Bulletin of Environmental Contamination and Toxicology, 2003)

Comparison of soil nitrogen mineralization and nitrification in a mixed grassland and forested ecosystem in central Taiwan - Jeffrey S. Owen; Ming Kuang Wang; Hai Lin Sun; Hen Biau King; Chung Ho Wang; Chin Fang Chuang (Plant and Soil, 2003)

Trace Metals in Candle Smoke - T.-S. Lin; F.-M. Shen; J.-L. Chen; M.-H. Yang (Bulletin of Environmental Contamination and Toxicology, 2003)

Involvement of the terminus of grouper betanodavirus capsid protein in virus-like particle assembly - M. W. Lu; C. S. Lin (Archives of Virology, 2003)

Establishment of cell lines from a tropical grouper, Epinephelus awoara (Temminck & Schlegel), and their susceptibility to grouper irido‐ and nodaviruses - Y‐S Lai; J A C John; C‐H Lin; I‐C Guo; S‐C Chen; K Fang; C‐H Lin; C‐Y Chang (Journal of Fish Diseases, 2003)
Four tropical marine fish cell lines have been established from the eye, fin, heart and swim bladder of grouper, Epinephelus awoara (Temminck & Schlegel). Optimum media and temperature conditions for maximum growth were standardized. The eye and swim bladder cells were mostly epithelial, but the fin and heart cells were mostly fibroblastic. The viability of cells was 95% after 1 year of storage in liquid nitrogen (−196 °C). Besides these four cell lines, previously established grouper brain, kidney and liver cell lines were also used for a viral susceptibility study which showed that all the cell lines were sensitive to grouper iridovirus, whereas only brain, fin and liver cell lines were susceptible to the yellow grouper nervous necrosis virus (a nodavirus). Electron microscopy studies of the grouper irido‐ and nodaviruses in ultrathin sections of infected cells showed an abundance of viral particles in the cytoplasm of the virus‐infected cells indicating the effective replication of these two viruses. It is suggested that these cell lines can be used for the isolation of putative fish specific viruses and provide a valuable tool to study the mechanisms of host–pathogen interactions. Furthermore, these cell lines upon transfection, using pEGFP‐C1 and pEGFP‐aMT 2.5 (ayu metallothionein promoter), produced significant fluorescent signals indicating their utility for exogenous studies.

A framework for integrating the songbird brain - Jarvis E.; Smith V.; Wada K.; Rivas M.; McElroy M.; Smulders T.; Carninci P.; Hayashizaki Y.; Dietrich F.; Wu X.; McConnell P.; Yu J.; et al. (Journal of Comparative Physiology A, 2002)

Lactococcus garvieae , a cause of disease in grey mullet, Mugil cephalus L., in Taiwan - S‐C Chen; L‐L Liaw; H‐Y Su; S‐C Ko; C‐Y Wu; H‐C Chaung; Y‐H Tsai; K‐L Yang; Y‐C Chen; T‐H Chen; G‐R Lin; S‐Y Cheng; et al. (Journal of Fish Diseases, 2002)

Spatial pattern of chloroplast DNA variation of Cyclobalanopsis glauca in Taiwan and East Asia - Sophie S. F. Huang; Shih‐Ying Hwang; Tsan‐Piao Lin (Molecular Ecology, 2002)
This study examined the spatial pattern of chloroplast DNA (cpDNA) variation in Cyclobalanopsis glauca (Thunb. ex Murray) Oerst. (Fagaceae) in 140 trees from Taiwan (25 populations), Japan (three), Ryukyus (two), Hong Kong (one) and Mainland China (one). By sequencing three cpDNA intergenic spacer fragments using universal primers ( trn T ‐trn L, trn V ‐trn M, including the trn V intron, and pet G ‐trn P), we found a total of 1980 bp and 15 polymorphic sites. Among them, 12 sites were caused by point mutation, and three resulted from insertion. This gives rise to a total of 13 cpDNA haplotypes. The level of differentiation among the populations studied is relatively high ( G ST = 0.612). Two ancestral haplotypes (A and B) are distributed widely in East Asia. Interestingly, all the derived cpDNA variations are found only in Taiwan but not in other areas. The Central Mountain Ridge (CMR) of Taiwan creates an unsurpassed barrier to the east–west gene flow of C. glauca . Among the populations on the west of CMR, only three separated populations, Yangmingshan, Wushe and Chinshuiying, have high haplotype diversity, each consisting of sister haplotypes all mutated from the same ancestral haplotype. Thus, they have probably originated from de novo mutation after the last glaciation. This inference agrees with the observation that no spatial autocorrelation existed on the west side. Two unrelated dominant lineages on the east of the CMR (haplotypes D and F) showed significant spatial genetic structure. Estimate of N ST – G ST was –0.090 and differed significantly from zero. Thus at the local scale, the phylogeographical component of the genetic structure is significant on the east of the CMR. Accompanied by published palynological records of the last glaciation, this study suggests the possibility that these two types were colonized northward from the southeastern part of Taiwan. ‘Star‐like’ genealogy is characterized, with all the haplotypes coalescing rapidly and as a general outcome of population expansion ( Page & Holmes 1998 ). A neutrality test also suggested a demographic expansion recovered from a bottleneck. We therefore inferred that the southeastern part of Taiwan might be a potential refugium for C. glauca .

Specific detection ofPythium aphanidermatum from hydroponic nutrient solution by booster PCR with DNA primers developed from mitochondrial DNA - P. H. Wang; L. M. Boo; Y. S. Lin; Y. Yeh (Phytoparasitica, 2002)

Residential Water Supply as a Likely Cause of Community-Acquired Legionnaires' Disease in an Immunocompromised Host - Chen Y-S.; Lin W-R.; Liu Y-C.; Chang C-L.; Gan V-L.; Huang W-K.; Huang T-S.; Wann S-R.; Lin H-H.; Lee S.; Huang C-K.; Chin C.; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Downregulation of PTEN/MMAC/TEP1 expression in human prostate cancer cell line DU145 by growth stimuli - Dhundy R. Bastola; Gurcharan S. Pahwa; Ming-Fong Lin; Pi-Wan Cheng (Molecular and Cellular Biochemistry, 2002)

Stratification and seasonal stability of diverse bacterial communities in a Pinus merkusii (pine) forest soil in central Java, Indonesia - Agna S. Krave; Bin Lin; Martin Braster; Anniet M. Laverman; Nico M. van Straalen; Wilfred F. M. Röling; Henk W. van Verseveld (Environmental Microbiology, 2002)
Summary In Java, Indonesia, many nutrient‐poor soils are intensively reforested with Pinus merkusii (pine). Information on nutrient cycles and microorganisms involved in these cycles will benefit the management of these important forests. Here, seasonal effects on the stratification of bacterial community structure in the soil profile of a tropical pine forest are described, and differences in bacterial communities are related to chemical and physical soil parameters. Culture‐independent community profiles of litter, fragmented litter and mineral soil layers were made by denaturing gradient gel electrophoresis (DGGE) of 16S rDNA‐specific polymerase chain reaction (PCR) fragments. The community profiles of the different soil layers clustered separately, correlating with significant differences in organic matter content between the three layers. The bacterial communities appeared to be stable during the wet season of 1998. The drought in 1997, caused by the El Niño climatic effect, did not influence the bacterial communities in fragmentation and mineral soil, although moisture content and other soil parameters were markedly lower than in the wet season. However, communities in litter were influenced by drought. In the litter layer, the moisture content was significantly lower than in the fragmentation and mineral layers during the dry season. A clone library was made from a litter sample taken during the wet season. Partial sequencing of 74 clones and linking the DGGE banding positions of these clones to bands in the DGGE profile of the sample from which the clone library was derived showed considerable bacterial diversity. Alpha‐proteobacteria (40.5% of the clones, of which 57% belonged to the Rhizobium–Agrobacterium group) and high‐G+C content, Gram‐positive bacteria (36.5%) dominated the clone library.

Mapping quantitative trait loci controlling seed longevity in rice (Oryza sativa L.) - K. Miura; S. Lin; M. Yano; T. Nagamine (Theoretical and Applied Genetics, 2002)

Genetic dissection of a genomic region for a quantitative trait locus, Hd3, into two loci, Hd3a and Hd3b, controlling heading date in rice - L. Monna; H. Lin; S. Kojima; T. Sasaki; M. Yano (Theoretical and Applied Genetics, 2002)

Assessment of Treatment Alternatives for Laboratory COD Wastewater: a Practical Comparison with Emphasis on Cost and Performance - Shing Tet Leong; S. Muttamara; Preecha Laortanakul; Hung-Ta Lin (Environmental Monitoring and Assessment, 2002)

Comparison of Bidirectional Cephalexin Transport Across MDCK and Caco-2 Cell Monolayers: Interactions with Peptide Transporters - Wendy S. Putnam; Lin Pan; Ken Tsutsui; Lori Takahashi; Leslie Z. Benet (Pharmaceutical Research, 2002)

Protection against translocating Salmonella typhimurium infection in mice by feeding the immuno-enhancing probiotic Lactobacillus rhamnosus strain HN001 - Harsharnjit S. Gill; Quan Shu; Hai Lin; Kay J. Rutherfurd; Martin L. Cross (Medical Microbiology and Immunology, 2001)

Thallium Concentration in Lake Trout from Lake Michigan - T.-S. Lin; J. Nriagu; X.-Q. Wang (Bulletin of Environmental Contamination and Toxicology, 2001)

A genetic linkage map of Nicotiana plumbaginifolia/ Nicotiana longiflora based on RFLP and RAPD markers - T. Y. Lin; Y. Y. Kao; S. Lin; R. F. Lin; C. M. Chen; C. H. Huang; C. K. Wang; Y. Z. Lin; C. C. Chen (Theoretical and Applied Genetics, 2001)

Plasmids carrying cloned fragments of RF DNA from the filamentous phage φLf can be integrated into the host chromosome via site-specific integration and homologous recombination - N.-T. Lin; R.-Y. Chang; S.-J. Lee; Y.-H. Tseng (Molecular Genetics and Genomics, 2001)

Sphingolipids as biomarkers of fumonisin exposure and risk of esophageal squamous cell carcinoma in China - Christian C. Abnet; Craig B. Borkowf; You-Lin Qiao; Paul S. Albert; Elaine Wang; Alfred H. Merrill; Steven D. Mark; Zhi-Wei Dong; Philip R. Taylor; Sanford M. Dawsey (Cancer Causes & Control, 2001)

Rapid molecular analysis of the haemagglutinin gene of human influenza A H3N2 viruses isolated in Spain from 1996 to 2000 - M. T. Coiras; J. C. Aguilar; M. Galiano; S. Carlos; V. Gregory; Y. P. Lin; A. Hay; P. Pérez-Breña (Archives of Virology, 2001)

Development of the Fragment Constant Method for Estimating the Partition Coefficients of Nonionic Organic Mixtures - Z. Lin, H. Yu, S. Gao, J. Cheng, L. Wa (Archives of Environmental Contamination and Toxicology, 2001)

Exploring suitability for tropical crop cultivation in Hainan Island by SOTAL methodology - Zhang Xue-lei; S. Mantel; Zhang Gan-lin; V. W. P. van Engelen (Journal of Geographical Sciences, 2001)

( R )-Methanandamide and Δ 9 -THC as discriminative stimuli in rats: tests with the cannabinoid antagonist SR-141716 and the endogenous ligand anandamide - Järbe T.; Lamb R.; Lin S.; Makriyannis A. (Psychopharmacology, 2001)

RS-100642-198, a novel sodium channel blocker, provides differential neuroprotection against hypoxia/hypoglycemia, veratridine or glutamate-mediated neurotoxicity in primary cultures of rat cerebellar neurons - Jitendra R. Dave; Yu Lin; Haresh S. Ved; Michael L. Koenig; Larry Clapp; John Hunter; Frank C. Tortella (Neurotoxicity Research, 2001)

Bioaccumulation of Arsenic in Aquacultural Large-Scale Mullet Liza macrolepis from Blackfoot Disease Area in Taiwan - M.-C. Lin; C.-M. Liao; C.-W. Liu; S. Singh (Bulletin of Environmental Contamination and Toxicology, 2001)

Propagation of yellow grouper nervous necrosis virus (YGNNV) in a new nodavirus‐susceptible cell line from yellow grouper, Epinephelus awoara (Temminck & Schlegel), brain tissue - Y‐S Lai; S Murali; H‐C Chiu; H‐Y Ju; Y‐S Lin; S‐C Chen; I‐C Guo; K Fang; C‐Y Chang (Journal of Fish Diseases, 2001)
A nodavirus was isolated from diseased yellow grouper, Epinephelus awoara , larvae cultured in southern Taiwan. The histopathology and RT–PCR results confirmed that it was a fish nodavirus; its coat protein gene sequence was similar to that of red spotted grouper nervous necrosis virus (RGNNV) and it is named yellow grouper nervous necrosis virus (YGNNV). A new nodavirus‐susceptible cell line, grouper brain (GB) was established and characterized from the brain tissue of yellow grouper. The GB cells multiplied well in Leibovitz’s L‐15 medium supplemented with 10% foetal bovine serum at temperatures between 24 and 32 °C, and have been subcultured more than 80 times, becoming a continuous cell line. The GB cell line consists of fibroblast‐like cells and some epithelioid cells. The cell line yielded titres of YGNNV up to 10 8.5 TCID 50 mL –1 . The GB cells effectively replicated the virus at 28 °C, which could be purified to homogeneity by caesium chloride gradient centrifugation. Electron microscopy studies showed that purified virus particles were 25–30 nm in diameter. The cytoplasm of infected cells was filled with aggregates of virus particles. These results indicate that the GB cell line is a significant tool for the study of fish nodaviruses.

Distribution of glucose-6-phosphate dehydrogenase mutations in Southeast Asia - Kuni Iwai; Akira Hirono; Hiroyuki Matsuoka; Fumihiko Kawamoto; Toru Horie; Khin Lin; Indah S. Tantular; Yoes P. Dachlan; Harsono Notopuro; Noor I. Hidayah; Abdul M. Salim; Hisaichi Fujii; et al. (Human Genetics, 2001)

Toward the mapping of physiological and agronomic characters on a rice function map: QTL analysis and comparison between QTLs and expressed sequence tags - K. Ishimaru; M. Yano; N. Aoki; K. Ono; T. Hirose; S. Y. Lin; L. Monna; T. Sasaki; R. Ohsugi (Theoretical and Applied Genetics, 2001)

Molecular epidemiology of enterovirus 71 in Taiwan - P.-Y. Chu; K.-H. Lin; K.-P. Hwang; L.-C. Chou; C.-F. Wang; S.-R. Shih; J.-R. Wang; Y. Shimada; H. Ishiko (Archives of Virology, 2001)

Large-Eddy Simulations of the Atmospheric Boundary Layer Using a New Subgrid-Scale Model – I. Slightly unstable and neutral cases - Feng Ding; S. Pal Arya; Yuh-Lang Lin (Environmental Fluid Mechanics, 2001)

Large-Eddy Simulations of the Atmospheric Boundary Layer Using a New Subgrid-Scale Model – II. Weakly and moderately stable cases - Feng Ding; S. Pal Arya; Yuh-Lang Lin (Environmental Fluid Mechanics, 2001)

Blood and Urine Cadmium Levels in Relation to Demographic and Life Style in Middle Aged and Elderly Men - Y. C. Chen; Y. S. Pu; R. S. Lin; C. Y. Yang; M. K. Lai; S. H. Liu; F.-C. Sung (Bulletin of Environmental Contamination and Toxicology, 2001)

Characterization of grouper nervous necrosis virus (GNNV) - S C Chi; B J Lo; S C Lin (Journal of Fish Diseases, 2001)
Grouper nervous necrosis virus (GNNV) was isolated from moribund grouper larvae, Epinephelus sp., using a fish cell line GF‐1. The present study describes the biochemical and biophysical properties of GNNV and the expression of GNNV in diseased grouper larvae. Viral protein was detectable in most of the GNNV‐infected GF‐1 cells by the fluorescent antibody technique (FAT) after 12 h post‐infection (p.i.), although no cytopathic effect (CPE) appeared at that time. Clear CPE developed on the third day, and complete disintegration of the monolayer occurred over the subsequent two days. The infectivity of GNNV can be blocked following treatment at 60 °C for 1 h. GNNV was sensitive to pH 3 and pH 10–12 with a 4 log 10 drop in infectivity. Purified GNNV was analysed by SDS–PAGE, and then stained with periodic acid silver. The positive staining indicated that its two capsid proteins were glycoproteins. Genomic RNAs of GNNV were extracted from purified virions and analysed. The molecular weights of genomic RNAs were 1.02 × 10 6 and 0.50 × 10 6 Da. The T2 region of the coat protein gene of GNNV was amplified by polymerase chain reaction (PCR), and the multiple alignment of the T2 sequence of two GNNV isolates with four genotypes of fish nodaviruses revealed that these two isolates (GNNV9410 and GNNV9508) belong to the red‐spotted grouper nervous necrosis virus (RGNNV) genotype. The tissue distribution of GNNV in naturally infected grouper larvae was investigated by in situ hybridization using a dig‐labelled probe, which showed that GNNV was not only detected in the brain and retina, but also in the gill, skeletal muscle, liver, pyloric gland, intestine and blood cells in the heart.

Differences in size and growth rates of male and female migrating Japanese eels in Pearl River, China - W. N. Tzeng; H. R. Lin; C. H. Wang; S. N. Xu (Journal of Fish Biology, 2000)
The Sr/Ca ratios in otoliths of silver Japanese eels Anguilla japonica , in Pearl River, China, indicated that both sexes did not stay in brackish water and grew in fresh water from the glass eel stage until spawning migration. This did not support the hypothesis that females tended to distribute upstream and males might be restricted to estuaries. The back‐calculated total length of males at glass eel stage was not significantly different from that of females, indicating that the hypothesis that small glass eels became males and larger ones became females may not be true. The mean (±S.D.) age and total length of males at migration were 6·4±1·6 years and 48·3±4·5 cm, which were significantly smaller than for females, 8·3±1·6 years and 61·4±4·1 cm. The age of migration was related inversely to growth rate for both sexes. Growth parameters of the von Bertalanffy growth equation were K =0·21 cm year°1, L ∞ =55·7 cm and t o =‐0·55 year for males and K =0·14 cm year −1 , L ∞ =77·5 cm and t o =‐0·60 year for females. The difference in asymptotic length ( L ∞ ) between males and females may be because females postpone migration to achieve larger size for maximizing reproductive success.

Assessing Landscape Condition Relative to Water Resources in the Western United States: A Strategic Approach - K. Bruce Jones; Daniel T. Heggem; Timothy G. Wade; Anne C. Neale; Donald W. Ebert; Maliha S. Nash; Megan H. Mehaffey; Karl A. Hermann; Anthony R. Selle; Scott Augustine; Iris A. Goodman; Joel Pedersen; et al. (Environmental Monitoring and Assessment, 2000)

Aliphatic Aldehydes Produced by Heating Chinese Cooking Oils - J.-M. Lin; S.-J. Liou (Bulletin of Environmental Contamination and Toxicology, 2000)

Differential expression of dystrophin, utrophin, and dystrophin-associated proteins in human muscle culture - V. Radojevic; S. Lin; J.-M. Burgunder (Cell and Tissue Research, 2000)

Aliphatic Aldehydes Produced by Heating Chinese Cooking Oils - J.-M. Lin; S.-J. Liou (Bulletin of Environmental Contamination and Toxicology, 2000)

Development of a plant regeneration system based on friable embryogenic callus in the ornamental Alstroemeria - H. -S. Lin; C. van der Toorn; K. J. J. M. Raemakers; R. G. F. Visser; M.J. De Jeu; E. Jacobsen (Plant Cell Reports, 2000)

Rapid early onset lymphocyte cell death in mice resistant, but not susceptible to Leishmania major infection - Julie Desbarats; Jeffrey E. Stone; Lin Lin; Zahra F. Zakeri; Gerald S. Davis; Linda M. Pfeiffer; Richard G. Titus; M. Karen Newell (Apoptosis, 2000)

Central and peripheral tissue distribution of diclofenac after subcutaneous injection in the rat - R. F. Grace; S. R. Edwards; L. E. Mather; Y. Lin; I. Power (Inflammopharmacology, 2000)

Serum tocopherols, selenium and lung cancer risk among tin miners in China - Duminda Ratnasinghe; Joseph A. Tangrea; Michele R. Forman; Terry Hartman; Elaine W. Gunter; You-Lin Qiao; Shu-Xiang Yao; Michael J. Barett; Carol A. Giffen; Yener Erozan; Melvyn S. Tockman; Philip R. Taylor (Cancer Causes & Control, 2000)

Melanocortin 1 receptor variation in the domestic dog - J.M. Newton; Alison L. Wilkie; Lin He; Siobhán A. Jordan; Danika L. Metallinos; Nigel G. Holmes; Ian J. Jackson; Gregory S. Barsh (Mammalian Genome, 2000)

Mineralization of organic sulfur and its importance as a reservoir of plant-available sulfur in upland soils of north China - W. Zhou; S. T. Li; H. Wang; P. He; B. Lin (Biology and Fertility of Soils, 1999)

Flavonoids as inducers of extracellular proteins and exopolysaccharides of Sinorhizobium fredii - C. C. Lin; Y. C. Chen; S. C. Song; L. P. Lin (Biology and Fertility of Soils, 1999)

Agricultural Chemicals in the Alluvial Aquifer of a Typical County of the Arkansas Delta - H. S. Lin; H. D. Scott; K. F. Steele; H. I. Inyang (Environmental Monitoring and Assessment, 1999)

Compression studies of gibbsite and its high-pressure polymorph - E. Huang; J.-F. Lin; J. Xu; T. Huang; Y.-C. Jean; H.-S. Sheu (Physics and Chemistry of Minerals, 1999)

Cadmium-Inducible Metallothionein in Tilapia ( Oreochromis mossambicus ) - S. M. Wu *, , C. F. Weng; M. J. Yu; C. C. Lin; S. T. Chen; J. C. Hwang; P. P. Hwang (Bulletin of Environmental Contamination and Toxicology, 1999)

Characterization of three distinct cDNA clones encoding cysteine proteinases from maize (Zea mays L.) callus - Tibor Pechan; Binghua Jiang; David Steckler; Lijun Ye; Lei Lin; Dawn S. Luthe; W. Paul Williams (Plant Molecular Biology, 1999)

Glove Permeation Tests Using Novel Microchemical Techniques for 2,4-Dichlorophenoxyacetic Acid (2,4-D) Derivatives - Y.-W. Lin; S. S. Que Hee (Archives of Environmental Contamination and Toxicology, 1999)

Porphyra cultivation in Alaska: conchocelis growth of three indigenous species - Michael S. Stekoll; Rulong Lin (Hydrobiologia, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Δ 9 -THC training dose as a determinant for ( R )-methanandamide generalization in rats - T. U. C. Järbe; R. J. Lamb; A. Makriyannis; S. Lin; A. Goutopoulos (Psychopharmacology, 1998)

Familial clustering of rheumatoid arthritis with other autoimmune diseases - Jing-Ping Lin; Joseph M. Cash; Sharon Z. Doyle; Sandra Peden; Keith Kanik; Chris I. Amos; S. J. Bale; Ronald L. Wilder (Human Genetics, 1998)

Chemical Ecology of Cottonwood Leaf Beetle Adult Feeding Preferences on Populus - S. Lin; B. F. Binder; E. R. Hart (Journal of Chemical Ecology, 1998)

Insect Feeding Stimulants from the Leaf Surface of Populus - S. Lin; B. F. Binder; E. R. Hart (Journal of Chemical Ecology, 1998)

A morphological study of cells isolated from the perfused gill of dab and Atlantic salmon - S.‐H. Lin; G. A. Davidson; C. J. Secombes; A. E. Ellis (Journal of Fish Biology, 1998)
Single cell suspensions were derived from the gills of dab Limanda limanda and Atlantic salmon Salmo salar which were free from blood cell contamination. Gills were perfused with heparinized saline before the cells were liberated from their resident position using a procedure employing chelating agents and collagenase digestion. Cells were characterized using light and electron microscopy as well as histochemical staining. The results indicate that the cell types resident in the gill tissue should be capable of expressing local immune competence. Small and large lymphocytes, macrophages, neutrophils, eosinophilic granule cells, goblet cells, chloride cells and cells of unusual morphology were identified especially the presence of goblet cells apparently within epithelial‐like cells.

Fine mapping of quantitative trait loci Hd-1, Hd-2 and Hd-3, controlling heading date of rice, as single Mendelian factors - T. Yamamoto; Y. Kuboki; S. Y. Lin; T. Sasaki; M. Yano (Theoretical and Applied Genetics, 1998)

Mapping quantitative trait loci controlling seed dormancy and heading date in rice, Oryza sativa L., using backcross inbred lines - S. Y. Lin; T. Sasaki; M. Yano (Theoretical and Applied Genetics, 1998)

Dietary flavonoids interact with trace metals and affect metallothionein level in human intestinal cells - Shiu-Ming Kuo; Penny S. Leavitt; Chih-Ping Lin (Biological Trace Element Research, 1998)

A detailed characterization of the effects of four cannabinoid agonists on operant lever pressing - D. Carriero; J. Aberman; S. Y. Lin; A. Hill; A. Makriyannis; J. D. Salamone (Psychopharmacology, 1998)

Micropropagation of Bambusa edulis through nodal explants of field-grown culms and flowering of regenerated plantlets - C.-S. Lin; W.-C. Chang (Plant Cell Reports, 1998)

Maturation-dependent gene expression in a conditionally transformed liver progenitor cell line - A. S. Fiorino; A. M. Diehl; H. Z. Lin; I. R. Lemischka; L. M. Reid (In Vitro Cellular & Developmental Biology - Animal, 1998)

Effects of zinc supplementation on the plasma glucose level and insulin activity in genetically obese (ob/ob) mice - Ming-Der Chen; Shy-Jane Liou; Pi-Yao Lin; Vivian C. Yang; Paul S. Alexander; Wen-Han Lin (Biological Trace Element Research, 1998)

Pre- and Postnatal Exposure to 3,3',4,4'-Tetrachlorobiphenyl: II. Effects on the Reproductive Capacity and Fertilizing Ability of Eggs in Female Mice - A. Huang; S. Lin; R. Inglis; D. Powell; K. Chou (Archives of Environmental Contamination and Toxicology, 1998)

Transgenic peppermint ( Mentha × piperita L.) plants obtained by cocultivation with Agrobacterium tumefaciens - X. Niu; K. Lin; P. M. Hasegawa; R. A. Bressan; S. C. Weller (Plant Cell Reports, 1998)

Estimation of myocardial glucose utilisation with PET using the left ventricular time-activity curve as a non-invasive input function - X. Li; D. Feng; K. -P. Lin; S. -C. Huang (Medical & Biological Engineering & Computing, 1998)

Mapping quantitative trait loci associated with regeneration ability of seed callus in rice, Oryza sativa L. - F. Taguchi-Shiobara; S. Y. Lin; K. Tanno; T. Komatsuda; M. Yano; T. Sasaki; S. Oka (Theoretical and Applied Genetics, 1997)

Analysis of QTL×environment interaction for yield components and plant height in rice - J.-Y. Zhuang; H.-X. Lin; J. Lu; H.-R. Qian; S. Hittalmani; N. Huang; K.-L. Zheng (Theoretical and Applied Genetics, 1997)

Direct shoot regeneration from excised leaf explants of in vitro grown seedlings of Alstroemeria L. - H. S. Lin; M. J. De Jeu; E. Jacobsen (Plant Cell Reports, 1997)

CaEGTA uncompetitively inhibits calcium activation of whorl morphogenesis inAcetabularia - Lionel G. Harrison; G. Donaldson; W. Lau; M. Lee; B. P. Lin; S. Lohachitranont; I. Setyawati; J. Yue (Protoplasma, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Three-dimensional P-wave Velocity Structure of the Bear Valley Region of Central California - C.-H. Lin; S. W. Roecker (Pure and Applied Geophysics, 1997)

Regulation of lipoprotein metabolism by estrogen in inbred strains of mice occurs primarily by posttranscriptional mechanisms - Rai Ajit K. Srivastava; Elaine S. Krul; Renee C. Lin; Gustav Schonfeld (Molecular and Cellular Biochemistry, 1997)

Stimulation of testicular function by exogenous testosterone in male protandrous black porgy, Acanthopagrus schlegeli - E.‐L. Lau; B.‐Y. Lin; F.‐Y. Lee; L.‐T. Sun; S. Dufour; C.‐F. Chang (Journal of Fish Biology, 1997)
When 4 mg of testosterone (T) per kg food was given to 1‐year‐old protandrous male black porgy Acanthopagrus schlegeli for 7 months, gonadosomatic index was significantly higher than when the dose was 0.5 mg kg −1 food. Both doses of T prolonged the spawning season, and increased the number of spermiating fish and milt volume. Sperm concentrations were similar in spermiating black porgy from the treated and control groups. Low levels of oestradiol‐17β were observed during the experimental period while elevated levels of plasma T were observed only in March in both control and T‐treated groups. Significantly higher levels of plasma 11‐ketotestosterone (11‐KT) were observed in the 0.5‐ and 4.0‐mg T‐treated groups during the spawning season as compared to the control group. The present data suggest that both 0.5‐ and 4·0‐mg T doses stimulate testicular weight, increase numbers of spermiating males and milt volume without affecting the sperm concentrations. Plasma 11‐KT concentrations were elevated during T treatment and closely correlated with testicular development and spermiation.

Sweet potato (Ipomoea batatas) trypsin inhibitors expressed in transgenic tobacco plants confer resistance against Spodoptera litura - K.-W. Yeh; M.-I. Lin; S.-J. Tuan; Y.-M. Chen; C.-J. Lin; S.-S. Kao (Plant Cell Reports, 1997)

Diversity associated with the second expressed H L A - D R B locus in the human population - FuMeei Robbins; Carolyn Katovich Hurley; Ting Tang; Hanlong Yao; Y. S. Lin; Judy Wade; Nancy Goeken; Robert J. Hartzman (Immunogenetics, 1997)

Temporal selectivity for complex signals by single neurons in the torus semicircularis of Pleurodema thaul (Amphibia: Leptodactylidae) - Mario Penna; Wen-Yu Lin; Albert S. Feng (Journal of Comparative Physiology A, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Rubisco of Dunaliella tertiolecta is redistributed between the pyrenoid and the stroma as a light?/shade response - S. Lin; E. J. Carpenter (Marine Biology, 1997)

A preliminary study of the formation of precipitation systems under undisturbed conditions during TAMEX - C. -S. Chen; C. -Y. Lin (Meteorology and Atmospheric Physics, 1997)

A high resolution numerical study of Gulf of Mexico fronts and eddies - D. E. Dietrich; C. A. Lin; A. Mestas-Nunez; D. S. Ko (Meteorology and Atmospheric Physics, 1997)

Determination of urinary zinc, chromium, and copper in steel production workers - C. J. Horng; S. R. Lin (Biological Trace Element Research, 1996)

Lipid peroxidation in rats administrated with mercuric chloride - Y. L. Huang; S. L. Cheng; T. H. Lin (Biological Trace Element Research, 1996)

Capsid protein of cucumber mosaic virus accumulates in the nuclei and at the periphery of the nucleoli in infected cells - N. -S. Lin; C. -E. Hsieh; Y. -H. Hsu (Archives of Virology, 1996)

Envelope gene sequences of human T-lymphotropic virus type I in Taiwan - M. T. Lin; Y. C. Chen; P. J. Chen; Y. C. Yang; J. L. Tang; J. M. Wu; S. E. Chuang; C. S. Yang (Archives of Virology, 1996)

Lead-catalyzed peroxidation of essential unsaturated fatty acid - S. J. Yiin; T. H. Lin (Biological Trace Element Research, 1995)

N-Nitroso-N-(3-keto-1,2-butanediol)-3′-nitrotyramine - C. -J. Wang; H. -P. Huang; T. -H. Tseng; Y. -L. Lin; S. -J. Shiow (Archives of Toxicology, 1995)

Satellite RNA associated with bamboo mosaic potexvirus shares similarity with satellites associated with sobemoviruses - J. S. Liu; N. S. Lin (Archives of Virology, 1995)

Different sensitivities to cadmium in tilapia larvae (Oreochromis mossambicus; teleostei) - P. P. Hwang; S. W. Lin; H. C. Lin (Archives of Environmental Contamination and Toxicology, 1995)

A long lytic cycle in filamentous phage Cf1tv infectingXanthomonas campestris pv.citri - T. -T. Kuo; C. -C. Chiang; S. -Y. Chen; J. -H. Lin; J. -L. Kuo (Archives of Virology, 1994)

Consequences of pruning in morphometry of coronary vasculature - Ghassan S. Kassab; Daniel H. Lin; Yuan-Cheng B. Fung (Annals of Biomedical Engineering, 1994)

Simultaneous determination of Zn, Cd, Pb, and Cu in urine of patients with blackfoot disease using anodic stripping voltammetry - T. C. Pan; C. J. Horng; S. R. Lin; T. H. Lin; C. W. Huang (Biological Trace Element Research, 1993)

The skin, tongue, and brain as favorable organs for hog cholera diagnosis by immunofluorescence - I. C. Pan; T. S. Huang; C. H. Pan; Shenq-Yi Chern; Shu-Hwae Lee; Y. L. Lin; B. Y. Huang; C. C. Lin; N. J. Li; J. P. Lin; Y. H. Yang; S. Y. Chiu; et al. (Archives of Virology, 1993)

A new typing method for the avian infectious bronchitis virus using polymerase chain reaction and restriction enzyme fragment length polymorphism - Z. Lin; A. Kato; Y. Kudou; S. Ueda (Archives of Virology, 1991)

Typing of recent infectious bronchitis virus isolates causing nephritis in chicken - Z. Lin; A. Kato; Y. Kudou; K. Umeda; S. Ueda (Archives of Virology, 1991)

Evolutionary study on the coxsackievirus A 24 variant causing acute hemorrhagic conjunctivitis by oligonucleotide mapping analysis of RNA genome - K. Miyamura; N. Takeda; M. Tanimura; T. Ogino; S. Yamazaki; C. -W. Chen; K. -H. Lin; S. Y. Lin; A. Ghafoor; M. Yin-Murphy (Archives of Virology, 1990)

Effects of tributyltin on defense-related activities of oyster hemocytes - William S. Fisher; Arieh Wishkovsky; Fu -Lin E. Chu (Archives of Environmental Contamination and Toxicology, 1990)

Characteristics of spontaneously produced and of virus-induced human LuKII cell interferons - Lulu A. Pickering; L. S. Lin; F. H. Sarkar (Archives of Virology, 1983)

Mutants of Rhizobium japonicum defective in nodulation - Gary Stacey; Alan S. Paau; K. Dale Noel; Robert J. Maier; Lin E. Silver; Winston J. Brill (Archives of Microbiology, 1982)

Production, purification and characterization of rat interferon - L. S. Lin; S. L. Abreu (Archives of Virology, 1979)

Acute hepatotoxicity of a tetrachlorobiphenyl?Changes in the hepatocyte ultrastructure and plasma membrane-bound enzymes - F. S. Lin; M. T. Hsia; J. R. Allen (Archives of Environmental Contamination and Toxicology, 1979)

Characterization of the size and charge heterogeneities of human leukocyte interferon populations - L. S. Lin; Marzenna Wiranowska-Stewart; T. Chudzio; W. E. Stewart (Archives of Virology, 1978)